Insecticide seed treatments for managing maggots (Diptera: Anthomyiidae) in onion across selected regions in North America - Leonardo D. Salgado; Alan G. Taylor; Mary Ruth McDonald; Rob G. Wilson; Timothy D. Waters; Josephine B. Antwi; Stuart Reitz; Nathan Hesler; Brian A. Nault (Crop Protection, 2026)

Who stays, who leaves? Recreational fishing responses to harmful algal blooms in Lake Erie - Yining Wu; Brent L. Sohngen; Stuart A. Ludsin (Ecological Economics, 2026)

Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Pan-continental assessment of socioeconomic and environmental predictors of PFAS occurrence in European rivers from a harmonised monitoring study - Jun Li; Alistair B.A. Boxall; Caroline Swan; Selwyn Hoeks; Racliffe W.S. Lai; John L. Wilkinson; Recep C. Altinbag; Åsa Arrhenius; Roman Ashauer; Thomas Backhaus; Besnik Baraj; Vasiliki G. Beretsou; et al. (Water Research, 2026)

Utility of monocyte-derived cells to investigate immune-mediated drug-induced liver injury - Monique Ulepic; Maria F. Vargas; Stuart Astbury; Magdalena Rausch; Sibylle Pfammatter; Sophia L. Samodelov; Jane I. Grove; Gerd A. Kullak-Ublick; Nicholas R.F. Hannan; Guruprasad P. Aithal; Michele Visentin (Toxicology Letters, 2026)

Microbial carbon use efficiency is governed by site-level soil and climate factors and does not explain soil carbon gains under diversified crop rotations - Timothy M. Bowles; Maria Mooshammer; A. Stuart Grandy; Kevin Geyer; Serita D. Frey; Francisco Calderón; Steve Culman; Bill Deen; Kari Dunfield; Virginia L. Jin; R. Michael Lehman; Shannon L. Osborne; et al. (Soil Biology and Biochemistry, 2026)

Shrub and sedge rhizosphere communities display distinct affinities toward exudates and soil organic matter degradation: a quantitative stable isotope probing analysis - Sean R. Schaefer; Steven J. Blazewicz; Hannah Holland-Moritz; Caitlin Hicks Pries; G. Mike Allen; Jennifer Pett-Ridge; Fernando Montaño-López; A. Stuart Grandy; William Wieder; Jessica G. Ernakovich (Soil Biology and Biochemistry, 2026)

An end-to-end model framework for understanding and predicting changes in Antarctic marine ecosystems - Ilari Stollberg; Sophie Bestley; Andrew Constable; Elizabeth A. Fulton; Javier Porobic; David Green; Denise O’Sullivan; Mao Mori; Stuart Corney; Michael Sumner; Jessica Melbourne-Thomas (Ecological Modelling, 2026)

Interspecific differences in microplastic accumulation and polymer profiles from regurgitated pellets of coexisting raptors - Rana Ozturk; Gbotemi A. Adediran; Dominic P. Brass; William F. Mills; Matt Stevens; Alexander Robinson; Stuart Black (Environmental Pollution, 2026)

Associations between metabolic dysfunction–associated steatotic liver disease and physical and mental health–related quality of life in older adults - Marzieh Nasr Azadani; Mojtaba Lotfaliany; Najmeh Davoodian; Michael Berk; Robyn L. Woods; Joanne Ryan; John J. McNeil; Julie A. Pasco; Nigel Stocks; Stuart K. Roberts; William Kemp; Ammar Majeed; et al. (GeroScience, 2026)

Provocation of occupational asthma by non-specific irritation and its relevance for the classification of chemicals as respiratory allergens: a case study of methyl methacrylate - Mark A. Pemberton; Stuart Hindle; Ian Kimber (Regulatory Toxicology and Pharmacology, 2026)

Comparing loss-on-ignition, acid decarbonation and combustion elemental analysis for measuring organic carbon concentrations – recommendations for best practice - Robert B. Sparkes; Stuart A. Rae; Lucy McMahon; Hannah L. Mossman; David McKendry; Clare E. Dean; Graham Tinsley; Frances Fowden; Connor J. Grisdale; Hafiza Begum; Holly Hope; Charlotte McEnhill; et al. (Organic Geochemistry, 2026)

Ordovician Reversed Superchron: Fact or Fallacy? - Nastaran Ahanin; Stuart A. Gilder; Jan Ove R. Ebbestad; Sophie Roud; Fabian Dellefant; Bjarne S.G. Almqvist; Yury Zablotski (Earth and Planetary Science Letters, 2026)

Model reduction and analysis: A case study of a malaria control model - Maame Akua Korsah; Stuart T. Johnston; Kathryn Tiedje; Karen Day; Camelia R. Walker; Jennifer A. Flegg (Journal of Theoretical Biology, 2026)

Evaluating a structured expert elicitation approach for adaptive conservation management based on lessons from five years in practice - Helen J. Mayfield; James Brazill‐Boast; Mick Andren; Michiala Bowen; Adam Fawcett; Trent Forge; Luke Foster; Ross Goldingay; Paul Hillier; Meagan Hinds; Simon Lee; Erica Mahon; et al. (Conservation Biology, 2026)
Adaptive management of threatened species relies on having ex ante estimates of species’ responses to different interventions. Structured expert elicitation is often used to generate these estimates, but comparisons of these expert‐predicted outcomes with observed results are rare. This study aims to evaluate the utility of expert elicitation for adaptive management in the New South Wales Saving our Species program in Australia by revisiting six species management plans that were generated from tailored structured elicitation guidelines developed five years prior. Each species’ management plan included a defined scope, conceptual model, monitoring indicators, and estimated response to management curves under different scenarios. Experts reviewed the conceptual models after five years of management and compared the predicted response to management with observed monitoring data. In three of the six case studies, observed outcomes closely matched predictions. Where predictions diverged, factors such as unanticipated new threats and unexpected responses to interventions potentially contributed to discrepancies. However, in all cases, the structured approach provided a clear logic for planning, enabling managers to systematically refine their understanding. The conceptual models and response curves were valuable for collaborating, communicating, and generating hypotheses for unexpected results. This work demonstrates the value of tailored guidelines in supporting adaptive management processes and showcases the value of documenting expert knowledge in management settings with high uncertainty.

Effect of six weeks ubiquinol supplementation on mitochondrial respiratory function and exercise capacity in healthy males - Jarred P. Acton; Nehal S. Alsharif; Jack W. Bond; Stuart P. Cocksedge; Abbie G. Mclellan; Donald L. Peden; Mark P. Funnell; Hannah F. Dugdale; Lewis J. James; Richard A. Ferguson; Tom Clifford; Stephen J. Bailey (European Journal of Applied Physiology, 2026)
Coenzyme Q10 (CoQ 10 ) is an integral component of the mitochondrial electron transfer system. Most studies have administered the oxidised form of CoQ 10 (ubiquinone) and observed no effects on mitochondrial respiratory function or endurance exercise performance. The reduced form of CoQ 10 , ubiquinol (UQH 2 ), has greater bioavailability than ubiquinone, but the effects of UQH 2 supplementation on mitochondrial respiratory function and exercise capacity are unclear. Fifty-four healthy, recreationally active males were randomised to receive either 300 mg·day − 1 UQH 2 or placebo (PLA) for 6 weeks in a double-blind independent-group design. Before and after the supplementation period, skeletal muscle mitochondrial respiration variables and protein content of the mitochondrial leak proteins, adenine nucleotide translocase1 + 2 (ANT1 + 2) and uncoupling protein-3 (UCP-3), were assessed. In addition, participants completed a severe-intensity cycle test to exhaustion to assess time to the limit of tolerance (T Lim ) and oxygen uptake (V̇O 2 ) kinetics. Compared to pre-supplementation and PLA, UQH 2 supplementation increased plasma [CoQ 10 ] ( P < 0.05), and lowered inverse respiratory control ratio (Pre-PLA: 0.064 ± 0.034 vs. Post-PLA: 0.072 ± 0.026; Pre- UQH 2 : 0.073 ± 0.039 vs. Post-UQH 2 : 0.044 ± 0.019; P < 0.05), suggestive of improved oxidative phosphorylation coupling efficiency. There were no differences in ANT1 + 2 or UCP-3 protein content post-supplementation compared to pre-supplementation between groups ( P > 0.05). End-exercise V̇O 2 , change in V̇O 2 between 2 min and end-exercise, and T Lim were not different between groups post-supplementation ( P > 0.05). Six-weeks UQH 2 supplementation increased plasma [CoQ 10 ] and oxidative phosphorylation coupling efficiency, but did not alter mitochondrial leak proteins, T Lim or V̇O 2 kinetics during severe-intensity exercise in healthy, active males.

Cytoplasmic flow dynamics in arbuscular mycorrhizal fungi are intrinsic and independent of plant hosts - Malin Klein; Loreto Oyarte Gálvez; Daniel van der Lugt; Corentin Bisot; Simon van Staalduine; Stuart A. West; Vasilis Kokkoris; Lemeng Dong; Harro Bouwmeester; Thomas S. Shimizu; James T. Weedon; E. Toby Kiers (Fungal Biology, 2026)

Bayesian hierarchical stock–recruitment models for setting conservation limits for Atlantic salmon stocks in Scotland - James P. Ounsley; Nora N. Hanson; Gordon W. Smith; Jonathan P. Gillson; Brian A. Shields; Stuart J. Middlemas (Journal of Fish Biology, 2026)
Atlantic salmon ( Salmo salar L.) populations in Scotland are subject to active management and conservation practices which require biological reference points (BRPs), specifically conservation limits, defined at the level of the stock. Acquiring the data necessary to independently derive these BRPs for all managed populations in Scotland is prohibitive, motivating the use of Bayesian hierarchical stock–recruitment models. These models provide a framework for the joint analysis of multiple monitored stocks, and the transportation of BRPs to non‐monitored stocks. This framework was adapted to introduce nationally relevant and available covariates that might explain variation in recruitment dynamics among stocks and reduce uncertainty in posterior predictions of BRPs. Model selection was designed to maximise the prediction of BRPs for new stocks via leave‐one‐group‐out cross‐validation. Out‐of‐sample predictive performance was maximised by including information on latitude, land usage within the catchment and historic catch per area of salmon habitat in the model. The extensions to Bayesian hierarchical stock–recruitment methods presented here, when applied at a national scale, result in more locally discriminative posterior predictions compared to existing methods and are readily applicable to other stocks and species.

Telomere length dynamics do not predict subclinical atherosclerosis progression over a six-year period - Vicente Andrés; Juan M. Fernández-Alvira; Beatriz Dorado; Ana Guío-Carrión; Ana García-Álvarez; Inés García-Lunar; Antonio Fernández-Ortiz; José J. Fuster; Stuart Pocock; Borja Ibáñez; María A. Blasco; Valentín Fuster (GeroScience, 2026)

The Scotland–Canada overturning array (SCOTIA): twenty years of meridional overturning in the subpolar North Atlantic - Alan D. Fox; Neil J. Fraser; Kristin Burmeister; Sam C. Jones; Stuart A. Cunningham; Lewis A. Drysdale; Ahmad Fehmi Dilmahamod; Johannes Karstensen (Ocean Science, 2026)
The Atlantic meridional overturning circulation (AMOC) is expected to decline dramatically over the 21st century, with severe impacts for Northern Hemisphere climate. After 20 years of sustained monitoring in the subtropics, a detectable AMOC weakening trend is now beginning to emerge. However, continuous observations at subpolar latitudes are currently too short-lived to determine any weakening signal above the large-amplitude interannual variability. Here, we introduce a new subpolar observing configuration, SCOTIA (Scotland–Canada overturning array), combining parts of the existing OSNAP mooring array with scattered CTD and Argo data, to extend the record of subpolar AMOC backward in time to cover the subtropical monitoring period, 2004–2024. SCOTIA facilitates a rigorous comparison of the decadal-scale variability in transports and overturning at subpolar and subtropical latitudes. Our results show subpolar AMOC varies on pentadal to decadal timescales with an amplitude comparable to that observed in the subtropics. Anomalously high overturning during 2016–2020 was driven by increased southward transports in the density classes associated with Labrador Sea Water. We find no statistically significant trend in subpolar AMOC during the period 2004–2024.

Validation of SPH code Spheral to model interacting solid bodies in a supersonic flow - Veronika A. Korneyeva; Jason M. Pearl; Kathryn M. Kumamoto; J. Michael Owen; Cody D. Raskin; Megan B. Syal; Nicholaus J. Parziale; Stuart J. Laurence (Icarus, 2026)

Techno-economic assessment of coal fugitive methane abatement in Australia using currently available technology - Courtney M. Regan; Andy Wilkins; Thomas S. Brinsmead; Richard Mattus; Felicia A. Ruiz; Regina Sander; Nikki Prater; Qingdong Qu; Stuart Addinell (International Journal of Coal Geology, 2026)

The future of evolutionary behavioral biology - Theo C. M. Bakker; James F. A. Traniello; Tim R. Birkhead; Monika Borgerhoff Mulder; Bernard Crespi; Niels J. Dingemanse; Raghavendra Gadagkar; Ashleigh S. Griffin; Mark E. Hauber; Bert Hölldobler; John L. Hoogland; Sarah B. Hrdy; et al. (Behavioral Ecology and Sociobiology, 2026)

Global Analysis of Shallow Underwater Fish Observation Research: 70 Years of Progress, Persistent Geographic Biases and a Path Forward - Angus John van Wyk; Rick D. Stuart‐Smith; Jordan S. Goetze; Eva Maire; Elodie Heyns‐Veale; Kaylee Smit; Tim J. Langlois; M. Aaron MacNeil; Alejandro Pérez‐Matus; Amanda T. Lombard; Ana Carolina; Christy Semmens; et al. (Fish and Fisheries, 2026)
Marine ecosystems are increasingly threatened by overfishing, pollution, coastal development and climate change, underscoring the need for long‐term, representative information on key fish populations and habitats to inform management and policy. Underwater fish observation (UFObs) techniques, such as Underwater Visual Census (UVC), stereo‐Baited Remote Underwater Video (stereo‐BRUV) and Remotely Operated Vehicles (ROVs), play a key role in sustaining long‐term data collection. Despite technological advancements, gaps persist in understanding research focus, geographic distribution and methodological biases inherent in these methods. We conducted a scientometric analysis of 1443 peer‐reviewed publications (1953–2023), employing natural language processing and network analysis to map the research landscape. We identified 15 knowledge clusters, including marine protected areas, apex predator conservation and reef ecosystems. Our findings reveal increasing use of BRUVS and ROVs in studies of marine protected areas and subsea infrastructure, while UVC remains prevalent in shallow coral reef research. Geographic representation is skewed, with the field dominated by researchers based in Australia and the United States, and underrepresented in Africa and Southeast Asia. This imbalance highlights the need for more inclusive, globally coordinated monitoring and reporting. Our results underscore the urgency of standardising protocols within each observation method and developing interoperable reporting frameworks across techniques to maximise data comparability and foster international collaboration. Addressing these challenges will strengthen the field's capacity to inform global conservation strategies and support sustainable fisheries management.

Seasonal variation of microplastics in indoor environments from Birmingham, UK: Implication for ingestion and inhalation exposure - William A. Stubbings; Hassan Khalid Ageel; Stuart Harrad; Mohamed Abou-Elwafa Abdallah (Chemosphere, 2026)

Digital technologies and the study of adaptation in small-scale fisheries - Juan Carlos Villaseñor-Derbez; Rebeca Fernández; Stuart Fulton; Arturo Hernández-Velasco; Tamara Hernández; C. Brock Woodson; Juan Camilo Cárdenas; Giulio A. DeLeo; Jorge Torre; Fiorenza Micheli (Ocean & Coastal Management, 2026)

A Bayesian inversion of TROPOMI methane observations over South Africa: Implications for bottom-up inventories - Keneuoe A. Maliehe; James Goulding; Stuart Marsh; Mohammed S. Alam (Science of The Total Environment, 2026)

Effects of duration of a plant-based diet stimulus at first feeding on nutritional programming in Atlantic salmon (Salmo salar) - Xu Gong; Matthew Sprague; Stuart McMillan; Pedro Gómez-Requeni; Fernando Norambuena; Sam A. M. Martin; Douglas R. Tocher; Mónica B. Betancor (Fish Physiology and Biochemistry, 2026)
Nutritional programming could potentially be a strategy for sustainable aquaculture to adapt fish to feeds formulated with low levels of marine ingredients. The present study examined the effects of early dietary stimulus duration and the impacts of a later challenge with a similar diet. At first feeding, Atlantic salmon ( Salmo salar ) fry of ~ 0.15 g initial weight were fed a vegetable diet (77% plant-based ingredients) for either 1 (V1) or 2 weeks (V2), while a control group (M) received a marine diet (86% marine-based ingredients) for the 2 weeks (stimulus phase). All fish then received a marine diet for 16 weeks (intermediate phase) before being refed a vegetable diet for 6 weeks (challenge phase). Water temperature was 13 °C during the trial, and the only difference between the three experimental groups (V1, V2 and M) was their dietary regime during the first 2 weeks. Obviously, stimulus duration had no phenotypic impacts on growth or tissue fatty acid compositions of either total or polar lipids after challenge. However, the expressions of key genes of LC-PUFA biosynthesis were upregulated significantly in the V1 group, whereas the expressions of most transcription factors were downregulated in the V2 group. After the challenge, the circular muscle thickness of the intestine in the V1 group was increased by 15%, and goblet cell numbers were reduced by 15%. Overall, further investigations about the duration of the stimulus and assessment with longer challenges are required to elicit positive effects and to refine the use of nutritional programming in Atlantic salmon.

Experimental and molecular observations associated with sub-lethal autotoxicity in cultivated Asparagopsis taxiformis following exudate accumulation - Tomas Lang; Jianli Liu; Stuart J.H. Smith; Scott F. Cummins; Nicholas A. Paul; Alexandra H. Campbell (Algal Research, 2026)

How England got to mandatory biodiversity net gain: A timeline - Alice Stuart; Alan Bond; Aldina M. A. Franco; Chris Gerrard; Julia Baker; Kerry ten Kate; Tom Butterworth; Joseph Bull; Jo Treweek (Ambio, 2026)
Biodiversity net gain (BNG) is a “net outcome” planning policy which aims for development projects to leave biodiversity in a better state than before they started. Understanding the origins and history of existing mandatory BNG is necessary to understand the drivers and barriers that have influenced the policy to date and could inform the development and implementation of future BNG policies. Biodiversity net gain legislation was first discussed in Parliament in England through the passage of the Environment Act (2021) and became a mandatory requirement for most terrestrial and intertidal developments in February 2024. The policy uses habitat attributes as a proxy for biodiversity and represented the widest reaching net outcome policy in the world at the point of its introduction. As such, it is expected to have a significant impact on future land use decisions in England. This paper uses a mixture of literature review and the knowledge of those involved in the early stages of this BNG policy development in England to present a timeline of the stages that have led to mandatory biodiversity net gain. In doing so, we highlight formative events and documents, as an important first step in understanding its history and understanding how this can be used to inform future biodiversity policy.

Seasonal Flooding Disrupts Expected Depth‐Dependent Patterns of Mineral Associated Carbon, Nitrogen, and Phosphorus Across Land Uses - Hannah P. Lieberman; Christian von Sperber; Rachael Harman‐Denhoed; A. Stuart Grandy; Cynthia M. Kallenbach (Global Change Biology, 2026)
Approximately 25%–70% of soil organic matter (OM) is stored below 30 cm, rendering subsoil OM cycling an important control on OM persistence. With climate change, soils are experiencing new pedoclimatic disturbances like seasonal flooding that can destabilize mineral associated organic matter (MAOM) and undermine carbon (C), nitrogen (N), and phosphorus (P) persistence. Our current understanding of how OM cycles down the soil profile is largely based on well‐drained soils. Thus, it remains uncertain if expected depth‐dependent trends and subsoil OM persistence differ in soils subjected to seasonal flooding across land uses. We collected 1‐m‐deep soil cores within a seasonal floodplain, representing a land‐use gradient: forest, pasture, and cropland. We compared MAOM concentrations (C, N, and P), stoichiometry, isotopic, and molecular chemical composition, in combination with microbial biomass and carbon use efficiency at four soil depths to understand the transformation and persistence of OM with depth. We found that the composition of OM by depth in our soils diverges from common trends in well‐drained soils. For example, in well‐drained soils, we expect a decrease in mineral associated C:N, and an increase in polar compounds with depth, as these compounds are thought to be more persistent. Instead, we found an increase in MAOM C:N in the forest and cropland, and an increase in non‐polar C rich compounds in all land uses with depth. The pasture varied from the forest and cropland, with OM composition largely unchanged with depth. Our results suggest that the extensive root system in the pasture causes desorption of older compounds resulting in younger, plant derived compounds at all depths. We propose that the controls on persistence differ in a seasonal floodplain, where MAOM persistence is shaped more by compound resistance to hydrological stress than by formation pathways.

Hybrid particulate matter generated by lava-ignited wildfires at the Litli-Hrútur 2023 eruption, Iceland - Laura Wainman; Evgenia Ilyinskaya; Melissa Anne Pfeffer; Penny E. Wieser; David Damby; James B. McQuaid; Celine Mandon; Enikö Bali; Josefa Sepulveda-Araya; Richard Walshaw; Caleb Hall; Stuart Micklethwaite; et al. (Science of The Total Environment, 2026)

Bioaccumulation of arsenic in mine waste contaminated soil using Poa labillardieri (Steud.) and soil amendments: A short-term pilot trial - Julie A. Besedin; Darislav A. Besedin; Leadin S. Khudur; Sali K. Biek; Gerardo Aguilar; Pacian Netherway; Albert L. Juhasz; Stuart Horner; Andrew S. Ball (Science of The Total Environment, 2026)

Static Alternating Field Demagnetization of Rocks: Why Three Axes are not Enough - David Finn; Stuart A. Gilder; Dario Bilardello; Michael R. Wack; Robert S. Coe; Michael Jackson; Wyn Williams; Leon Kaub; Michael J. Branney (Studia Geophysica et Geodaetica, 2026)
Paleomagnetism relies4 on stable remanent magnetizations held in rocks to reconstruct the ancient geomagnetic field direction and intensity. However, rocks may carry secondary overprints that obscure or completely destroy the original signal. To study the stability of the magnetic vector(s), laboratories routinely apply static alternating field demagnetization along three orthogonal axes (AFD₃), which is fast, non-destructive, and easy to automate. Here, we present a multiparticle model that shows AFD₃ can deviate the natural remanent magnetization (NRM). Deviations can be avoided when fulfilling two conditions: (i) the NRM was acquired in a weak field where magnetization intensity varies linearly with field strength, and (ii) the sample is magnetically isotropic. The first condition is generally satisfied for rocks holding thermal or detrital remanent magnetizations, but not those affected by an isothermal remanence (e.g., lightning), even though AFD₃ is often used to remove them. In rocks with an anisotropic particle orientation distribution, stepwise AFD₃ progressively removes different coercivity subpopulations as a function of grain orientation so the effective remanence anisotropy of the surviving carriers changes during demagnetization. The anisotropy-driven deflection therefore evolves with AF step, producing curvilinear demagnetization trajectories. Our theoretical results argue for caution when applying AFD₃ to anisotropic samples or those with isothermal overprints. Undesired NRM rotation can be avoided by tumble demagnetization or mitigated by increasing the number of alternating field axis orientations.

Non-Tensorial Anhysteretic Remanent Anisotropy and the Detection of Composite Fabrics - David Finn; Michael R. Wack; Stuart A. Gilder; Michael Jackson; Robert S. Coe; Dario Bilardello; Leon Kaub; Wyn Williams; Michael J. Branney (Studia Geophysica et Geodaetica, 2026)
The anisotropy of anhysteretic remanent magnetization (AARM) provides a powerful, nondestructive means of assessing magnetic fabrics. It is widely applied to infer strain and emplacement conditions in sedimentary, volcanic, and intrusive rocks. AARM is generally represented by a symmetric second-rank tensor describing its orientation, strength, and shape. AARM, however, departs from a tensorial shape when the number of grains carrying each directionally imparted anhysteretic remanence (ARM) varies with ARM orientation – a condition that arises when the alternating field (AF) over which the ARM is imparted does not fully activate the sample. Experimental data from a highly anisotropic ignimbrite sample, together with multiparticle modeling, show that such partial activation produces non-tensorial AARMs. Although this behavior complicates tensor analysis, non-tensorial AARM can reveal superimposed fabrics, provided that users can apply AF and ARM in a broad range of orientations. This article presents theoretical models that demonstrate non-tensorial behavior and explains how to utilize these properties to discern superimposed fabrics in natural samples.

Elucidating the role of microplastics as reservoirs of brominated flame retardants in river sediment - Jingxi Jin; Shijie Wang; Yulong Ma; Simeon Onoja; William A. Stubbings; Mohamed Abou-Elwafa Abdallah; Stuart Harrad (Journal of Hazardous Materials, 2026)

Changing volatile emissions and sources along the Ethiopian Rift - Abate A. Melaku; Gemechu B. Teferi; Takele Mihretie; Snorri Gudbrandsson; Yared Sinetebeb; Peter H. Barry; Tobias P. Fischer; Finlay M. Stuart; Ugur Balci; Sæmundur A. Halldórsson; Chris J. Ballentine; Darren J. Hillegonds; et al. (Earth and Planetary Science Letters, 2026)

Correction to: The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2026)

Mapping area of habitat for inland wetland species - Francesca A. Ridley; Catherine A. Sayer; Louise Mair; Daniele Baisero; Monika Böhm; Thomas M. Brooks; Stuart H. M. Butchart; Viola Clausnitzer; Jeorg Freyhof; Günther Grill; Ian Harrison; Randall R. Jiménez; et al. (Conservation Biology, 2026)
Area of habitat (AOH) maps provide a high‐resolution representation of the habitat available in a species’ range and can support conservation policy and planning processes. However, until recently, there was insufficient knowledge on the distribution of inland wetlands and freshwater biodiversity to develop AOH mapping methods specifically tailored to inland wetlands. We used a combined empirical and thematic approach to translate inland wetland habitat classes in the International Union for Conservation of Nature (IUCN) Habitats Classification Scheme into spatially explicit wetland‐cover types derived from the Global Lakes and Wetlands Database 2 and the World Karst Aquifer Map. The AOH was subsequently estimated as the area in the mapped range that corresponded to each species’ habitat and elevation associations. We developed and tested the method with IUCN Red List assessment data, range maps, and point locality data for fishes, odonates, decapod crustaceans, and mollusks (22,876 species). The method performed well in comparison with similar methods already developed for terrestrial mammals, birds, amphibians, and reptiles. The mean map prevalence (proportion of area in a species’ range that was AOH) was 18–32% for each taxonomic group. Based on data on known localities of occurrence, 78–100% of species per taxonomic group had a higher classification accuracy than expected if AOH were distributed in the range at random. This represents an increased accuracy in the distribution of wetland species. Our study represents the first attempt to distinguish between inland wetland habitat subclasses and to include subterranean habitats in an AOH mapping method. Our method will facilitate the inclusion of previously underrepresented taxa in key conservation tools and analyses and is expected to increase the accuracy of AOH mapping for any species associated with inland wetlands.

A decade of continuous Rockall Trough transport observations using moorings and gliders - Kristin Burmeister; Sam C. Jones; Neil J. Fraser; Alan D. Fox; Stuart A. Cunningham; Lewis A. Drysdale; Mark E. Inall; Tiago S. Dotto; N. Penny Holliday (Ocean Science, 2026)
The Rockall Trough, northwest of Scotland and Ireland, is a key conduit for the North Atlantic Current (NAC) and European Slope Current (ESC) transporting heat and salt toward the Nordic Seas and Arctic Ocean while mediating exchanges between the open ocean and the European shelf. We present a decade-long record of Rockall Trough circulation from the Ellett Array providing the first continuous estimates of heat and freshwater transport between 2014 and 2024. We develop a methodology that combines the high spatial resolution of gliders with the high temporal resolution of moorings and ocean reanalysis output producing continuous eastern boundary velocity fields of the ESC for integration into the full Rockall Trough transport product. This approach improves the mean structure of the ESC, capturing the southward undercurrent previously unresolved and enhancing the ability to reproduce extreme, likely mesoscale, transport events. The Rockall Trough transport is dominated by the NAC flowing through the mid basin, exhibiting multi-year variability consistent with changes in the subpolar gyre and the mid-2010s cold freshwater anomaly. The ESC acts as a secondary driver, is not correlated with the NAC and is influenced by along-slope wind stress. Since 2022, warmer and saltier conditions, amplified by the 2023 extreme North Atlantic marine heatwave, have strengthened northward volume, heat, and salt transport through the Ellett Array. Our results highlight the value of sustained glider-based boundary current observations for Atlantic climate monitoring and demonstrate that the combined mooring–glider framework provides a robust and transferable approach for long-term ocean transport monitoring.

Multi-scale observations during the 2024 mass coral bleaching event on Heron Reef, Australia - Devin A. Rowell; Nicholas M. Hammerman; Kirsten M. Golding; Tania Marie Kenyon; Zoe Meziere; Courtney Morgans; Kristen Taylor Brown; Faye F. Diederiks; David E. Carrasco Rivera; Karen Eigeland; Roima Paewai-Huggins; Kathryn Markey; et al. (Marine Biology, 2026)

Missing or Mis‐Telling the Story? Trade‐Offs for Restriction‐Site Associated Compared to Whole Genome Sequencing - Kamolphat Atsawawaranunt; Katarina C. Stuart; Annabel Whibley; Kyle M. Ewart; Lee A. Rollins; Rebecca N. Johnson; Anna W. Santure (Molecular Ecology, 2026)
Researchers must navigate several trade‐offs when deciding which population sequencing method to use. The decision between reduced representation approaches and whole genome sequencing (WGS) impacts marker density, sequencing depth and costs per sample, which will in turn affect the power to accurately characterise certain genomic features, such as regions of the genome exhibiting signals of selection. To investigate the effect of sequencing method on the detection of putatively adaptive regions, we compared selection scan analyses of a set of restriction site‐associated DNA sequencing (RADseq) datasets for the common myna ( Acridotheres tristis ) with a WGS dataset with fewer individuals. Although selection scan statistics were found to be correlated between datasets, no common outliers were found when using outlier thresholds typically applied in such studies. We compared allele frequencies and genotypes across datasets and found that discordances were due to missing markers, different individuals sampled or erroneous genotyping. Most importantly, two regions with strong signals of selection identified through WGS data were missed in the lower density dataset, and population‐specific allelic dropout, which can result from restriction enzyme cut site loss in RADseq, created false signals of selection in these datasets. Our results highlight the advantages of WGS over RADseq when used for selection scan analyses, especially for highly structured populations such as those observed in many invasive or endangered species.

A Beginner's Guide to Structural Variants in Eco‐Evolutionary Population Genomics - Katarina C. Stuart; Rebekah A. Oomen; Anna Tigano; Maren Wellenreuther; Jana Wold; David L. Field; Claire Mérot (Molecular Ecology, 2026)
Whole‐genome sequencing (WGS) has greatly expanded researchers' ability to study structural variants (SVs), that is, the variation in the presence, number, orientation or position of a DNA sequence. This has paved the way to study the eco‐evolutionary dynamics of SVs across the tree of life and within a population genomics framework. In this review, we provide the necessary fundamentals to help researchers generate and analyse population‐level SV data. We discuss the unique properties of different SV groups and how these fundamental differences interact with important biological and evolutionary processes using both empirical results and theory. This includes discussion of unresolved issues around SVs, such as technical difficulties in identification, accounting for diversity and evaluating functional effects. We explicitly integrate into this discussion transposable elements, which are an important component of SVs often identified in population‐level variant data. Finally, we focus on the practical side of SV analysis, offering a framework for SV identification and data analysis. In particular, we examine the heterogeneous nature of SV properties (type, length, sequence identity) that should be considered when studying them in ecology and evolution. This review aims to provide resources and guidelines to help researchers navigate the complexities of a relatively new field of eco‐evolutionary genomics research.

Chemistry and He isotope systematics of olivine as tracers of source in mantle xenoliths from Harrat Hutaymah and Harrat Kishb Cenozoic lava fields, Western Saudi Arabia - Ahmed Hasan Ahmed; Abdel-Kader M. Moghazi; Finlay M. Stuart; Shehta Abdallah; Moustafa Hashad; Kamal A. Ali (Geochemistry, 2025)

Removal of Copper and Lead Ions from Water Using Dopamine-Modified Waste Marine Plastic - Huiyi Zhang; Stuart W. Gibb; Neil A. James; Kenneth G. Boyd; Sabolc Pap (Environmental Processes, 2025)

The role of MEGF10 in myoblast fusion and hypertrophic response to overload of skeletal muscle - Louise Richardson; Ruth Hughes; Colin A. Johnson; Stuart Egginton; Michelle Peckham (Journal of Muscle Research and Cell Motility, 2025)
Biallelic mutations in multiple EGF domain protein 10 ( MEGF10 ) gene cause EMARDD (early myopathy, areflexia, respiratory distress and dysphagia) in humans, a severe recessive myopathy, associated with reduced numbers of PAX7 positive satellite cells. To better understand the role of MEGF10 in satellite cells, we overexpressed human MEGF10 in mouse H-2k b -tsA58 myoblasts and found that it inhibited fusion. Addition of purified extracellular domains of human MEGF10, with (ECD) or without (EGF) the N-terminal EMI domain to H-2k b -tsA58 myoblasts, showed that the ECD was more effective at reducing myoblast adhesion and fusion by day 7 of differentiation, yet promoted adhesion of myoblasts to non-adhesive surfaces, highlighting the importance of the EMI domain in these behaviours. We additionally tested the role of Megf10 in vivo using transgenic mice with reduced ( Megf10 +/− ) or no ( Megf10 −/− ) Megf10. We found that the extensor digitorum longus muscle had fewer anti-Pax7 stained cell nuclei and was less able to undergo hypertrophy in response to muscle overload concomitant with a lower level of satellite cell activation. Taken together, our data suggest that MEGF10 may promote satellite cell adhesion and survival and prevent premature fusion helping to explain its role in EMARDD.

Crown Exposure Regulates Aboveground Wood Productivity Responses to Soil Fertility in Lowland Tropical Forests - José A. Medina‐Vega; Álvaro Duque; Daniel Zuleta; Nicolás Castaño; Renato Valencia; Salomón Aguilar; David Mitre; Rolando Pérez; Shawn K. Y. Lum; David F. R. P. Burslem; Michael J. O'Brien; Glen Reynolds; et al. (Ecology Letters, 2025)
Understanding the drivers of aboveground wood productivity (AWP) in tropical forests is crucial for explaining ecosystem functioning and predicting their responses to environmental change. While climatic water availability is a well‐established driver, the role of soil nutrients and their interaction with other resources remains uncertain. We investigated how soil nutrients and light interactions shape AWP in lowland tropical forests using fine‐scale soil and tree (≥ 1 cm DBH) data from 15 large forest plots. Canopy‐exposed trees are nutrient‐limited, with AWP increasing more with phosphorus (P) than with potassium (K), indicating P's greater role in plant growth and productivity. Conversely, understory AWP declined in fertile areas, likely due to intensified size‐asymmetric competition. At the population level (mean across canopy layers), no relationship between soil nutrients and AWP emerged because contrasting responses among layers offset any overall association. Our results suggest that fine‐scale heterogeneity and canopy stratification drive nutrient effects on tropical forest productivity.

Replication of experiments and the canonisation of incorrect conclusions - Stuart A. West; Maxwell N. Burton-Chellew (Evolution and Human Behavior, 2025)

Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

Organic ultraviolet filters in Irish sediments and biosolids - Martin Sharkey; Yulong Ma; Liu Yang; Stuart Harrad; Mark G. Healy; William A. Stubbings; Ann Marie Coggins (Science of The Total Environment, 2025)

Repeated barrier drown-out is required to facilitate long-distance migration of a potamodromous fish - Jason D. Thiem; Benjamin G. Fanson; David Ryan; Gavin L. Butler; David A. Crook; Doug J. Harding; Anthony Townsend; Ian J. Wooden; Ivor Stuart (Aquatic Sciences, 2025)
Migratory fish species are highly vulnerable to stream fragmentation. Potamodromous golden perch ( Macquaria ambigua ) inhabit the barrier-laden Murray–Darling Basin (MDB), Australia’s largest river system, and its lifecycle includes a requirement for uninterrupted stretches of flowing water habitat. Owing to these barriers, large-scale connectivity in many regions is limited to periods of high flow events that facilitate barrier drown-out. We undertook a 3-year (2021–2024) study using telemetry to quantify the movements of 150 adult golden perch from the Barwon–Darling River over a period that encompassed numerous high flow events and flooding. Approximately 75% of tagged golden perch undertook movements > 50 km, with > 90% of movements in an upstream direction, extending up to 1500 km and associated with increased river discharge. Tributary entries were detected on multiple occasions, with an apparent preference for specific tributaries. Ten fish migrated > 1000 km upstream across multiple flow events. The results of this study (1) highlight the importance of the Barwon–Darling River and tributaries as a key migration conduit for adult golden perch, (2) demonstrate that multiple flow events are required to achieve large-scale dispersal and (3) provide quantitative flow-movement relationships that can be used to support inter-regional management actions. These management actions might include barrier removal, the construction of fishways and protection of tributary–mainstem flow events.

Population Genetics and Invasion History of the European Starling Across Aotearoa New Zealand - Bryan Thompson; Kamolphat Atsawawaranunt; Melissa C. Nehmens; William S. Pearman; E. Owen Perkins; Pavel Pipek; Lee A. Rollins; Hui Zhen Tan; Annabel Whibley; Anna W. Santure; Katarina C. Stuart (Molecular Ecology, 2025)
The expansion of human settlements over the past few centuries is responsible for an unprecedented number of invasive species introductions globally. An important component of biological invasion management is understanding how introduction history and postintroduction processes have jointly shaped present‐day distributions and patterns of population structure, diversity and adaptation. One example of a successful invader is the European starling ( Sturnus vulgaris ), which was intentionally introduced to numerous countries in the 19th century, including Aotearoa New Zealand, where it has become firmly established. We used reduced representation sequencing to characterise the genetic population structure of the European starling in New Zealand, comparing it to that present in sampling locations in the native range and invasive Australian range. The population structure and genetic diversity patterns we found suggested restricted gene flow from the majority of New Zealand to the northmost sampling location (Auckland). We also profiled genetic bottlenecks and shared outlier genomic regions, which supported historical accounts of translocations between both Australian subpopulations and New Zealand, and provided evidence of which documented translocation events were more likely to have been successful. Using these results as well as historic demographic patterns, we demonstrate how genomic analysis complements even well‐documented invasion histories to better understand invasion processes, with direct implications for understanding contemporary gene flow and informing invasion management.

Impact of wildfires on sediment quality in estuaries in New South Wales, Australia - Thayanne L. Barros; Mariana Mayer-Pinto; Katherine A. Dafforn; Stuart L. Simpson; Mark Farrell; Sally A. Bracewell; Emma L. Johnston (Chemosphere, 2025)

Noble gas constraint of CO2 source and connectivity in a CO2-rich gas reservoir, offshore Angola - Stuart M.V. Gilfillan; James A. Scott; Honggang Zhou; Magali Pujol (Marine and Petroleum Geology, 2025)

Climate-driven trans-Tasman population increase of the habitat-modifying, range extending sea urchin Centrostephanus rodgersii - Sterling B. Tebbett; Graham J. Edgar; Celia A. Balemi; John P. Keane; Nick T. Shears; Arie J.P. Spyksma; Rick D. Stuart-Smith; Scott D. Ling (Journal of Environmental Management, 2025)

The influence of primary depositional conditions on Hg behaviour during early thermal maturation - Asri O. Indraswari; Joost Frieling; Erdem Idiz; Tamsin A. Mather; Alexander J. Dickson; Hugh C. Jenkyns; Stuart A. Robinson; Isabel M. Fendley; Oliver Neilson (Chemical Geology, 2025)

Seasonality of meridional overturning in the subpolar North Atlantic: density flux as a metric for understanding the Atlantic meridional overturning circulation - Alan D. Fox; Neil J. Fraser; Stuart A. Cunningham (Ocean Science, 2025)
The Atlantic meridional overturning circulation (AMOC) has a notable seasonal component. This influences the jet stream and the location, frequency, and intensity of extreme weather events. Understanding this seasonality is important for mitigating the impacts of AMOC changes on European weather and climate. Here, we place meridional overturning and fluxes in a coherent framework. This framework highlights the integral relationship between meridional overturning circulation and property transports, both being functions purely of the overturning streamfunction Ψ. Using this framework, we examine the seasonality observed in overturning and density, temperature, and freshwater fluxes at the Overturning in the Subpolar North Atlantic Program (OSNAP) line in the subpolar North Atlantic. We find the seasonal cycle of the MOC metric (the standard measure of overturning, defined as the maximum of the overturning streamfunction) to be dominated by Ekman transports and the large-scale seasonal cycle of surface density; heat flux to be dominated by barotropic velocity variability; the seasonal cycle of freshwater flux to be dominated by a combination of barotropic velocities and the salinity in the western boundary current; and density flux to reflect a broad range of characteristics and processes. We show that the MOC metric is a poor predictor, on seasonal timescales, of either density fluxes or the more societally relevant ocean heat and freshwater transports. This is due to each of these metrics responding to different physical processes. The MOC metric, on seasonal timescales at least, has very high sensitivity to near-surface physical characteristics in a limited geographical area. These characteristics are not necessarily reflective of the fundamental processes driving overturning. Therefore, we suggest caution in the use of the standard MOC metric when studying overturning and the routine use of the density flux as a valuable additional overturning metric.

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Assessing the ability of advanced pre-treatment to reduce disinfection by-product formation and finished water toxicity - Peta A. Neale; Stuart J. Khan; Jiaying Li; Denis M. O’Carroll; Frederic D.L. Leusch (Water Research, 2025)

Ice-burial history and early Holocene thinning of the Scandinavian Ice Sheet at Gaustatoppen, southern Norway - Jane Lund Andersen; Nathaniel A. Lifton; Henriette Linge; Finlay Stuart; Jesper Olsen; Vivi K. Pedersen (Quaternary Science Reviews, 2025)

Limited mercury (Hg) partitioning into bitumen and efficient gaseous Hg reabsorption during early thermal maturation of organic-rich mudrocks - Asri O. Indraswari; Joost Frieling; Erdem Idiz; Tamsin A. Mather; Hugh C. Jenkyns; Stuart A. Robinson; Alexander J. Dickson (Geochimica et Cosmochimica Acta, 2025)

Rational desalting strategy enables controllable fabrication of oil-loaded polysaccharide coacervate particles - Mingwei Wang; Zilong Zhong; Qinyu Zhang; Haiyan Huang; Jiangtao Guo; Shiting Zhang; Martien A. Cohen Stuart; Junyou Wang; Yuanyuan Chen (Food Hydrocolloids, 2025)

Biophysical drivers of coral reef community structure across a tropical benthic seascape - Rosalie A. Wright; Sasha Hills; Courtney E. Stuart; Kaya Malhi; Pirta Palola; Cassandra E. Benkwitt; Hannah E. Epstein; Teva Beguet; Helen V. Ford; Melissa Ward; Lisa M. Wedding (Coral Reefs, 2025)
Coral reefs are global biodiversity hotspots, important for ocean health and providing ecosystem services for thousands of species (including humans). Coral benthic communities form the structural basis of these ecosystems, influencing ecological processes and ecosystem functions. For thousands of years, coral benthic communities have been driven by naturally occurring properties of the environment, which we refer to as biophysical drivers. However, as humans increasingly encroach on and alter coastal marine ecosystems, anthropogenic conditions may override biophysical drivers, making it challenging to identify the sources of changes in community composition and consequent ecosystem functioning. Here, we use multivariate analyses to demonstrate that bathymetric slope (surface steepness) and intercardinal bearing, a proxy for wind and wave exposure, are significant drivers of benthic composition across Tetiaroa, French Polynesia, a remote coral atoll where the influences of biophysical conditions have not been previously investigated. Distance-based redundancy analysis concluded that together, these biophysical variables explained 66.02% of the variance in benthic community composition. Determining the most important drivers of benthic community composition in this area of minimal human influence provides baseline data for natural coral reef ecosystems. This information will help us understand and predict coral reef community responses to changing environmental conditions and guide conservation and restoration efforts of this ecologically important atoll.

The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2025)

Environmental Predictability in Phylogenetic Comparative Analysis: How to Measure It and Does It Matter? - Ming Liu; Louis Bell‐Roberts; Carlos A. Botero; Charlie K. Cornwallis; Stuart A. West (Global Ecology and Biogeography, 2025)
Aim Abiotic environmental conditions shape ecological and evolutionary processes, yet quantifying their influence on organisms remains challenging due to variation among metrics and their intercorrelations. This study evaluates the utility of temporal environmental predictability measures and assesses their explanatory power in phylogenetic comparative analyses. Innovation We systematically compare widely used metrics of predictability and explore their correlations with environmental means and variances in a global meteorological dataset. Using cooperative breeding birds as a case study, we assess the impact of including predictability metrics in phylogenetic comparative analyses. We demonstrate the consequences of choosing specific metrics and the trade‐offs between increased data inclusion and model interpretability. Main Conclusions Predictability metrics, though intuitively meaningful, have been conceptualised and quantified with diverse approaches. We found that different measures of predictability can exhibit contrasting global patterns and strong correlations with other environmental quantities. Therefore, our findings caution against overloading statistical analyses with correlated predictors, highlighting the need for a thoughtful selection of environmental metrics to avoid spurious interpretations in ecological and evolutionary studies.

Using inclusive fitness and eco-evolutionary theory to model cultural evolution - Ryosuke Iritani; Stuart A. West (Evolution and Human Behavior, 2025)

Domains of laws yet domains of No Law: Energy and work, responsible free will choice, and doing - Sudip Patra; Stuart A. Kauffman (BioSystems, 2025)

Phylogeography of reef fishes across the line Islands: uncovering population structure in a data deficient region - Mackenzie Woods; Brian J. Zgliczynski; Stuart A. Sandin; Dakota Betz; Ronald S. Burton (Marine Biology, 2025)
Despite decades of study, it remains difficult to predict the genetic structure of populations of marine species, even with extensive knowledge of the regional oceanography, geography, and the life history of the species. Genetic data provide key insights into population structure that cannot be otherwise inferred. To this end, phylogeographic patterns across the Line Islands were assessed in three unrelated species of reef-associated fish, Stegastes aureus , Lutjanus bohar , and Pseudanthias bartlettorum using the mitochondrial gene cytochrome oxidase I (COI). All three species show evidence of significant population differentiation, with the sharpest break separating the southernmost islands of Vostok and Millennium from the islands to the north. This pattern is broadly consistent with results of larval dispersal simulations based on available ocean current data and estimated planktonic dispersal durations for the three species. Bayesian generalized linear modeling shows correlation between geographic distance and genetic distance for L. bohar and P. bartlettorum but was unable to find a significant predictor variable for differentiation in S. aureus . While the presence of differentiated fish populations within the Line Islands is clearly demonstrated, the reasons for the apparent phylogeographic break near the southern end of the archipelago remain unclear.

Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

Consistent Unimodal Body Length Distributions in Hundreds of Reef Fishes Across Diverse Life Histories - Freddie J. Heather; Shane A. Richards; Nils C. Krueck; Rick D. Stuart‐Smith; Simon J. Brandl; Jordan M. Casey; Graham J. Edgar; Neville Barrett; Valeriano Parravicini; Asta Audzijonyte (Fish and Fisheries, 2025)
Animal body size distributions result from interactions of growth, mortality and recruitment. In ecology and fisheries science, theoretical models of fish body size distributions are widely used but rely on life‐history parameters—growth coefficient (K) and natural mortality rate (M)—that remain unknown for most species and are challenging to estimate. Analysing data from underwater visual surveys and exhaustive sampling, representing 3068 populations across 797 species of shallow‐water, mostly unfished marine fishes, we demonstrate that post‐recruitment body length distributions exhibit a consistent unimodal shape across species and populations. When scaled to the mean body length, these distributions are strikingly similar across all teleost and elasmobranch species, with diverse life histories and maximum body sizes ranging from 1 cm to 3 m. Observed size structure can be approximated by a truncated normal distribution with a coefficient of variation of ~0.34 (SE = 0.002). Such consistent observed body size distributions could be aligned with Beverton–Holt population dynamics theory, if assuming an M/K ratio of ~1.5 and logistic observational selectivity with 50% detectability at ~40% of maximum body length. Alternatively, observed distributions could reflect deviations from theoretical expectations, and reconciling the unimodal distributions with theory may require relaxing some model assumptions, such as continuous recruitment, constant density‐independent growth or constant natural mortality. Overall, the consistency of population‐ and species‐level body length distributions means that unfished size structure could be predicted from a single body size parameter. It also suggests evolutionary convergence of diverse growth and mortality processes towards a narrow range of viable outcomes.

International Consortium on Ageing-Related Pathologies (ICCARP) Audiovestibular Group: fostering international consensus to refine International Classification of Diseases (ICD-11) codes for hearing loss across the life course - Dialechti Tsimpida; Michael A. Akeroyd; Barry L. Bentley; Shuvarthi Bhattacharjee; Michael R. Bowl; Emma Broome; Stuart R. G. Calimport; Sian Calvert; Gary Christopher; Tom Dening; Silvia Di Bonaventura; Ankita Goswami; et al. (GeroScience, 2025)

Identification of a novel potyvirus from the nickel-hyperaccumulating plant Senecio coronatus in South Africa - Dongjin Choi; Stuart K. Meier; Hyerin Park; Seungwoo Baek; Myeung Seok Choi; Robert A. Ingle; Yoonsoo Hahn (South African Journal of Botany, 2025)

Investigating the desorption of polybrominated diphenyl ethers from polyethylene microplastics to sediment - Jingxi Jin; Shijie Wang; Simeon Onoja; Yulong Ma; William A. Stubbings; Mohamed Abou-Elwafa Abdallah; Stuart Harrad (Science of The Total Environment, 2025)

ESG mapping of the Australian mining sector – The state of play on mobilising spatial datasets for decision making - Eléonore Lèbre; Karol Czarnota; Stuart D.C. Walsh; Marcus Haynes; Natasha Ufer; Laura J. Sonter; Rachakonda Sreekar; Pascal Bolz; Nevenka Bulovic; Claire Côte; Nadja C. Kunz; Steven Micklethwaite; et al. (Resources Policy, 2025)

The Itremo Massif Protected Area in the Central Highlands of Madagascar — a plant species checklist - Franck Rakotonasolo; Landy R. Rajaovelona; Andry A. Rakotoarisoa; Fitiavana Rasaminirina; Nantenaina H. Rakotomalala; Ary Misa Andry; Velosoa Razafiniary; Henintsoa Razanajatovo; Nomentsoa Randriamamonjy; Vonona Randrianasolo; Olinirina P. Nanjarisoa; Solofo E. Rakotoarisoa; et al. (Kew Bulletin, 2025)
Summary The Itremo Massif Protected Area was established and is managed by Kew Madagascar. Here, we publish a plant species checklist of the Itremo Massif Protected Area. It is one of the first expert-verified plant species checklists to be generated for a protected area in Madagascar and includes 749 plant species, 353 genera and 103 families. For each species, full synonymy, notes on vernacular names, global distribution, distribution in Madagascar, elevation, habitat and ecology, flowering period, conservation status and specimen lists are provided.

Sugarcane (Saccharum spp. hybrids) biotechnology research in South Africa - Sandra J. Snyman; Aimee C. Koch; Robyn M. Jacob; Shailesh V. Joshi; Sharon A. McFarlane; Christell van der Vyver; R. Stuart Rutherford (In Vitro Cellular & Developmental Biology - Plant, 2025)
Commercial sugarcane, Saccharum spp. hybrids, arose from interspecific crossing in the late 1890s and the resultant complex polyploid genome has challenged conventional breeding approaches. The grower- and miller-funded South African Sugarcane Research Institute (SASRI) has a 100-yr history which began by breeding for local agroclimatic regions. Biotechnology for cultivar improvement was introduced in the early 1990s. Collaborations with local research institutes and the International Consortium for Sugarcane Biotechnology (ICSB) have enabled advances such as the genome sequence being published this year, signifying a real opportunity to implement bioinformatic and marker techniques for targeted cultivar enhancement. This review focuses on biotechnology-related interventions that have supported sugarcane research and resulted in SASRI-bred N cultivars being widely grown in many sub-Saharan African sugarcane-growing countries.

Synthesis of zeolites from different kaolin deposits worldwide - Abdulsalami S. Kovo; Stuart M. Holmes; Carlos A. Rios; Abdulrazak J. Otaru; Ambali S. Abdulkareem; Victoria C. Eluwa (Applied Clay Science, 2025)

Microplastics in agricultural soils following sewage sludge applications: Evidence from a 25-year study - Stuart J.F.F. Ramage; Malcolm Coull; Patricia Cooper; Colin D. Campbell; Radhakrishna Prabhu; Kyari Yates; Lorna A. Dawson; Sandhya Devalla; Eulyn Pagaling (Chemosphere, 2025)

Conservation changed but not divided - Sam A. Reynolds; Sara Beery; Neil Burgess; Mark Burgman; Stuart H.M. Butchart; Steven J. Cooke; David Coomes; Finn Danielsen; Enrico Di Minin; América Paz Durán; Amy Hinsley; Sadiq Jaffer; et al. (Trends in Ecology & Evolution, 2025)

Vehicles kill birds on sandy beaches: The global evidence - Thomas A. Schlacher; Michael A. Weston; Brooke Maslo; Jenifer E. Dugan; Kyle A. Emery; David M. Hubbard; Brendan P. Kelaher; Mariano Lastra; Stuart E. Parsons (Science of The Total Environment, 2025)

Unraveling composite magnetic fabrics through tensor decomposition - David Finn; Josef Jezek; Stuart A. Gilder; Michael R. Wack; Felix Ostermeier; Michael Jackson; Robert S. Coe; Michael J. Branney (Physics of the Earth and Planetary Interiors, 2025)

Comparison of naturally altered archaeological glasses from a marine environment with accelerated laboratory tests; implications for modelling long-term corrosion - Clare L. Thorpe; Nick Aldred; Stuart Creasey-Gray; Martin C. Stennett; Eperke A. Rencz; Susan Nehzati; Latham T. Haigh; Garry Manifold; Nishta Vallo; Christoph Lenting; Claire L. Corkhill; Russell J. Hand (Applied Geochemistry, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Soil Carbon Saturation: What Do We Really Know? - Katerina Georgiou; Denis Angers; Ryan E. Champiny; M. Francesca Cotrufo; Matthew E. Craig; Sebastian Doetterl; A. Stuart Grandy; Jocelyn M. Lavallee; Yang Lin; Emanuele Lugato; Christopher Poeplau; Katherine S. Rocci; et al. (Global Change Biology, 2025)
Managing soils to increase organic carbon storage presents a potential opportunity to mitigate and adapt to global change challenges, while providing numerous co‐benefits and ecosystem services. However, soils differ widely in their potential for carbon sequestration, and knowledge of biophysical limits to carbon accumulation may aid in informing priority regions. Consequently, there is great interest in assessing whether soils exhibit a maximum capacity for storing organic carbon, particularly within organo–mineral associations given the finite nature of reactive minerals in a soil. While the concept of soil carbon saturation has existed for over 25 years, recent studies have argued for and against its importance. Here, we summarize the conceptual understanding of soil carbon saturation at both micro‐ and macro‐scales, define key terminology, and address common concerns and misconceptions. We review methods used to quantify soil carbon saturation, highlighting the theory and potential caveats of each approach. Critically, we explore the utility of the principles of soil carbon saturation for informing carbon accumulation, vulnerability to loss, and representations in process‐based models. We highlight key knowledge gaps and propose next steps for furthering our mechanistic understanding of soil carbon saturation and its implications for soil management.

Supplementation strategies to control propionic acid accumulation resulting from ammonia inhibition in dry anaerobic digestion: Osmoprotectants, activated carbon and trace elements - Ildefonso Rocamora; Stuart T. Wagland; Francis Hassard; Raffaella Villa; Miriam Peces; Ioannis A. Fotidis; Edmon W. Simpson; Oliver Fernández; Yadira Bajón-Fernández (Journal of Environmental Chemical Engineering, 2025)

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

The potential for AI to revolutionize conservation: a horizon scan - Sam A. Reynolds; Sara Beery; Neil Burgess; Mark Burgman; Stuart H.M. Butchart; Steven J. Cooke; David Coomes; Finn Danielsen; Enrico Di Minin; América Paz Durán; Francis Gassert; Amy Hinsley; et al. (Trends in Ecology & Evolution, 2025)

Galactic cosmic ray environment predictions for the NASA BioSentinel Mission, part 2:Post-mission validation - Shirin Rahmanian; Tony C. Slaba; Stuart George; Leslie A. Braby; Sharmila Bhattacharya; Tore Straume; Sergio R. Santa Maria (Life Sciences in Space Research, 2025)

Source versus crustal processing and the evolution of the mantle wedge in the Trans-Mexican Volcanic Belt: Constraints from Os-O-He isotope systematics in olivine - J. Ahmadi; E. Widom; S.M. Straub; R. Sanchez; D.C. Kuentz; A. Gómez-Tuena; R. Espinasa-Perena; I.N. Bindeman; F.M. Stuart (Chemical Geology, 2025)

Evaluating the effectiveness of seabird bycatch mitigation measures for pelagic longlines in the South Atlantic - James B. Bell; Johannes H. Fischer; Ana P.B. Carneiro; Shane Griffiths; Alessandra Bielli; Sebastián Jiménez; Steffen Oppel; Richard A. Phillips; Helen M. Wade; Oliver Yates; Stuart A. Reeves (Biological Conservation, 2025)

Groundtruthing assessments of lab-based coral thermal tolerance with large-area imaging - Crystal J. McRae; Nathaniel Hanna Holloway; Guanyan Keelung Chen; Michael T. Connelly; Hung-Kai Chen; Zong-Min Ye; Kendall S. Chancellor; Yu-Chi Chang; Ming-Qi Jiang; Kwok Wai Lam; Yu-Ting Qiu; Tung-Yung Fan; et al. (Coral Reefs, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

CoralBleachRisk —Global Projections of Coral Bleaching Risk in the 21st Century - Camille Mellin; Stuart Brown; Scott F. Heron; Damien A. Fordham (Global Ecology and Biogeography, 2025)
Motivation Timing, duration and severity of marine heatwaves are changing rapidly in response to anthropogenic climate change, thereby increasing the frequency of coral bleaching events. Mass coral bleaching events result from cumulative heat stress, which is commonly quantified through degree heating weeks (DHW). Here we introduce CoralBleachRisk , a daily‐resolution global dataset that characterises sea surface temperatures, heat stress anomalies and the timing, duration and magnitude of severe coral bleaching conditions from the recent past (1985) to the future (2100) under three contrasting Shared Socioeconomic Pathways. Our projections are downscaled to a 0.5° resolution ( ~ 50 km), bias‐corrected and validated using remotely sensed data of sea surface temperatures and a global dataset of historical coral bleaching events. An accompanying online software tool allows non‐specialist users to access aggregated metrics of coral bleaching risk and generate time series projections of coral vulnerability for Earth's coral reefs. Our dataset enables regional to global comparisons of future trends in severe coral bleaching risk. Main Types of Variables Contained Sea surface temperature (SST), SST anomaly, DHW, annual timing and duration of Bleaching Alerts. Spatial Location Global. Time Period 1985–2100. Major Taxa and Level of Measurement Coral communities. Software Format Netcdf (.nc).

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Adverse impacts of off-road vehicles on coastal dune vegetation are widespread, substantial, and long-lasting: Evidence from a global meta-analysis of sandy beach-dune systems - Thomas A. Schlacher; Michael A. Weston; Shane Orchard; Brendan P. Kelaher; Brooke Maslo; Jenifer E. Dugan; David M. Hubbard; Leonardo Costa; Melanie J. Bishop; Kristal N. Kostoglu; Ben L. Gilby; Christofer J. Henderson; et al. (Estuarine, Coastal and Shelf Science, 2025)

Small-scale fisheries in ecologically sensitive areas in Latin America and the Caribbean: Do marine protected areas benefit fisheries governance? - Ana Cinti; Luisa Ramirez; Mauricio Castrejón; Jaime A. Aburto; Luciana Loto; Stuart Fulton; Mario Rueda; Alexandre Schiavetti; Francisco J. Fernández-Rivera Melo; Manuel Bravo; Daniela Trigueirinho Alarcon; Valéria Penchel Araújo; et al. (Ambio, 2025)
Many small-scale fisheries (SSFs) in Latin America and the Caribbean (LAC) operate in ecologically sensitive areas, where balancing conservation and resource use is challenging. 'Multiple-use' marine protected areas (MPAs) have been implemented to accommodate SSFs (among other uses) within areas designated for conservation, creating opportunities and challenges for SSF governance. We analyzed eleven case studies from LAC to explore: (1) how different MPA institutional designs affect key aspects of SSF governance and (2) the links between these effects and the type of initiative that promoted MPA establishment (origin). Results indicate that the existence of an MPA benefited SSF governance in many ways, with more pronounced positive effects in MPAs with mixed to bottom-up origin supported by well-organized fishing groups. In addition, the presence of supportive MPA authorities that leveraged local capacities and initiatives and adopted flexible and collaborative governance systems made a difference in several cases. Lessons for integrating MPA and SSF governance are drawn.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Antibiotics residues in inland and transitional sediments - Martin Sharkey; William A. Stubbings; Stuart Harrad; Mark G. Healy; Shijie Wang; Jingxi Jin; Ann Marie Coggins (Chemosphere, 2024)

Comprehensive characterization of European house dust contaminants: Concentrations and profiles, geographical variability, and implications for chemical regulation and health risk - Peter Haglund; Nikiforos A. Alygizakis; Adrian Covaci; Lisa Melymuk; Pernilla Bohlin Nizzetto; Pawel Rostkowski; Alexandre Albinet; Sylvana Alirai; Dagny Aurich; Stefan Bieber; Ana Ballesteros-Gómez; Amanda A. Brennan; et al. (Science of The Total Environment, 2024)

Simulation of bench-scale CO2 injection using a coupled continuum-discrete approach - Nicholas A. Ashmore; Magdalena M. Krol; Stuart M.V. Gilfillan; Cole J.C. Van De Ven; Kevin G. Mumford; Ian L. Molnar (Science of The Total Environment, 2024)

Legacy and emerging flame retardants in sediments and wastewater treatment plant-derived biosolids - Martin Sharkey; Shijie Wang; Stuart Harrad; William A. Stubbings; Mark G. Healy; Jingxi Jin; Ann Marie Coggins (Science of The Total Environment, 2024)

Widespread upper-ocean deoxygenation in the Alpine-Mediterranean Tethys during the Toarcian Oceanic Anoxic Event - Wenhan Chen; David B. Kemp; Hugh C. Jenkyns; Stuart A. Robinson; Shouyi Jiang; Chengrong Pan; Chao Li (Global and Planetary Change, 2024)

Investigation of simultaneous production of H2 and separable carbon from CH4 in a fluidised bed of NiO/Ca2Fe2O5/CaO particles - Karine Alkhatib; Made Santihayu Sukma; Stuart A. Scott; Yaoyao Zheng (Fuel, 2024)

Spatial and temporal variation in the prevalence of illegal lead shot in reared and wild mallards harvested in England - Emily A. Strong; Sarah L. Crowley; Julia L. Newth; Michelle F. O'Brien; Rosa Lopez Colom; Sean A. Davis; Ruth L. Cromie; Stuart Bearhop; Robbie A. McDonald (Environmental Pollution, 2024)

Evaluation of ballistics euthanasia applied to stranded cetaceans using ethological and post-mortem computed tomography assessment - Rebecca M. Boys; Brian C. W. Kot; Gordon Lye; Ngaio J. Beausoleil; Stuart Hunter; Karen A. Stockin (Veterinary Research Communications, 2024)
Debilitated stranded cetaceans with low survival likelihood, may require euthanasia to avoid further suffering. Euthanasia can involve chemical or physical methods, including ballistics. Ballistics should cause instantaneous, permanent insensibility through brainstem disruption. Despite wide application, there is limited understanding of ballistics-related welfare outcomes. We opportunistically examined behaviour of three maternally-dependent cetaceans following shooting and the related cranial disruption post-mortem using computed tomography (PMCT). Our aim was to understand whether a ‘humane death’, i.e., euthanasia, was achieved. Each animal was shot using different projectile types: soft non-bonded, solid, and soft bonded. In two animals, insensibility was not immediately assessed following shooting, although both were reported as ‘instantaneously insensible’. From our analysis, all animals displayed musculoskeletal responses to shooting, including peduncle stiffening and slack lower jaw, followed by musculature relaxation 24-, 10.3- and 20.8-seconds post-ballistics, respectively. The animal shot with a soft non-bonded projectile also displayed agonal convulsions and tail-lifting for 16-seconds post-shot; these were not observed for solid or soft bonded projectiles. PMCT findings indicated projectile disruption to the brainstem and/or spinal cord likely to cause near-instantaneous insensibility. However, extra-cranial wounding was also evident for the soft non-bonded projectile, highlighting potential for additional welfare compromise. Our results demonstrate that ballistics can achieve a relatively rapid death in young, stranded cetaceans, but careful equipment selection is required. To ensure a humane death, verification of insensibility must be undertaken immediately following shooting. Further studies should be undertaken to improve knowledge of appropriate procedures and equipment for euthanasia, ensuring humane deaths for compromised cetaceans.

Nutrients and polyphenols-rich Sorghum bicolor genotypes as complementary therapy for Alzheimer’s disease - Rasheed A. Abdulraheem; Ralph N. Martins; Prashant Bharadwaj; Zhaoyu Li; Ranil Coorey; Stuart Johnson; W. M. A. D. Binosha Fernando (Phytochemistry Reviews, 2024)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder and most common cause of dementia among older people. The main pathological hallmarks of AD are formation of insoluble amyloid beta senile plaques and paired helical filaments of neurofibrillary tangles. AD features gradual memory decline, mild to severe cognitive impairment, eventually total dependence of patients on caregivers. Currently available drugs have not been able to modify AD pathology. This has drawn increasing attention to plant food materials with high nutritional and bioactive constituents as potential complementary therapy for AD. Sorghum bicolor is a widely available cost-effective source of proteins, fats, crude fibres, biopeptides and polyphenols which are vital for human wellbeing. This review discussed the major mechanisms underlying AD pathology. The nutritional and bioactive constituents of Sorghum bicolor grains were extensively described. There is limited report on anti-AD activities of sorghum grains. Therefore, the pharmacological mechanisms of action including scavenging of reactive oxygen species, inhibition of oxidative stress, anti-acetylcholinesterase activity and modulation of mitophagy were only speculated. This comprehensive update suggests more robust innovative studies that will provide critical theoretical details necessary to promote utilization of sorghum grains as functional food or source of bioactive molecules for AD therapy.

Dynamic rates of Freshwater Drum near the northern extent of their range: evidence of environment-recruitment relationships - Marshall Stuart; Nicholas Kludt; Mark A. Pegg; Federica Montesanto; Cade Lyon; Connor J. Chance-Ossowski (Environmental Biology of Fishes, 2024)

Paleoclimatic Controls on Clay Mineral Distribution in the Early Cretaceous (Barremian): The Wessex Basin, Southeast England - Oladapo O. Akinlotan; Ogechukwu A. Moghalu; Stuart J. Hatter; Byami A. Jolly; Okwudiri A. Anyiam (Journal of Earth Science, 2024)

Unifying Coral Reef States Through Space and Time Reveals a Changing Ecosystem - Simon J. Brandl; Jérémy Carlot; Rick D. Stuart‐Smith; Sally A. Keith; Nicholas A. J. Graham; Graham J. Edgar; Jérémy Wicquart; Shaun K. Wilson; Rucha Karkarey; Mary K. Donovan; Jesus E. Arias‐Gonzalez; Rohan Arthur; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological state shifts that alter the structure and function of entire ecosystems are a concerning consequence of human impact. Yet, when, where and why discrete ecological states emerge remains difficult to predict and monitor, especially in high‐diversity systems. We sought to quantify state shifts and their drivers through space and time in the most ecologically complex marine ecosystem: tropical coral reefs. Location Worldwide. Time Period 1987–2019. Major Taxa Studied Coral reef communities. Methods Using a global dataset of 3375 coral reef surveys, along with 13 time series datasets ranging between 1987 and 2019, we applied a novel double‐dichotomy approach to classify coral reefs into four simplified and discrete states based on the relative contributions of corals versus algae to benthic cover and small‐bodied versus large‐bodied fishes to fish standing stock. We then examined state shifts considering a range of spatial predictors and tested whether states have shifted directionally over time, and the nature of the most common transitions. Results We show that geographic, environmental and anthropogenic context fundamentally shapes coral reef states at the local scale, which explains disparities among case studies, and stakes out critical baseline expectations for regional management efforts. We also reveal clear multi‐decadal state shifts on coral reefs: over time, systems dominated by reef‐building corals and small‐bodied, planktivorous fishes tend to have been replaced with reefs characterised by algae and larger‐bodied fishes. Main Conclusions Our results suggest a previously unrecognised transition from systems that harness external subsidies through small‐bodied consumers associated with structurally complex live corals, to herbivore‐dominated systems with stronger bottom‐up dynamics. Overall, the partitioning of complex reef ecosystems into a small suite of discrete ecological states suggests that spatial context‐dependency, shifting baselines and changes in reef functioning are crucial considerations for coral reef management in the 21st century.

Exome variant prioritization in a large cohort of hearing-impaired individuals indicates IKZF2 to be associated with non-syndromic hearing loss and guides future research of unsolved cases - Hedwig M. Velde; Maryam Vaseghi-Shanjani; Jeroen J. Smits; Gayatri Ramakrishnan; Jaap Oostrik; Mieke Wesdorp; Galuh Astuti; Helger G. Yntema; Lies Hoefsloot; Cris P. Lanting; Martijn A. Huynen; Anna Lehman; et al. (Human Genetics, 2024)
Although more than 140 genes have been associated with non-syndromic hereditary hearing loss (HL), at least half of the cases remain unexplained in medical genetic testing. One reason is that pathogenic variants are located in ‘novel’ deafness genes. A variant prioritization approach was used to identify novel (candidate) genes for HL. Exome-wide sequencing data were assessed for subjects with presumed hereditary HL that remained unexplained in medical genetic testing by gene-panel analysis. Cases in group AD had presumed autosomal dominantly inherited HL (n = 124), and in group AR, presumed autosomal recessive HL (n = 337). Variants in known and candidate deafness genes were prioritized based on allele frequencies and predicted effects. Selected variants were tested for their co-segregation with HL. Two cases were solved by variants in recently identified deafness genes ( ABHD12 , TRRAP ). Variant prioritization also revealed potentially causative variants in candidate genes associated with recessive and X-linked HL. Importantly, missense variants in IKZF2 were found to co-segregate with dominantly inherited non-syndromic HL in three families. These variants specifically affected Zn 2+ -coordinating cysteine or histidine residues of the zinc finger motifs 2 and 3 of the encoded protein Helios. This finding indicates a complex genotype–phenotype correlation for IKZF2 defects, as this gene was previously associated with non-syndromic dysfunction of the immune system and ICHAD syndrome, including HL. The designed strategy for variant prioritization revealed that IKZF2 variants can underlie non-syndromic HL. The large number of candidate genes for HL and variants therein stress the importance of inclusion of family members for variant prioritization.

A framework for optimising opportunistic collaborative syntheses to propel ecological conservation - Ana M.M. Sequeira; Amanda E. Bates; Graeme Hays; David W. Sims; Samantha Andrzejaczek; Asta Audzijonyte; Julia K. Baum; Martin Beal; Barbara Block; Joshua Cinner; Kaitlyn Cowley; Eric Gilman; et al. (Biological Conservation, 2024)

Comparison of three reanalysis‐driven regional climate models over New Zealand: Climatology and extreme events - Isaac Campbell; Peter B. Gibson; Stephen Stuart; Ashley M. Broadbent; Abha Sood; Amir A. S. Pirooz; Neelesh Rampal (International Journal of Climatology, 2024)
Three ~12‐km reanalysis‐driven regional climate models (RCMs) are evaluated in terms of capturing climatologies and extremes of precipitation, temperature and surface wind over Aotearoa/New Zealand (NZ). NZ provides an excellent case study for evaluating high‐resolution RCMs due to its coastal and complex terrain and isolated geographical position in the midlatitudes, exposed to both tropical and polar influences. Overall, we find that the RCMs faithfully reproduce the observed climate, with precipitation and temperature climatologies particularly well‐captured. However, the RCMs display significant differences from observations in capturing the surface wind climatology, highlighting a remaining key challenge. The excess “drizzle problem” is apparent to varying degrees, leading to a weaker representation in the length of meteorological drought in some regions. The RCMs also diverge in reproducing diurnal temperature range which appears partly related to cloud cover. Finally, we discuss the important role of observational uncertainty in the context of model evaluation.

The contribution of nearshore oceanography to temporal variation in larval dispersal - Katrina A. Catalano; Elizabeth J. Drenkard; Enrique N. Curchitser; Allison G. Dedrick; Michelle R. Stuart; Humberto R. Montes; Malin L. Pinsky (Ecology, 2024)
Patterns of population connectivity shape ecological and evolutionary phenomena from population persistence to local adaptation and can inform conservation strategy. Connectivity patterns emerge from the interaction of individual behavior with a complex and heterogeneous environment. Despite ample observation that dispersal patterns vary through time, the extent to which variation in the physical environment can explain emergent connectivity variation is not clear. Empirical studies of its contribution promise to illuminate a potential source of variability that shapes the dynamics of natural populations. We leveraged simultaneous direct dispersal observations and oceanographic transport simulations of the clownfish Amphiprion clarkii in the Camotes Sea, Philippines, to assess the contribution of oceanographic variability to emergent variation in connectivity. We found that time‐varying oceanographic simulations on both annual and monsoonal timescales partly explained the observed dispersal patterns, suggesting that temporal variation in oceanographic transport shapes connectivity variation on these timescales. However, interannual variation in observed mean dispersal distance was nearly 10 times the expected variation from biophysical simulations, revealing that additional biotic and abiotic factors contribute to interannual connectivity variation. Simulated dispersal kernels also predicted a smaller scale of dispersal than the observations, supporting the hypothesis that undocumented abiotic factors and behaviors such as swimming and navigation enhance the probability of successful dispersal away from, as opposed to retention near, natal sites. Our findings highlight the potential for coincident observations and biophysical simulations to test dispersal hypotheses and the influence of temporal variability on metapopulation persistence, local adaptation, and other population processes.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Environmental factors have stronger effects than biotic processes in patterns of intertidal populations along the southeast coast of Brazil - Cesar A.M.M. Cordeiro; André Pardal; Luis Giménez; Áurea M. Ciotti; Stuart R. Jenkins; Michael T. Burrows; Gray A. Williams; Ronaldo A. Christofoletti (Marine Environmental Research, 2024)

Revisiting reactive oxygen species production in hypoxia - Ricardo Alva; Jacob E. Wiebe; Jeffrey A. Stuart (Pflügers Archiv - European Journal of Physiology, 2024)

Methane fluxes in tidal marshes of the conterminous United States - Ariane Arias‐Ortiz; Jaxine Wolfe; Scott D. Bridgham; Sara Knox; Gavin McNicol; Brian A. Needelman; Julie Shahan; Ellen J. Stuart‐Haëntjens; Lisamarie Windham‐Myers; Patty Y. Oikawa; Dennis D. Baldocchi; Joshua S. Caplan; et al. (Global Change Biology, 2024)
Methane (CH 4 ) is a potent greenhouse gas (GHG) with atmospheric concentrations that have nearly tripled since pre‐industrial times. Wetlands account for a large share of global CH 4 emissions, yet the magnitude and factors controlling CH 4 fluxes in tidal wetlands remain uncertain. We synthesized CH 4 flux data from 100 chamber and 9 eddy covariance (EC) sites across tidal marshes in the conterminous United States to assess controlling factors and improve predictions of CH 4 emissions. This effort included creating an open‐source database of chamber‐based GHG fluxes ( https://doi.org/10.25573/serc.14227085 ). Annual fluxes across chamber and EC sites averaged 26 ± 53 g CH 4 m −2 year −1 , with a median of 3.9 g CH 4 m −2 year −1 , and only 25% of sites exceeding 18 g CH 4 m −2 year −1 . The highest fluxes were observed at fresh‐oligohaline sites with daily maximum temperature normals (MATmax) above 25.6°C. These were followed by frequently inundated low and mid‐fresh‐oligohaline marshes with MATmax ≤25.6°C, and mesohaline sites with MATmax >19°C. Quantile regressions of paired chamber CH 4 flux and porewater biogeochemistry revealed that the 90th percentile of fluxes fell below 5 ± 3 nmol m −2 s −1 at sulfate concentrations >4.7 ± 0.6 mM, porewater salinity >21 ± 2 psu, or surface water salinity >15 ± 3 psu. Across sites, salinity was the dominant predictor of annual CH 4 fluxes, while within sites, temperature, gross primary productivity (GPP), and tidal height controlled variability at diel and seasonal scales. At the diel scale, GPP preceded temperature in importance for predicting CH 4 flux changes, while the opposite was observed at the seasonal scale. Water levels influenced the timing and pathway of diel CH 4 fluxes, with pulsed releases of stored CH 4 at low to rising tide. This study provides data and methods to improve tidal marsh CH 4 emission estimates, support blue carbon assessments, and refine national and global GHG inventories.

Lead-up and manifestation of the Oceanic Anoxic Event 2 at the DSDP Site 398 (Vigo Seamount, NW Iberian offshore): Palynological and geochemical insights - Iván Rodríguez-Barreiro; Artai A. Santos; Uxue Villanueva-Amadoz; Stephen Louwye; Stuart A. Robinson; José B. Diez (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Lanthanum and cerium functionalised forestry waste biochar for phosphate removal: Mechanisms and real-world applications - Sabolc Pap; Qunying Zhao; Ilgaz Cakin; Paul P.J. Gaffney; Stuart W. Gibb; Mark A. Taggart (Chemical Engineering Journal, 2024)

The new kid on the block in insect pest management: sprayable RNAi goes commercial - Junjie Yan; Ralf Nauen; Stuart Reitz; Andrei Alyokhin; Jiang Zhang; David Mota-Sanchez; Yonggyun Kim; Subba Reddy Palli; Silvia I. Rondon; Brian A. Nault; Juan Luis Jurat-Fuentes; Michael S. Crossley; et al. (Science China Life Sciences, 2024)

Epichloë – a key element of New Zealand’s agricultural landscape - Stuart D. Card; Daniel A. Bastías; Wei Zhang; David E. Hume; John R. Caradus (New Zealand Journal of Botany, 2024)

Comparison of two carbonaceous supported Fe-rich adsorbents for arsenate removal: A functionalisation and mechanistic study with applicability to groundwater treatment - Sabolc Pap; Maja Turk Sekulic; Hai Nguyen Tran; Huan-Ping Chao; Peter J. Gilbert; Stuart W. Gibb; Mark A. Taggart (Chemosphere, 2024)

Plastic ingestion and trace element contamination of Manx shearwaters Puffinus puffinus on the Faroe Islands - William F. Mills; Catrin Norris; Stuart Black; Richard A. Phillips; Sjúrður Hammer; Bergur Olsen; Jóhannis Danielsen (Marine Pollution Bulletin, 2024)

Catalytic pyrolysis of high-density polyethylene (HDPE) over hierarchical ZSM-5 zeolites produced by microwave-assisted chelation-alkaline treatment - Zhipeng Qie; Huan Xiang; Huaizhong Xiang; Run Zou; Abdullah Alhelali; Hassan Alhassawi; Shengzhe Ding; Yilai Jiao; Stuart M. Holmes; Arthur A. Garforth; Xin Gao; Jiawei Wang; et al. (Fuel, 2024)

An Earthen Sill as a Measure to Mitigate Salt Intrusion in Estuaries - Gijs G. Hendrickx; Laura A. Manuel; Stuart G. Pearson; Stefan G. J. Aarninkhof; Ehab A. Meselhe (Estuaries and Coasts, 2024)
At a global scale, deltas are vital economic hubs, in part due to the combination of their access to inland regions via river systems with their proximity to sea. However, with the sea in close vicinity also comes the threat of freshwater contamination by saline seawater, especially during droughts. This study explores the potential of a mitigation measure to estuarine salt intrusion, namely the construction of a (temporary) earthen sill—a measure implemented in the Lower Mississippi River near New Orleans (LA, USA). This study suggests design guidelines on how a sill can be used to mitigate estuarine salt intrusion: the design should focus on the longitudinal placement and the height of the sill, and the mitigating efficiency of the sill reduces with increasing tidal range. Overall, a (temporary) sill has great potential to reduce salt intrusion in salt wedge estuaries if there is sufficient water depth available.

Dietary metabarcoding of keystone sardine species reveals the importance of their ichthyoplankton prey in food webs of the Southern Brazilian Bight fisheries - Anna Karolina Oliveira de Queiroz; Maria A. Gasalla; Marcele Laux; Renato Renison Moreira Oliveira; Fabricio dos Anjos Santa Rosa; Audun Schrøder‐Nielsen; Felippe A. Postuma; João Bráullio de Luna Sales; Hugo J. de Boer; Quentin Mauvisseau; Jonathan Stuart Ready (Fisheries Oceanography, 2024)
Clupeiform fishes are ecologically and economically important species contributing to industrial and artisanal fisheries worldwide. They represent key links in food webs, influencing the dynamic between trophic levels. The dietary interactions of these species are poorly studied in many regions, yet essential for fisheries management. To elucidate the role of these species in food webs of the Southern Brazilian Bight pelagic fisheries, we used metabarcoding analysis of fish stomach contents of Clupeiformes and possible predators. Onboard sampling from March to September 2016 allowed for processing of 87 stomach samples representing 31 species (including 12 samples representing three species of Clupeiformes). Links between trophic levels showed the predominance of Sardinella brasiliensis and Engraulis anchoita as important dietary items of a large range of fishes (28 species belonging to 18 families) and representing the majority of the total prey read abundance assigned to clupeiform fishes (~46% and ~32%, respectively). Opisthonema oglinum contributed to the diet of 16 species in 13 families and ~18% of total read abundance of clupeiform fishes as prey. The appearance of multiple clupeiform taxa in the diet of predators that are not commonly associated with pelagic prey indicates that ecosystem‐based fisheries management should not be separated between pelagic and demersal fisheries. The diet of Clupeiformes revealed an unexpectedly large diversity of fish species and a low proportion of invertebrates (

Site-specific risk-based threshold (RBT) concentrations for sewage-associated markers in estuarine swimming waters - Warish Ahmed; Mary E. Schoen; Jeffrey Soller; Joanna Ciol Harrison; Kerry A. Hamilton; Metasebia Gebrwold; Stuart L. Simpson; Sudhi Payyappat; Michele Cassidy; Nathan Harrison; Colin Besley (Science of The Total Environment, 2024)

Machine learning-based metabolomics analysis reveals the early biomarkers for Diplodia stem-end rot in grapefruit caused by Lasiodiplodia theobromae - Jin-Pyo An; Jingwen Li; Katia Rodrigues-Stuart; Megan M. Dewdney; Mark A. Ritenour; Yu Wang (Postharvest Biology and Technology, 2024)

Emplacement of shocked basement clasts during crater excavation in the Ries impact structure - Fabian Dellefant; Lina Seybold; Claudia A. Trepmann; Stuart A. Gilder; Iuliia V. Sleptsova; Stefan Hölzl; Melanie Kaliwoda (International Journal of Earth Sciences, 2024)
In the Aumühle quarry of the Ries impact structure, moderately shocked clasts from the Variscan basement occur sandwiched between overlying suevite and components derived from the Mesozoic sedimentary cover of the underlying Bunte Breccia without distinct shock effects. We analyzed the clasts by optical microscopy, scanning electron microscopy (SEM/EDS/EBSD), and Raman spectroscopy to unravel their emplacement relation to the overlying suevite and the sediment-rock clasts of the Bunte Breccia. Clasts sizes range up to few decimeters and are embedded in a fine-grained lithic matrix; no impact-melt fragments are observed. Amphibolite clasts contain maskelynite with few lamellar remnants of feldspar, indicating shock pressures of 28–34 GPa. Amphiboles have cleavage fractures and ( $$\overline{1}$$ 1 ¯ 01) mechanical twins suggesting differential stresses > 400 MPa. Felsic gneiss components have optically isotropic SiO 2 indicative of shock pressures ≈35 GPa. Metagranite cataclasite clasts contain shocked calcite aggregates and quartz with a high density of fine rhombohedral planar deformation features indicating shock pressures ≈20 GPa. The moderately shocked basement clasts originate from deeper levels of the transient cavity and lower radial distance to the center of the structure compared to the sediment-rock clasts. Both were ballistically ejected during crater excavation. In accordance with palaeo- and rock magnetic data, they were mixed during turbulent deposition at the top of the Bunte Breccia before the emplacement of suevite. The high amount of basement clasts below suevite and on top of the underlying Bunte Breccia is consistent with the commonly reported inverse stratigraphy in the Ries impact structure. Graphical Abstract

Comparison between dexmedetomidine and a combination of medetomidine-vatinoxan on muscle tissue saturation in privately-owned adult dogs undergoing intradermal testing - Stuart R. McKenzie; Ludovica Chiavaccini; Raiane A. Moura; Domenico Santoro (Research in Veterinary Science, 2024)

Environmental DNA highlights the influence of salinity and agricultural run-off on coastal fish assemblages in the Great Barrier Reef region - Aashi Parikh; Johan Pansu; Adam Stow; Michael St J. Warne; Christine Chivas; Paul Greenfield; Frédéric Boyer; Stuart Simpson; Rachael Smith; Jacob Gruythuysen; Geoffrey Carlin; Natalie Caulfield; et al. (Environmental Pollution, 2024)

Corrigendum to “Modelling mould growth in domestic environments using relative humidity and temperature” [Build. Environ. 208 (2022) 108583] - Tamaryn Menneer; Markus Mueller; Richard A. Sharpe; Stuart Townley (Building and Environment, 2024)

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Physiological mechanisms associated with the use of a passive heat intervention: positive implications for soccer substitutes - Gavin Cowper; Stuart Goodall; Kirsty M. Hicks; Louise Burnie; Kai T. Fox; Ashleigh Keenan; Enrico De Martino; Marc A. Briggs (European Journal of Applied Physiology, 2024)
Purpose Soccer substitutes are exposed to periods of limited activity before entering match-play, likely negating benefits of active warm-ups. This study aimed to determine the effects of using a passive heat intervention following a pre-match, and half-time warm-up, on muscle and core temperature in soccer players during ambient (18 °C) and cold (2 °C) conditions. Methods On four occasions, 8 male players, completed a pre-match warm-up, followed by 45 min of rest. Following this, participants completed a half-time re-warm-up followed by an additional 45 min of rest, simulating a full match for an unplaying substitute. During periods of rest, participants wore either standardised tracksuit bottoms (CON), or heated trousers (HEAT), over typical soccer attire. Results Vastus lateralis temperature declined less in HEAT compared to CON following the 1st half in 2 °C (Δ − 4.39 ± 0.81 vs. − 6.21 ± 1.32 °C, P = 0.002) and 18 °C (Δ − 2.48 ± 0.71 vs. − 3.54 ± 0.88 °C, P = 0.003). These findings were also observed in the 2nd half for the 2 °C (Δ − 4.36 ± 1.03 vs. − 6.26 ± 1.04 °C, P = 0.002) and 18 °C (Δ − 2.85 ± 0.57 vs. − 4.06 ± 1 °C, P = 0.018) conditions. In addition, core temperature declined less in HEAT compared to CON following the 1st (Δ − 0.41 ± 0.25 vs. − 0.84 ± 0.41 °C, P = 0.037) and 2nd (Δ − 0.25 ± 0.33 vs. − 0.64 ± 0.34 °C, P = 0.028) halves of passive rest in 2 °C, with no differences in the 18 °C condition. Perceptual data confirmed that participants were more comfortable in HEAT vs. CON in 2 °C ( P < 0.01). Conclusions Following active warm-ups, heated trousers attenuate the decline in muscle temperature in ambient and cold environments.

An experimental study of benthic habitat selection in yellow-phase American eels (Anguilla rostrata) - Melissa A. Braham; Stuart A. Welsh; Dustin M. Smith (Environmental Biology of Fishes, 2024)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Neogene–Quaternary initiation of the Southern Malawi Rift and linkage to the reactivated Carboniferous–Jurassic Shire Rift - Oyewande Ojo; Stuart N. Thomson; Daniel A. Laó-Dávila (Tectonophysics, 2024)

Organophosphate triesters and their diester degradation products in the atmosphere–A critical review - Shijie Wang; Jingxi Jin; Yulong Ma; William A. Stubbings; Muideen Remilekun Gbadamosi; Mohamed Abou-Elwafa Abdallah; Stuart Harrad (Environmental Pollution, 2024)

Human habitat modification, not apex scavenger decline, drives isotopic niche variation in a carnivore community - Olivia Bell; Menna E. Jones; Manuel Ruiz-Aravena; David G. Hamilton; Sebastien Comte; Rowena Hamer; Rodrigo K. Hamede; Jason Newton; Stuart Bearhop; Robbie A. McDonald (Oecologia, 2024)
Top carnivores can influence the structure of ecological communities, primarily through competition and predation; however, communities are also influenced by bottom-up forces such as anthropogenic habitat disturbance. Top carnivore declines will likely alter competitive dynamics within and amongst sympatric carnivore species. Increasing intraspecific competition is generally predicted to drive niche expansion and/or individual specialisation, while interspecific competition tends to constrain niches. Using stable isotope analysis of whiskers, we studied the effects of Tasmanian devil Sarcophilus harrisii declines upon the population- and individual-level isotopic niches of Tasmanian devils and sympatric spotted-tailed quolls Dasyurus maculatus subsp. maculatus. We investigated whether time since the onset of devil decline (a proxy for severity of decline) and landscape characteristics affected the isotopic niche breadth and overlap of devil and quoll populations. We quantified individual isotopic niche breadth for a subset of Tasmanian devils and spotted-tailed quolls and assessed whether between-site population niche variation was driven by individual-level specialisation. Tasmanian devils and spotted-tailed quolls demonstrated smaller population-level isotopic niche breadths with increasing human-modified habitat, while time since the onset of devil decline had no effect on population-level niche breadth or interspecific niche overlap. Individual isotopic niche breadths of Tasmanian devils and spotted-tailed quolls were narrower in human-modified landscapes, likely driving population isotopic niche contraction, however, the degree of individuals’ specialisation relative to one another remained constant. Our results suggest that across varied landscapes, mammalian carnivore niches can be more sensitive to the bottom-up forces of anthropogenic habitat disturbance than to the top-down effects of top carnivore decline.

Goats discriminate emotional valence in the human voice - Marianne A. Mason; Stuart Semple; Harry H. Marshall; Alan G. McElligott (Animal Behaviour, 2024)

Social-ecological vulnerability to environmental extremes and adaptation pathways in small-scale fisheries of the southern California Current - Fiorenza Micheli; Andrea Saenz-Arroyo; Emilius Aalto; Rodrigo Beas-Luna; Charles A. Boch; Juan Camilo Cardenas; Giulio A. De Leo; Eduardo Diaz; Antonio Espinoza-Montes; Elena Finkbeiner; Jan Freiwald; Stuart Fulton; et al. (Frontiers in Marine Science, 2024)
Coastal ecosystems and human communities are threatened worldwide by climate change, and shocks from social, market and political change. There is an urgent global need to promote resilient food production and livelihoods in the face of these shocks. Small-scale fisheries (SSF) in rural settings can be particularly vulnerable as they frequently lack the resources, rights and infrastructure to respond to shocks originating outside the focal systems. We examined ecological and social outcomes of environmental extremes in a SSF socio-ecological system (SES) by using long-term oceanographic (between 2010-2019) and ecological (2006-2018) data tracking change in a kelp forest ecosystem of Baja California, Mexico, and concurrent documentation of proactive and reactive actions of a fishing community organized in a cooperative. Results indicate a complex landscape of ‘winners’ and ‘losers’ among species and fisheries exposed to unprecedented environmental extremes, including marine heat waves and prolonged hypoxia, and a suite of adaptive actions by the local fishing cooperative, and others in the region, that have helped confront these rapid and drastic changes. Cooperatives have established voluntary marine reserves to promote recovery of affected populations and have invested in diversification of activities enabled by access rights, collective decision-making, and participatory science programs. Results indicate that local actions can support social and ecological resilience in the face of shocks, and that enabling locally-driven adaptation pathways is critical to resilience. This case study highlights the crucial importance of strengthening and supporting rights, governance, capacity, flexibility, learning, and agency for coastal communities to respond to change and sustain their livelihoods and ecosystems in the long run.

Aligning theoretical and empirical representations of soil carbon-to-nitrogen stoichiometry with process-based terrestrial biogeochemistry models - Katherine S. Rocci; Cory C. Cleveland; Brooke A. Eastman; Katerina Georgiou; A. Stuart Grandy; Melannie D. Hartman; Emma Hauser; Hannah Holland-Moritz; Emily Kyker-Snowman; Derek Pierson; Peter B. Reich; Else P. Schlerman; et al. (Soil Biology and Biochemistry, 2024)

Integrated cyclostratigraphy of the Cau core (SE Spain) - A timescale for climate change during the early Aptian Anoxic Event (OAE 1a) and the late Aptian - Rafael Martínez-Rodríguez; Sietske J. Batenburg; José M. Castro; Ginés A. de Gea; Luis M. Nieto; Pedro A. Ruiz-Ortiz; Stuart Robinson (Global and Planetary Change, 2024)

Elevated atmospheric CO 2 drives decreases in stable soil organic carbon in arid ecosystems: Evidence from a physical fractionation and organic compound analysis - Kelsey H. Jensen; A. Stuart Grandy; Jed P. Sparks (Global Change Biology, 2024)
The increasing concentration of CO 2 in the atmosphere is perturbing the global carbon (C) cycle, altering stocks of organic C, including soil organic matter (SOM). The effect of this disturbance on soils in arid ecosystems may differ from other ecosystems due to water limitation. In this study, we conducted a density fractionation on soils previously harvested from the Nevada Desert FACE Facility (NDFF) to understand how elevated atmospheric CO 2 (eCO 2 ) affects SOM stability. Soils from beneath the perennial shrub, Larrea tridentata , and from unvegetated interspace were subjected to a sodium polytungstate density fractionation to separate light, particulate organic matter (POM, 3 ) from heavier, mineral associated organic matter (MAOM, >1.85 g/cm 3 ). These fractions were analyzed for organic C, total N, δ 13 C and δ 15 N, to understand the mechanisms behind changes. The heavy fraction was further analyzed by pyrolysis GC/MS to assess changes in organic compound composition. Elevated CO 2 decreased POM‐C and MAOM‐C in soils beneath L. tridentata while interspace soils exhibited only a small increase in MAOM‐N. Analysis of δ 13 C revealed incorporation of new C into both POM and MAOM pools indicating eCO 2 stimulated rapid turnover of both POM and MAOM. The largest losses of POM‐C and MAOM‐C observed under eCO 2 occurred in soils 20–40 cm in depth, highlighting that belowground C inputs may be a significant driver of SOM decomposition in this ecosystem. Pyrolysis GC/MS analysis revealed a decrease in organic compound diversity in the MAOM fraction of L. tridentata soils, becoming more similar to interspace soils under eCO 2 . These results provide further evidence that MAOM stability may be compromised under disturbance and that SOC stocks in arid ecosystems are vulnerable under continued climate change.

Closing the gap between existing large‐area imaging research and marine conservation needs - Orion S. McCarthy; Kanisha Contractor; Will F. Figueira; Arthur C. R. Gleason; T. Shay Viehman; Clinton B. Edwards; Stuart A. Sandin (Conservation Biology, 2024)
Emerging technology has immense potential to increase the scale and efficiency of marine conservation. One such technology is large‐area imaging (LAI), which relies on structure‐from‐motion photogrammetry to create composite products, including 3‐dimensional (3‐D) environmental models, that are larger in spatial extent than the individual images used to create them. Use of LAI has become widespread in certain fields of marine science, primarily to measure the 3D structure of benthic ecosystems and track change over time. However, the use of LAI in the field of marine conservation appears limited. We conducted a review of the coral reef literature on the use of LAI to identify research themes and regional trends in applications of this technology. We also surveyed 135 coral reef scientists and conservation practitioners to determine community familiarity with LAI, evaluate barriers practitioners face in using LAI, and identify applications of LAI believed to be most exciting or relevant to coral conservation. Adoption of LAI was limited primarily to researchers at institutions based in advanced economies and was applied infrequently to conservation, although conservation practitioners and survey respondents from emerging economies indicated they expect to use LAI in the future. Our results revealed disconnect between current LAI research topics and conservation priorities identified by practitioners, highlighting the need for more diverse, conservation‐relevant research using LAI. We provide recommendations for how early adopters of LAI (typically Global North scientists from well‐resourced institutions) can facilitate access to this conservation technology. These recommendations include developing training resources, creating partnerships for data storage and analysis, publishing standard operating procedures for LAI workflows, standardizing methods, developing tools for efficient data extraction from LAI products, and conducting conservation‐relevant research using LAI.

A horizon scan of global biological conservation issues for 2024 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Stuart H.M. Butchart; Holly M. Butterworth; Stewart J. Clarke; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jennifer James; et al. (Trends in Ecology & Evolution, 2024)

Organophosphate ester flame retardants and plasticizers in house dust and mental health outcomes among Canadian mothers: A nested prospective cohort study in CHILD - Stephanie A. Foster; Molly L. Kile; Perry Hystad; Miriam L. Diamond; Liisa M. Jantunen; Piush J. Mandhane; Theo J. Moraes; Garthika Navaranjan; James A. Scott; Elinor Simons; Padmaja Subbarao; Tim K. Takaro; et al. (Environmental Research, 2024)

Neural network for evaluation of the impact of the UK COVID-19 national lockdown on atmospheric concentrations of PAHs and PBDEs - André Henrique Rosa; William A. Stubbings; Olumide Emmanuel Akinrinade; Erik Sartori Jeunon Gontijo; Stuart Harrad (Environmental Pollution, 2024)

Knowledge and values drive acceptability of lethal control of kangaroos among the Australian public - Stuart Dawson; Courtenay Dawson; Malcolm S. Kennedy; Tracey L. Kreplins; John D.C. Linnell; Patricia A. Fleming (Biological Conservation, 2024)

Effects of management objectives and rules on marine conservation outcomes - Natalie C. Ban; Emily S. Darling; Georgina G. Gurney; Whitney Friedman; Stacy D. Jupiter; W. Peni Lestari; Irfan Yulianto; Sinta Pardede; Sukma A. R. Tarigan; Puji Prihatiningsih; Sangeeta Mangubhai; Waisea Naisilisili; et al. (Conservation Biology, 2023)
Understanding the relative effectiveness and enabling conditions of different area‐based management tools is essential for supporting efforts that achieve positive biodiversity outcomes as area‐based conservation coverage increases to meet newly set international targets. We used data from a coastal social–ecological monitoring program in 6 Indo‐Pacific countries to analyze whether social, ecological, and economic objectives and specific management rules (temporal closures, fishing gear‐specific, species‐specific restrictions) were associated with coral reef fish biomass above sustainable yield levels across different types of area‐based management tools (i.e., comparing those designated as marine protected areas [MPAs] with other types of area‐based management). All categories of objectives, multiple combinations of rules, and all types of area‐based management had some sites that were able to sustain high levels of reef fish biomass—a key measure for coral reef functioning—compared with reference sites with no area‐based management. Yet, the same management types also had sites with low biomass. As governments advance their commitments to the Kunming–Montreal Global Biodiversity Framework and the target to conserve 30% of the planet's land and oceans by 2030, we found that although different types of management can be effective, most of the managed areas in our study regions did not meet criteria for effectiveness. These findings underscore the importance of strong management and governance of managed areas and the need to measure the ecological impact of area‐based management rather than counting areas because of their designation.

The importance of time-resolved personal Dosimetry in space: The ISS Crew Active Dosimeter - Ramona Gaza; A. Steve Johnson; Bryan Hayes; Thomas Campbell-Ricketts; Jani Rakkola; Mena Abdelmelek; Cary Zeitlin; Stuart George; Nicholas Stoffle; Andrew Castro; Clif Amberboy; Edward Semones (Life Sciences in Space Research, 2023)

Particle showers detected on ISS in Timepix pixel detectors - Martin Kroupa; Thomas Campbell-Ricketts; Stuart P. George; Amir A. Bahadori; Lawrence S. Pinsky (Life Sciences in Space Research, 2023)

The role of mantle melting in granite-associated hydrothermal systems: He–Ar isotopes in fluids responsible for Sn–Ag–Pb–Zn mineralization in northeast China - Zhenhua Zhou; Jingwen Mao; Finlay M. Stuart; Xinkai Chen; Simon A. Wilde; Hegen Ouyang; Xu Gao; Jiaqi Zhao (Mineralium Deposita, 2023)

Integrating Menominee model for sustainable forestry with Systems Thinking competency through 3D virtual tours - Ellie Nasr-Azadani; Erica A. H. Smithwick; Stuart J. Steidle; Melissa S. Lucash; Denice H. Wardrop; Nathan T. Fregien; Thomas R. Kenote (Sustainability Science, 2023)
Sustainability competencies enable planners, the public, local communities, academics, and development practitioners to address environmental challenges, better envision the future and devise practical solutions. A key competency in this framework is Systems Thinking, allowing individuals to think comprehensively at different temporal and spatial scales. Among all interested groups, local and Indigenous communities play a significant role in preserving the sustainability of the natural environment and co-producing knowledge based on traditional ecological knowledge. Hence, new approaches are needed to integrate traditional ecological values into competency-based practices to articulate problems and related solutions. This project introduces place-based scenarios rooted in conventional forest management concerning two identified subsets of Bloom’s Taxonomy, Remembering and Understanding, including some competencies necessary for thinking systemically. Overall, 57 participants, including students and staff of the College of Menominee Nation and Menominee community members, in northeast Wisconsin, USA, randomly experienced two visual tools with the same information presented as either: a website with simple 2D images or a 3D virtual tour to investigate which visualization method can help better articulate systems, their components, and behaviors. Participants answered two kinds of questionnaires based on either cognitive mapping or reflection on place-based scenarios. The results show that 3D virtual tour users better demonstrated proficiency in Remembering and Understanding compared to users who experienced the 2D website. Our results thus highlight the potential for 3D virtual experiences to enable sustainability competencies. However, given the observed differences among age and educational groups, future visualization tools and associated research methods should attend to audiences’ competencies, preferences, and comfort, especially among older age groups.

Assessing animal welfare during a stranding of pygmy killer whales ( Feresa attenuata ) - Rebecca M. Boys; Ngaio J. Beausoleil; Stuart Hunter; Emma L. Betty; Bethany Hinton; Karen A. Stockin (Marine Mammal Science, 2023)
Empirical assessment of cetacean welfare to inform stranding interventions is lacking. Here, potential welfare indicators are described for two stranded pygmy killer whales ( Feresa attenuata ), along with euthanasia procedures and pathology of potential relevance. The animals were filmed for 3.5 and 1.5 hr, respectively, allowing assessment of 19 indicators, including animal behaviors and human interventions. Eight interventions and 19 animal behaviors were identified; 17 and 11 behaviors were displayed by animal 1 and 2, respectively. Examination of ballistics euthanasia revealed atypical projectile placement and characterized animal behavioral responses, but welfare implications could not be assessed as insensibility was not verified in‐field. Pulmonary edema and renal degeneration were documented in both animals; differential etiologies include ischemia–reperfusion, shock, and/or myopathy. Potential relationships among histopathology and welfare indicators are explored to infer affective experiences. For example, simultaneous head‐lifting with respiration increased over time which, alongside pulmonary edema, suggests these animals experienced breathlessness. Other likely affective states include fatigue and discomfort; there are insufficient data to estimate the intensity or duration of these experiences or to provide an overall welfare grade/score. Further data are required to validate the proposed welfare indicators and to progress development of holistic approaches to welfare assessment at cetacean strandings.

Molecular complexity and diversity of persistent soil organic matter - Andrew R. Jones; Ram C. Dalal; Vadakattu V.S.R. Gupta; Susanne Schmidt; Diane E. Allen; Geraldine E. Jacobsen; Michael Bird; A. Stuart Grandy; Jonathan Sanderman (Soil Biology and Biochemistry, 2023)

Life in the fast lane: Revisiting the fast growth—High survival paradigm during the early life stages of fishes - Dominique Robert; Jun Shoji; Pascal Sirois; Akinori Takasuka; Ignacio A. Catalán; Arild Folkvord; Stuart A. Ludsin; Myron A. Peck; Su Sponaugle; Patricia M. Ayón; Richard D. Brodeur; Emily Y. Campbell; et al. (Fish and Fisheries, 2023)
Early life survival is critical to successful replenishment of fish populations, and hypotheses developed under the Growth‐Survival Paradigm (GSP) have guided investigations of controlling processes. The GSP postulates that recruitment depends on growth and mortality rates during early life stages, as well as their duration, after which the mortality declines substantially. The GSP predicts a shift in the frequency distribution of growth histories with age towards faster growth rates relative to the initial population because slow‐growing individuals are subject to high mortality (via starvation and predation). However, mortality data compiled from 387 cases published in 153 studies (1971–2022) showed that the GSP was only supported in 56% of cases. Selection against slow growth occurred in two‐thirds of field studies, leaving a non‐negligible fraction of cases showing either an absence of or inverse growth‐selective survival, suggesting the growth‐survival relationship is more complex than currently considered within the GSP framework. Stochastic simulations allowed us to assess the influence of key intrinsic and extrinsic factors on the characteristics of surviving larvae and identify knowledge gaps on the drivers of variability in growth‐selective survival. We suggest caution when interpreting patterns of growth selection because changes in variance and autocorrelation of individual growth rates among cohorts can invalidate fundamental GSP assumptions. We argue that breakthroughs in recruitment research require a comprehensive, population‐specific characterization of the role of predation and intrinsic factors in driving variability in the distribution and autocorrelation of larval growth rates, and of the life stage corresponding to the endpoint of pre‐recruited life.

The exhumation history of the middle Hsuehshan Range, Taiwan, as revealed by zircon thermochronological modeling - Chase J. Shyu; Eh Tan; Linda A. Kirstein; Finlay M. Stuart; Yue-Gau Chen (Tectonophysics, 2023)

Challenges in cybersecurity: Lessons from biological defense systems - Edward Schrom; Ann Kinzig; Stephanie Forrest; Andrea L. Graham; Simon A. Levin; Carl T. Bergstrom; Carlos Castillo-Chavez; James P. Collins; Rob J. de Boer; Adam Doupé; Roya Ensafi; Stuart Feldman; et al. (Mathematical Biosciences, 2023)

Permafrost-thaw lake development in Central Yakutia: sedimentary ancient DNA and element analyses from a Holocene sediment record - Izabella Baisheva; Luidmila Pestryakova; Sardana Levina; Ramesh Glückler; Boris K. Biskaborn; Stuart A. Vyse; Birgit Heim; Ulrike Herzschuh; Kathleen R. Stoof-Leichsenring (Journal of Paleolimnology, 2023)
In Central Yakutia (Siberia) livelihoods of local communities depend on alaas (thermokarst depression) landscapes and the lakes within. Development and dynamics of these alaas lakes are closely connected to climate change, permafrost thawing, catchment conditions, and land use. To reconstruct lake development throughout the Holocene we analyze sedimentary ancient DNA (sedaDNA) and biogeochemistry from a sediment core from Lake Satagay, spanning the last c. 10,800 calibrated years before present (cal yrs BP). SedaDNA of diatoms and macrophytes and microfossil diatom analysis reveal lake formation earlier than 10,700 cal yrs BP. The sedaDNA approach detected 42 amplicon sequence variants (ASVs) of diatom taxa, one ASV of Eustigmatophyceae ( Nannochloropsis ), and 12 ASVs of macrophytes. We relate diatom and macrophyte community changes to climate-driven shifts in water level and mineral and organic input, which result in variable water conductivity, in-lake productivity, and sediment deposition. We detect a higher lake level and water conductivity in the Early Holocene (c. 10,700–7000 cal yrs BP) compared to other periods, supported by the dominance of Stephanodiscus sp. and Stuckenia pectinata . Further climate warming towards the Mid-Holocene (7000–4700 cal yrs BP) led to a shallowing of Lake Satagay, an increase of the submerged macrophyte Ceratophyllum, and a decline of planktonic diatoms. In the Late Holocene (c. 4700 cal yrs BP–present) stable shallow water conditions are confirmed by small fragilarioid and staurosiroid diatoms dominating the lake. Lake Satagay has not yet reached the final stage of alaas development, but satellite imagery shows an intensification of anthropogenic land use, which in combination with future warming will likely result in a rapid desiccation of the lake.

Variability in composition of parrotfish bite scars across space and over time on a central Pacific atoll - Jonathan A. Charendoff; Clinton B. Edwards; Nicole E. Pedersen; Vid Petrovic; Brian Zgliczynski; Stuart A. Sandin; Jennifer E. Smith (Coral Reefs, 2023)
Parrotfishes are conspicuous herbivores, microvores, and detritivores in coral reef ecosystems, and the impacts of their feeding, particularly their capacity to expose reef carbonate, have received much attention. In many cases, parrotfish assemblages have been shown to control algal proliferation and promote the settlement of corals and crustose coralline algae (CCA). In extreme cases, high densities of parrotfishes may negatively affect net reef accretion through bioerosion and targeted coral predation. Most evidence describing the impacts of parrotfish foraging on benthic community structure is based upon correlations between benthic composition and parrotfish behavior or abundance, with much less known about process-based change of individual parrotfish bite scars through time. Here, we estimated parrotfish bite selectivity and determined the change in benthic composition within parrotfish bite scars relative to change in the overall reefscape using data collected over a 12-month duration from the fore reef habitat at Palmyra Atoll. We identified 2150 parrotfish bite scars which appeared most frequently on turf algae covered substrata but also on coral, CCA, and encrusting macroalgae. Of those bites taken on live coral, 96% of scars returned to live coral within 12 months. Notably, adult coral survivorship in bite scars was higher than at randomly sampled coral-covered locations not affected by parrotfish bites. The exposed substrate within bite scars was most commonly colonized by the dominant benthic functional group in the area immediately surrounding the scar. We found little evidence of coral recruitment to bite scars (1/2150); however, CCA growth on bites initially on turf algae increased from 18.4 to 32.9% across the two time intervals. Our results suggest that benthic areas affected by parrotfish bites were more likely to undergo a successional shift to a more calcified state relative to unaffected benthic areas, indicating that parrotfish grazing helps maintain highly calcified coral reef ecosystems.

Correction to: Global invasion history and native decline of the common starling: insights through genetics - Katarina C. Stuart; Natalie R. Hofmeister; Julia M. Zichello; Lee A. Rollins (Biological Invasions, 2023)

Negative effects of urbanisation on diurnal and nocturnal pollen‐transport networks - Emilie E. Ellis; Jill L. Edmondson; Kathryn H. Maher; Helen Hipperson; Stuart A. Campbell (Ecology Letters, 2023)
Pollinating insects are declining due to habitat loss and climate change, and cities with limited habitat and floral resources may be particularly vulnerable. The effects of urban landscapes on pollination networks remain poorly understood, and comparative studies of taxa with divergent niches are lacking. Here, for the first time, we simultaneously compare nocturnal moth and diurnal bee pollen‐transport networks using DNA metabarcoding and ask how pollination networks are affected by increasing urbanisation. Bees and moths exhibited substantial divergence in the communities of plants they interact with. Increasing urbanisation had comparable negative effects on pollen‐transport networks of both taxa, with significant declines in pollen species richness. We show that moths are an important, but overlooked, component of urban pollen‐transport networks for wild flowering plants, horticultural crops, and trees. Our findings highlight the need to include both bee and non‐bee taxa when assessing the status of critical plant‐insect interactions in urbanised landscapes.

KRILLPODYM: a mechanistic, spatially resolved model of Antarctic krill distribution and abundance - David B. Green; Olivier Titaud; Sophie Bestley; Stuart P. Corney; Mark A. Hindell; Rowan Trebilco; Anna Conchon; Patrick Lehodey (Frontiers in Marine Science, 2023)
Robust prediction of population responses to changing environments requires the integration of factors controlling population dynamics with processes affecting distribution. This is true everywhere but especially in polar pelagic environments. Biological cycles for many polar species are synchronised to extreme seasonality, while their distributions may be influenced by both the prevailing oceanic circulation and sea-ice distribution. Antarctic krill (krill, Euphausia superba ) is one such species exhibiting a complex life history that is finely tuned to the extreme seasonality of the Southern Ocean. Dependencies on the timing of optimal seasonal conditions have led to concerns over the effects of future climate on krill’s population status, particularly given the species’ important role within Southern Ocean ecosystems. Under a changing climate, established correlations between environment and species may breakdown. Developing the capacity for predicting krill responses to climate change therefore requires methods that can explicitly consider the interplay between life history, biological conditions, and transport. The Spatial Ecosystem And Population Dynamics Model (SEAPODYM) is one such framework that integrates population and general circulation modelling to simulate the spatial dynamics of key organisms. Here, we describe a modification to SEAPODYM, creating a novel model – KRILLPODYM – that generates spatially resolved estimates of krill biomass and demographics. This new model consists of three major components: (1) an age-structured population consisting of five key life stages, each with multiple age classes, which undergo age-dependent growth and mortality, (2) six key habitats that mediate the production of larvae and life stage survival, and (3) spatial dynamics driven by both the underlying circulation of ocean currents and advection of sea-ice. We present the first results of KRILLPODYM, using published deterministic functions of population processes and habitat suitability rules. Initialising from a non-informative uniform density across the Southern Ocean our model independently develops a circumpolar population distribution of krill that approximates observations. The model framework lends itself to applied experiments aimed at resolving key population parameters, life-stage specific habitat requirements, and dominant transport regimes, ultimately informing sustainable fishery management.

Entry fees enhance marine protected area management and outcomes - Chris Brown; Gabby N. Ahmadia; Dominic A. Andradi-Brown; Nur Arafeh-Dalmau; Christina A. Buelow; Max D. Campbell; Graham J. Edgar; Jonas Geldmann; David Gill; Rick D. Stuart-Smith (Biological Conservation, 2023)

Reconstructing mechanisms of extinctions to guide mammal conservation biogeography - Sean Tomlinson; Mark V. Lomolino; John C. Z. Woinarski; Brett P. Murphy; Elizabeth Reed; Chris N. Johnson; Sarah Legge; Kristofer M. Helgen; Stuart C. Brown; Damien A. Fordham (Journal of Biogeography, 2023)
An emerging research program on population and geographic range dynamics of Australia's mammals illustrates an approach to better understand and respond to geographic range collapses of threatened wildlife in general. In 1788, Europeans colonized an Australia with a diverse and largely endemic mammal fauna, where many species that are now extinct or threatened were common and widespread. Subsequent population declines, range collapses and extinctions were caused by introduced predators and herbivores, altered land use, modified fire regimes and the synergies between these threats. Declines in population and range size continue for many Australian mammals despite legislative protection and conservation interventions. Here, we propose an approach that integrates museum data and other historical records into process‐explicit macroecological models to better resolve mammal distributions and abundances as they were at European arrival. We then illustrate how this integrative approach can identify the likely synergistic mechanisms causing mammal population declines across these and other landscapes. This emerging research approach, undertaken with fine temporal and spatial resolution, but at large geographic scales, will provide valuable insights into the different pathways to, and drivers of, extinction. Such insights may, in turn, underpin conservation strategies based on a process‐explicit understanding of population decline and range collapse under alternative scenarios of impending climate and environmental change. Given that similar information is available for other regional biotas, the approach we describe here can be adapted to conserve threatened wildlife in other regions across the globe.

Tidal to decadal scale hydrodynamics at two contrasting cold-water coral sites in the Northeast Atlantic - Christian Mohn; Jørgen L.S. Hansen; Marina Carreiro-Silva; Stuart A. Cunningham; Evert de Froe; Carlos Dominguez-Carrió; Stefan Gary; Ronnie N. Glud; Cordula Göke; Clare Johnson; Telmo Morato; Eva Friis Møller; et al. (Progress in Oceanography, 2023)

Successful use of sexed stallion semen for in vitro embryo production; a preliminary study - Pouya Dini; Alejandro de la Fuente; Juan C Samper; Cristina Cabrera; GR Holyoak; Sheila Megehee; Stuart A Meyers (Journal of Equine Veterinary Science, 2023)

The exploration of NiO/Ca2Fe2O5/CaO in chemical looping methane conversion for syngas and H2 production - Yaoyao Zheng; Made Santihayu Sukma; Stuart A. Scott (Chemical Engineering Journal, 2023)

Modeling airborne pollen concentrations at an urban scale with pollen release from individual trees - Daniel S. W. Katz; Alan P. Baptist; Stuart A. Batterman (Aerobiologia, 2023)

Integrating larval connectivity into the marine conservation decision‐making process across spatial scales - Dominic Muenzel; Kay Critchell; Courtney Cox; Stuart J. Campbell; Raymond Jakub; Wahid Suherfian; La Sara; Iliana Chollett; Eric A. Treml; Maria Beger (Conservation Biology, 2023)
Larval dispersal connectivity is typically integrated into spatial conservation decisions at regional or national scales, but implementing agencies struggle with translating these methods to local scales. We used larval dispersal connectivity at regional (hundreds of kilometers) and local (tens of kilometers) scales to aid in design of networks of no‐take reserves in Southeast Sulawesi, Indonesia. We used Marxan with Connectivity informed by biophysical larval dispersal models and remotely sensed coral reef habitat data to design marine reserve networks for 4 commercially important reef species across the region. We complemented regional spatial prioritization with decision trees that combined network‐based connectivity metrics and habitat quality to design reserve boundaries locally. Decision trees were used in consensus‐based workshops with stakeholders to qualitatively assess site desirability, and Marxan was used to identify areas for subsequent network expansion. Priority areas for protection and expected benefits differed among species, with little overlap in reserve network solutions. Because reef quality varied considerably across reefs, we suggest reef degradation must inform the interpretation of larval dispersal patterns and the conservation benefits achievable from protecting reefs. Our methods can be readily applied by conservation practitioners, in this region and elsewhere, to integrate connectivity data across multiple spatial scales.

Anthropogenic nitrogen pollution threats and challenges to the health of South Asian coral reefs - Stuart C. Painter; Yuri Artioli; Fathimath Hana Amir; Jessica Arnull; Raja S. Ganeshram; Nizam Ibrahim; V. Deepak Samuel; R.S. Robin; R. Raghuraman; R. Purvaja; R. Ramesh; Arjan Rajasuriya; et al. (Frontiers in Marine Science, 2023)
Nitrogen pollution is a widespread and growing problem in the coastal waters of South Asia yet the ecological impacts on the region’s coral ecosystems are currently poorly known and understood. South Asia hosts just under 7% of global coral reef coverage but has experienced significant and widespread coral loss in recent decades. The extent to which this coral ecosystem decline at the regional scale can be attributed to the multiple threats posed by nitrogen pollution has been largely overlooked in the literature. Here, we assess the evidence for nitrogen pollution impacts on corals in the central Indian Ocean waters of India, Sri Lanka and the Maldives. We find that there is currently limited evidence with which to clearly demonstrate widespread impacts on coral reefs from nitrogen pollution, including from its interactions with other stressors such as seawater warming. However, this does not prove there are no significant impacts, but rather it reflects the paucity of appropriate observations and related understanding of the range of potential impacts of nitrogen pollution at individual, species and ecosystem levels. This situation presents significant research, management and conservation challenges given the wide acceptance that such pollution is problematic. Following from this, we recommend more systematic collection and sharing of robust observations, modelling and experimentation to provide the baseline on which to base prescient pollution control action.

Socially transferred materials: why and how to study them - Sanja Maria Hakala; Haruna Fujioka; Katharina Gapp; Ornela De Gasperin; Eléonore Genzoni; Rebecca M. Kilner; Joris M. Koene; Barbara König; Timothy A. Linksvayer; Marie-Pierre Meurville; Matteo A. Negroni; Hugo Palejowski; et al. (Trends in Ecology & Evolution, 2023)

Frontiers of Mathematical Biology: A workshop honouring Professor Edmund Crampin - Robyn Araujo; Douglas Brumley; Joe Cursons; Karen Day; Matthew Faria; Jennifer A. Flegg; Domenic Germano; Hilary Hunt; Peter Hunter; Adrianne Jenner; Stuart Johnston; James M. McCaw; et al. (Mathematical Biosciences, 2023)

Influence of glacier type on bloom phenology in two Southwest Greenland fjords - A.E. Stuart-Lee; J. Mortensen; T. Juul-Pedersen; J.J. Middelburg; K. Soetaert; M.J. Hopwood; A. Engel; L. Meire (Estuarine, Coastal and Shelf Science, 2023)

A Numerical Study of SMART Cables Potential in Marine Hazard Early Warning for the Sumatra and Java Regions - Amir Salaree; Bruce M. Howe; Yihe Huang; Stuart A. Weinstein; Andi Eka Sakya (Pure and Applied Geophysics, 2023)

Global invasion history and native decline of the common starling: insights through genetics - Katarina C. Stuart; Natalie R. Hofmeister; Julia M. Zichello; Lee A. Rollins (Biological Invasions, 2023)
Few invasive birds are as globally successful as the Common or European Starling ( Sturnus vulgaris ). Native to the Palearctic, the starling has been intentionally introduced to North and South America, South Africa, Australia, and the Pacific Islands, enabling us to explore species traits that may contribute to its invasion success. Coupling the rich studies of life history and more recent explorations of genomic variation among invasions, we illustrate how eco-evolutionary dynamics shape the invasion success of this long-studied and widely distributed species. Especially informative is the comparison between Australian and North American invasions, because these populations colonized novel ranges concurrently and exhibit shared signals of selection despite distinct population histories. In this review, we describe population dynamics across the native and invasive ranges, identify putatively selected traits that may influence the starling’s spread, and suggest possible determinants of starling success world-wide. We also identify future opportunities to utilize this species as a model for avian invasion research, which will inform our understanding of species’ rapid evolution in response to environmental change.

Controlling common carp (Cyprinus carpio): barriers, biological traits, and selective fragmentation - M. L. Piczak; P. A. Bzonek; T. C. Pratt; P. W. Sorensen; I. G. Stuart; T. Theÿsmeÿer; N. E. Mandrak; J. D. Midwood; S. J. Cooke (Biological Invasions, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Small-scale oxygen distribution patterns in a coral reef - Adam S. Candy; Shannara K. Taylor Parkins; Fleur C. Van Duyl; Benjamin Mueller; Milou G. I. Arts; Will Barnes; Marie Carstensen; Yun J. H. Scholten; Yusuf C. El-Khaled; Christian Wild; Linda Wegley Kelly; Craig E. Nelson; et al. (Frontiers in Marine Science, 2023)
One mechanism giving fleshy algae a competitive advantage over corals during reef degradation is algal-induced and microbially-mediated hypoxia (typically less than 69.5 µmol oxygen L −1 ). During hypoxic conditions oxygen availability becomes insufficient to sustain aerobic respiration in most metazoans. Algae are more tolerant of low oxygen conditions and may outcompete corals weakened by hypoxia. A key question on the ecological importance of this mechanism remains unanswered: How extensive are local hypoxic zones in highly turbulent aquatic environments, continuously flushed by currents and wave surge? To better understand the concert of biological, chemical, and physical factors that determine the abundance and distribution of oxygen in this environment, we combined 3D imagery, flow measurements, macro- and micro-organismal abundance estimates, and experimentally determined biogenic oxygen and carbon fluxes as input values for a 3D bio-physical model. The model was first developed and verified for controlled flume experiments containing coral and algal colonies in direct interaction. We then developed a three-dimensional numerical model of an existing coral reef plot off the coast of Curaçao where oxygen concentrations for comparison were collected in a small-scale grid using fiberoptic oxygen optodes. Oxygen distribution patterns given by the model were a good predictor for in situ concentrations and indicate widespread localized differences exceeding 50 µmol L -1 over distances less than a decimeter. This suggests that small-scale hypoxic zones can persist for an extended period of time in the turbulent environment of a wave- and surge- exposed coral reef. This work highlights how the combination of three-dimensional imagery, biogenic fluxes, and fluid dynamic modeling can provide a powerful tool to illustrate and predict the distribution of analytes (e.g., oxygen or other bioactive substances) in a highly complex system.

Comparing spatial conservation prioritization methods with site‐ versus spatial dependency‐based connectivity - Dominic Muenzel; Kay Critchell; Courtney Cox; Stuart J. Campbell; Raymond Jakub; Iliana Chollett; Nils Krueck; Daniel Holstein; Eric A. Treml; Maria Beger (Conservation Biology, 2023)
Larval dispersal is an important component of marine reserve networks. Two conceptually different approaches to incorporate dispersal connectivity into spatial planning of these networks exist, and it is an open question as to when either is most appropriate. Candidate reserve sites can be selected individually based on local properties of connectivity or on a spatial dependency‐based approach of selecting clusters of strongly connected habitat patches. The first acts on individual sites, whereas the second acts on linked pairs of sites. We used a combination of larval dispersal simulations representing different seascapes and case studies of biophysical larval dispersal models in the Coral Triangle region and the province of Southeast Sulawesi, Indonesia, to compare the performance of these 2 methods in the spatial planning software Marxan. We explored the reserve design performance implications of different dispersal distances and patterns based on the equilibrium settlement of larvae in protected and unprotected areas. We further assessed different assumptions about metapopulation contributions from unprotected areas, including the case of 100% depletion and more moderate scenarios. The spatial dependency method was suitable when dispersal was limited, a high proportion of the area of interest was substantially degraded, or the target amount of habitat protected was low. Conversely, when subpopulations were well connected, the 100% depletion was relaxed, or more habitat was protected, protecting individual sites with high scores in metrics of connectivity was a better strategy. Spatial dependency methods generally produced more spatially clustered solutions with more benefits inside than outside reserves compared with site‐based methods. Therefore, spatial dependency methods potentially provide better results for ecological persistence objectives over enhancing fisheries objectives, and vice versa. Different spatial prioritization methods of using connectivity are appropriate for different contexts, depending on dispersal characteristics, unprotected area contributions, habitat protection targets, and specific management objectives. Comparación entre los métodos de priorización de la conservación espacial con sitio y la conectividad espacial basada en la dependencia

Effects of activation and assisted reproduction techniques on the composition, structure, and properties of the sauger (Sander Canadensis) spermatozoa plasma membrane - Bryan Blawut; Barbara Wolfe; Chris Premanandan; Gustavo Schuenemann; Stuart A. Ludsin; Shan-Lu Liu; D.N. Rao Veeramachaneni; Marco A. Coutinho da Silva (Theriogenology, 2023)

Temporal trends in concentrations of brominated flame retardants in UK foodstuffs suggest active impacts of global phase-out of PBDEs and HBCDD - Yulong Ma; William A. Stubbings; Mohamed Abou-Elwafa Abdallah; Reginald Cline-Cole; Stuart Harrad (Science of The Total Environment, 2023)

Revising supraglacial rock avalanche magnitudes and frequencies in Glacier Bay National Park, Alaska - William D. Smith; Stuart A. Dunning; Neil Ross; Jon Telling; Erin K. Jensen; Dan H. Shugar; Jeffrey A. Coe; Marten Geertsema (Geomorphology, 2023)

Perfluoroalkyl substances exposure in firefighters: Sources and implications - Paul E. Rosenfeld; Kenneth R. Spaeth; Linda L. Remy; Vera Byers; Stuart A. Muerth; Ryan C. Hallman; Jasmine Summers-Evans; Sofia Barker (Environmental Research, 2023)

In-planta transient transformation of avocado (Persea americana) by vacuum agroinfiltration of aerial plant parts - Jorge Alberto Salazar-González; Manuela Castro-Medina; Luis Enrique Bernardino-Rivera; Eduardo Martínez-Terrazas; Stuart A. Casson; Rafael Urrea-López (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)
Avocado, Persea americana Mill, is one of the most traded tropical fruits in the international market. To date, stable and transient transformation has only been achieved for of zygotic embryos and not of adult plant tissue, which limits functional genomics research. We provide the first transient Agrobacterium -mediated transformation methodology in avocado leaves that overcomes the recalcitrance to transformation of this species. We investigated the effect of Agrobacterium strain, leaf stage, wounding pre-treatment, the phytohormone jasmonic acid, and vacuum infiltration on transient transformation of avocado leaves. Using the Agrobacterium strain LBA4404 and the RUBY reporter a transformation frequency of up to 27% was obtained for avocado detached leaves. The transformation efficiency depended on the age of the leaf, with an intermediate stage of leaf development showing the highest efficiency of transient reporter gene expression. Microwounding pre-treatment facilitates agroinfiltration and coupled with leaf age are the primary factors influencing competence for transient transformation. Jasmonic acid did not significantly affect transient transformation in the absence of microwounding. However, microwounding and 250 µM of jasmonic acid acted synergistically to significantly enhance transient expression. Using this methodology with localized vacuum agroinfiltration, transient transformation of attached avocado leaves was achieved. This method unlocks the use of Agrobacterium -mediated transient transformation as a tool for explore gene function and metabolic pathways in both, detached and attached avocado leaves.

Analysis of the critical components of flash drought using the standardized evaporative stress ratio - Stuart G. Edris; Jeffrey B. Basara; Jordan I. Christian; Eric D. Hunt; Jason A. Otkin; Scott T. Salesky; Bradley G. Illston (Agricultural and Forest Meteorology, 2023)

Observation-based estimates of volume, heat, and freshwater exchanges between the subpolar North Atlantic interior, its boundary currents, and the atmosphere - Sam C. Jones; Neil J. Fraser; Stuart A. Cunningham; Alan D. Fox; Mark E. Inall (Ocean Science, 2023)
The Atlantic Meridional Overturning Circulation (AMOC) transports heat and salt between the tropical Atlantic and Arctic oceans. The interior of the North Atlantic subpolar gyre (SPG) is responsible for the much of the water mass transformation in the AMOC, and the export of this water to intensified boundary currents is crucial for projecting air–sea interaction onto the strength of the AMOC. However, the magnitude and location of exchange between the SPG and the boundary remains unclear. We present a novel climatology of the SPG boundary using quality-controlled CTD (conductivity–temperature–depth) and Argo hydrography, defining the SPG interior as the oceanic region bounded by 47∘ N and the 1000 m isobath. From this hydrography we find geostrophic flow out of the SPG around much of the boundary with minimal seasonality. The horizontal density gradient is reversed around western Greenland, where the geostrophic flow is into the SPG. Surface Ekman forcing drives net flow out of the SPG in all seasons with pronounced seasonality, varying between 2.45 ± 0.73 Sv in the summer and 7.70 ± 2.90 Sv in the winter. We estimate heat advected into the SPG to be between 0.14 ± 0.05 PW in the winter and 0.23 ± 0.05 PW in the spring, and freshwater advected out of the SPG to be between 0.07 ± 0.02 Sv in the summer and 0.15 ± 0.02 Sv in the autumn. These estimates approximately balance the surface heat and freshwater fluxes over the SPG domain. Overturning in the SPG varies seasonally, with a minimum of 6.20 ± 1.40 Sv in the autumn and a maximum of 10.17 ± 1.91 Sv in the spring, with surface Ekman the most likely mediator of this variability. The density of maximum overturning is at 27.30 kg m−3, with a second, smaller maximum at 27.54 kg m−3. Upper waters (σ0 27.54 kg m−3) exiting to the south. Our results support the present consensus that the formation and pre-conditioning of Subpolar Mode Water in the north-eastern Atlantic is a key determinant of AMOC strength.

Water resources of Afghanistan and related hazards under rapid climate warming: a review - Jamal A. N. Shokory; Bettina Schaefli; Stuart N. Lane (Hydrological Sciences Journal, 2023)

Re-envisioning community genetics: community empowerment in preventive genomics - Hannah Wand; Daphne O. Martschenko; Annamaria Smitherman; Sheryl Michelson; Ting Pun; John S. Witte; Stuart A. Scott; Mildred K. Cho; Euan A. Ashley; Elyse Goldberg; Linda Knepper; Sheryl Michelson; et al. (Journal of Community Genetics, 2023)

Global assessment of chemical quality of drinking water: The case of trihalomethanes - Cristina M Villanueva; Iro Evlampidou; Fathelrahman Ibrahim; Carolina Donat-Vargas; Antonia Valentin; Anca-Maria Tugulea; Shinya Echigo; Dragana Jovanovic; Albert T Lebedev; Mildred Lemus-Pérez; Manuel Rodriguez-Susa; Arben Luzati; et al. (Water Research, 2023)

Complex crop rotations improve organic nitrogen cycling - Lauren C. Breza; Maria Mooshammer; Timothy M. Bowles; Virginia L. Jin; Marty R. Schmer; Bennett Thompson; A. Stuart Grandy (Soil Biology and Biochemistry, 2023)

Chlorinated organophosphate esters in Irish waste foams and fabrics: Concentrations, preliminary assessment of temporal trends and evaluation of the impact of a concentration limit value - Stuart Harrad; Martin Sharkey; William A. Stubbings; Misbah Alghamdi; Harald Berresheim; Marie Coggins; André Henrique Rosa; Daniel Drage (Science of The Total Environment, 2023)

Workers' exposure to dust and potentially toxic elements during steel cutting in two ship dismantling cases - Sefer Anil Gunbeyaz; Evanthia Giagloglou; Rafet Emek Kurt; Karin Garmer Rogge; Selim Alkaner; Stuart A. McKenna; Osman Turan; Richard Lord (Ocean Engineering, 2023)

An assessment of the validity and reliability of the P022–P version of e-Celsius core temperature capsules - Thomas W. Service; Katerina Junker; Breanna Service; Cory J. Coehoorn; Marisa Harrington; Steven Martin; Lynneth A. Stuart-Hill (Journal of Thermal Biology, 2023)

Time-varying effects of local weather on behavior and probability of breeding deferral in two Arctic-nesting goose populations - Stephanie A. Cunningham; Toryn L. J. Schafer; Christopher K. Wikle; Jay A. VonBank; Bart M. Ballard; Lei Cao; Stuart Bearhop; Anthony D. Fox; Geoff M. Hilton; Alyn J. Walsh; Larry R. Griffin; Mitch D. Weegman (Oecologia, 2023)
Arctic-nesting geese face energetic challenges during spring migration, including ecological barriers and weather conditions (e.g., precipitation and temperature), which in long-lived species can lead to a trade-off to defer reproduction in favor of greater survival. We used GPS location and acceleration data collected from 35 greater white-fronted geese of the North American midcontinent and Greenland populations at spring migration stopovers, and novel applications of Bayesian dynamic linear models to test daily effects of minimum temperature and precipitation on energy expenditure (i.e., overall dynamic body acceleration, ODBA) and proportion of time spent feeding (PTF), then examined the daily and additive importance of ODBA and PTF on probability of breeding deferral using stochastic antecedent models. We expected distinct responses in behavior and probability of breeding deferral between and within populations due to differences in stopover area availability. Time-varying coefficients of weather conditions were variable between ODBA and PTF, and often did not show consistent patterns among birds, indicating plasticity in how individuals respond to conditions. An increase in antecedent ODBA was associated with a slightly increased probability of deferral in midcontinent geese but not Greenland geese. Probability of deferral decreased with increased PTF in both populations. We did not detect any differentially important time periods. These results suggest either that movements and behavior throughout spring migration do not explain breeding deferral or that ecological linkages between bird decisions during spring and subsequent breeding deferral were different between populations and across migration but occurred at different time scales than those we examined.

Evidence for older carbon loss with lowered water tables and changing plant functional groups in peatlands - Julia E. M. Stuart; Colin L. Tucker; Erik A. Lilleskov; Randall K. Kolka; Rodney A. Chimner; Katherine A. Heckman; Evan S. Kane (Global Change Biology, 2023)
A small imbalance in plant productivity and decomposition accounts for the carbon (C) accumulation capacity of peatlands. As climate changes, the continuity of peatland net C storage relies on rising primary production to offset increasing ecosystem respiration (ER) along with the persistence of older C in waterlogged peat. A lowering in the water table position in peatlands often increases decomposition rates, but concurrent plant community shifts can interactively alter ER and plant productivity responses. The combined effects of water table variation and plant communities on older peat C loss are unknown. We used a full‐factorial 1‐m 3 mesocosm array with vascular plant functional group manipulations (Unmanipulated Control, Sedge only, and Ericaceous only) and water table depth (natural and lowered) treatments to test the effects of plants and water depth on CO 2 fluxes, decomposition, and older C loss. We used Δ 14 C and δ 13 C of ecosystem CO 2 respiration, bulk peat, plants, and porewater dissolved inorganic C to construct mixing models partitioning ER among potential sources. We found that the lowered water table treatments were respiring C fixed before the bomb spike (1955) from deep waterlogged peat. Lowered water table Sedge treatments had the oldest dissolved inorganic 14 C signature and the highest proportional peat contribution to ER. Decomposition assays corroborated sustained high rates of decomposition with lowered water tables down to 40 cm below the peat surface. Heterotrophic respiration exceeded plant respiration at the height of the growing season in lowered water table treatments. Rates of gross primary production were only impacted by vegetation, whereas ER was affected by vegetation and water table depth treatments. The decoupling of respiration and primary production with lowered water tables combined with older C losses suggests that climate and land‐use‐induced changes in peatland hydrology can increase the vulnerability of peatland C stores.

Connectivity between countries established by landbirds and raptors migrating along the African–Eurasian flyway - João L. Guilherme; Victoria R. Jones; Inês Catry; Martin Beal; Maria P. Dias; Steffen Oppel; Juliet A. Vickery; Chris M. Hewson; Stuart H. M. Butchart; Ana S. L. Rodrigues (Conservation Biology, 2023)
The conservation of long‐distance migratory birds requires coordination between the multiple countries connected by the movements of these species. The recent expansion of tracking studies is shedding new light on these movements, but much of this information is fragmented and inaccessible to conservation practitioners and policy makers. We synthesized current knowledge on the connectivity established between countries by landbirds and raptors migrating along the African–Eurasian flyway. We reviewed tracking studies to compile migration records for 1229 individual birds, from which we derived 544 migratory links, each link corresponding to a species’ connection between a breeding country in Europe and a nonbreeding country in sub‐Saharan Africa. We used these migratory links to analyze trends in knowledge over time and spatial patterns of connectivity per country (across species), per species (across countries), and at the flyway scale (across all countries and all species). The number of tracking studies available increased steadily since 2010 (particularly for landbirds), but the coverage of existing tracking data was highly incomplete. An average of 7.5% of migratory landbird species and 14.6% of raptor species were tracked per country. More data existed from central and western European countries, and it was biased toward larger bodied species. We provide species‐ and country‐level syntheses of the migratory links we identified from the reviewed studies, involving 123 populations of 43 species, migrating between 28 European and 43 African countries. Several countries (e.g., Spain, Poland, Ethiopia, Democratic Republic of Congo) are strategic priorities for future tracking studies to complement existing data, particularly on landbirds. Despite the limitations in existing tracking data, our data and results can inform discussions under 2 key policy instruments at the flyway scale: the African–Eurasian Migratory Landbirds Action Plan and the Memorandum of Understanding on the Conservation of Migratory Birds of Prey in Africa and Eurasia.

Agriculture without paraquat is feasible without loss of productivity—lessons learned from phasing out a highly hazardous herbicide - Alexander M. Stuart; Charles N. Merfield; Finbarr G. Horgan; Sheila Willis; Meriel A. Watts; Fernando Ramírez-Muñoz; Jorge Sánchez U; Leah Utyasheva; Michael Eddleston; Mark L. Davis; Lars Neumeister; Manoé R. Sanou; et al. (Environmental Science and Pollution Research, 2023)
A small proportion of the thousands of pesticides on the market today are associated with a disproportionately high incidence of severe acute pesticide poisoning and suicide. Paraquat stands out as one of the most lethal pesticides in common use, frequently involved in fatal incidents due to suicides or accidental exposure. Even though paraquat has been banned in over 67 countries, it is still widely used in many others, particularly in Asia and Latin America. Based on a literature review and consultations, this paper identifies options for replacing paraquat and distils practical lessons from numerous successes around the world. Our aim is to support regulators, policymakers, agronomists and the supply chain sector with practical information related to phasing out paraquat . Production data consistently failed to show any negative effects of banning paraquat on agricultural productivity. A wide range of alternative approaches to weed management and crop defoliation are available, many of which do not rely on herbicides. Over 1.25 million farmers in low- and middle-income countries (LMICs) successfully produce a range of crops for private voluntary standards (PVS) in food and fiber supply chains which prohibit paraquat use. We conclude from the findings of this study that eliminating paraquat will save lives without reducing agricultural productivity. Less hazardous and more sustainable alternatives exist. To enhance successful adoption and uptake of these methods on a wide scale, farmers require training and support within an enabling policy environment.

The effect of dietary carbohydrate to lipid ratios on growth performance in juvenile California yellowtail Seriola dorsalis - Jonas R. Miller; Guillaume P. Salze; Kevin R. Stuart; Mark A. Drawbridge; D. Allen Davis (Aquaculture, 2023)

Pilot-scale phosphate recovery from wastewater to create a fertiliser product: An integrated assessment of adsorbent performance and quality - Sabolc Pap; Huiyi Zhang; Aleksandra Bogdan; Derek T. Elsby; Stuart W. Gibb; Barbara Bremner; Mark A. Taggart (Water Research, 2023)

Corrigendum to “Thermal history of the Siberian Traps Large Igneous Province revealed by new thermochronology data from intrusions” [Tectonophysics 836 (2022) 229385] - Tatyana E. Bagdasaryan; Stuart N. Thomson; Anton V. Latyshev; Roman V. Veselovskiy; Victor A. Zaitsev; Alexander E. Marfin; Vladimir S. Zakharov; Denis S. Yudin (Tectonophysics, 2023)

Evaluating wipe sampling parameters to assess method performance and data confidence during remediation of hazardous pesticide misuse chemicals on indoor materials - Stuart A. Willison; Daniel Stout; Amy Mysz; James Starr; Dennis Tabor; Barbara Wyrzykowska-Ceradini; Josh Nardin; Eric Morris; Emily Gibb Snyder (Science of The Total Environment, 2023)

Coastal freshening drives acidification state in Greenland fjords - Henry C. Henson; Johnna M. Holding; Lorenz Meire; Søren Rysgaard; Colin A. Stedmon; Alice Stuart-Lee; Jørgen Bendtsen; Mikael Sejr (Science of The Total Environment, 2023)

Prediction of enteric methane emissions by sheep using an intercontinental database - Alejandro Belanche; Alexander N. Hristov; Henk J. van Lingen; Stuart E. Denman; Ermias Kebreab; Angela Schwarm; Michael Kreuzer; Mutian Niu; Maguy Eugène; Vincent Niderkorn; Cécile Martin; Harry Archimède; et al. (Journal of Cleaner Production, 2023)

Contaminant pulse following wildfire is associated with shifts in estuarine benthic communities - Sally A. Bracewell; Thayanne L. Barros; Mariana Mayer-Pinto; Katherine A. Dafforn; Stuart L. Simpson; Emma L. Johnston (Environmental Pollution, 2023)

Quantum aspects of the brain-mind relationship: A hypothesis with supporting evidence - Stuart A. Kauffman; Dean Radin (BioSystems, 2023)

In-Silico Modelling of Transdermal Delivery of Macromolecule Drugs Assisted by a Skin Stretching Hypobaric Device - Daniel Sebastia-Saez; Faiza Benaouda; Chui Hua Lim; Guoping Lian; Stuart A. Jones; Liang Cui; Tao Chen (Pharmaceutical Research, 2023)
Objectives To develop a simulation model to explore the interplay between mechanical stretch and diffusion of large molecules into the skin under locally applied hypobaric pressure, a novel penetration enhancement method. Methods Finite element method was used to model the skin mechanical deformation and molecular diffusion processes, with validation against in-vitro transdermal permeation experiments. Simulations and experimental data were used together to investigate the transdermal permeation of large molecules under local hypobaric pressure. Results Mechanical simulations resulted in skin stretching and thinning (20%–26% hair follicle diameter increase, and 21%–27% skin thickness reduction). Concentration of dextrans in the stratum corneum was below detection limit with and without hypobaric pressure. Concentrations in viable epidermis and dermis were not affected by hypobaric pressure (approximately 2 μg $$\bullet$$ ∙ cm −2 ). Permeation into the receptor fluid was substantially enhanced from below the detection limit at atmospheric pressure to up to 6 μg $$\bullet$$ ∙ cm −2 under hypobaric pressure. The in-silico simulations compared satisfactorily with the experimental results at atmospheric conditions. Under hypobaric pressure, satisfactory comparison was attained when the diffusion coefficients of dextrans in the skin layers were increased from $$\sim$$ ∼ 10 μm 2 $$\bullet$$ ∙ s −1 to between 200–500 μm 2 $$\bullet$$ ∙ s −1 . Conclusions Application of hypobaric pressure induces skin mechanical stretching and enlarges the hair follicle. This enlargement alone cannot satisfactorily explain the increased transdermal permeation into the receptor fluid under hypobaric pressure. The results from the in-silico simulations suggest that the application of hypobaric pressure increases diffusion in the skin, which leads to improved overall transdermal permeation.

De novo mutations in the BMP signaling pathway in lambdoid craniosynostosis - Andrew T. Timberlake; Emre Kiziltug; Sheng Chih Jin; Carol Nelson-Williams; Erin Loring; August Allocco; Arnaud Marlier; Siddharth Banka; Helen Stuart; Maria Rita Passos-Buenos; Rafael Rosa; Silvia R. Rogatto; et al. (Human Genetics, 2023)

Species divergence under competition and shared predation - Marius Roesti; Jeffrey S. Groh; Stephanie A. Blain; Magnus Huss; Peter Rassias; Daniel I. Bolnick; Yoel E. Stuart; Catherine L. Peichel; Dolph Schluter (Ecology Letters, 2023)
Species competing for resources also commonly share predators. While competition often drives divergence between species, the effects of shared predation are less understood. Theoretically, competing prey species could either diverge or evolve in the same direction under shared predation depending on the strength and symmetry of their interactions. We took an empirical approach to this question, comparing antipredator and trophic phenotypes between sympatric and allopatric populations of threespine stickleback and prickly sculpin fish that all live in the presence of a trout predator. We found divergence in antipredator traits between the species: in sympatry, antipredator adaptations were relatively increased in stickleback but decreased in sculpin. Shifts in feeding morphology, diet and habitat use were also divergent but driven primarily by stickleback evolution. Our results suggest that asymmetric ecological character displacement indirectly made stickleback more and sculpin less vulnerable to shared predation, driving divergence of antipredator traits between sympatric species.

Can Aphid Herbivory Induce Intergenerational Effects of Endophyte-conferred Resistance in Grasses? - Ludmila M. Bubica Bustos; Andrea C. Ueno; Fernando Biganzoli; Stuart D. Card; Wade J. Mace; María A. Martínez-Ghersa; Pedro E. Gundel (Journal of Chemical Ecology, 2022)

Range and extinction dynamics of the steppe bison in Siberia: A pattern‐oriented modelling approach - July A. Pilowsky; Sean Haythorne; Stuart C. Brown; Mario Krapp; Edward Armstrong; Barry W. Brook; Carsten Rahbek; Damien A. Fordham (Global Ecology and Biogeography, 2022)
Aim To determine the ecological processes and drivers of range collapse, population decline and eventual extinction of the steppe bison in Eurasia. Location Siberia. Time period Pleistocene and Holocene. Major taxa studied Steppe bison ( Bison priscus ). Methods We configured 110,000 spatially explicit population models (SEPMs) of climate–human–steppe bison interactions in Siberia, which we ran at generational time steps from 50,000 years before present. We used pattern‐oriented modelling (POM) and fossil‐based inferences of distribution and demographic change of steppe bison to identify which SEPMs adequately simulated important interactions between ecological processes and biological threats. These “best models” were then used to disentangle the mechanisms that were integral in the population decline and later extinction of the steppe bison in its last stronghold in Eurasia. Results Our continuous reconstructions of the range and extinction dynamics of steppe bison were able to reconcile inferences of spatio‐temporal occurrence and the timing and location of extinction in Siberia based on hundreds of radiocarbon‐dated steppe bison fossils. We showed that simulating the ecological pathway to extinction for steppe bison in Siberia in the early Holocene required very specific ecological niche constraints, demographic processes and a constrained synergy of climate and human hunting dynamics during the Pleistocene–Holocene transition. Main conclusions Ecological processes and drivers that caused ancient population declines of species can be reconstructed at high spatio‐temporal resolutions using SEPMs and POM. Using this approach, we found that climatic change and hunting by humans are likely to have interacted with key ecological processes to cause the extinction of the steppe bison in its last refuge in Eurasia.

Clarifying the evidence for microbial‐ and plant‐derived soil organic matter, and the path toward a more quantitative understanding - Emily D. Whalen; A. Stuart Grandy; Noah W. Sokol; Marco Keiluweit; Jessica Ernakovich; Richard G. Smith; Serita D. Frey (Global Change Biology, 2022)
Predicting and mitigating changes in soil carbon (C) stocks under global change requires a coherent understanding of the factors regulating soil organic matter (SOM) formation and persistence, including knowledge of the direct sources of SOM (plants vs. microbes). In recent years, conceptual models of SOM formation have emphasized the primacy of microbial‐derived organic matter inputs, proposing that microbial physiological traits (e.g., growth efficiency) are dominant controls on SOM quantity. However, recent quantitative studies have challenged this view, suggesting that plants make larger direct contributions to SOM than is currently recognized by this paradigm. In this review, we attempt to reconcile these perspectives by highlighting that variation across estimates of plant‐ versus microbial‐derived SOM may arise in part from methodological limitations. We show that all major methods used to estimate plant versus microbial contributions to SOM have substantial shortcomings, highlighting the uncertainty in our current quantitative estimates. We demonstrate that there is significant overlap in the chemical signatures of compounds produced by microbes, plant roots, and through the extracellular decomposition of plant litter, which introduces uncertainty into the use of common biomarkers for parsing plant‐ and microbial‐derived SOM, especially in the mineral‐associated organic matter (MAOM) fraction. Although the studies that we review have contributed to a deeper understanding of microbial contributions to SOM, limitations with current methods constrain quantitative estimates. In light of recent advances, we suggest that now is a critical time to re‐evaluate long‐standing methods, clearly define their limitations, and develop a strategic plan for improving the quantification of plant‐ and microbial‐derived SOM. From our synthesis, we outline key questions and challenges for future research on the mechanisms of SOM formation and stabilization from plant and microbial pathways.

Impact of bacterial strain acquisition in the lung of patients with COPD: the AERIS study - Lucio Malvisi; Aparna Yarraguntla; Marie-Cécile Mortier; Karen Osman; David W. Cleary; Béatrice Sente; Thierry G. Pascal; Vincent Weynants; Stuart C. Clarke; Laura Taddei; Tom M. A. Wilkinson; Jeanne-Marie Devaster; et al. (Infectious Diseases, 2022)

Spatiotemporal influences of climate and humans on muskox range dynamics over multiple millennia - Elisabetta Canteri; Stuart C. Brown; Niels Martin Schmidt; Rasmus Heller; David Nogués‐Bravo; Damien A. Fordham (Global Change Biology, 2022)
Processes leading to range contractions and population declines of Arctic megafauna during the late Pleistocene and early Holocene are uncertain, with intense debate on the roles of human hunting, climatic change, and their synergy. Obstacles to a resolution have included an overreliance on correlative rather than process‐explicit approaches for inferring drivers of distributional and demographic change. Here, we disentangle the ecological mechanisms and threats that were integral in the decline and extinction of the muskox ( Ovibos moschatus ) in Eurasia and in its expansion in North America using process‐explicit macroecological models. The approach integrates modern and fossil occurrence records, ancient DNA, spatiotemporal reconstructions of past climatic change, species‐specific population ecology, and the growth and spread of anatomically modern humans. We show that accurately reconstructing inferences of past demographic changes for muskox over the last 21,000 years require high dispersal abilities, large maximum densities, and a small Allee effect. Analyses of validated process‐explicit projections indicate that climatic change was the primary driver of muskox distribution shifts and demographic changes across its previously extensive (circumpolar) range, with populations responding negatively to rapid warming events. Regional analyses show that the range collapse and extinction of the muskox in Europe (~13,000 years ago) was likely caused by humans operating in synergy with climatic warming. In Canada and Greenland, climatic change and human activities probably combined to drive recent population sizes. The impact of past climatic change on the range and extinction dynamics of muskox during the Pleistocene–Holocene transition signals a vulnerability of this species to future increased warming. By better establishing the ecological processes that shaped the distribution of the muskox through space and time, we show that process‐explicit macroecological models have important applications for the future conservation and management of this iconic species in a warming Arctic.

Exceptional freshening and cooling in the eastern subpolar North Atlantic caused by reduced Labrador Sea surface heat loss - Alan D. Fox; Patricia Handmann; Christina Schmidt; Neil Fraser; Siren Rühs; Alejandra Sanchez-Franks; Torge Martin; Marilena Oltmanns; Clare Johnson; Willi Rath; N. Penny Holliday; Arne Biastoch; et al. (Ocean Science, 2022)
Observations of the eastern subpolar North Atlantic in the 2010s show exceptional freshening and cooling of the upper ocean, peaking in 2016 with the lowest salinities recorded for 120 years. Published theories for the mechanisms driving the freshening include: reduced transport of saltier, warmer surface waters northwards from the subtropics associated with reduced meridional overturning; shifts in the pathways of fresher, cooler surface water from the Labrador Sea driven by changing patterns of wind stress; and the eastward expansion of the subpolar gyre. Using output from a high-resolution hindcast model simulation, we propose that the primary cause of the exceptional freshening and cooling is reduced surface heat loss in the Labrador Sea. Tracking virtual fluid particles in the model backwards from the eastern subpolar North Atlantic between 1990 and 2020 shows the major cause of the freshening and cooling to be an increased outflow of relatively fresh and cold surface waters from the Labrador Sea; with a minor contribution from reduced transport of warmer, saltier surface water northward from the subtropics. The cooling, but not the freshening, produced by these changing proportions of waters of subpolar and subtropical origin is mitigated by reduced along-track heat loss to the atmosphere in the North Atlantic Current. We analyse modelled boundary exchanges and water mass transformation in the Labrador Sea to show that since 2000, while inflows of lighter surface waters remain steady, the increasing output of these waters is due to reduced surface heat loss in the Labrador Sea beginning in the early 2000s. Tracking particles further upstream reveals that the primary source of the increased volume of lighter water transported out of the Labrador Sea is increased recirculation of water, and therefore longer residence times, in the upper 500–1000 m of the subpolar gyre.

An integrated approach to assessing abiotic and biotic threats to post‐fire plant species recovery: Lessons from the 2019–2020 Australian fire season - Rachael V. Gallagher; Stuart P. Allen; Berin D. E. Mackenzie; David A. Keith; Rachael H. Nolan; Libby Rumpff; Carl R. Gosper; Geoffrey Pegg; Stephen van Leeuwen; Mark K. J. Ooi; Colin J. Yates; Cory Merow; et al. (Global Ecology and Biogeography, 2022)
Aim Existing abiotic and biotic threats to plant species (e.g., disease, drought, invasive species) affect their capacity to recover post‐fire. We use a new, globally applicable framework to assess the vulnerability of 26,062 Australian plant species to a suite of active threats after the 2019–2020 fires. Location Australia. Time period 2019–2020. Major species studied Plants. Methods Spatial data for existing threats and information on species‐level susceptibility were combined with estimates of the extent of range burnt in southern Australia (> 22°S) to assign species against 10 criteria into vulnerability categories ( high , medium , low , none , data deficient ). We explore in detail results for three threats (drought, disease, feral animals), highlighting where impacts from multiple threats ranked high vulnerability may compound to reduce post‐fire recovery. Results Analysis of the full suite of 10 vulnerability criteria, which encompass a broad range of threats, revealed large numbers of species vulnerable to poor post‐fire recovery from one or more different hazards ( high vulnerability: 1,243 species; medium vulnerability: 2,450 species). Collectively, 457 plant species that burnt extensively (> 50%) across their range are highly vulnerable to poor recovery due to exposure to pre‐fire drought conditions (235 species), disease (186 species), or feral animals (97 species). Of these 457 species, 61 are vulnerable to more than one of these three threats, highlighting how a suite of interacting hazards can impact plant recovery after fire. Main conclusions While fire can renew plant populations by stimulating recruitment and resetting competitive interactions, the presence of existing threats in post‐fire landscapes jeopardizes recovery. The simultaneous impact of multiple threats that impact recovery can create a suite of hazards that contribute to declines and, potentially, extinction. Our method for rapid post‐fire vulnerability assessment can be applied to large numbers of plant species or other biota in fire affected regions globally.

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

Faster ocean warming threatens richest areas of marine biodiversity - Stuart C. Brown; Camille Mellin; Jorge García Molinos; Eline D. Lorenzen; Damien A. Fordham (Global Change Biology, 2022)
The vulnerability of marine biodiversity to accelerated rates of climatic change is poorly understood. By developing a new method for identifying extreme oceanic warming events during Earth's most recent deglaciation, and comparing these to 21st century projections, we show that future rates of ocean warming will disproportionately affect the most speciose marine communities, potentially threatening biodiversity in more than 70% of current‐day global hotspots of marine species richness. The persistence of these richest areas of marine biodiversity will require many species to move well beyond the biogeographic realm where they are endemic, at rates of redistribution not previously seen. Our approach for quantifying exposure of biodiversity to past and future rates of oceanic warming provides new context and scalable information for deriving and strengthening conservation actions to safeguard marine biodiversity under climate change.

Associations of self-reported occupational exposures and settings to ALS: a case–control study - Stephen A. Goutman; Jonathan Boss; Christopher Godwin; Bhramar Mukherjee; Eva L. Feldman; Stuart A. Batterman (International Archives of Occupational and Environmental Health, 2022)
Background Environmental exposures contribute to the pathogenesis of amyotrophic lateral sclerosis (ALS), a fatal and progressive neurological disease. Identification of these exposures is important for targeted screening and risk factor modification. Objective To identify occupational exposures that are associated with a higher risk of ALS using both survey and standard occupational classification (SOC) coding procedures, and to highlight how exposure surveys can complement SOC coding. Methods ALS participants and neurologically healthy controls recruited in Michigan completed a detailed exposure assessment on their four most recent and longest held occupations. Exposure scores were generated from the exposure survey, and occupations were assigned to SOC codes by experienced exposure scientists. Results This study included 381 ALS and 272 control participants. ALS participants reported higher duration-adjusted occupational exposure to particulate matter (OR = 1.45, 95% CI 1.19–1.78, p < 0.001), volatile organic compounds (OR = 1.22, 95% CI 1.02–1.45, p = 0.029), metals (OR = 1.48, 95% CI 1.21–1.82, p < 0.001), and combustion and diesel exhaust pollutants (OR = 1.20, 95% CI 1.01–1.43, p = 0.041) prior to ALS diagnosis, when adjusted for sex, age, and military service compared to controls. In multivariable models, only occupational exposure to metals remained significant risk (OR = 1.56, 95% CI 1.11–2.20, p = 0.011), although in an adaptive elastic net model, particulate matter (OR = 1.203), pesticides (OR = 1.015), and metals (1.334) were all selected as risk factors. Work in SOC code “Production Occupations” was associated with a higher ALS risk. SOC codes “Building and Grounds Cleaning and Maintenance Occupations”, “Construction and Extraction Occupations”, “Installation, Maintenance, and Repair Occupations”, and “Production Occupations” were all associated with a higher exposure to metals as determined using survey data. Discussion Occupational exposure to particulate matter, volatile organic compounds, metals, pesticides, and combustion and diesel exhaust and employment in “Production Occupations” was associated with an increased ALS risk in this cohort.

Hydrologic Setting Dictates the Sensitivity of Ecosystem Metabolism to Climate Variability in Lakes - Isabella A. Oleksy; Stuart E. Jones; Christopher T. Solomon (Ecosystems, 2022)
Global change is influencing production and respiration in ecosystems across the globe. Lakes in particular are changing in response to climatic variability and cultural eutrophication, resulting in changes in ecosystem metabolism. Although the primary drivers of production and respiration such as the availability of nutrients, light, and carbon are well known, heterogeneity in hydrologic setting (for example, hydrological connectivity, morphometry, and residence) across and within regions may lead to highly variable responses to the same drivers of change, complicating our efforts to predict these responses. We explored how differences in hydrologic setting among lakes influenced spatial and inter annual variability in ecosystem metabolism, using high-frequency oxygen sensor data from 11 lakes over 8 years. Trends in mean metabolic rates of lakes generally followed gradients of nutrient and carbon concentrations, which were lowest in seepage lakes, followed by drainage lakes, and higher in bog lakes. We found that while ecosystem respiration (ER) was consistently higher in wet years in all hydrologic settings, gross primary production (GPP) only increased in tandem in drainage lakes. However, interannual rates of ER and GPP were relatively stable in drainage lakes, in contrast to seepage and bog lakes which had coefficients of variation in metabolism between 22–32%. We explored how the geospatial context of lakes, including hydrologic residence time, watershed area to lake area, and landscape position influenced the sensitivity of individual lake responses to climatic variation. We propose a conceptual framework to help steer future investigations of how hydrologic setting mediates the response of metabolism to climatic variability.

Ilmenite and magnetite microfabrics in shocked gneisses from the Vredefort impact structure, South Africa - Fabian Dellefant; Claudia A. Trepmann; Stuart A. Gilder; Iuliia V. Sleptsova; Melanie Kaliwoda; Benjamin P. Weiss (Contributions to Mineralogy and Petrology, 2022)
We investigated microfabrics of shocked Archean gneisses from two, 10 m-deep drill cores located near the center of the Vredefort impact structure in an area that is characterized by a prominent, long-wavelength negative magnetic anomaly (< − 3000 nT) together with short-wavelength, high-amplitude anomalies attributed to lightning strikes. Planar fractures and feather features in quartz, which can be partially recrystallized, indicate shock conditions less than 20 GPa. Micrometer-sized magnetite and ilmenite along shock-related shear fractures in quartz and feldspar emanate from adjacent deformed coarse (> 100 µm) ilmenite and magnetite host grains. These fine-scaled veins suggest mobilization of magnetite and ilmenite during shear deformation of host Fe-phases and adjacent silicates, probably associated with frictional heating. Coarse ilmenite has fine-lamellar mechanical twins parallel to {10 $$\overline{1}$$ 1 ¯ 1} and single (0001) twins, indicative of dislocation-glide-controlled deformation under non-isostatic stresses related to shock. A few µm-wide magnetite lamellae parallel to {10 $$\overline{1}$$ 1 ¯ 1} and spheroidal magnetite (diameter ≈10 µm) within coarse ilmenite document exsolution after shock. Dauphiné twins associated with planar features in quartz imply cooling from 650 to 725 °C after shock, which accords with estimates of pre-impact basement temperatures from petrographic studies. The Curie temperature of magnetite is 580 °C; therefore, the central negative magnetic anomaly was produced as a thermoremanent magnetization acquired during cooling of the initially hot crust. The long-wavelength anomaly was likely amplified by the newly created magnetite that also acquired a thermal remanence. Although the magnetic properties of surface samples are often influenced by lightning strikes, we found no microstructural evidence for lightning-related processes.

Earth stewardship: Shaping a sustainable future through interacting policy and norm shifts - F. Stuart Chapin; Elke U. Weber; Elena M. Bennett; Reinette Biggs; Jeroen van den Bergh; W. Neil Adger; Anne-Sophie Crépin; Stephen Polasky; Carl Folke; Marten Scheffer; Kathleen Segerson; John M. Anderies; et al. (Ambio, 2022)
Transformation toward a sustainable future requires an earth stewardship approach to shift society from its current goal of increasing material wealth to a vision of sustaining built, natural, human, and social capital—equitably distributed across society, within and among nations. Widespread concern about earth’s current trajectory and support for actions that would foster more sustainable pathways suggests potential social tipping points in public demand for an earth stewardship vision. Here, we draw on empirical studies and theory to show that movement toward a stewardship vision can be facilitated by changes in either policy incentives or social norms. Our novel contribution is to point out that both norms and incentives must change and can do so interactively. This can be facilitated through leverage points and complementarities across policy areas, based on values, system design, and agency. Potential catalysts include novel democratic institutions and engagement of non-governmental actors, such as businesses, civic leaders, and social movements as agents for redistribution of power. Because no single intervention will transform the world, a key challenge is to align actions to be synergistic, persistent, and scalable.

Tree crown damage and its effects on forest carbon cycling in a tropical forest - Jessica F. Needham; Gabriel Arellano; Stuart J. Davies; Rosie A. Fisher; Valerie Hammer; Ryan G. Knox; David Mitre; Helene C. Muller‐Landau; Daniel Zuleta; Charlie D. Koven (Global Change Biology, 2022)
Crown damage can account for over 23% of canopy biomass turnover in tropical forests and is a strong predictor of tree mortality; yet, it is not typically represented in vegetation models. We incorporate crown damage into the Functionally Assembled Terrestrial Ecosystem Simulator (FATES), to evaluate how lags between damage and tree recovery or death alter demographic rates and patterns of carbon turnover. We represent crown damage as a reduction in a tree's crown area and leaf and branch biomass, and allow associated variation in the ratio of aboveground to belowground plant tissue. We compare simulations with crown damage to simulations with equivalent instant increases in mortality and benchmark results against data from Barro Colorado Island (BCI), Panama. In FATES, crown damage causes decreases in growth rates that match observations from BCI. Crown damage leads to increases in carbon starvation mortality in FATES, but only in configurations with high root respiration and decreases in carbon storage following damage. Crown damage also alters competitive dynamics, as plant functional types that can recover from crown damage outcompete those that cannot. This is a first exploration of the trade‐off between the additional complexity of the novel crown damage module and improved predictive capabilities. At BCI, a tropical forest that does not experience high levels of disturbance, both the crown damage simulations and simulations with equivalent increases in mortality does a reasonable job of capturing observations. The crown damage module provides functionality for exploring dynamics in forests with more extreme disturbances such as cyclones and for capturing the synergistic effects of disturbances that overlap in space and time.

Old and new horizons on Persea americana transformation techniques and applications - Diana Isabel Tamayo-Ramos; Jorge Alberto Salazar-González; Stuart A. Casson; Rafael Urrea-López (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Benthic assemblages are more predictable than fish assemblages at an island scale - Stuart A. Sandin; Esmeralda Alcantar; Randy Clark; Ramón de León; Faisal Dilrosun; Clinton B. Edwards; Andrew J. Estep; Yoan Eynaud; Beverly J. French; Michael D. Fox; Dave Grenda; Scott L. Hamilton; et al. (Coral Reefs, 2022)
Decades of research have revealed relationships between the abundance of coral reef taxa and local conditions, especially at small scales. However, a rigorous test of covariation requires a robust dataset collected across wide environmental or experimental gradients. Here, we surveyed spatial variability in the densities of major coral reef functional groups at 122 sites along a 70 km expanse of the leeward, forereef habitat of Curaçao in the southern Caribbean. These data were used to test the degree to which spatial variability in community composition could be predicted based on assumed functional relationships and site-specific anthropogenic, physical, and ecological conditions. In general, models revealed less power to describe the spatial variability of fish biomass than cover of reef builders (R 2 of best-fit models: 0.25 [fish] and 0.64 [reef builders]). The variability in total benthic cover of reef builders was best described by physical (wave exposure and reef relief) and ecological (turf algal height and coral recruit density) predictors. No metric of anthropogenic pressure was related to spatial variation in reef builder cover. In contrast, total fish biomass showed a consistent (albeit weak) association with anthropogenic predictors (fishing and diving pressure). As is typical of most environmental gradients, the spatial patterns of both fish biomass density and reef builder cover were spatially autocorrelated. Residuals from the best-fit model for fish biomass retained a signature of spatial autocorrelation while the best-fit model for reef builder cover removed spatial autocorrelation, thus reinforcing our finding that environmental predictors were better able to describe the spatial variability of reef builders than that of fish biomass. As we seek to understand spatial variability of coral reef communities at the scale of most management units (i.e., at kilometer- to island-scales), distinct and scale-dependent perspectives will be needed when considering different functional groups.

Development of Inspired Therapeutics Pediatric VAD: Computational Analysis and Characterization of VAD V3 - Landon H. Tompkins; Barry N. Gellman; Steven R. Prina; Gino F. Morello; Thomas Roussel; Jonathan A. Kopechek; Stuart J. Williams; Priscilla C. Petit; Mark S. Slaughter; Steven C. Koenig; Kurt A. Dasse (Cardiovascular Engineering and Technology, 2022)

Giant Tree Frog diversification in West and Central Africa: Isolation by physical barriers, climate, and reproductive traits - Kyle E. Jaynes; Edward A. Myers; Václav Gvoždík; David C. Blackburn; Daniel M. Portik; Eli Greenbaum; Gregory F. M. Jongsma; Mark‐Oliver Rödel; Gabriel Badjedjea; Abraham Bamba‐Kaya; Ninda L. Baptista; Jeannot B. Akuboy; et al. (Molecular Ecology, 2022)
Secondary sympatry amongst sister lineages is strongly associated with genetic and ecological divergence. This pattern suggests that for closely related species to coexist in secondary sympatry, they must accumulate differences in traits that mediate ecological and/or reproductive isolation. Here, we characterized inter‐ and intraspecific divergence in three giant tree frog species whose distributions stretch across West and Central Africa. Using genome‐wide single‐nucleotide polymorphism data, we demonstrated that species‐level divergence coincides temporally and geographically with a period of large‐scale forest fragmentation during the late Pliocene. Our environmental niche models further supported a dynamic history of climatic suitability and stability, and indicated that all three species occupy distinct environmental niches. We found modest morphological differentiation amongst the species with significant divergence in tympanum diameter and male advertisement call. In addition, we confirmed that two species occur in secondary sympatry in Central Africa but found no evidence of hybridization. These patterns support the hypothesis that cycles of genetic exchange and isolation across West and Central Africa have contributed to globally significant biodiversity. Furthermore, divergence in both ecology and reproductive traits appear to have played important roles in maintaining distinct lineages. At the intraspecific level, we found that climatic refugia, precipitation gradients, marine incursions, and potentially riverine barriers generated phylogeographic structure throughout the Pleistocene and into the Holocene. Further studies examining phenotypic divergence and secondary contact amongst these geographically structured populations may demonstrate how smaller scale and more recent biogeographic barriers contribute to regional diversification.

Spatial compositional turnover varies with trophic level and body size in marine assemblages of micro‐ and macroorganisms - Amanda K. Pettersen; Melinda A. Coleman; Guillaume Latombe; Sebastian Vadillo Gonzalez; Nathan L. R. Williams; Justin R. Seymour; Alexandra H. Campbell; Torsten Thomas; Renata Ferrari; Rick D. Stuart‐Smith; Graham J. Edgar; Peter D. Steinberg; et al. (Global Ecology and Biogeography, 2022)
Aim Spatial compositional turnover varies considerably among co‐occurring assemblages of organisms, presumably shaped by common processes related to species traits. We investigated patterns of spatial turnover in a diverse set of marine assemblages using zeta diversity, which extends traditional pairwise measures of turnover to capture the roles of both rare and common species in shaping assemblage turnover. We tested the generality of hypothesized patterns related to ecological traits and provide insights into mechanisms of biodiversity change. Location Temperate pelagic and benthic marine assemblages of micro‐ and macroorganisms along south‐eastern Australia (30–36° S latitude). Time period 2008–2021. Major taxa studied Bacteria, phytoplankton, zooplankton, fish, and macrobenthic groups. Methods Six marine datasets spanning bacteria to fishes were collated for measures of “species” occurrence, with a 1° latitude grain. For each assemblage, ecological traits of body size, habitat and trophic level were analysed for the form and rate of decline in zeta diversity and for the species retention rate. Results Species at higher trophic levels showed two to three times the rate of zeta diversity decline compared with lower trophic levels, indicating an increase in turnover from phytoplankton to carnivorous fishes. Body size showed the hypothesized unimodal relationship with rates of turnover for macroorganisms. Patterns of bacterial turnover contrasted with those found for macroorganisms, with the highest levels of turnover in pelagic habitats compared with benthic (kelp‐associated) habitats. The shape of retention rate curves showed the importance of both rare and common species in driving turnover; a finding that would not have been observable using pairwise (beta diversity) measures of turnover. Main conclusions Our results support theoretical predictions for phytoplankton and macroorganisms, showing an increase in turnover rate with trophic level, but these predictions did not hold for bacteria. Such deviations from theory need to be investigated further to identify underlying processes that govern microbial assemblage dynamics.

Factors controlling the effects of mutualistic bacteria on plants associated with fungi - Daniel A. Bastías; Emma R. Applegate; Linda J. Johnson; Stuart D. Card (Ecology Letters, 2022)
Plants interacting with mutualistic fungi (MF) or antagonistic fungi (AF) can form associations with bacteria. We assessed whether the performance gain conferred by mutualistic bacteria to fungal‐associated plants is affected by the interaction between symbiont traits, type of bacterial‐protective traits against AF and abiotic/biotic stresses. Results showed that (A) performance gain conferred by bacteria to MF‐associated plants was greater when symbionts promoted distinct rather than similar plant functions, (B) bacterial‐based alleviation of the AF's negative effect on plants was independent of the type of protective trait, (C) bacteria promoted a greater performance of symbiotic plants in presence of biotic, but not abiotic, stress compared to stress‐free situations. The plant performance gain was not affected by any fungal‐bacterial trait combination but optimised when bacteria conferred resistance traits in biotic stress situations. The effects of bacteria on fungal‐associated plants were controlled by the interaction between the symbionts' functional traits and the relationship between bacterial traits and abiotic/biotic stresses.

Local and large-scale spatial variation in a marine predator–prey interaction in the southwestern Atlantic - André Pardal; Stuart R. Jenkins; Ronaldo A. Christofoletti (Oecologia, 2022)

Post-settlement demographics of reef building corals suggest prolonged recruitment bottlenecks - Lauranne Sarribouette; Nicole E. Pedersen; Clinton B. Edwards; Stuart A. Sandin (Oecologia, 2022)
For many organisms, early life stages experience significantly higher rates of mortality relative to adults. However, tracking early life stage individuals through time in natural settings is difficult, limiting our understanding of the duration of these ‘mortality bottlenecks’, and the time required for survivorship to match that of adults. Here, we track a cohort of juvenile corals (1–5 cm maximum diameter) from 12 taxa at a remote atoll in the Central Pacific from 2013 to 2017 and describe patterns of annual survivorship. Of the 537 juveniles initially detected, 219 (41%) were alive 4 years later, 163 (30%) died via complete loss of live tissue from the skeleton, and the remaining 155 (29%) died via dislodgement. The differing mortality patterns suggest that habitat characteristics, as well as species-specific features, may influence early life stage survival. Across most taxa, survival fit a logistic model, reaching > 90% annual survival within 4 years. These data suggest that mortality bottlenecks characteristic of ‘recruitment’ extend up to 5 years after individuals can be visually detected. Ultimately, replenishment of adult coral populations via sexual reproduction is needed to maintain both coral cover and genetic diversity. This study provides key insights into the dynamics and time scales that characterize these critical early life stages.

Morphological and Functional Divergence of the Lower Jaw Between Native and Invasive Red Foxes - Colline Brassard; Jesse L. Forbes-Harper; Heather M. Crawford; John-Michael Stuart; Natalie M. Warburton; Michael C. Calver; Peter Adams; Elodie Monchâtre-Leroy; Jacques Barrat; Sandrine Lesellier; Claude Guintard; Hélène Garès; et al. (Journal of Mammalian Evolution, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Data Quality Influences the Predicted Distribution and Habitat of Four Southern-Hemisphere Albatross Species - Kimberly T. Goetz; Fabrice Stephenson; Andrew Hoskins; Aidan D. Bindoff; Rachael A. Orben; Paul M. Sagar; Leigh G. Torres; Caitlin E. Kroeger; Lisa A. Sztukowski; Richard A. Phillips; Stephen C. Votier; Stuart Bearhop; et al. (Frontiers in Marine Science, 2022)
Few studies have assessed the influence of data quality on the predicted probability of occurrence and preferred habitat of marine predators. We compared results from four species distribution models (SDMs) for four southern-hemisphere albatross species, Buller’s ( Thalassarche bulleri ), Campbell ( T. impavida ), grey-headed ( T. chrysostoma ), and white-capped ( T. steadi ), based on datasets of differing quality, ranging from no location data to twice-daily locations of individual birds collected by geolocation devices. Two relative environmental suitability (RES) models were fit using minimum and maximum preferred and absolute values for each environmental variable based on (1) monthly 50% kernel density contours and background environmental data, and (2) primary literature or expert opinion. Additionally, two boosted regression tree (BRT) models were fit using (1) opportunistic sightings data, and (2) geolocation data from bird-borne electronic tags. Using model-specific threshold values, habitat was quantified for each species and model. Model variables included distance from land, bathymetry, sea surface temperature, and chlorophyll- a concentration. Results from both RES models and the BRT model fit with opportunistic sightings were compared to those from the BRT model fit using geolocation data to assess the influence of data quality on predicted occupancy and habitat. For all species, BRT models outperformed RES models. BRT models offer a predictive advantage over RES models by being able to identify relevant variables, incorporate environmental interactions, and provide spatially explicit estimates of model uncertainty. RES models resulted in larger, less refined areas of predicted habitat for all species. Our study highlights the importance of data quality in predicting the distribution and habitat of albatrosses and emphasises the need to consider the pros and cons associated with different levels of data quality when using SDMs to inform management decisions. Furthermore, we examine the overlap in preferred habitat predicted by each SDM with fishing effort. We discuss the influence of data quality on predicting the wide-scale distributions of pelagic seabirds and how these impacts could result in different protection measures.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Organic carbon and salinity affect desorption of PFAS from estuarine sediments - Divina A. Navarro; Danielle P. Oliver; Stuart L. Simpson; Rai S. Kookana (Journal of Soils and Sediments, 2022)

Development of Inspired Therapeutics Pediatric VAD: Benchtop Evaluation of Impeller Performance and Torques for MagLev Motor Design - Landon H. Tompkins; Steven R. Prina; Barry N. Gellman; Gino F. Morello; Thomas Roussel; Jonathan A. Kopechek; Stuart J. Williams; Priscilla C. Petit; Mark S. Slaughter; Steven C. Koenig; Kurt A. Dasse (Cardiovascular Engineering and Technology, 2022)

Warming world, changing ocean: mitigation and adaptation to support resilient marine systems - Rowan Trebilco; Aysha Fleming; Alistair J. Hobday; Jess Melbourne-Thomas; Amelie Meyer; Jan McDonald; Phillipa C. McCormack; Kelli Anderson; Narissa Bax; Stuart P. Corney; Leo X. C. Dutra; Hannah E. Fogarty; et al. (Reviews in Fish Biology and Fisheries, 2022)

Decision-making with ecological process for coastal and marine planning: current literature and future directions - Debbie A. Chamberlain; Hugh P. Possingham; Stuart R. Phinn (Aquatic Ecology, 2022)

Historical museum samples enable the examination of divergent and parallel evolution during invasion - Katarina C. Stuart; William B. Sherwin; Jeremy J. Austin; Melissa Bateson; Marcel Eens; Matthew C. Brandley; Lee A. Rollins (Molecular Ecology, 2022)
During the Anthropocene, Earth has experienced unprecedented habitat loss, native species decline and global climate change. Concurrently, greater globalization is facilitating species movement, increasing the likelihood of alien species establishment and propagation. There is a great need to understand what influences a species’ ability to persist or perish within a new or changing environment. Examining genes that may be associated with a species’ invasion success or persistence informs invasive species management, assists with native species preservation and sheds light on important evolutionary mechanisms that occur in novel environments. This approach can be aided by coupling spatial and temporal investigations of evolutionary processes. Here we use the common starling, Sturnus vulgaris , to identify parallel and divergent evolutionary change between contemporary native and invasive range samples and their common ancestral population. To do this, we use reduced‐representation sequencing of native samples collected recently in northwestern Europe and invasive samples from Australia, together with museum specimens sampled in the UK during the mid‐19th century. We found evidence of parallel selection on both continents, possibly resulting from common global selective forces such as exposure to pollutants. We also identified divergent selection in these populations, which might be related to adaptive changes in response to the novel environment encountered in the introduced Australian range. Interestingly, signatures of selection are equally as common within both invasive and native range contemporary samples. Our results demonstrate the value of including historical samples in genetic studies of invasion and highlight the ongoing and occasionally parallel role of adaptation in both native and invasive ranges.

Pond methane dynamics, from microbial communities to ecosystem budget, during summer in Alaska - Carmella Vizza; Stuart E. Jones; Julia A. Hart; William E. West; Gary A. Lamberti (Limnology and Oceanography, 2022)
Ponds play a larger role in the global freshwater methane (CH 4 ) budget than predicted from surface area alone. To improve our understanding of pond CH 4 dynamics, we measured summer CH 4 production, concentrations, and emissions to the atmosphere in nine Alaskan wetland ponds along with potential physical, chemical, and biological regulators. Pond CH 4 production (0.64, 0.086–1.3 mmol m −2 d −1 ; median, interquartile range), as assessed with slurry incubations, was positively related to water‐column temperature and chlorophyll a (Chl a ), negatively influenced by oxygen levels, and varied with microbial community structure. Average water‐column CH 4 concentrations (0.39, 0.21–0.87 μ mol L −1 ) were lower in deeper ponds and at higher oxygen levels, and as expected, they were correlated with diffusive emissions (0.055, 0.024–0.20 mmol m −2 d −1 ) assessed with flux chambers. Based on a mass balance approach, 39–99% of CH 4 produced in ponds was oxidized. Pond ebullition (3.7, 0.60–24 mmol m −2 d −1 ) was higher and more variable than diffusive emissions. Additionally, pond ebullition rates were better correlated with production rates from the previous month. We also systematically compared the ratio of ebullition to diffusive CH 4 emissions in our ponds and other northern lakes, which was negatively related to water depth ( n = 71), but positively related to Chl a (n = 28). Our study sheds light on the factors that influence pond CH 4 dynamics and demonstrates that pond ebullition is a significant CH 4 source worthy of continued study.

Variable vulnerability to climate change in New Zealand lizards - Scott Jarvie; Travis Ingram; David G. Chapple; Rodney A. Hitchmough; Stuart V. Nielsen; Joanne M. Monks (Journal of Biogeography, 2022)
Aim The primary drivers of species and population extirpations have been habitat loss, overexploitation and invasive species, but human‐mediated climate change is expected to be a major driver in future. To minimise biodiversity loss, conservation managers should identify species vulnerable to climate change and prioritise their protection. Here, we estimate climatic suitability for two species‐rich taxonomic groups, then use phylogenetic analyses to assess vulnerability to climate change. Location Aotearoa New Zealand (NZ). Taxa NZ lizards: diplodactylid geckos and eugongylinae skinks. Methods We built correlative species distribution models (SDMs) for NZ geckos and skinks to estimate climatic suitability under current climate and 2070 future climate scenarios. We then used Bayesian phylogenetic mixed models (BPMMs) to assess vulnerability for both groups with predictor variables for life‐history traits (body size and activity phase) and current distribution (elevation and latitude). We explored two scenarios: an unlimited dispersal scenario, where projections track climate, and a no‐dispersal scenario, where projections are restricted to areas currently identified as suitable. Results SDMs projected vulnerability to climate change for most modelled lizards. For species' ranges projected to decline in climatically suitable areas, average decreases were between 42% and 46% for geckos and 33% and 52% for skinks, although area did increase or remain stable for a minority of species. For the no‐dispersal scenario, the average decrease for geckos was 37%–52% and for skinks was 33%–52%. Our BPMMs showed phylogenetic signal in climate change vulnerability for both groups, with elevation increasing vulnerability for geckos, and body size reducing vulnerability for skinks. Main conclusions New Zealand lizards showed variable vulnerability to climate change, with most species' ranges predicted to decrease. For species whose suitable climatic space is projected to disappear from within their current range, managed relocation could be considered to establish populations in regions that will be suitable under future climates.

Editorial: Advances in 3D Habitat Mapping of Marine Ecosystem Ecology and Conservation - Renata Ferrari; Javier X. Leon; Andrew J. Davies; John H. R. Burns; Stuart A. Sandin; Will F. Figueira; Manuel Gonzalez-Rivero (Frontiers in Marine Science, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Quantification of blue carbon pathways contributing to negative feedback on climate change following glacier retreat in West Antarctic fjords - Nadescha Zwerschke; Chester J. Sands; Alejandro Roman‐Gonzalez; David K. A. Barnes; Alice Guzzi; Stuart Jenkins; Carlos Muñoz‐Ramírez; James Scourse (Global Change Biology, 2022)
Global warming is causing significant losses of marine ice around the polar regions. In Antarctica, the retreat of tidewater glaciers is opening up novel, low‐energy habitats (fjords) that have the potential to provide a negative feedback loop to climate change. These fjords are being colonized by organisms on and within the sediment and act as a sink for particulate matter. So far, blue carbon potential in Antarctic habitats has mainly been estimated using epifaunal megazoobenthos (although some studies have also considered macrozoobenthos). We investigated two further pathways of carbon storage and potential sequestration by measuring the concentration of carbon of infaunal macrozoobenthos and total organic carbon (TOC) deposited in the sediment. We took samples along a temporal gradient since time of last glacier ice cover (1–1000 years) at three fjords along the West Antarctic Peninsula. We tested the hypothesis that seabed carbon standing stock would be mainly driven by time since last glacier covered. However, results showed this to be much more complex. Infauna were highly variable over this temporal gradient and showed similar total mass of carbon standing stock per m 2 as literature estimates of Antarctic epifauna. TOC mass in the sediment, however, was an order of magnitude greater than stocks of infaunal and epifaunal carbon and increased with time since last ice cover. Thus, blue carbon stocks and recent gains around Antarctica are likely much higher than previously estimated as is their negative feedback on climate change.

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

Increasing the spatial and temporal impact of ecological research: A roadmap for integrating a novel terrestrial process into an Earth system model - Emily Kyker‐Snowman; Danica L. Lombardozzi; Gordon B. Bonan; Susan J. Cheng; Jeffrey S. Dukes; Serita D. Frey; Elin M. Jacobs; Risa McNellis; Joshua M. Rady; Nicholas G. Smith; R. Quinn Thomas; William R. Wieder; et al. (Global Change Biology, 2022)
Terrestrial ecosystems regulate Earth's climate through water, energy, and biogeochemical transformations. Despite a key role in regulating the Earth system, terrestrial ecology has historically been underrepresented in the Earth system models (ESMs) that are used to understand and project global environmental change. Ecology and Earth system modeling must be integrated for scientists to fully comprehend the role of ecological systems in driving and responding to global change. Ecological insights can improve ESM realism and reduce process uncertainty, while ESMs offer ecologists an opportunity to broadly test ecological theory and increase the impact of their work by scaling concepts through time and space. Despite this mutualism, meaningfully integrating the two remains a persistent challenge, in part because of logistical obstacles in translating processes into mathematical formulas and identifying ways to integrate new theories and code into large, complex model structures. To help overcome this interdisciplinary challenge, we present a framework consisting of a series of interconnected stages for integrating a new ecological process or insight into an ESM. First, we highlight the multiple ways that ecological observations and modeling iteratively strengthen one another, dispelling the illusion that the ecologist's role ends with initial provision of data. Second, we show that many valuable insights, products, and theoretical developments are produced through sustained interdisciplinary collaborations between empiricists and modelers, regardless of eventual inclusion of a process in an ESM. Finally, we provide concrete actions and resources to facilitate learning and collaboration at every stage of data‐model integration. This framework will create synergies that will transform our understanding of ecology within the Earth system, ultimately improving our understanding of global environmental change, and broadening the impact of ecological research.

Cover Image - Damien A. Fordham; Stuart C. Brown; H. Reşit Akçakaya; Barry W. Brook; Sean Haythorne; Andrea Manica; Kevin T. Shoemaker; Jeremy J. Austin; Benjamin Blonder; Julia Pilowsky; Carsten Rahbek; David Nogues‐Bravo (Ecology Letters, 2022)

Process‐explicit models reveal pathway to extinction for woolly mammoth using pattern‐oriented validation - Damien A. Fordham; Stuart C. Brown; H. Reşit Akçakaya; Barry W. Brook; Sean Haythorne; Andrea Manica; Kevin T. Shoemaker; Jeremy J. Austin; Benjamin Blonder; July A. Pilowsky; Carsten Rahbek; David Nogues‐Bravo (Ecology Letters, 2022)
Pathways to extinction start long before the death of the last individual. However, causes of early stage population declines and the susceptibility of small residual populations to extirpation are typically studied in isolation. Using validated process‐explicit models, we disentangle the ecological mechanisms and threats that were integral in the initial decline and later extinction of the woolly mammoth. We show that reconciling ancient DNA data on woolly mammoth population decline with fossil evidence of location and timing of extinction requires process‐explicit models with specific demographic and niche constraints, and a constrained synergy of climatic change and human impacts. Validated models needed humans to hasten climate‐driven population declines by many millennia, and to allow woolly mammoths to persist in mainland Arctic refugia until the mid‐Holocene. Our results show that the role of humans in the extinction dynamics of woolly mammoth began well before the Holocene, exerting lasting effects on the spatial pattern and timing of its range‐wide extinction.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Functional traits reveal the dominant drivers of long‐term community change across a North American Great Lake - James S. Sinclair; Michael E. Fraker; James M. Hood; Kenneth T. Frank; Mark R. DuFour; Ann Marie Gorman; Stuart A. Ludsin (Global Change Biology, 2021)
Ecosystems worldwide have been impacted by multiple anthropogenic stressors, yet efforts to understand and manage these impacts have been hindered by difficulties in disentangling relative stressor effects. Theoretically, the actions of individual stressors can be delineated based on associated changes in functional traits and these relationships should be generalizable across communities comprised of different species. Thus, combining trait perspectives with community composition data could help to identify the relative influence of different stressors. We evaluated the utility of this combined approach by quantifying shifts in fish species and trait composition in Lake Erie during the past 50 years (1969–2018) in relation to human‐driven changes in nutrient inputs, climate warming, and biological invasions. Species and trait shifts were also compared between two Lake Erie basins, which differ in their environmental and biological characteristics, to identify trait responses that were generalizable across different ecosystems versus those that were context dependent. Our analyses revealed consistent species changes across basins, and shifts in feeding and thermal traits, that were primarily associated with altered nutrient inputs (oligotrophication followed by eutrophication). We found no or inconsistent trait‐based evidence for the effects of warming and two invasive fishes. Context‐dependent trait responses were also evident; nutrient inputs were related to shifts in species tolerant of turbidity in the shallow, eutrophic western basin, which contrasted to shifts between benthopelagic and benthic species in the deeper central basin. Our results reveal the dominant effects of specific stressors on a large freshwater lake and offer a framework for combining species‐based and trait‐based approaches to delineate the impacts of simultaneous stressors on communities of perturbed natural ecosystems.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Role of air–sea fluxes and ocean surface density in the production of deep waters in the eastern subpolar gyre of the North Atlantic - Tillys Petit; M. Susan Lozier; Simon A. Josey; Stuart A. Cunningham (Ocean Science, 2021)
Wintertime convection in the North Atlantic Ocean is a key component of the global climate as it produces dense waters at high latitudes that flow equatorward as part of the Atlantic Meridional Overturning Circulation (AMOC). Recent work has highlighted the dominant role of the Irminger and Iceland basins in the production of North Atlantic Deep Water. Dense water formation in these basins is mainly explained by buoyancy forcing that transforms surface waters to the deep waters of the AMOC lower limb. Air–sea fluxes and the ocean surface density field are both key determinants of the buoyancy-driven transformation. We analyze these contributions to the transformation in order to better understand the connection between atmospheric forcing and the densification of surface water. More precisely, we study the impact of air–sea fluxes and the ocean surface density field on the transformation of subpolar mode water (SPMW) in the Iceland Basin, a water mass that “pre-conditions” dense water formation downstream. Analyses using 40 years of observations (1980–2019) reveal that the variance in SPMW transformation is mainly influenced by the variance in density at the ocean surface. This surface density is set by a combination of advection, wind-driven upwelling and surface fluxes. Our study shows that the latter explains ∼ 30 % of the variance in outcrop area as expressed by the surface area between the outcropped SPMW isopycnals. The key role of the surface density in SPMW transformation partly explains the unusually large SPMW transformation in winter 2014–2015 over the Iceland Basin.

Environmental gradients predict the ratio of environmentally acquired carotenoids to self‐synthesised pteridine pigments - Devi Stuart‐Fox; Katrina J. Rankin; Adrian Lutz; Adam Elliott; Andrew F. Hugall; Claire A. McLean; Iliana Medina (Ecology Letters, 2021)
Carotenoids are important pigments producing integument colouration; however, their dietary availability may be limited in some environments. Many species produce yellow to red hues using a combination of carotenoids and self‐synthesised pteridine pigments. A compelling hypothesis is that pteridines replace carotenoids in environments where carotenoid availability is limited. To test this hypothesis, we quantified concentrations of five carotenoid and six pteridine pigments in multiple skin colours and individuals from 27 species of agamid lizards. We show that environmental gradients predict the ratio of carotenoids to pteridines; carotenoid concentrations are lower and pteridine concentrations higher in arid environments with low vegetation productivity. Both carotenoid and pteridine pigments were present in all species, but only pteridine concentrations explained colour variation among species and there were no correlations between carotenoid and pteridine pigments with a similar hue. These results suggest that in arid environments, where carotenoids are likely limited, species may compensate by synthesising more pteridines but do not necessarily replace carotenoids with pteridines of similar hue.

Limited Progress in Improving Gender and Geographic Representation in Coral Reef Science - Gabby N. Ahmadia; Samantha H. Cheng; Dominic A. Andradi-Brown; Stacy K. Baez; Megan D. Barnes; Nathan J. Bennett; Stuart J. Campbell; Emily S. Darling; Estradivari; David Gill; Erika Gress; Georgina G. Gurney; et al. (Frontiers in Marine Science, 2021)
Despite increasing recognition of the need for more diverse and equitable representation in the sciences, it is unclear whether measurable progress has been made. Here, we examine trends in authorship in coral reef science from 1,677 articles published over the past 16 years (2003–2018) and find that while representation of authors that are women (from 18 to 33%) and from non-OECD nations (from 4 to 13%) have increased over time, progress is slow in achieving more equitable representation. For example, at the current rate, it would take over two decades for female representation to reach 50%. Given that there are more coral reef non-OECD countries, at the current rate, truly equitable representation of non-OECD countries would take even longer. OECD nations also continue to dominate authorship contributions in coral reef science (89%), in research conducted in both OECD (63%) and non-OECD nations (68%). We identify systemic issues that remain prevalent in coral reef science (i.e., parachute science, gender bias) that likely contribute to observed trends. We provide recommendations to address systemic biases in research to foster a more inclusive global science community. Adoption of these recommendations will lead to more creative, innovative, and impactful scientific approaches urgently needed for coral reefs and contribute to environmental justice efforts.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Geological and hydrogeological assessment of the Brito Formation: Municipio de Tola, Nicaragua - James K. Adamson; G. Thomas LaVanchy; Brandon Stone; James A. Clark; Stuart J. Dykstra; Matthew J. Taylor (Hydrogeology Journal, 2021)
There are sparse hydrogeological data and insufficient hydrogeological knowledge in many areas of the world reliant on groundwater. Nicaragua’s Pacific coast is one such region that is also experiencing water scarcity resulting from increasing demand on groundwater resources and climate change. The primary source of water in the region is the aquifer system associated with the Brito Formation, which is a marine sedimentary stratum of mostly sandstone that blankets 75 km of coastline in southwest Nicaragua. This study focused on the Tola municipality with the objective to advance a conceptual understanding of the hydrogeology and to support sustainable water development. Results demonstrate a heterogeneous aquifer system with regional flow characteristics and other factors that influence groundwater availability and water quality. Primary porosity is low, and secondary porosity is the primary mechanism of aquifer storage and is influenced by geological structure and diagenesis processes. Groundwater recharge is spatially and temporally heterogeneous and direct recharge is low. Infiltration of streamflow and runoff, especially early in the rainy season, is thought to be a large component of groundwater recharge. Climate, flow and recharge dynamics, and low storage capacity make the Brito Formation a sensitive resource and vulnerable to drought, increased abstraction, and climate change. This assessment provides data and insights useful for informing future studies and investments within the region and may be applicable in other Central American and Caribbean nations with coastal sandstone aquifers.

Compound-Specific Stable Isotope Analysis of Amino Acids in Pelagic Shark Vertebrae Reveals Baseline, Trophic, and Physiological Effects on Bulk Protein Isotope Records - Sarah Magozzi; Simon R. Thorrold; Leah Houghton; Victoria A. Bendall; Stuart Hetherington; Gonzalo Mucientes; Lisa J. Natanson; Nuno Queiroz; Miguel N. Santos; Clive N. Trueman (Frontiers in Marine Science, 2021)
Variations in stable carbon and nitrogen isotope compositions in incremental tissues of pelagic sharks can be used to infer aspects of their spatial and trophic ecology across life-histories. Interpretations from bulk tissue isotopic compositions are complicated, however, because multiple processes influence these values, including variations in primary producer isotope ratios and consumer diets and physiological processing of metabolites. Here we challenge inferences about shark tropho-spatial ecology drawn from bulk tissue isotope data using data for amino acids. Stable isotope compositions of individual amino acids can partition the isotopic variance in bulk tissue into components associated with primary production on the one hand, and diet and physiology on the other. The carbon framework of essential amino acids (EAAs) can be synthesised de novo only by plants, fungi and bacteria and must be acquired by consumers through the diet. Consequently, the carbon isotopic composition of EAAs in consumers reflects that of primary producers in the location of feeding, whereas that of non-essential amino acids (non-EAAs) is additionally influenced by trophic fractionation and isotope dynamics of metabolic processing. We determined isotope chronologies from vertebrae of individual blue sharks and porbeagles from the North Atlantic. We measured carbon and nitrogen isotope compositions in bulk collagen and carbon isotope compositions of amino acids. Despite variability among individuals, common ontogenetic patterns in bulk isotope compositions were seen in both species. However, while life-history movement inferences from bulk analyses for blue sharks were supported by carbon isotope data from essential amino acids, inferences for porbeagles were not, implying that the observed trends in bulk protein isotope compositions in porbeagles have a trophic or physiological explanation, or are suprious effects. We explored variations in carbon isotope compositions of non-essential amino acids, searching for systematic variations that might imply ontogenetic changes in physiological processing, but patterns were highly variable and did not explain variance in bulk protein δ 13 C values. Isotopic effects associated with metabolite processing may overwhelm spatial influences that are weak or inconsistently developed in bulk tissue isotope values, but interpreting mechanisms underpinning isotopic variation in patterns in non-essential amino acids remains challenging.

Regulatory approaches for genome edited agricultural plants in select countries and jurisdictions around the world - Jon Entine; Maria Sueli S. Felipe; Jan-Hendrik Groenewald; Drew L. Kershen; Martin Lema; Alan McHughen; Alexandre Lima Nepomuceno; Ryo Ohsawa; Reynante L. Ordonio; Wayne A. Parrott; Hector Quemada; Carl Ramage; et al. (Transgenic Research, 2021)
Genome editing in agriculture and food is leading to new, improved crops and other products. Depending on the regulatory approach taken in each country or region, commercialization of these crops and products may or may not require approval from the respective regulatory authorities. This paper describes the regulatory landscape governing genome edited agriculture and food products in a selection of countries and regions.

Participatory Monitoring—A Citizen Science Approach for Coastal Environments - Paula Kasten; Stuart R. Jenkins; Ronaldo A. Christofoletti (Frontiers in Marine Science, 2021)
In this article the authors share their experiences, results, and lessons learned during the creation of a coastal biodiversity participatory monitoring initiative. Throughout 2019, we delivered five training workshops to 51 citizen scientists. Data collected by the citizens scientists were validated by checking its similarities against that gathered by specialists. High similarity values were found, indicating that, if proper training is provided, there is a great potential for citizen scientists to contribute biodiversity data with high value. During this process a certain level of variation in data produced by specialists was found, drawing attention to the need for prior alignment among specialists who may offer training for citizens. In addition, despite overall similar results between specialists and participants, some differences emerged in particular parts of the habitat; for example, the bivalve zones presented higher complexity and hence greater challenge. Identifying key challenges for participants is key to developing appropriate citizen science protocols. Here it is provided preliminary evidence that supports the use of the monitoring protocol to obtain biodiversity data gathered by citizen scientists, assuring its scientific quality. Enhancing participation by the community and specialists is key to further validate the approach and to effectively expand such protocols, enhancing the level of biodiversity data collection. In order to promote participation, and maintain citizen scientist engagement in the initiative, it is recommended the development of new investigations that assess the interests and motivations of the public to take part. It is also fundamentally important to have an effective strategy to communicate the results of participants’ monitoring and their applicability to local and global issues, thus maximizing the continuity of engagement of citizen scientists.

Correction to: TCA cycle metabolic compromise due to an aberrant S‑nitrosoproteome in HIV‑associated neurocognitive disorder with methamphetamine use - Paschalis‑Thomas Doulias; Tomohiro Nakamura; Henry Scott; Scott R. McKercher; Abdullah Sultan; Amanda Deal; Matthew Albertolle; Harry Ischiropoulos; Stuart A. Lipton (Journal of NeuroVirology, 2021)

TCA cycle metabolic compromise due to an aberrant S-nitrosoproteome in HIV-associated neurocognitive disorder with methamphetamine use - Paschalis-Thomas Doulias; Tomohiro Nakamura; Henry Scott; Scott R. McKercher; Abdullah Sultan; Amanda Deal; Matthew Albertolle; Harry Ischiropoulos; Stuart A. Lipton (Journal of NeuroVirology, 2021)

Persistence of a reef fish metapopulation via network connectivity: theory and data - Allison G. Dedrick; Katrina A. Catalano; Michelle R. Stuart; J. Wilson White; Humberto R. Montes; Malin L. Pinsky (Ecology Letters, 2021)
Determining metapopulation persistence requires understanding both demographic rates and patch connectivity. Persistence is well understood in theory but has proved challenging to test empirically for marine and other species with high connectivity that precludes classic colonisation–extinction dynamics. Here, we assessed persistence for a yellowtail anemonefish ( Amphiprion clarkii ) metapopulation using 7 years of annual sampling data along 30 km of coastline. We carefully accounted for uncertainty in demographic rates. Despite stable population abundances through time and sufficient production of surviving offspring for replacement, the pattern of connectivity made the metapopulation unlikely to persist in isolation and reliant on immigrants from outside habitat. To persist in isolation, the metapopulation would need higher fecundity or to retain essentially all recruits produced. This assessment of persistence in a marine metapopulation shows that stable abundance alone does not indicate persistence, emphasising the necessity of assessing both demographic and connectivity processes to understand metapopulation dynamics.

Global protected‐area coverage and human pressure on tidal flats - Narelle K. Hill; Bradley K. Woodworth; Stuart R. Phinn; Nicholas J. Murray; Richard A. Fuller (Conservation Biology, 2021)
Tidal flats are a globally distributed coastal ecosystem important for supporting biodiversity and ecosystem services. Local to continental‐scale studies have documented rapid loss of tidal habitat driven by human impacts, but assessments of progress in their conservation are lacking. With an internally consistent estimate of distribution and change, based on Landsat satellite imagery, now available for the world's tidal flats, we examined tidal flat representation in protected areas (PAs) and human pressure on tidal flats. We determined tidal flat representation and its net change in PAs by spatially overlaying tidal flat maps with the World Database of Protected Areas. Similarly, we overlaid the most recent distribution map of tidal flats (2014–2016) with the human modification map (HM c ) (range from 0, no human pressure, to 1, very high human pressure) to estimate the human pressure exerted on this ecosystem. Sixty‐eight percent of the current extent of tidal flats is subject to moderate to very high human pressure (HM c > 0.1), but 31% of tidal flat extent occurred in PAs, far exceeding PA coverage of the marine (6%) and terrestrial (13%) realms. Net change of tidal flat extent inside PAs was similar to tidal flat net change outside PAs from 1999 to 2016. Substantial shortfalls in protection of tidal flats occurred across Asia, where large intertidal extents coincided with high to very high human pressure (HM c > 0.4–1.0) and net tidal flat losses up to 86.4 km² (95% CI 83.9–89.0) occurred inside individual PAs in the study period. Taken together, our results show substantial progress in PA designation for tidal flats globally, but that PA status alone does not prevent all habitat loss. Safeguarding the world's tidal flats will thus require deeper understanding of the factors that govern their dynamics and effective policy that promotes holistic coastal and catchment management strategies.

Quantifying dispersal variability among nearshore marine populations - Katrina A. Catalano; Allison G. Dedrick; Michelle R. Stuart; Jonathan B. Puritz; Humberto R. Montes; Malin L. Pinsky (Molecular Ecology, 2021)
Dispersal drives diverse processes from population persistence to community dynamics. However, the amount of temporal variation in dispersal and its consequences for metapopulation dynamics is largely unknown for organisms with environmentally driven dispersal (e.g., many marine larvae, arthropods and plant seeds). Here, we used genetic parentage analysis to detect larval dispersal events in a common coral reef fish, Amphiprion clarkii , along 30 km of coastline consisting of 19 reef patches in Ormoc Bay, Leyte, Philippines. We quantified variation in the dispersal kernel across seven years (2012–2018) and monsoon seasons with 71 parentage assignments from 791 recruits and 1,729 adults. Connectivity patterns differed significantly among years and seasons in the scale and shape but not in the direction of dispersal. This interannual variation in dispersal kernels introduced positive temporal covariance among dispersal routes that theory predicts is likely to reduce stochastic metapopulation growth rates below the growth rates expected from only a single or a time‐averaged connectivity estimate. The extent of variation in mean dispersal distance observed here among years is comparable in magnitude to the differences across reef fish species. Considering dispersal variation will be an important avenue for further metapopulation and metacommunity research across diverse taxa.

Our future in the Anthropocene biosphere - Carl Folke; Stephen Polasky; Johan Rockström; Victor Galaz; Frances Westley; Michèle Lamont; Marten Scheffer; Henrik Österblom; Stephen R. Carpenter; F. Stuart Chapin; Karen C. Seto; Elke U. Weber; et al. (Ambio, 2021)
The COVID-19 pandemic has exposed an interconnected and tightly coupled globalized world in rapid change. This article sets the scientific stage for understanding and responding to such change for global sustainability and resilient societies. We provide a systemic overview of the current situation where people and nature are dynamically intertwined and embedded in the biosphere, placing shocks and extreme events as part of this dynamic; humanity has become the major force in shaping the future of the Earth system as a whole; and the scale and pace of the human dimension have caused climate change, rapid loss of biodiversity, growing inequalities, and loss of resilience to deal with uncertainty and surprise. Taken together, human actions are challenging the biosphere foundation for a prosperous development of civilizations. The Anthropocene reality—of rising system-wide turbulence—calls for transformative change towards sustainable futures. Emerging technologies, social innovations, broader shifts in cultural repertoires, as well as a diverse portfolio of active stewardship of human actions in support of a resilient biosphere are highlighted as essential parts of such transformations.

Ecotrons: Powerful and versatile ecosystem analysers for ecology, agronomy and environmental science - Jacques Roy; François Rineau; Hans J. De Boeck; Ivan Nijs; Thomas Pütz; Samuel Abiven; John A. Arnone; Craig V. M. Barton; Natalie Beenaerts; Nicolas Brüggemann; Matteo Dainese; Timo Domisch; et al. (Global Change Biology, 2021)
Ecosystems integrity and services are threatened by anthropogenic global changes. Mitigating and adapting to these changes require knowledge of ecosystem functioning in the expected novel environments, informed in large part through experimentation and modelling. This paper describes 13 advanced controlled environment facilities for experimental ecosystem studies, herein termed ecotrons, open to the international community. Ecotrons enable simulation of a wide range of natural environmental conditions in replicated and independent experimental units while measuring various ecosystem processes. This capacity to realistically control ecosystem environments is used to emulate a variety of climatic scenarios and soil conditions, in natural sunlight or through broad‐spectrum lighting. The use of large ecosystem samples, intact or reconstructed, minimizes border effects and increases biological and physical complexity. Measurements of concentrations of greenhouse trace gases as well as their net exchange between the ecosystem and the atmosphere are performed in most ecotrons, often quasi continuously. The flow of matter is often tracked with the use of stable isotope tracers of carbon and other elements. Equipment is available for measurements of soil water status as well as root and canopy growth. The experiments ran so far emphasize the diversity of the hosted research. Half of them concern global changes, often with a manipulation of more than one driver. About a quarter deal with the impact of biodiversity loss on ecosystem functioning and one quarter with ecosystem or plant physiology. We discuss how the methodology for environmental simulation and process measurements, especially in soil, can be improved and stress the need to establish stronger links with modelling in future projects. These developments will enable further improvements in mechanistic understanding and predictive capacity of ecotron research which will play, in complementarity with field experimentation and monitoring, a crucial role in exploring the ecosystem consequences of environmental changes.

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Signatures of selection in a recent invasion reveal adaptive divergence in a highly vagile invasive species - Katarina C. Stuart; Adam P. A. Cardilini; Phillip Cassey; Mark F. Richardson; William B. Sherwin; Lee A. Rollins; Craig D. H. Sherman (Molecular Ecology, 2021)
A detailed understanding of population genetics in invasive populations helps us to identify drivers of successful alien introductions. Here, we investigate putative signals of selection in Australian populations of invasive common starlings, Sturnus vulgaris , and seek to understand how these have been influenced by introduction history. We used reduced representation sequencing to determine population structure, and identify Single Nucleotide Polymorphisms (SNPs) that are putatively under selection. We found that since their introduction into Australia, starling populations have become genetically differentiated despite the potential for high levels of dispersal, and that starlings have responded to selective pressures imposed by a wide range of environmental conditions across their geographic range. Isolation by distance appears to have played a strong role in determining genetic substructure across the starling's Australian range. Analyses of candidate SNPs that are putatively under selection indicated that aridity, precipitation and temperature may be important factors driving adaptive variation across the starling's invasive range in Australia. However, we also noted that the historic introduction regime may leave footprints on sites flagged as being under adaptive selection, and encourage critical interpretation of selection analyses in non‐native populations.

The effect of dietary phytochemicals on nuclear factor erythroid 2-related factor 2 (Nrf2) activation: a systematic review of human intervention trials - Tom Clifford; Jarred P. Acton; Stuart P. Cocksedge; Kelly A. Bowden Davies; Stephen J. Bailey (Molecular Biology Reports, 2021)
We conducted a systematic review of human trials examining the effects of dietary phytochemicals on Nrf2 activation. In accordance with the PRISMA guidelines, Medline, Embase and CAB abstracts were searched for articles from inception until March 2020. Studies in adult humans that measured Nrf2 activation (gene or protein expression changes) following ingestion of a phytochemical, either alone or in combination were included. The study was pre-registered on the Prospero database (Registration Number: CRD42020176121). Twenty-nine full-texts were retrieved and reviewed for analysis; of these, eighteen were included in the systematic review. Most of the included participants were healthy, obese or type 2 diabetics. Study quality was assessed using the Cochrane Collaboration Risk of Bias Assessment tool. Twelve different compounds were examined in the included studies: curcumin, resveratrol and sulforaphane were the most common ( n = 3 each). Approximately half of the studies reported increases in Nrf2 activation ( n = 10); however, many were of poor quality and had an unclear or high risk of bias. There is currently limited evidence that phytochemicals activate Nrf2 in humans. Well controlled human intervention trials are needed to corroborate the findings from in vitro and animal studies.

Scavenging amphipods from the Wallaby-Zenith Fracture Zone: Extending the hadal paradigm beyond subduction trenches - Johanna N. J. Weston; Rachael A. Peart; Heather A. Stewart; Heather Ritchie; Stuart B. Piertney; Thomas D. Linley; Alan J. Jamieson (Marine Biology, 2021)
Our understanding of the ecology of the hadal zone (> 6000 m depth) is based solely on subduction trenches, leaving other geomorphological features, such as fracture zones, troughs, and basins, understudied. To address this knowledge gap, the Wallaby-Zenith Fracture Zone, Indian Ocean (WZFZ; ~ 22°S, 102°E; maximum depth 6625 m measured during Expedition SO258) was studied using free-fall baited landers. We assessed the amphipod distribution and community assemblage of this non-subduction hadal feature and compared it to subduction hadal features. Eleven species were identified across the abyssal-hadal transition zone using a paired morphological and DNA barcoding approach. The community composition was found to change gradually from abyssal to hadal depths, which contrasts with the ecotone shift characteristic of subduction trenches. A large population of Bathycallisoma schellenbergi (Birstein & Vinogradov, 1958), a quintessential hadal amphipod, was present at the flat bottom of the WZFZ. Further, an mtDNA phylogeny resolved a degree of phylogeographic structure between the B. schellenbergi WZFZ population and four previously sampled Pacific Ocean subduction trench populations, indicating these features are not interconnected through ongoing gene flow. Combined, these data indicate that some amphipods have far broader distributions than previously understood, with some species present in both hadal subduction trenches and non-subduction fracture zones and basins interspersed across the abyssal plains. This initial exploration highlights that whilst non-subduction features are an overlooked minor fraction of the total hadal area, they are essential to our understanding of the ecological and evolutionary dynamics across the hadal zone.

Characterisation of LV myocardial exercise function by 2-D strain deformation imaging in elite adolescent footballers - Guido E. Pieles; Lucy Gowing; Diane Ryding; Dave Perry; Steven R. McNally; A. Graham Stuart; Craig A. Williams (European Journal of Applied Physiology, 2021)
Purpose Few data exist on the descriptions of LV myocardial mechanics and reserve during dynamic exercise of adolescent athletes. The aim of this study was to describe the LV myocardial and cardiopulmonary changes during exercise using 2-D strain deformation imaging. Methods Elite adolescent male football players ( n = 42) completed simultaneous cardiopulmonary exercise testing (CPET) and exercise echocardiography measurement of LV myocardial deformation by 2-D strain imaging. LV longitudinal and circumferential 2-D strain and strain rates were analyzed at each stage during incremental exercise to a work rate of 150 W. Additionally, exercise LV myocardial deformation and its relation to metabolic exercise parameters were evaluated at each exercise stage and in recovery using repeated measures ANOVA, linear regression and paired t tests. Results LV peak systolic baseline 2-D strain (longitudinal: − 15.4 ± 2.5%, circumferential: − 22.5 ± 3.1%) increased with each exercise stage, but longitudinal strain plateaued at 50 W (mean strain reserve − 7.8 ± 3.0) and did not significantly increase compared to subsequent exercise stages ( P > 0.05), whilst circumferential strain (mean strain reserve − 11.6 ± 3.3) significantly increased ( P < 0.05) throughout exercise up to 150 W as the dominant mechanism of exercise LV contractility increase. Regression analyses showed LV myocardial strain increased linearly relative to HR, VO 2 and O 2 pulse ( P < 0.05) for circumferential deformation, but showed attenuation for longitudinal deformation. Conclusion This study describes LV myocardial deformation dynamics by 2-D strain and provides reference values for LV myocardial strain and strain rate during exercise in adolescent footballers. It found important differences between LV longitudinal and circumferential myocardial mechanics during exercise and introduces a methodology that can be used to quantify LV function and cardiac reserve during exercise in adolescent athletes.

Global root traits (GRooT) database - Nathaly R. Guerrero‐Ramírez; Liesje Mommer; Grégoire T. Freschet; Colleen M. Iversen; M. Luke McCormack; Jens Kattge; Hendrik Poorter; Fons van der Plas; Joana Bergmann; Thom W. Kuyper; Larry M. York; Helge Bruelheide; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait data are fundamental to the quantitative description of plant form and function. Although root traits capture key dimensions related to plant responses to changing environmental conditions and effects on ecosystem processes, they have rarely been included in large‐scale comparative studies and global models. For instance, root traits remain absent from nearly all studies that define the global spectrum of plant form and function. Thus, to overcome conceptual and methodological roadblocks preventing a widespread integration of root trait data into large‐scale analyses we created the Global Root Trait (GRooT) Database. GRooT provides ready‐to‐use data by combining the expertise of root ecologists with data mobilization and curation. Specifically, we (a) determined a set of core root traits relevant to the description of plant form and function based on an assessment by experts, (b) maximized species coverage through data standardization within and among traits, and (c) implemented data quality checks. Main types of variables contained GRooT contains 114,222 trait records on 38 continuous root traits. Spatial location and grain Global coverage with data from arid, continental, polar, temperate and tropical biomes. Data on root traits were derived from experimental studies and field studies. Time period and grain Data were recorded between 1911 and 2019. Major taxa and level of measurement GRooT includes root trait data for which taxonomic information is available. Trait records vary in their taxonomic resolution, with subspecies or varieties being the highest and genera the lowest taxonomic resolution available. It contains information for 184 subspecies or varieties, 6,214 species, 1,967 genera and 254 families. Owing to variation in data sources, trait records in the database include both individual observations and mean values. Software format GRooT includes two csv files. A GitHub repository contains the csv files and a script in R to query the database.

Accelerated invasion of decapod crustaceans in the southernmost point of the Atlantic coast of Europe: A non-natives’ hot spot? - Enrique González-Ortegón; Stuart Jenkins; Bella S. Galil; Pilar Drake; Jose A. Cuesta (Biological Invasions, 2020)

Extended Pelagic Life in a Bathybenthic Octopus - Roger Villanueva; Vladimir V. Laptikhovsky; Stuart B. Piertney; Fernando Ángel Fernández-Álvarez; Martin A. Collins; Jonathan D. Ablett; Alejandro Escánez (Frontiers in Marine Science, 2020)
Planktonic stages of benthic octopuses can reach relatively large sizes in some species, usually in oceanic, epipelagic waters while living as part of the macroplankton. These young octopuses appear to delay settlement on the seabed for an undetermined period of time that is probably longer than for those octopus paralarvae living in coastal, neritic waters. The reason for this delay is unknown and existing information about their biology is very scarce. Here we report on the presence of juvenile and subadult forms of the bathybenthic octopus Pteroctopus tetracirrhus in oceanic waters of the South and North Atlantic and its association with the pyrosomid species Pyrosoma atlanticum , apparently used by the octopus as a refuge or shelter. The relatively large size of the P. tetracirrhus living in oceanic waters as the individuals reported here, together with the morphological characteristics of this bathybenthic species including its gelatinous body, minute suckers embedded in swollen skin and the deep interbrachial web, indicates that P. tetracirrhus may be considered a model of a transitional octopus species that is colonizing the pelagic environment by avoiding descending to the bathyal benthos. This process seems to occur in the same way as in the supposed origin of the ctenoglossan holopelagic octopods of the families Amphitretidae, Bolitaenidae, and Vitreledonellidae, which have arisen via neoteny from the planktonic paralarval stages of benthic octopuses.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Using structured eradication feasibility assessment to prioritize the management of new and emerging invasive alien species in Europe - Olaf Booy; Pete A. Robertson; Niall Moore; Jess Ward; Helen E. Roy; Tim Adriaens; Richard Shaw; Johan Van Valkenburg; Gabrielle Wyn; Sandro Bertolino; Olivier Blight; Etienne Branquart; et al. (Global Change Biology, 2020)
Prioritizing the management of invasive alien species (IAS) is of global importance and within Europe integral to the EU IAS regulation. To prioritize management effectively, the risks posed by IAS need to be assessed, but so too does the feasibility of their management. While the risk of IAS to the EU has been assessed, the feasibility of management has not. We assessed the feasibility of eradicating 60 new (not yet established) and 35 emerging (established with limited distribution) species that pose a threat to the EU, as identified by horizon scanning. The assessment was carried out by 34 experts in invasion management from across Europe, applying the Non‐Native Risk Management scheme to defined invasion scenarios and eradication strategies for each species, assessing the feasibility of eradication using seven key risk management criteria. Management priorities were identified by combining scores for risk (derived from horizon scanning) and feasibility of eradication. The results show eradication feasibility score and risk score were not correlated, indicating that risk management criteria evaluate different information than risk assessment. In all, 17 new species were identified as particularly high priorities for eradication should they establish in the future, whereas 14 emerging species were identified as priorities for eradication now. A number of species considered highest priority for eradication were terrestrial vertebrates, a group that has been the focus of a number of eradication attempts in Europe. However, eradication priorities also included a diverse range of other taxa (plants, invertebrates and fish) suggesting there is scope to broaden the taxonomic range of attempted eradication in Europe. We demonstrate that broad scale structured assessments of management feasibility can help prioritize IAS for management. Such frameworks are needed to support evidence‐based decision‐making.

Novel co‐occurrence of functionally redundant consumers induced by range expansion alters community structure - Moisés A. Aguilera; Nelson Valdivia; Bernardo R. Broitman; Stuart R. Jenkins; Sergio A. Navarrete (Ecology, 2020)
Ongoing climate change is shifting the geographic distributions of some species, potentially imposing rapid changes in local community structure and ecosystem functioning. Besides changes in population‐level interspecific interactions, such range shifts may also cause changes in functional structure within the host assemblages, which can result in losses or gains in ecosystem functions. Because consumer‐resource dynamics are central to community regulation, functional reorganization driven by introduction of new consumer species can have large consequences on ecosystem functions. Here we experimentally examine the extent to which the recent poleward range expansion of the intertidal grazer limpet Scurria viridula along the coast of Chile has altered the role of the resident congeneric limpet S. zebrina, and whether the net collective impacts, and functional structure, of the entire herbivore guild have been modified by the introduction of this new member. We examined the functional role of Scurria species in controlling ephemeral algal cover, bare rock availability, and species richness and diversity, and compared the effects in the region of range overlap against their respective “native” abutted ranges. Experiments showed depression of per capita effects of the range‐expanded species within the region of overlap, suggesting environmental conditions negatively affect individual performance. In contrast, effects of S. zebrina were commonly invariant at its range edge. When comparing single species versus polycultures, effects on bare rock cover were altered by the presence of the other Scurria species, suggesting competition between Scurria species. Importantly, although the magnitude of S. viridula effects at the range overlap was reduced, its addition to the herbivore guild seems to complement and intensify the role of the guild in reducing green algal cover, species richness and increasing bare space provision. Our study thus highlights that range expansion of an herbivore can modify the functional guild structure in the recipient community. It also highlights the complexity of predicting how functional structure may change in the face of natural or human‐induced range expansions. There is a need for more field‐based examination of regional functional compensation, complementarity, or inhibition before we can construct a conceptual framework to anticipate the consequences of species range expansions.

Controls on Ocean Color Spectra Observed During the North Atlantic Aerosols and Marine Ecosystems Study (NAAMES) - James G. Allen; David A. Siegel; Norman B. Nelson; Stuart Halewood (Frontiers in Marine Science, 2020)

Analytical and Computational Advances, Opportunities, and Challenges in Marine Organic Biogeochemistry in an Era of “Omics” - Andrew D. Steen; Stephanie Kusch; Hussain A. Abdulla; Nevenka Cakić; Sarah Coffinet; Thorsten Dittmar; James M. Fulton; Valier Galy; Kai-Uwe Hinrichs; Anitra E. Ingalls; Boris P. Koch; Elizabeth Kujawinski; et al. (Frontiers in Marine Science, 2020)

Urban-scale variation in pollen concentrations: a single station is insufficient to characterize daily exposure - Daniel S. W. Katz; Stuart A. Batterman (Aerobiologia, 2020)

Pollen production for 13 urban North American tree species: allometric equations for tree trunk diameter and crown area - Daniel S. W. Katz; Jonathan R. Morris; Stuart A. Batterman (Aerobiologia, 2020)

Ecological momentary assessment of temptations and lapses in non-daily smokers - Saul Shiffman; Sarah M. Scholl; Jason Mao; Stuart G. Ferguson; Donald Hedeker; Hilary A. Tindle (Psychopharmacology, 2020)

Quantifying life history demographics of the scleractinian coral genus Pocillopora at Palmyra Atoll - Sho M. Kodera; Clinton B. Edwards; Vid Petrovic; Nicole E. Pedersen; Yoan Eynaud; Stuart A. Sandin (Coral Reefs, 2020)

Using Modern Conservation Tools for Innovative Management of Coral Reefs: The MANACO Consortium - Oliver Selmoni; Gaël Lecellier; Lara Ainley; Antoine Collin; Raimana Doucet; Vaimiti Dubousquet; Hudson Feremaito; Edouard Ito Waia; Stuart Kininmonth; Hélène Magalon; Siola’a Malimali; Ateliana Maugateau; et al. (Frontiers in Marine Science, 2020)

Hydro-Morphological Characterization of Coral Reefs for Wave Runup Prediction - Fred Scott; Jose A. A. Antolinez; Robert McCall; Curt Storlazzi; Ad Reniers; Stuart Pearson (Frontiers in Marine Science, 2020)

Tiered analysis of whole-exome sequencing for epilepsy diagnosis - Paul J. Dunn; Bridget H. Maher; Cassie L. Albury; Shani Stuart; Heidi G. Sutherland; Neven Maksemous; Miles C. Benton; Robert A. Smith; Larisa M. Haupt; Lyn R. Griffiths (Molecular Genetics and Genomics, 2020)

Translational studies of intravenous and intracerebroventricular routes of administration for CNS cellular biodistribution for BMN 250, an enzyme replacement therapy for the treatment of Sanfilippo type B - Anita Grover; Danielle Crippen-Harmon; Lacey Nave; Jon Vincelette; Jill C. M. Wait; Andrew C. Melton; Roger Lawrence; Jillian R. Brown; Katherine A. Webster; Bryan K. Yip; Brian Baridon; Catherine Vitelli; et al. (Drug Delivery and Translational Research, 2020)
BMN 250 is being developed as enzyme replacement therapy for Sanfilippo type B, a primarily neurological rare disease, in which patients have deficient lysosomal alpha- N -acetylglucosaminidase (NAGLU) enzyme activity. BMN 250 is taken up in target cells by the cation-independent mannose 6-phosphate receptor (CI-MPR, insulin-like growth factor 2 receptor), which then facilitates transit to the lysosome. BMN 250 is dosed directly into the central nervous system via the intracerebroventricular (ICV) route, and the objective of this work was to compare systemic intravenous (IV) and ICV delivery of BMN 250 to confirm the value of ICV dosing. We first assess the ability of enzyme to cross a potentially compromised blood–brain barrier in the Naglu −/− mouse model and then assess the potential for CI-MPR to be employed for receptor-mediated transport across the blood–brain barrier. In wild-type and Naglu −/− mice, CI-MPR expression in brain vasculature is high during the neonatal period but virtually absent by adolescence. In contrast, CI-MPR remains expressed through adolescence in non-affected non-human primate and human brain vasculature. Combined results from IV administration of BMN 250 in Naglu −/− mice and IV and ICV administration in healthy juvenile non-human primates suggest a limitation to therapeutic benefit from IV administration because enzyme distribution is restricted to brain vascular endothelial cells: enzyme does not reach target neuronal cells following IV administration, and pharmacological response following IV administration is likely restricted to clearance of substrate in endothelial cells. In contrast, ICV administration enables central nervous system enzyme replacement with biodistribution to target cells.

Long-term trends in albatross diets in relation to prey availability and breeding success - William F. Mills; José C. Xavier; Stuart Bearhop; Yves Cherel; Stephen C. Votier; Claire M. Waluda; Richard A. Phillips (Marine Biology, 2020)

Synthesis optimisation and characterisation of chitosan-calcite adsorbent from fishery-food waste for phosphorus removal - Sabolc Pap; Caroline Kirk; Barbara Bremner; Maja Turk Sekulic; Stuart W. Gibb; Snezana Maletic; Mark A. Taggart (Environmental Science and Pollution Research, 2020)
Here, Box-Behnken design (BBD) approaches were utilised to optimise synthesis methodology for the chitosan-calcite rich adsorbent (CCM) made from fishery-food waste material (crab carapace), using low-temperature activation and potassium hydroxide (KOH). The effect of activation temperature, activation time and impregnation ratio was studied. The final adsorbent material was evaluated for its phosphorus (P) removal efficiency from liquid phase. Results showed that impregnation ratio was the most significant individual factor as this acted to increase surface deacetylation of the chitin (to chitosan) and increased the number of amine groups (–NH 2 ) in the chitosan chain. P removal efficiency approached 75.89% (at initial P concentration of 20 mg/L) under optimised experimental conditions, i.e. where the impregnation ratio for KOH:carapace (g/g) was 1:1, the activation temperature was 105 °C and the activation time was 150 min. Predicted responses were in good agreement with the experimental data. Additionally, the pristine and CCM material were further analysed using scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM/EDX), Brunauer-Emmett-Teller technique (BET), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and thermal gravimetric analysis (TGA). Characterisation showed enhancements in surface chemistry (introducing positively charged amine groups), textural properties and thermal stability of the CCM.

Adaptive capacity in social–ecological systems: a framework for addressing bark beetle disturbances in natural resource management - Stuart Cottrell; Katherine M. Mattor; Jesse L. Morris; Christopher J. Fettig; Pavlina McGrady; Dorothy Maguire; Patrick M. A. James; Jennifer Clear; Zach Wurtzebach; Yu Wei; Andrea Brunelle; Jessica Western; et al. (Sustainability Science, 2020)

Average Fitness Differences on NK Landscapes - Wim Hordijk; Stuart A. Kauffman; Peter F. Stadler (Theory in Biosciences, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Fish Diet Shifts Associated with the Northern Gulf of Mexico Hypoxic Zone - Cassandra N. Glaspie; Melissa Clouse; Klaus Huebert; Stuart A. Ludsin; Doran M. Mason; James J. Pierson; Michael R. Roman; Stephen B. Brandt (Estuaries and Coasts, 2019)

Changes in benthic community composition associated with the outbreak of the corallimorph, Rhodactis howesii, at Palmyra Atoll - Amanda L. Carter; Clinton B. Edwards; Michael D. Fox; Corinne G. Amir; Yoan Eynaud; Maggie D. Johnson; Levi S. Lewis; Stuart A. Sandin; Jennifer E. Smith (Coral Reefs, 2019)

Anthropogenic N deposition alters soil organic matter biochemistry and microbial communities on decaying fine roots - William A. Argiroff; Donald R. Zak; Rima A. Upchurch; Sydney O. Salley; A. Stuart Grandy (Global Change Biology, 2019)
Fine root litter is a primary source of soil organic matter (SOM), which is a globally important pool of C that is responsive to climate change. We previously established that ~20 years of experimental nitrogen (N) deposition has slowed fine root decay and increased the storage of soil carbon (C; +18%) across a widespread northern hardwood forest ecosystem. However, the microbial mechanisms that have directly slowed fine root decay are unknown. Here, we show that experimental N deposition has decreased the relative abundance of Agaricales fungi (−31%) and increased that of partially ligninolytic Actinobacteria (+24%) on decaying fine roots. Moreover, experimental N deposition has increased the relative abundance of lignin‐derived compounds residing in SOM (+53%), and this biochemical response is significantly related to shifts in both fungal and bacterial community composition. Specifically, the accumulation of lignin‐derived compounds in SOM is negatively related to the relative abundance of ligninolytic Mycena and Kuehneromyces fungi, and positively related to Microbacteriaceae. Our findings suggest that by altering the composition of microbial communities on decaying fine roots such that their capacity for lignin degradation is reduced, experimental N deposition has slowed fine root litter decay, and increased the contribution of lignin‐derived compounds from fine roots to SOM. The microbial responses we observed may explain widespread findings that anthropogenic N deposition increases soil C storage in terrestrial ecosystems. More broadly, our findings directly link composition to function in soil microbial communities, and implicate compositional shifts in mediating biogeochemical processes of global significance.

Foraging consistency of coral reef fishes across environmental gradients in the central Pacific - Brian J. Zgliczynski; Gareth J. Williams; Scott L. Hamilton; Elisabeth G. Cordner; Michael D. Fox; Yoan Eynaud; Robert H. Michener; Les S. Kaufman; Stuart A. Sandin (Oecologia, 2019)

Applying habitat and population‐density models to land‐cover time series to inform IUCN Red List assessments - Luca Santini; Stuart H. M. Butchart; Carlo Rondinini; Ana Benítez‐López; Jelle P. Hilbers; Aafke M. Schipper; Mirza Cengic; Joseph A. Tobias; Mark A. J. Huijbregts (Conservation Biology, 2019)
The IUCN (International Union for Conservation of Nature) Red List categories and criteria are the most widely used framework for assessing the relative extinction risk of species. The criteria are based on quantitative thresholds relating to the size, trends, and structure of species’ distributions and populations. However, data on these parameters are sparse and uncertain for many species and unavailable for others, potentially leading to their misclassification or classification as data deficient. We devised an approach that combines data on land‐cover change, species‐specific habitat preferences, population abundance, and dispersal distance to estimate key parameters (extent of occurrence, maximum area of occupancy, population size and trend, and degree of fragmentation) and hence predict IUCN Red List categories for species. We applied our approach to nonpelagic birds and terrestrial mammals globally (∼15,000 species). The predicted categories were fairly consistent with published IUCN Red List assessments, but more optimistic overall. We predicted 4.2% of species (467 birds and 143 mammals) to be more threatened than currently assessed and 20.2% of data deficient species (10 birds and 114 mammals) to be at risk of extinction. Incorporating the habitat fragmentation subcriterion reduced these predictions 1.5–2.3% and 6.4–14.9% (depending on the quantitative definition of fragmentation) for threatened and data deficient species, respectively, highlighting the need for improved guidance for IUCN Red List assessors on the application of this aspect of the IUCN Red List criteria. Our approach complements traditional methods of estimating parameters for IUCN Red List assessments. Furthermore, it readily provides an early‐warning system to identify species potentially warranting changes in their extinction‐risk category based on periodic updates of land‐cover information. Given our method relies on optimistic assumptions about species distribution and abundance, all species predicted to be more at risk than currently evaluated should be prioritized for reassessment.

Upregulation of Proteolytic Pathways and Altered Protein Biosynthesis Underlie Retinal Pathology in a Mouse Model of Alzheimer’s Disease - Mehdi Mirzaei; Kanishka Pushpitha; Liting Deng; Nitin Chitranshi; Veer Gupta; Rashi Rajput; Abu Bakr Mangani; Yogita Dheer; Angela Godinez; Matthew J. McKay; Karthik Kamath; Dana Pascovici; et al. (Molecular Neurobiology, 2019)

Evolution of permafrost in China during the last 20 ka - Huijun Jin; Xiaoying Jin; Ruixia He; Dongliang Luo; Xiaoli Chang; Shaoling Wang; Sergey S Marchenko; Sizhong Yang; Chaolu Yi; Shijie Li; Stuart A Harris (Science China Earth Sciences, 2019)

Limited coral mortality following acute thermal stress and widespread bleaching on Palmyra Atoll, central Pacific - Michael D. Fox; Amanda L. Carter; Clinton B. Edwards; Yuichiro Takeshita; Maggie D. Johnson; Vid Petrovic; Corinne G. Amir; Enric Sala; Stuart A. Sandin; Jennifer E. Smith (Coral Reefs, 2019)

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

Spatial resilience of the Great Barrier Reef under cumulative disturbance impacts - Camille Mellin; Samuel Matthews; Kenneth R.N. Anthony; Stuart C. Brown; M. Julian Caley; Kerryn A. Johns; Kate Osborne; Marjetta Puotinen; Angus Thompson; Nicholas H. Wolff; Damien A. Fordham; M. Aaron MacNeil (Global Change Biology, 2019)
In the face of increasing cumulative effects from human and natural disturbances, sustaining coral reefs will require a deeper understanding of the drivers of coral resilience in space and time. Here we develop a high‐resolution, spatially explicit model of coral dynamics on Australia's Great Barrier Reef (GBR). Our model accounts for biological, ecological and environmental processes, as well as spatial variation in water quality and the cumulative effects of coral diseases, bleaching, outbreaks of crown‐of‐thorns starfish ( Acanthaster cf. solaris ), and tropical cyclones. Our projections reconstruct coral cover trajectories between 1996 and 2017 over a total reef area of 14,780 km 2 , predicting a mean annual coral loss of −0.67%/year mostly due to the impact of cyclones, followed by starfish outbreaks and coral bleaching. Coral growth rate was the highest for outer shelf coral communities characterized by digitate and tabulate Acropora spp. and exposed to low seasonal variations in salinity and sea surface temperature, and the lowest for inner‐shelf communities exposed to reduced water quality. We show that coral resilience (defined as the net effect of resistance and recovery following disturbance) was negatively related to the frequency of river plume conditions, and to reef accessibility to a lesser extent. Surprisingly, reef resilience was substantially lower within no‐take marine protected areas, however this difference was mostly driven by the effect of water quality. Our model provides a new validated, spatially explicit platform for identifying the reefs that face the greatest risk of biodiversity loss, and those that have the highest chances to persist under increasing disturbance regimes.

The Australian National Rabbit Database: 50 yr of population monitoring of an invasive species - Emilie Roy‐Dufresne; Miguel Lurgi; Stuart C. Brown; Konstans Wells; Brian Cooke; Greg Mutze; David Peacock; Phill Cassey; Dave Berman; Barry W. Brook; Susan Campbell; Tarnya Cox; et al. (Ecology, 2019)
With ongoing introductions into Australia since the 1700s, the European rabbit ( Oryctolagus cuniculus ) has become one of the most widely distributed and abundant vertebrate pests, adversely impacting Australia's biodiversity and agroeconomy. To understand the population and range dynamics of the species and its impacts better, occurrence and abundance data have been collected by researchers and citizens from sites covering a broad spectrum of climatic and environmental conditions in Australia. The lack of a common and accessible repository for these data has, however, limited their use in determining important spatiotemporal drivers of the structure and dynamics of the geographical range of rabbits in Australia. To meet this need, we created the Australian National Rabbit Database, which combines more than 50 yr of historical and contemporary survey data collected from throughout the range of the species in Australia. The survey data, obtained from a suite of complementary monitoring methods, were combined with high‐resolution weather, climate, and environmental information, and an assessment of data quality. The database provides records of rabbit occurrence (689,265 records) and abundance (51,241 records, >120 distinct sites) suitable for identifying the spatiotemporal drivers of the rabbit's distribution and for determining spatial patterns of variation in its key life‐history traits, including maximum rates of population growth. Because all data are georeferenced and date stamped, they can be coupled with information from other databases and spatial layers to explore the potential effects of rabbit occurrence and abundance on Australia's native wildlife and agricultural production. The Australian National Rabbit Database is an important tool for understanding and managing the European rabbit in its invasive range and its effects on native biodiversity and agricultural production. It also provides a valuable resource for addressing questions related to the biology, success, and impacts of invasive species more generally. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Atlantic Meridional Overturning Circulation: Observed Transport and Variability - Eleanor Frajka-Williams; Isabelle J. Ansorge; Johanna Baehr; Harry L. Bryden; Maria Paz Chidichimo; Stuart A. Cunningham; Gokhan Danabasoglu; Shenfu Dong; Kathleen A. Donohue; Shane Elipot; Patrick Heimbach; N. Penny Holliday; et al. (Frontiers in Marine Science, 2019)

Polarity, planes of cell division, and the evolution of plant multicellularity - Karl J. Niklas; Randy Wayne; Mariana Benítez; Stuart A. Newman (Protoplasma, 2019)

Deformation capacity of reinforced concrete columns with smooth reinforcement - Eyitayo A. Opabola; Kenneth J. Elwood; Stuart Oliver (Bulletin of Earthquake Engineering, 2019)

Identifying transformational space for transdisciplinarity: using art to access the hidden third - Toddi A. Steelman; Evan Andrews; Sarah Baines; Lalita Bharadwaj; Emilie Rose Bjornson; Lori Bradford; Kendrick Cardinal; Gary Carriere; Jennifer Fresque-Baxter; Timothy D. Jardine; Ingrid MacColl; Stuart Macmillan; et al. (Sustainability Science, 2019)

A boreal songbird's 20,000 km migration across North America and the Atlantic Ocean - William V. DeLuca; Bradley K. Woodworth; Stuart A. Mackenzie; Amy E. M. Newman; Hilary A. Cooke; Laura M. Phillips; Nikole E. Freeman; Alex O. Sutton; Lila Tauzer; Carol McIntyre; Iain J. Stenhouse; Scott Weidensaul; et al. (Ecology, 2019)

Real-Time Monitoring with a Tablet App Improves Implementation of Treatments to Enhance Forest Structural Diversity - Colin T Maher; Emily Oja; Abigail Marshall; Matthew Cunningham; Lucas Townsend; Graham Worley-Hood; Luke Ruffner Robinson; Taylor Margot; Drew Lyons; Stuart Fety; Eryn E Schneider; Sean M A Jeronimo; et al. (Journal of Forestry, 2019)

Methane Cycling Contributes to Distinct Patterns in Carbon Stable Isotopes of Wetland Detritus - Julia A. Hart; Carmella Vizza; William E. West; Dominic T. Chaloner; Stuart E. Jones; Gary A. Lamberti (Wetlands, 2019)

Genetic swamping and possible species collapse: tracking introgression between the native Candy Darter and introduced Variegate Darter - Isaac Gibson; Amy B. Welsh; Stuart A. Welsh; Daniel A. Cincotta (Conservation Genetics, 2019)

Absence of PCB Hot Spot Effect in Walleye Sander vitreus from Lower Green Bay of Lake Michigan - Charles P. Madenjian; Daniel J. Dembkowski; Daniel A. Isermann; Stuart A. Batterman; Sergei M. Chernyak; Stewart F. Cogswell; Mark E. Holey (Archives of Environmental Contamination and Toxicology, 2019)

Evidence for enhanced late-stage larval quality, not survival, through maternal carry-over effects in a space monopolizing barnacle - Paula Kasten; Stuart R. Jenkins; Réjean Tremblay; Augusto A. V. Flores (Hydrobiologia, 2019)

Body size, reef area and temperature predict global reef‐fish species richness across spatial scales - D. R. Barneche; E. L. Rezende; V. Parravicini; E. Maire; G. J. Edgar; R. D. Stuart‐Smith; J. E. Arias‐González; C. E. L. Ferreira; A. M. Friedlander; A. L. Green; O. J. Luiz; F. A. Rodríguez‐Zaragoza; et al. (Global Ecology and Biogeography, 2019)
Aim To investigate biotic and abiotic correlates of reef‐fish species richness across multiple spatial scales. Location Tropical reefs around the globe, including 485 sites in 109 sub‐provinces spread across 14 biogeographic provinces. Time period Present. Major taxa studied 2,523 species of reef fish. Methods We compiled a database encompassing 13,050 visual transects. We used hierarchical linear Bayesian models to investigate whether fish body size, reef area, isolation, temperature, and anthropogenic impacts correlate with reef‐fish species richness at each spatial scale (i.e., sites, sub‐provinces, provinces). Richness was estimated using coverage‐based rarefaction. We also tested whether species packing (i.e., transect‐level species richness/m 2 ) is correlated with province‐level richness. Results Body size had the strongest effect on species richness across all three spatial scales. Reef area and temperature were both positively correlated with richness at all spatial scales. At the site scale only, richness decreased with reef isolation. Species richness was not correlated with proxies of human impacts. Species packing was correlated with species richness at the province level following a sub‐linear power function. Province‐level differences in species richness were also mirrored by patterns of body size distribution at the site scale. Species‐rich provinces exhibited heterogeneous assemblages of small‐bodied species with small range sizes, whereas species‐poor provinces encompassed homogeneous assemblages composed by larger species with greater dispersal capacity. Main conclusions Our findings suggest that body size distribution, reef area and temperature are major predictors of species richness and accumulation across scales, consistent with recent theories linking home range to species–area relationships as well as metabolic effects on speciation rates. Based on our results, we hypothesize that in less diverse areas, species are larger and likely more dispersive, leading to larger range sizes and less turnover between sites. Our results indicate that changes in province‐level (i.e., regional) richness should leave a tractable fingerprint in local assemblages, and that detailed studies on local‐scale assemblage composition may be informative of responses occurring at larger scales.

Adaptive management and planning for the conservation of four threatened large Asian mammals in a changing climate - Jiban Chandra Deb; Stuart Phinn; Nathalie Butt; Clive A. McAlpine (Mitigation and Adaptation Strategies for Global Change, 2019)

Developing a 3D intestinal epithelium model for livestock species - Hayley Derricott; Lisa Luu; Wai Yee Fong; Catherine S. Hartley; Luke J. Johnston; Stuart D. Armstrong; Nadine Randle; Carrie A. Duckworth; Barry J. Campbell; Jonathan M. Wastling; Janine L. Coombes (Cell and Tissue Research, 2019)

Prey nutrient content creates omnivores out of predators - Todd A. Ugine; Stuart B. Krasnoff; Robert J. Grebenok; Spencer T. Behmer; John E. Losey (Ecology Letters, 2019)
The proximate forces that create omnivores out of herbivores and predators have long fascinated ecologists, but the causal reasons for a shift to omnivory are poorly understood. Determining what factors influence changes in trophic position are essential as omnivory plays a central role in theoretical and applied ecology. We used sevenspotted lady beetles ( Coccinella septempunctata ) to test how prey nutrient content affects beetles’ propensity to engage in herbivory. We show that beetles consuming an all‐prey diet demonstrate normal growth and development, but suffer a complete loss of fitness (spermatogenic failure) that is restored via herbivory and supplementation with phytosterols and cholesterol. Furthermore, we show that lady beetles possess a state‐dependent sterol‐specific appetite and redressed their sterol deficit by feeding on foliage. These results demonstrate that predators balance their nutrient intake via herbivory when prey quality is low, and reveal a selective force (sterol nutrition) that drives predatory taxa to omnivory.

The structure and context of male and female song in White-throated Dippers - Lucy Magoolagan; Peter J. Mawby; Flora A. Whitehead; Stuart P. Sharp (Journal of Ornithology, 2019)

Using meta‐omics of contaminated sediments to monitor changes in pathways relevant to climate regulation - Simone C. Birrer; Katherine A. Dafforn; Melanie Y. Sun; Rohan B. H. Williams; Jaimie Potts; Peter Scanes; Brendan P. Kelaher; Stuart L. Simpson; Staffan Kjelleberg; Sanjay Swarup; Peter Steinberg; Emma L. Johnston (Environmental Microbiology, 2019)
Summary Microbially mediated biogeochemical processes are crucial for climate regulation and may be disrupted by anthropogenic contaminants. To better manage contaminants, we need tools that make real‐time causal links between stressors and altered microbial functions, and the potential consequences for ecosystem services such as climate regulation. In a manipulative field experiment, we used metatranscriptomics to investigate the impact of excess organic enrichment and metal contamination on the gene expression of nitrogen and sulfur metabolisms in coastal sediments. Our gene expression data suggest that excess organic enrichment results in (i) higher transcript levels of genes involved in the production of toxic ammonia and hydrogen sulfide and (ii) lower transcript levels associated with the degradation of a greenhouse gas (nitrous oxide). However, metal contamination did not have any significant impact on gene expression. We reveal the genetic mechanisms that may lead to altered productivity and greenhouse gas production in coastal sediments due to anthropogenic contaminants. Our data highlight the applicability of metatranscriptomics as a management tool that provides an immense breadth of information and can identify potentially impacted process measurements that need further investigation.

Resistance training in young men induces muscle transcriptome-wide changes associated with muscle structure and metabolism refining the response to exercise-induced stress - Felipe Damas; Carlos Ugrinowitsch; Cleiton A. Libardi; Paulo R. Jannig; Amy J. Hector; Chris McGlory; Manoel E. Lixandrão; Felipe C. Vechin; Horacio Montenegro; Valmor Tricoli; Hamilton Roschel; Stuart M. Phillips (European Journal of Applied Physiology, 2018)

Effects of hybridization on sea turtle fitness - Luciano S. Soares; Karen A. Bjorndal; Alan B. Bolten; Maria A. G. dei Marcovaldi; Pedro B. Luz; Rodrigo Machado; Rachel Lo; Stuart F. McDaniel; Adam C. Payton; Thomas B. Waltzek; Marta L. Wayne (Conservation Genetics, 2018)

Effects of Pollution From Anthropogenic Point Sources on the Recruitment of Sessile Estuarine Reef Biota - Amelia E. Fowles; Graham J. Edgar; Rick D. Stuart-Smith; James B. Kirkpatrick; Nicole Hill; Russell J. Thomson; Elisabeth M. A. Strain (Frontiers in Marine Science, 2018)

A Framework for Understanding Variation in Pelagic Gross Primary Production of Lake Ecosystems - Patrick T. Kelly; Christopher T. Solomon; Jacob A. Zwart; Stuart E. Jones (Ecosystems, 2018)

High‐turbidity events in Western Lake Erie during ice‐free cycles: Contributions of river‐loaded vs. resuspended sediments - Qianru Niu; Meng Xia; Stuart A. Ludsin; Philip Y. Chu; Doran M. Mason; Edward S. Rutherford (Limnology and Oceanography, 2018)
High‐turbidity events (HTEs) are common phenomena in shallow‐water environments that can alter ecological interactions. The relative contributions of river input (external loading) vs. resuspension (internal loading) to the occurrence, duration, and influenced areas of HTEs are not fully understood in most systems, owing to the lack of long‐term, source‐specified sediment maps. Using a Finite Volume Community Ocean Model‐based wave‐current forced sediment model, we investigated sediment dynamics in the shallow, river‐dominated Western Lake Erie during ice‐free cycles (April–November) of 2002–2012. Results indicated that wind waves predominated sediment dynamics in the offshore areas, with river discharges causing substantial inshore to offshore gradients. Owing to varying wind waves and river discharges, both the mean and extreme sediment dynamics had distinctive seasonal variations. The basin was turbid during spring and fall, with frequent (> 15%), broad (O [10 2 –10 3 km 2 ]), and more persistent (means of 3.2/4.4 d during spring/fall) HTEs caused mainly by resuspension events. During summer, the basin was clearer with occasional ( 2 km 2 ]), and short (mean of 1.5 d) HTEs near the mouths generated by pulsing river loadings. Although river loading rarely induced basin‐wide HTEs, they were important during floods, enlarging the high‐turbidity areas by 11.3%. Overall, by delineating the drivers of HTEs in Western Lake Erie, this study furthered the understanding of sediment dynamics in shallow ecosystems and provides a basis for investigating the ecological impact of sediments from different sources in river‐ and wave‐energetic systems.

Lipomyces starkeyi: an emerging cell factory for production of lipids, oleochemicals and biotechnology applications - Bonnie A. McNeil; David T. Stuart (World Journal of Microbiology and Biotechnology, 2018)

Mapping of novel salt tolerance QTL in an Excalibur × Kukri doubled haploid wheat population - Muhammad A. Asif; Rhiannon K. Schilling; Joanne Tilbrook; Chris Brien; Kate Dowling; Huwaida Rabie; Laura Short; Christine Trittermann; Alexandre Garcia; Edward G. Barrett-Lennard; Bettina Berger; Diane E. Mather; et al. (Theoretical and Applied Genetics, 2018)
Key message Novel QTL for salinity tolerance traits have been detected using non-destructive and destructive phenotyping in bread wheat and were shown to be linked to improvements in yield in saline fields. Abstract Soil salinity is a major limitation to cereal production. Breeding new salt-tolerant cultivars has the potential to improve cereal crop yields. In this study, a doubled haploid bread wheat mapping population, derived from the bi-parental cross of Excalibur × Kukri, was grown in a glasshouse under control and salinity treatments and evaluated using high-throughput non-destructive imaging technology. Quantitative trait locus (QTL) analysis of this population detected multiple QTL under salt and control treatments. Of these, six QTL were detected in the salt treatment including one for maintenance of shoot growth under salinity ( QG (1 – 5) .asl - 7A ), one for leaf Na + exclusion ( QNa.asl - 7A ) and four for leaf K + accumulation ( QK.asl - 2B.1 , QK.asl - 2B.2 , QK.asl - 5A and QK:Na.asl - 6A ). The beneficial allele for QG (1 – 5) .asl - 7A (the maintenance of shoot growth under salinity) was present in six out of 44 mainly Australian bread and durum wheat cultivars. The effect of each QTL allele on grain yield was tested in a range of salinity concentrations at three field sites across 2 years. In six out of nine field trials with different levels of salinity stress, lines with alleles for Na + exclusion and/or K + maintenance at three QTL ( QNa.asl - 7A , QK.asl - 2B.2 and QK:Na.asl - 6A ) excluded more Na + or accumulated more K + compared to lines without these alleles. Importantly, the QK.asl - 2B.2 allele for higher K + accumulation was found to be associated with higher grain yield at all field sites. Several alleles at other QTL were associated with higher grain yields at selected field sites.

Differential Morphological and Biochemical Recovery from Chemotherapy-Induced Peripheral Neuropathy Following Paclitaxel, Ixabepilone, or Eribulin Treatment in Mouse Sciatic Nerves - B. M. Cook; K. M. Wozniak; D. A. Proctor; R. B. Bromberg; Y. Wu; B. S. Slusher; B. A. Littlefield; M. A. Jordan; L. Wilson; Stuart C. Feinstein (Neurotoxicity Research, 2018)

Presence of a generalist entomopathogenic fungus influences the oviposition behaviour of an aphid-specific predator - A. G. C. de Azevedo; R. M. Stuart; L. Sigsgaard (BioControl, 2018)

3D human liver tissue from pluripotent stem cells displays stable phenotype in vitro and supports compromised liver function in vivo - Hassan Rashidi; Nguyet-Thin Luu; Salamah M. Alwahsh; Maaria Ginai; Sharmin Alhaque; Hua Dong; Rute A. Tomaz; Bertrand Vernay; Vasanthy Vigneswara; John M. Hallett; Anil Chandrashekran; Anil Dhawan; et al. (Archives of Toxicology, 2018)

Quantifying species recovery and conservation success to develop an IUCN Green List of Species - H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Molly K. Grace; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; David A. Keith; Barney Long; David P. Mallon; Erik Meijaard; et al. (Conservation Biology, 2018)
Stopping declines in biodiversity is critically important, but it is only a first step toward achieving more ambitious conservation goals. The absence of an objective and practical definition of species recovery that is applicable across taxonomic groups leads to inconsistent targets in recovery plans and frustrates reporting and maximization of conservation impact. We devised a framework for comprehensively assessing species recovery and conservation success. We propose a definition of a fully recovered species that emphasizes viability, ecological functionality, and representation; and use counterfactual approaches to quantify degree of recovery. This allowed us to calculate a set of 4 conservation metrics that demonstrate impacts of conservation efforts to date (conservation legacy); identify dependence of a species on conservation actions (conservation dependence); quantify expected gains resulting from conservation action in the medium term (conservation gain); and specify requirements to achieve maximum plausible recovery over the long term (recovery potential). These metrics can incentivize the establishment and achievement of ambitious conservation targets. We illustrate their use by applying the framework to a vertebrate, an invertebrate, and a woody and an herbaceous plant. Our approach is a preliminary framework for an International Union for Conservation of Nature (IUCN) Green List of Species, which was mandated by a resolution of IUCN members in 2012. Although there are several challenges in applying our proposed framework to a wide range of species, we believe its further development, implementation, and integration with the IUCN Red List of Threatened Species will help catalyze a positive and ambitious vision for conservation that will drive sustained conservation action.

Unmanned Aerial Systems (UAS) for environmental applications special issue preface - Anita Simic Milas; Joaquim João Sousa; Timothy A. Warner; Ana Cláudia Teodoro; Emanuel Peres; José Alberto Gonçalves; Jorge Delgado Garcia; Ricardo Bento; Stuart Phinn; Amy Woodget (International Journal of Remote Sensing, 2018)

Effects of long-term dietary administration of estrogen receptor-beta agonist diarylpropionitrile on ovariectomized female ICR (CD-1) mice - Sherry A. Said; Rachel Isedowo; Christilynn Guerin; Navreek N. Nar; Leesa Lillie; Shawn Bukovac; Jonathan J. Simone; Matthew R. Green; Cheryl M. McCormick; Jeffrey A. Stuart (GeroScience, 2018)

Taxonomy of the family Arenaviridae and the order Bunyavirales: update 2018 - Piet Maes; Sergey V. Alkhovsky; Yīmíng Bào; Martin Beer; Monica Birkhead; Thomas Briese; Michael J. Buchmeier; Charles H. Calisher; Rémi N. Charrel; Il Ryong Choi; Christopher S. Clegg; Juan Carlos de la Torre; et al. (Archives of Virology, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Human impacts decouple a fundamental ecological relationship—The positive association between host diversity and parasite diversity - Chelsea L. Wood; Brian J. Zgliczynski; Alison J. Haupt; Ana Sofía Guerra; Fiorenza Micheli; Stuart A. Sandin (Global Change Biology, 2018)
Human impacts on ecosystems can decouple the fundamental ecological relationships that create patterns of diversity in free‐living species. Despite the abundance, ubiquity, and ecological importance of parasites, it is unknown whether the same decoupling effects occur for parasitic species. We investigated the influence of fishing on the relationship between host diversity and parasite diversity for parasites of coral reef fishes on three fished and three unfished islands in the central equatorial Pacific. Fishing was associated with a shallowing of the positive host‐diversity–parasite‐diversity relationship. This occurred primarily through negative impacts of fishing on the presence of complex life‐cycle parasites, which created a biologically impoverished parasite fauna of directly transmitted parasites resilient to changes in host biodiversity. Parasite diversity appears to be decoupled from host diversity by fishing impacts in this coral reef ecosystem, which suggests that such decoupling might also occur for parasites in other ecosystems affected by environmental change.

The high-output singing displays of a lekking bat encode information on body size and individual identity - Cory A. Toth; Stuart Parsons (Behavioral Ecology and Sociobiology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Safety, tolerability and pharmacokinetics of GSK3008348, a novel integrin αvβ6 inhibitor, in healthy participants - Charlotte H. Maden; David Fairman; Michelle Chalker; Maria J. Costa; William A. Fahy; Nadia Garman; Pauline T. Lukey; Tim Mant; Simon Parry; Juliet K. Simpson; Robert J. Slack; Stuart Kendrick; et al. (European Journal of Clinical Pharmacology, 2018)

Performance of an elite, hybrid family of a northern × southern highbush cross (‘Draper’ × ‘Jewel’) - James F. Hancock; James W. Olmstead; Rachel A. Itle; Peter W. Callow; Stuart Neils-Kraft; Edmund J. Wheeler; Jozer Mangandi; Suneth S. Sooriyapathirana; Lisa J. Rowland; Ted A. Mackey; Nahla V. Bassil; Chad E. Finn (Euphytica, 2018)

A cross‐continental comparison of assemblages of seed‐ and fruit‐feeding insects in tropical rain forests: Faunal composition and rates of attack - Yves Basset; Chris Dahl; Richard Ctvrtecka; Sofia Gripenberg; Owen T. Lewis; Simon T. Segar; Petr Klimes; Héctor Barrios; John W. Brown; Sarayudh Bunyavejchewin; Buntika A. Butcher; Anthony I. Cognato; et al. (Journal of Biogeography, 2018)
Aim Insects feeding on seeds and fruits represent interesting study systems, potentially able to lower the fitness of their host plants. In addition to true seed eaters, a suite of insects feed on the fleshy parts of fruits. We examined the likelihood of community convergence in whole insect assemblages attacking seeds/fruits in three tropical rain forests. Location Three Forest GEO permanent forest plots within different biogeographical regions: Barro Colorado Island (Panama), Khao Chong (Thailand) and Wanang (Papua New Guinea). Methods We surveyed 1,186 plant species and reared 1.1 ton of seeds/fruits that yielded 80,600 insects representing at least 1,678 species. We assigned seeds/fruits to predation syndromes on the basis of plant traits relevant to insects, seed/fruit appearance and mesocarp thickness. Results We observed large differences in insect faunal composition, species richness and guild structure between our three study sites. We hypothesize that the high species richness of insect feeding on seeds/fruits in Panama may result from a conjunction of low plant species richness and high availability of dry fruits. Insect assemblages were weakly influenced by seed predation syndromes, both at the local and regional scale, and the effect of host phylogeny varied also among sites. At the driest site (Panama), the probability of seeds of a plant species being attacked depended more on seed availability than on the measured seed traits of that plant species. However, when seeds were attacked, plant traits shaping insect assemblages were difficult to identify and not related to seed availability. Main conclusions We observed only weak evidence of community convergence at the intercontinental scale among these assemblages. Our study suggests that seed eaters may be most commonly associated with dry fruits at relatively dry tropical sites where fleshy fruits may be less prevalent.

Ammonia‐oxidizing bacteria are the primary N 2 O producers in an ammonia‐oxidizing archaea dominated alkaline agricultural soil - Kelley A. Meinhardt; Nejc Stopnisek; Manmeet W. Pannu; Stuart E. Strand; Steven C. Fransen; Karen L. Casciotti; David A. Stahl (Environmental Microbiology, 2018)
Summary Most agricultural N 2 O emissions are a consequence of microbial transformations of nitrogen (N) fertilizer, and mitigating increases in N 2 O emission will depend on identifying microbial sources and variables influencing their activities. Here, using controlled microcosm and field studies, we found that synthetic N addition in any tested amount stimulated the production of N 2 O from ammonia‐oxidizing bacteria (AOB), but not archaea (AOA), from a bioenergy crop soil. The activities of these two populations were differentiated by N treatments, with abundance and activity of AOB increasing as nitrate and N 2 O production increased. Moreover, as N 2 O production increased, the isotopic composition of N 2 O was consistent with an AOB source. Relative N 2 O contributions by both populations were quantified using selective inhibitors and varying N availability. Complementary field analyses confirmed a positive correlation between N 2 O flux and AOB abundance with N application. Collectively, our data indicate that AOB are the major N 2 O producers, even with low N addition, and that better‐metered N application, complemented by selective inhibitors, could reduce projected N 2 O emissions from agricultural soils.

Air pollutant strategies to reduce adverse health impacts and health inequalities: a quantitative assessment for Detroit, Michigan - Sheena E. Martenies; Chad W. Milando; Stuart A. Batterman (Air Quality, Atmosphere & Health, 2018)

Impact of multiple stressors on juvenile fish in estuaries of the northeast Pacific - Jason D. Toft; Stuart H. Munsch; Jeffery R. Cordell; Kiira Siitari; Van C. Hare; Brett M. Holycross; Lisa A. DeBruyckere; Correigh M. Greene; Brent B. Hughes (Global Change Biology, 2018)
A key step in identifying global change impacts on species and ecosystems is to quantify effects of multiple stressors. To date, the science of global change has been dominated by regional field studies, experimental manipulation, meta‐analyses, conceptual models, reviews, and studies focusing on a single stressor or species over broad spatial and temporal scales. Here, we provide one of the first studies for coastal systems examining multiple stressor effects across broad scales, focused on the nursery function of 20 estuaries spanning 1,600 km of coastline, 25 years of monitoring, and seven fish and invertebrate species along the northeast Pacific coast. We hypothesized those species most estuarine dependent and negatively impacted by human activities would have lower presence and abundances in estuaries with greater anthropogenic land cover, pollution, and water flow stress. We found significant negative relationships between juveniles of two of seven species (Chinook salmon and English sole) and estuarine stressors. Chinook salmon were less likely to occur and were less abundant in estuaries with greater pollution stress. They were also less abundant in estuaries with greater flow stress, although this relationship was marginally insignificant. English sole were less abundant in estuaries with greater land cover stress. Together, we provide new empirical evidence that effects of stressors on two fish species culminate in detectable trends along the northeast Pacific coast, elevating the need for protection from pollution, land cover, and flow stressors to their habitats. Lack of response among the other five species could be related to differing resistance to specific stressors, type and precision of the stressor metrics, and limitations in catch data across estuaries and habitats. Acquiring improved measurements of impacts to species will guide future management actions, and help predict how estuarine nursery functions can be optimized given anthropogenic stressors and climate change scenarios.

Biophysical drivers of coral trophic depth zonation - Gareth J. Williams; Stuart A. Sandin; Brian J. Zgliczynski; Michael D. Fox; Jamison M. Gove; Justin S. Rogers; Kathryn A. Furby; Aaron C. Hartmann; Zachary R. Caldwell; Nichole N. Price; Jennifer E. Smith (Marine Biology, 2018)

Lower body blood flow restriction training may induce remote muscle strength adaptations in an active unrestricted arm - Anthony K. May; Aaron P. Russell; Stuart A. Warmington (European Journal of Applied Physiology, 2018)

Feasibility of analyzing DNA copy number variation in breast cancer tumor specimens from 1950 to 2010: how old is too old? - Nancy Krieger; Sheida Nabavi; Pamela D. Waterman; Ninah S. Achacoso; Luana Acton; Stuart J. Schnitt; Laurel A. Habel (Cancer Causes & Control, 2018)

Vegetation productivity responses to drought on tribal lands in the four corners region of the Southwest USA - Mohamed Abd Salam El-Vilaly; Kamel Didan; Stuart E. Marsh; Willem J. D. van Leeuwen; Michael A. Crimmins; Armando Barreto Munoz (Frontiers of Earth Science, 2018)

Effects of water level fluctuations on nitrogen dynamics in littoral macrophytes - Jing Lu; Stuart E. Bunn; Michele A. Burford (Limnology and Oceanography, 2018)
Sustained water level drawdown followed by rewetting has the potential to shift macrophytes from a nutrient sink to a source, but the fate of macrophyte‐derived nutrients after rewetting is not well understood. We investigated the fate of released nitrogen (N) from isotopically labeled macrophyte litter over a 4‐week period after rewetting. We used three treatments: (1) different species in the litter (invasive Cabomba caroliniana vs. native Hydrilla verticillata ); (2) sediment desiccation history (“dried then rewetted” vs. “constantly wet”); (3) living macrophytes (presence vs. absence). Our results showed that the Cabomba litter treatment had a significantly higher percentage of macrophyte‐derived 15 N in the dissolved fraction of the water column and assimilated by phytoplankton (higher chlorophyll a concentrations), compared to the Hydrilla litter. The treatments with sediment desiccation also had a significantly higher percentage of 15 N in the dissolved fraction and used by phytoplankton after rewetting, but less in the sediment, compared to the constantly wet treatment. The presence of living macrophytes partially reduced the 15 N increase in the water column and/or sediment, but the scale of the effect was species‐ and biomass‐dependent. Our study showed that sediment pre‐desiccation changed the fate of macrophyte‐derived 15 N after rewetting, increasing the impact on water quality. This was further exacerbated by the presence of litter from an invasive species. This study highlights the need to manage water levels to maintain healthy macrophyte beds and thereby addressing water quality issues in lakes and reservoirs.

Why decadal to century timescale palaeoclimate data are needed to explain present‐day patterns of biological diversity and change - Damien A. Fordham; Frédérik Saltré; Stuart C. Brown; Camille Mellin; Tom M. L. Wigley (Global Change Biology, 2018)
The current distribution of species, environmental conditions and their interactions represent only one snapshot of a planet that is continuously changing, in part due to human influences. To distinguish human impacts from natural factors, the magnitude and pace of climate shifts, since the Last Glacial Maximum, are often used to determine whether patterns of diversity today are artefacts of past climate change. In the absence of high‐temporal resolution palaeoclimate reconstructions, this is generally done by assuming that past climate change occurred at a linear pace between widely spaced (usually, ≥1,000 years) climate snapshots. We show here that this is a flawed assumption because regional climates have changed significantly across decades and centuries during glacial–interglacial cycles, likely causing rapid regional replacement of biota. We demonstrate how recent atmosphere‐ocean general circulation model ( AOGCM ) simulations of the climate of the past 21,000 years can provide credible estimates of the details of climate change on decadal to centennial timescales, showing that these details differ radically from what might be inferred from longer timescale information. High‐temporal resolution information can provide more meaningful estimates of the magnitude and pace of climate shifts, the location and timing of drivers of physiological stress, and the extent of novel climates. They also produce new opportunities to directly investigate whether short‐term climate variability is more important in shaping biodiversity patterns rather than gradual changes in long‐term climatic means. Together, these more accurate measures of past climate instability are likely to bring about a better understanding of the role of palaeoclimatic change and variability in shaping current macroecological patterns in many regions of the world.

Soil carbon cycling proxies: Understanding their critical role in predicting climate change feedbacks - Vanessa L. Bailey; Ben Bond‐Lamberty; Kristen DeAngelis; A. Stuart Grandy; Christine V. Hawkes; Kate Heckman; Kate Lajtha; Richard P. Phillips; Benjamin N. Sulman; Katherine E. O. Todd‐Brown; Matthew D. Wallenstein (Global Change Biology, 2018)
The complexity of processes and interactions that drive soil C dynamics necessitate the use of proxy variables to represent soil characteristics that cannot be directly measured (correlative proxies), or that aggregate information about multiple soil characteristics into one variable (integrative proxies). These proxies have proven useful for understanding the soil C cycle, which is highly variable in both space and time, and are now being used to make predictions of the fate and persistence of C under future climate scenarios. However, the C pools and processes that proxies represent must be thoughtfully considered in order to minimize uncertainties in empirical understanding. This is necessary to capture the full value of a proxy in model parameters and in model outcomes. Here, we provide specific examples of proxy variables that could improve decision‐making, and modeling skill, while also encouraging continued work on their mechanistic underpinnings. We explore the use of three common soil proxies used to study soil C cycling: metabolic quotient, clay content, and physical fractionation. We also consider how emerging data types, such as genome‐sequence data, can serve as proxies for microbial community activities. By examining some broad assumptions in soil C cycling with the proxies already in use, we can develop new hypotheses and specify criteria for new and needed proxies.

How complex should models be? Comparing correlative and mechanistic range dynamics models - Damien A. Fordham; Cleo Bertelsmeier; Barry W. Brook; Regan Early; Dora Neto; Stuart C. Brown; Sébastien Ollier; Miguel B. Araújo (Global Change Biology, 2018)
Criticism has been levelled at climate‐change‐induced forecasts of species range shifts that do not account explicitly for complex population dynamics. The relative importance of such dynamics under climate change is, however, undetermined because direct tests comparing the performance of demographic models vs. simpler ecological niche models are still lacking owing to difficulties in evaluating forecasts using real‐world data. We provide the first comparison of the skill of coupled ecological‐niche‐population models and ecological niche models in predicting documented shifts in the ranges of 20 British breeding bird species across a 40‐year period. Forecasts from models calibrated with data centred on 1970 were evaluated using data centred on 2010. We found that more complex coupled ecological‐niche‐population models (that account for dispersal and metapopulation dynamics) tend to have higher predictive accuracy in forecasting species range shifts than structurally simpler models that only account for variation in climate. However, these better forecasts are achieved only if ecological responses to climate change are simulated without static snapshots of historic land use, taken at a single point in time. In contrast, including both static land use and dynamic climate variables in simpler ecological niche models improve forecasts of observed range shifts. Despite being less skilful at predicting range changes at the grid‐cell level, ecological niche models do as well, or better, than more complex models at predicting the magnitude of relative change in range size. Therefore, ecological niche models can provide a reasonable first approximation of the magnitude of species' potential range shifts, especially when more detailed data are lacking on dispersal dynamics, demographic processes underpinning population performance, and change in land cover.

On the prevalence and dynamics of inverted trophic pyramids and otherwise top‐heavy communities - Douglas J. McCauley; Gabriel Gellner; Neo D. Martinez; Richard J. Williams; Stuart A. Sandin; Fiorenza Micheli; Peter J. Mumby; Kevin S. McCann (Ecology Letters, 2018)
Classically, biomass partitioning across trophic levels was thought to add up to a pyramidal distribution. Numerous exceptions have, however, been noted including complete pyramidal inversions. Elevated levels of biomass top‐heaviness (i.e. high consumer/resource biomass ratios) have been reported from Arctic tundra communities to Brazilian phytotelmata, and in species assemblages as diverse as those dominated by sharks and ants. We highlight two major pathways for creating top‐heaviness, via: (1) endogenous channels that enhance energy transfer across trophic boundaries within a community and (2) exogenous pathways that transfer energy into communities from across spatial and temporal boundaries. Consumer–resource models and allometric trophic network models combined with niche models reveal the nature of core mechanisms for promoting top‐heaviness. Outputs from these models suggest that top‐heavy communities can be stable, but they also reveal sources of instability. Humans are both increasing and decreasing top‐heaviness in nature with ecological consequences. Current and future research on the drivers of top‐heaviness can help elucidate fundamental mechanisms that shape the architecture of ecological communities and govern energy flux within and between communities. Questions emerging from the study of top‐heaviness also usefully draw attention to the incompleteness and inconsistency by which ecologists often establish definitional boundaries for communities.

Scientific Considerations for the Assessment and Management of Mine Tailings Disposal in the Deep Sea - Lindsay L. Vare; Maria C. Baker; John A. Howe; Lisa A. Levin; Carlos Neira; Eva Z. Ramirez-Llodra; Amanda Reichelt-Brushett; Ashley A. Rowden; Tracy M. Shimmield; Stuart L. Simpson; Eulogio H. Soto (Frontiers in Marine Science, 2018)

Do you see what I see? Mobile eye-tracker contextual analysis and inter-rater reliability - S. Stuart; D. Hunt; J. Nell; A. Godfrey; J. M. Hausdorff; L. Rochester; L. Alcock (Medical & Biological Engineering & Computing, 2018)

Visitor Preferences for Visual Changes in Bark Beetle-Impacted Forest Recreation Settings in the United States and Germany - Arne Arnberger; Martin Ebenberger; Ingrid E. Schneider; Stuart Cottrell; Alexander C. Schlueter; Eick von Ruschkowski; Robert C. Venette; Stephanie A. Snyder; Paul H. Gobster (Environmental Management, 2018)

Re-evaluating conservation priorities of New World tarantulas (Araneae: Theraphosidae) in a molecular framework indicates non-monophyly of the genera, Aphonopelma and Brachypelma - Steven P. Turner; Stuart J. Longhorn; Chris A. Hamilton; Ray Gabriel; Fernando PÉrez-Miles; Alfried P. Vogler (Systematics and Biodiversity, 2018)

Brain cortical characteristics of lifetime cognitive ageing - Simon R. Cox; Mark E. Bastin; Stuart J. Ritchie; David Alexander Dickie; Dave C. Liewald; Susana Muñoz Maniega; Paul Redmond; Natalie A. Royle; Alison Pattie; Maria Valdés Hernández; Janie Corley; Benjamin S. Aribisala; et al. (Brain Structure and Function, 2018)

Geographically distributed hybrid testing & collaboration between geotechnical centrifuge and structures laboratories - Mobin Ojaghi; Ignacio Lamata Martínez; Matt S. Dietz; Martin S. Williams; Anthony Blakeborough; Adam J. Crewe; Colin A. Taylor; S. P. Gopal Madabhushi; Stuart K. Haigh (Earthquake Engineering and Engineering Vibration, 2018)

Author Correction to: Size-mediated control of perch–midge coupling in Lake Erie transient dead zones - Daisuke Goto; James J. Roberts; Steven A. Pothoven; Stuart A. Ludsin; Henry A. Vanderploeg; Stephen B. Brandt; Tomas O. Höök (Environmental Biology of Fishes, 2017)

Size-mediated control of perch–midge coupling in Lake Erie transient dead zones - Daisuke Goto; James J. Roberts; Steven A. Pothoven; Stuart A. Ludsin; Henry A. Vanderploeg; Stephen B. Brandt; Tomas O. Höök (Environmental Biology of Fishes, 2017)

Large-area imaging reveals biologically driven non-random spatial patterns of corals at a remote reef - Clinton B. Edwards; Yoan Eynaud; Gareth J. Williams; Nicole E. Pedersen; Brian J. Zgliczynski; Arthur C. R. Gleason; Jennifer E. Smith; Stuart A. Sandin (Coral Reefs, 2017)

Risk and protective factors for structural brain ageing in the eighth decade of life - Stuart J. Ritchie; Elliot M. Tucker-Drob; Simon R. Cox; David Alexander Dickie; Maria del C. Valdés Hernández; Janie Corley; Natalie A. Royle; Paul Redmond; Susana Muñoz Maniega; Alison Pattie; Benjamin S. Aribisala; Adele M. Taylor; et al. (Brain Structure and Function, 2017)

Landscape patterns shape wetland pond ecosystem function from glacial headwaters to ocean - Carmella Vizza; Jacob A. Zwart; Stuart E. Jones; Scott D. Tiegs; Gary A. Lamberti (Limnology and Oceanography, 2017)
Examining patterns and processes along the aquatic continuum from headwaters to ocean can benefit from a landscape ecology approach, where hydrologic and ecological processes depend on landscape position. We conducted a study of freshwater wetland ponds subject to similar climatic conditions but distributed along a 20‐km trajectory from glacial headwaters to ocean in southcentral Alaska, U.S.A. Specifically, we investigated how proximity to glaciers and ocean influenced physical, chemical, and biological characteristics of ponds. Physicochemical patterns along a distance gradient from the ocean supported the hypothesized influence of elevation and potential atmospheric deposition of marine‐derived nitrogen, whereas those related to glacial flow path length may reflect inputs from glacial weathering. We expected that the effects of landscape and hydrology on physicochemical patterns would provide a template for shaping ecosystem processes, but ecosystem processes also appeared to contribute to physicochemical patterns across this landscape. Ponds more heavily influenced by glaciers tended to be more heterotrophic exhibiting greater rates of organic‐matter decomposition and ecosystem respiration, which were positively correlated with phosphorus and iron concentrations likely due to glacial weathering and remineralization processes. In contrast, ponds near the ocean tended to be more autotrophic exhibiting greater gross primary production and net ecosystem production, processes that may have contributed to greater total nitrogen, nitrogen to phosphorus ratios, and dissolved organic carbon concentrations. Consideration of the relative importance of hydrologic inputs across the landscape is needed because the acceleration of glacial melt and sea‐level rise by climate change may alter future broad‐scale patterns of ecosystem processes.

Porites coral response to an oceanographic and human impact gradient in the Line Islands - Jessica E. Carilli; Aaron C. Hartmann; Scott F. Heron; John M. Pandolfi; Kim Cobb; Hussein Sayani; Robert Dunbar; Stuart A. Sandin (Limnology and Oceanography, 2017)
Coral bleaching caused by heat stress (warm water) will arguably be the greatest driver of coral reef loss in the coming decades. Understanding how corals have adapted to distinct oceanographic regimes on multiple scales can provide insight into future tolerance and persistence, information critical to directed intervention or targeted protections. The northern Line Islands span a gradient in oceanographic regimes across latitudes, with seawater becoming warmer, fresher, more oligotrophic, and more saturated with aragonite away from the equator. The combination of this regional gradient and island‐scale (local) conditions was used as a natural experiment against which to test how massive Porites corals respond to these background conditions and episodic heat stress. We found that coral condition, represented by a metric combining tissue thickness, lipids, and calcification, was similar at almost all islands, though there were differences in how corals allocate resources among these biological parameters. Corals at Teraina, the most densely inhabited island, showed evidence for reduced calcification, potentially associated with human impacts and/or outflow of freshwater from the island. In contrast, Porites corals at Palmyra, a wildlife reserve, exhibited unexpectedly high tissue‐condition metrics for its latitude, suggesting an additional food source, possibly plankton‐rich lagoonal outflow. We did not find a strong relationship between human habitation and the response of Porites corals to recent heat stress. However, differences in coral calcification rates and energy stores between observed values and those expected based solely on the regional oceanographic gradient, suggests local effects have indirect impacts on these corals.

Further validation of the affective bias test for predicting antidepressant and pro-depressant risk: effects of pharmacological and social manipulations in male and female rats - Justyna K. Hinchcliffe; Sarah A. Stuart; Michael Mendl; Emma S. J. Robinson (Psychopharmacology, 2017)

Sleeper cells: the stringent response and persistence in the Borreliella ( Borrelia ) burgdorferi enzootic cycle - Felipe C. Cabello; Henry P. Godfrey; Julia V. Bugrysheva; Stuart A. Newman (Environmental Microbiology, 2017)
Summary Infections with tick‐transmitted Borreliella ( Borrelia ) burgdorferi , the cause of Lyme disease, represent an increasingly large public health problem in North America and Europe. The ability of these spirochetes to maintain themselves for extended periods of time in their tick vectors and vertebrate reservoirs is crucial for continuance of the enzootic cycle as well as for the increasing exposure of humans to them. The stringent response mediated by the alarmone (p)ppGpp has been determined to be a master regulator in B . burgdorferi . It modulates the expression of identified and unidentified open reading frames needed to deal with and overcome the many nutritional stresses and other challenges faced by the spirochete in ticks and animal reservoirs. The metabolic and morphologic changes resulting from activation of the stringent response in B . burgdorferi may also be involved in the recently described non‐genetic phenotypic phenomenon of tolerance to otherwise lethal doses of antimicrobials and to other antimicrobial activities. It may thus constitute a linchpin in multiple aspects of infections with Lyme disease borrelia, providing a link between the micro‐ecological challenges of its enzootic life‐cycle and long‐term residence in the tissues of its animal reservoirs, with the evolutionary side effect of potential persistence in incidental human hosts.

A Synergistic Approach for Evaluating Climate Model Output for Ecological Applications - Rachel D. Cavanagh; Eugene J. Murphy; Thomas J. Bracegirdle; John Turner; Cheryl A. Knowland; Stuart P. Corney; Walker O. Smith; Claire M. Waluda; Nadine M. Johnston; Richard G. J. Bellerby; Andrew J. Constable; Daniel P. Costa; et al. (Frontiers in Marine Science, 2017)

Climatic-Induced Shifts in the Distribution of Teak (Tectona grandis) in Tropical Asia: Implications for Forest Management and Planning - Jiban Chandra Deb; Stuart Phinn; Nathalie Butt; Clive A. McAlpine (Environmental Management, 2017)

Variations of leaf longevity in tropical moist forests predicted by a trait‐driven carbon optimality model - Xiangtao Xu; David Medvigy; Stuart Joseph Wright; Kaoru Kitajima; Jin Wu; Loren P. Albert; Giordane A. Martins; Scott R. Saleska; Stephen W. Pacala (Ecology Letters, 2017)
Leaf longevity ( LL ) varies more than 20‐fold in tropical evergreen forests, but it remains unclear how to capture these variations using predictive models. Current theories of LL that are based on carbon optimisation principles are challenging to quantitatively assess because of uncertainty across species in the ‘ageing rate:’ the rate at which leaf photosynthetic capacity declines with age. Here, we present a meta‐analysis of 49 species across temperate and tropical biomes, demonstrating that the ageing rate of photosynthetic capacity is positively correlated with the mass‐based carboxylation rate of mature leaves. We assess an improved trait‐driven carbon optimality model with in situ LL data for 105 species in two Panamanian forests. We show that our model explains over 40% of the cross‐species variation in LL under contrasting light environment. Collectively, our results reveal how variation in LL emerges from carbon optimisation constrained by both leaf structural traits and abiotic environment.

A test of an antipredatory function of conspicuous plastron coloration in hatchling turtles - Beth A. Reinke; Ryan Calsbeek; Devi Stuart-Fox (Evolutionary Ecology, 2017)

The Influence of Hydrologic Residence Time on Lake Carbon Cycling Dynamics Following Extreme Precipitation Events - Jacob A. Zwart; Stephen D. Sebestyen; Christopher T. Solomon; Stuart E. Jones (Ecosystems, 2017)

Genomic analysis of chimeric human cytomegalovirus vaccine candidates derived from strains Towne and Toledo - Nicolás M. Suárez; Betty Lau; George M. Kemble; Ronzo Lee; Edward S. Mocarski; Gavin W. G. Wilkinson; Stuart P. Adler; Michael A. McVoy; Andrew J. Davison (Virus Genes, 2017)

The effect of varenicline and nicotine patch on smoking rate and satisfaction with smoking: an examination of the mechanism of action of two pre-quit pharmacotherapies - Wenying Lu; Kate Chappell; Julia A. E. Walters; Glenn A. Jacobson; Rahul Patel; Natalie Schüz; Stuart G. Ferguson (Psychopharmacology, 2017)

Microtubule-Targeting Agents Eribulin and Paclitaxel Differentially Affect Neuronal Cell Bodies in Chemotherapy-Induced Peripheral Neuropathy - Sarah J. Benbow; Krystyna M. Wozniak; Bridget Kulesh; April Savage; Barbara S. Slusher; Bruce A. Littlefield; Mary Ann Jordan; Leslie Wilson; Stuart C. Feinstein (Neurotoxicity Research, 2017)

Diel periodicity and chronology of upstream migration in yellow-phase American eels (Anguilla rostrata) - Joni L. Aldinger; Stuart A. Welsh (Environmental Biology of Fishes, 2017)

Expression and characterization of codon-optimized Crimean-Congo hemorrhagic fever virus Gn glycoprotein in insect cells - Mehdi Rahpeyma; Alireza Samarbaf-Zadeh; Manoochehr Makvandi; Ata A. Ghadiri; Stuart D. Dowall; Fatemeh Fotouhi (Archives of Virology, 2017)

Climate change as a long-term stressor for the fisheries of the Laurentian Great Lakes of North America - Paris D. Collingsworth; David B. Bunnell; Michael W. Murray; Yu-Chun Kao; Zachary S. Feiner; Randall M. Claramunt; Brent M. Lofgren; Tomas O. Höök; Stuart A. Ludsin (Reviews in Fish Biology and Fisheries, 2017)

The value of virtual conferencing for ecology and conservation - Hannah Fraser; Kylie Soanes; Stuart A. Jones; Chris S. Jones; Matthew Malishev (Conservation Biology, 2017)
The objectives of conservation science and dissemination of its research create a paradox: Conservation is about preserving the environment, yet scientists spread this message at conferences with heavy carbon footprints. Ecology and conservation science depend on global knowledge exchange—getting the best science to the places it is most needed. However, conference attendance from developed countries typically outweighs that from developing countries that are biodiversity and conservation hotspots. If any branch of science should be trying to maximize participation while minimizing carbon emissions, it is conservation. Virtual conferencing is common in other disciplines, such as education and humanities, but it is surprisingly underused in ecology and conservation. Adopting virtual conferencing entails a number of challenges, including logistics and unified acceptance, which we argue can be overcome through planning and technology. We examined 4 conference models: a pure‐virtual model and 3 hybrid hub‐and‐node models, where hubs stream content to local nodes. These models collectively aim to mitigate the logistical and administrative challenges of global knowledge transfer. Embracing virtual conferencing addresses 2 essential prerequisites of modern conferences: lowering carbon emissions and increasing accessibility for remote, time‐ and resource‐poor researchers, particularly those from developing countries.

Large-scale forcing of the European Slope Current and associated inflows to the North Sea - Robert Marsh; Ivan D. Haigh; Stuart A. Cunningham; Mark E. Inall; Marie Porter; Ben I. Moat (Ocean Science, 2017)
The European Slope Current provides a shelf-edge conduit for Atlantic Water, a substantial fraction of which is destined for the northern North Sea, with implications for regional hydrography and ecosystems. Drifters drogued at 50 m in the European Slope Current at the Hebridean shelf break follow a wide range of pathways, indicating highly variable Atlantic inflow to the North Sea. Slope Current pathways, timescales and transports over 1988–2007 are further quantified in an eddy-resolving ocean model hindcast. Particle trajectories calculated with model currents indicate that Slope Current water is largely recruited from the eastern subpolar North Atlantic. Observations of absolute dynamic topography and climatological density support theoretical expectations that Slope Current transport is to first order associated with meridional density gradients in the eastern subpolar gyre, which support a geostrophic inflow towards the slope. In the model hindcast, Slope Current transport variability is dominated by abrupt 25–50 % reductions of these density gradients over 1996–1998. Concurrent changes in wind forcing, expressed in terms of density gradients, act in the same sense to reduce Slope Current transport. This indicates that coordinated regional changes of buoyancy and wind forcing acted together to reduce Slope Current transport during the 1990s. Particle trajectories further show that 10–40 % of Slope Current water is destined for the northern North Sea within 6 months of passing to the west of Scotland, with a general decline in this percentage over 1988–2007. Salinities in the Slope Current correspondingly decreased, evidenced in ocean analysis data. Further to the north, in the Atlantic Water conveyed by the Slope Current through the Faroe–Shetland Channel (FSC), salinity is observed to increase over this period while declining in the hindcast. The observed trend may have broadly compensated for a decline in the Atlantic inflow, limiting salinity changes in the northern North Sea during this period. Proxies for both Slope Current transport and Atlantic inflow to the North Sea are sought in sea level height differences across the FSC and between Shetland and the Scottish mainland (Wick). Variability of Slope Current transport on a wide range of timescales, from seasonal to multi-decadal, is implicit in sea level differences between Lerwick (Shetland) and Tórshavn (Faroes), in both tide gauge records from 1957 and a longer model hindcast spanning 1958–2012. Wick–Lerwick sea level differences in tide gauge records from 1965 indicate considerable decadal variability in the Fair Isle Current transport that dominates Atlantic inflow to the northwest North Sea, while sea level differences in the hindcast are dominated by strong seasonal variability. Uncertainties in the Wick tide gauge record limit confidence in this proxy.

Comparison of measured multi-decadal rainfall variability with farmers’ perceptions of and responses to seasonal changes in western Uganda - Jeremy E. Diem; Joel Hartter; Jonathan Salerno; Elvira McIntyre; A. Stuart Grandy (Regional Environmental Change, 2017)

A field test of the effects of body composition analysis by quantitative magnetic resonance on songbird stopover behaviour - Lisa V. Kennedy; Yolanda E. Morbey; Stuart A. Mackenzie; Philip D. Taylor; Christopher G. Guglielmo (Journal of Ornithology, 2017)

High Resolution Ultrasound Superharmonic Perfusion Imaging: In Vivo Feasibility and Quantification of Dynamic Contrast-Enhanced Acoustic Angiography - Brooks D. Lindsey; Sarah E. Shelton; K. Heath Martin; Kathryn A. Ozgun; Juan D. Rojas; F. Stuart Foster; Paul A. Dayton (Annals of Biomedical Engineering, 2017)

A new species of critically endangered edible yam endemic to northern Madagascar, Dioscorea irodensis (Dioscoreaceae) and its conservation - Paul Wilkin; James A. Kennerley; Mamy Tiana Rajaonah; Geodain Meva Huckël; Feno Rakotoarison; Tianjanahary Randriamboavonjy; Stuart Cable (Kew Bulletin, 2017)

Bioethanol Production from Brewers Spent Grains Using a Fungal Consolidated Bioprocessing (CBP) Approach - Stuart Wilkinson; Katherine A. Smart; Sue James; David J. Cook (BioEnergy Research, 2017)

Nestedness and species replacement along bathymetric gradients in the deep sea reflect productivity: a test with polychaete assemblages in the oligotrophic north‐west Gulf of Mexico - Carol T. Stuart; Solange Brault; Gilbert T. Rowe; Chih‐Lin Wei; Martine Wagstaff; Craig R. McClain; Michael A. Rex (Journal of Biogeography, 2017)
Aim To test the hypothesis that low productivity drives the nestedness component of β‐diversity in polychaetes at the deep‐sea floor. Location Western Gulf of Mexico. Methods We used A. Baselga's (2010, Global Ecology and Biogeography, 19 , 134–143) metrics of species replacement and nestedness to assess their overall significance with differences in depth and particulate organic carbon ( POC ) flux to the seafloor. We used M. A. Rodríguez‐Gironés & L. Santamaría's (2006, Journal of Biogeography , 33 , 924–935) BINMATNEST to calculate the significance and direction of nestedness with depth and POC flux. Results Nestedness was the most significant part of β‐diversity with depth and POC flux. The rank order of nestedness increased significantly with increasing depth, and decreased significantly with increasing POC flux. There was little endemism below 2000 m. Main conclusion The polychaete fauna in the deepest western Gulf of Mexico is largely a nested subset of the shallower upper to mid‐bathyal fauna. While the causes of β‐diversity in the deep sea are undoubtedly multivariate, the relative importance of turnover and nestedness appears to be modulated by productivity in the form of POC flux to the seafloor. Under circumstances of extremely low POC flux and animal density in the deepest reaches of the Gulf, nestedness may be caused by some populations being maintained by immigration from larger populations upslope, or by biogeographic filtering for tolerance to abyssal conditions. Resources at great depths in regions of exceptionally low productivity may be too limited to permit adaptation resulting in endemism and continued downslope turnover. If productivity helps to explain the nestedness part of β‐diversity, this may lead to a more unified theory of deep‐sea biodiversity.

Applying population and community ecology theory to advance understanding of belowground biogeochemistry - Robert W. Buchkowski; Mark A. Bradford; Andrew Stuart Grandy; Oswald J. Schmitz; William R. Wieder (Ecology Letters, 2017)
Approaches to quantifying and predicting soil biogeochemical cycles mostly consider microbial biomass and community composition as products of the abiotic environment. Current numerical approaches then primarily emphasise the importance of microbe–environment interactions and physiology as controls on biogeochemical cycles. Decidedly less attention has been paid to understanding control exerted by community dynamics and biotic interactions. Yet a rich literature of theoretical and empirical contributions highlights the importance of considering how variation in microbial population ecology, especially biotic interactions, is related to variation in key biogeochemical processes like soil carbon formation. We demonstrate how a population and community ecology perspective can be used to (1) understand the impact of microbial communities on biogeochemical cycles and (2) reframe current theory and models to include more detailed microbial ecology. Through a series of simulations we illustrate how density dependence and key biotic interactions, such as competition and predation, can determine the degree to which microbes regulate soil biogeochemical cycles. The ecological perspective and model simulations we present lay the foundation for developing empirical research and complementary models that explore the diversity of ecological mechanisms that operate in microbial communities to regulate biogeochemical processes.

Nucleus incertus promotes cortical desynchronization and behavioral arousal - Sherie Ma; Giancarlo Allocca; Emma K. E. Ong-Pålsson; Caitlin E. Singleton; David Hawkes; Stuart J. McDougall; Spencer J. Williams; Ross A. D. Bathgate; Andrew L. Gundlach (Brain Structure and Function, 2017)

A global analysis of traits predicting species sensitivity to habitat fragmentation - Douglas A. Keinath; Daniel F. Doak; Karen E. Hodges; Laura R. Prugh; William Fagan; Cagan H. Sekercioglu; Stuart H. M. Buchart; Matthew Kauffman (Global Ecology and Biogeography, 2017)
Aim Elucidating patterns in species responses to habitat fragmentation is an important focus of ecology and conservation, but studies are often geographically restricted, taxonomically narrow or use indirect measures of species vulnerability. We investigated predictors of species presence after fragmentation using data from studies around the world that included all four terrestrial vertebrate classes, thus allowing direct inter‐taxonomic comparison. Location World‐wide. Methods We used generalized linear mixed‐effect models in an information theoretic framework to assess the factors that explained species presence in remnant habitat patches (3342 patches; 1559 species, mostly birds; and 65,695 records of patch‐specific presence–absence). We developed a novel metric of fragmentation sensitivity, defined as the maximum rate of change in probability of presence with changing patch size (‘Peak Change’), to distinguish between general rarity on the landscape and sensitivity to fragmentation per se. Results Size of remnant habitat patches was the most important driver of species presence. Across all classes, habitat specialists, carnivores and larger species had a lower probability of presence, and those effects were substantially modified by interactions. Sensitivity to fragmentation (measured by Peak Change) was influenced primarily by habitat type and specialization, but also by fecundity, life span and body mass. Reptiles were more sensitive than other classes. Grassland species had a lower probability of presence, though sample size was relatively small, but forest and shrubland species were more sensitive. Main conclusions Habitat relationships were more important than life‐history characteristics in predicting the effects of fragmentation. Habitat specialization increased sensitivity to fragmentation and interacted with class and habitat type; forest specialists and habitat‐specific reptiles were particularly sensitive to fragmentation. Our results suggest that when conservationists are faced with disturbances that could fragment habitat they should pay particular attention to specialists, particularly reptiles. Further, our results highlight that the probability of presence in fragmented landscapes and true sensitivity to fragmentation are predicted by different factors.

Determinants of bird conservation‐action implementation and associated population trends of threatened species - David A. Luther; Thomas M. Brooks; Stuart H.M. Butchart; Matt W. Hayward; Marieke E. Kester; John Lamoreux; Amy Upgren (Conservation Biology, 2016)
Conservation actions, such as habitat protection, attempt to halt the loss of threatened species and help their populations recover. The efficiency and the effectiveness of actions have been examined individually. However, conservation actions generally occur simultaneously, so the full suite of implemented conservation actions should be assessed. We used the conservation actions underway for all threatened and near‐threatened birds of the world (International Union for Conservation of Nature Red List of Threatened Species) to assess which biological (related to taxonomy and ecology) and anthropogenic (related to geoeconomics) factors were associated with the implementation of different classes of conservation actions. We also assessed which conservation actions were associated with population increases in the species targeted. Extinction‐risk category was the strongest single predictor of the type of conservation actions implemented, followed by landmass type (continent, oceanic island, etc.) and generation length. Species targeted by invasive nonnative species control or eradication programs, ex situ conservation, international legislation, reintroduction, or education, and awareness‐raising activities were more likely to have increasing populations. These results illustrate the importance of developing a predictive science of conservation actions and the relative benefits of each class of implemented conservation action for threatened and near‐threatened birds worldwide.

Effects of sertraline, duloxetine, vortioxetine, and idazoxan in the rat affective bias test - Louise K. Refsgaard; Kia Haubro; Darryl S. Pickering; Sarah A. Stuart; Emma S. J. Robinson; Jesper T. Andreasen (Psychopharmacology, 2016)

Can captive populations function as sources of genetic variation for reintroductions into the wild? A case study of the Arabian oryx from the Phoenix Zoo and the Shaumari Wildlife Reserve, Jordan - Alexander Ochoa; Stuart A. Wells; Gary West; Ma’en Al-Smadi; Sergio A. Redondo; Sydnee R. Sexton; Melanie Culver (Conservation Genetics, 2016)

Resource partitioning among air‐breathing marine predators: are body size and mouth diameter the major determinants? - Fabiana Saporiti; Stuart Bearhop; Damián G. Vales; Laura Silva; Lisette Zenteno; Mauricio Tavares; Enrique A. Crespo; Luis Cardona (Marine Ecology, 2016)
Although the body size of consumers may be a determinant factor in structuring food webs, recent evidence indicates that body size may fail to fully explain differences in the resource use patterns of predators in some situations. Here we compared the trophic niche of three sympatric and sexually dimorphic air‐breathing marine predators (the South American sea lion, Otaria flavescens , the South American fur seal, Arctocephalus australis , and the Magellanic penguin, Spheniscus magellanicus ) in three areas of the Southwestern Atlantic Ocean (Río de la Plata and adjoining areas, Northern Patagonia and Southern Patagonia), in order to assess the importance of body size and mouth diameter in determining resource partitioning. Body weight and palate/bill breadth were used to characterize the morphology of each sex and species, whereas the trophic niche was assessed through the use of stable isotope ratios of carbon and nitrogen. The quantitative method Stable Isotope Bayesian Ellipses in R ( SIBER ) was used to compute the area of the Bayesian ellipses and the overlap of the isotopic niches. The results showed that morphological similarity was significantly correlated with isotopic distance between groups within the δ 13 C–δ 15 N bi‐plot space in the Río de la Plata area, but not in Northern and Southern Patagonia. Furthermore, resource partitioning between groups changed regionally, and some morphologically distinct groups exhibited a large trophic overlap in certain areas, such as the case of male penguins and male sea lions in Southern Patagonia. Conversely, female sea lions always overlapped with the much larger males of the same species, but never overlapped with the morphologically similar male fur seals. These results indicate that body size and mouth diameter are just two of the factors involved in resource partitioning within the guild of air‐breathing predators considered here, and for whom – under certain environmental conditions – other factors are more important than morphology.

Influences of Natural and Anthropogenic Factors and Tidal Restoration on Terrestrial Arthropod Assemblages in West Coast North American Estuarine Wetlands - Aaron T. David; Pascale A. L. Goertler; Stuart H. Munsch; Brittany R. Jones; Charles A. Simenstad; Jason D. Toft; Jeffery R. Cordell; Emily R. Howe; Ayesha Gray; Michael P. Hannam; William Matsubu; Erin E. Morgan (Estuaries and Coasts, 2016)

Controls over Ocean Mesopelagic Interior Carbon Storage (COMICS): Fieldwork, Synthesis, and Modeling Efforts - Richard J. Sanders; Stephanie A. Henson; Adrian P. Martin; Tom R. Anderson; Raffaele Bernardello; Peter Enderlein; Sophie Fielding; Sarah L. C. Giering; Manuela Hartmann; Morten Iversen; Samar Khatiwala; Phyllis Lam; et al. (Frontiers in Marine Science, 2016)

Geohazards and thermal regime analysis of oil pipeline along the Qinghai–Tibet Plateau Engineering Corridor - Wenbing Yu; Fenglei Han; Weibo Liu; Stuart A. Harris (Natural Hazards, 2016)

Experimental whole‐lake increase of dissolved organic carbon concentration produces unexpected increase in crustacean zooplankton density - Patrick T. Kelly; Nicola Craig; Christopher T. Solomon; Brian C. Weidel; Jacob A. Zwart; Stuart E. Jones (Global Change Biology, 2016)
The observed pattern of lake browning, or increased terrestrial dissolved organic carbon ( DOC ) concentration, across the northern hemisphere has amplified the importance of understanding how consumer productivity varies with DOC concentration. Results from comparative studies suggest these increased DOC concentrations may reduce crustacean zooplankton productivity due to reductions in resource quality and volume of suitable habitat. Although these spatial comparisons provide an expectation for the response of zooplankton productivity as DOC concentration increases, we still have an incomplete understanding of how zooplankton respond to temporal increases in DOC concentration within a single system. As such, we used a whole‐lake manipulation, in which DOC concentration was increased from 8 to 11 mg L −1 in one basin of a manipulated lake, to test the hypothesis that crustacean zooplankton production should subsequently decrease. In contrast to the spatially derived expectation of sharp DOC ‐mediated decline, we observed a small increase in zooplankton densities in response to our experimental increase in DOC concentration of the treatment basin. This was due to significant increases in gross primary production and resource quality (lower seston carbon‐to‐phosphorus ratio; C:P). These results demonstrate that temporal changes in lake characteristics due to increased DOC may impact zooplankton in ways that differ from those observed in spatial surveys. We also identified significant interannual variability across our study region, which highlights potential difficulty in detecting temporal responses of organism abundances to gradual environmental change (e.g., browning).

Atmospheric Electrification in Dusty, Reactive Gases in the Solar System and Beyond - Christiane Helling; R. Giles Harrison; Farideh Honary; Declan A. Diver; Karen Aplin; Ian Dobbs-Dixon; Ute Ebert; Shu-ichiro Inutsuka; Francisco J. Gordillo-Vazquez; Stuart Littlefair (Surveys in Geophysics, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Brain white matter structure and information processing speed in healthy older age - Ksenia A. Kuznetsova; Susana Muñoz Maniega; Stuart J. Ritchie; Simon R. Cox; Amos J. Storkey; John M. Starr; Joanna M. Wardlaw; Ian J. Deary; Mark E. Bastin (Brain Structure and Function, 2016)

Biogenic polycyclic aromatic hydrocarbons in sediments of the San Joaquin River in California (USA), and current paradigms on their formation - Stuart G. Wakeham; Elizabeth A. Canuel (Environmental Science and Pollution Research, 2016)

Impacts of adaptation and responsibility framings on attitudes towards climate change mitigation - Rachel A. Howell; Stuart Capstick; Lorraine Whitmarsh (Climatic Change, 2016)

Agricultural land usage transforms nitrifier population ecology - Anthony D. Bertagnolli; Dylan McCalmont; Kelley A. Meinhardt; Steven C. Fransen; Stuart Strand; Sally Brown; David A. Stahl (Environmental Microbiology, 2016)
Summary Application of nitrogen fertilizer has altered terrestrial ecosystems. Ammonia is nitrified by ammonia and nitrite‐oxidizing microorganisms, converting ammonia to highly mobile nitrate, contributing to the loss of nitrogen, soil nutrients and production of detrimental nitrogen oxides. Mitigating these costs is of critical importance to a growing bioenergy industry. To resolve the impact of management on nitrifying populations, amplicon sequencing of markers associated with ammonia and nitrite‐oxidizing taxa (ammonia monooxygenase‐ amo A , nitrite oxidoreductase‐ nxr B , respectively) was conducted from long‐term managed and nearby native soils in Eastern Washington, USA . Native nitrifier population structure was altered profoundly by management. The native ammonia‐oxidizing archaeal community (comprised primarily by N itrososphaera sister subclusters 1.1 and 2) was displaced by populations of N itrosopumilus , N itrosotalea and different assemblages of N itrososphaera (subcluster 1.1, and unassociated lineages of N itrososphaera ). A displacement of ammonia‐oxidizing bacterial taxa was associated with management, with native groups of Nitrosospira (cluster 2 related, cluster 3A.2) displaced by N itrosospira clusters 8B and 3A.1. A shift in nitrite‐oxidizing bacteria ( NOB ) was correlated with management, but distribution patterns could not be linked exclusively to management. Dominant nxrB sequences displayed only distant relationships to other NOB isolates and environmental clones.

The complete nucleotide sequence of pelargonium leaf curl virus - Wendy J. McGavin; Stuart A. MacFarlane (Archives of Virology, 2016)

Blood flow restriction exercise: acute versus chronic safety - Stuart A. Warmington; Craig A. Staunton; Anthony K. May; Christopher R. Brandner (European Journal of Applied Physiology, 2016)

Strong and stable geographic differentiation of swamp buffalo maternal and paternal lineages indicates domestication in the China/Indochina border region - Yi Zhang; Yongfang Lu; Marnoch Yindee; Kuan‐Yi Li; Hsiao‐Yun Kuo; Yu‐Ten Ju; Shaohui Ye; Md Omar Faruque; Qiang Li; Yachun Wang; Vu Chi Cuong; Lan Doan Pham; et al. (Molecular Ecology, 2016)
The swamp type of the Asian water buffalo is assumed to have been domesticated by about 4000 years BP , following the introduction of rice cultivation. Previous localizations of the domestication site were based on mitochondrial DNA (mt DNA ) variation within China, accounting only for the maternal lineage. We carried out a comprehensive sampling of China, Taiwan, Vietnam, Laos, Thailand, Nepal and Bangladesh and sequenced the mt DNA Cytochrome b gene and control region and the Y‐chromosomal ZFY , SRY and DBY sequences. Swamp buffalo has a higher diversity of both maternal and paternal lineages than river buffalo, with also a remarkable contrast between a weak phylogeographic structure of river buffalo and a strong geographic differentiation of swamp buffalo. The highest diversity of the swamp buffalo maternal lineages was found in south China and north Indochina on both banks of the Mekong River, while the highest diversity in paternal lineages was in the China/Indochina border region. We propose that domestication in this region was later followed by introgressive capture of wild cows west of the Mekong. Migration to the north followed the Yangtze valley as well as a more eastern route, but also involved translocations of both cows and bulls over large distances with a minor influence of river buffaloes in recent decades. Bayesian analyses of various migration models also supported domestication in the China/Indochina border region. Coalescence analysis yielded consistent estimates for the expansion of the major swamp buffalo haplogroups with a credibility interval of 900 to 3900 years BP . The spatial differentiation of mt DNA and Y‐chromosomal haplotype distributions indicates a lack of gene flow between established populations that is unprecedented in livestock.

Impact of alternative metrics on estimates of extent of occurrence for extinction risk assessment - Lucas N. Joppa; Stuart H. M. Butchart; Michael Hoffmann; Steve P. Bachman; H. Resit Akçakaya; Justin F. Moat; Monika Böhm; Robert A. Holland; Adrian Newton; Beth Polidoro; Adrian Hughes (Conservation Biology, 2016)
In International Union for Conservation of Nature (IUCN) Red List assessments, extent of occurrence (EOO) is a key measure of extinction risk. However, the way assessors estimate EOO from maps of species’ distributions is inconsistent among assessments of different species and among major taxonomic groups. Assessors often estimate EOO from the area of mapped distribution, but these maps often exclude areas that are not habitat in idiosyncratic ways and are not created at the same spatial resolutions. We assessed the impact on extinction risk categories of applying different methods (minimum convex polygon, alpha hull) for estimating EOO for 21,763 species of mammals, birds, and amphibians. Overall, the percentage of threatened species requiring down listing to a lower category of threat (taking into account other Red List criteria under which they qualified) spanned 11–13% for all species combined (14–15% for mammals, 7–8% for birds, and 12–15% for amphibians). These down listings resulted from larger estimates of EOO and depended on the EOO calculation method. Using birds as an example, we found that 14% of threatened and near threatened species could require down listing based on the minimum convex polygon (MCP) approach, an approach that is now recommended by IUCN. Other metrics (such as alpha hull) had marginally smaller impacts. Our results suggest that uniformly applying the MCP approach may lead to a one‐time down listing of hundreds of species but ultimately ensure consistency across assessments and realign the calculation of EOO with the theoretical basis on which the metric was founded.

Migratory diversity predicts population declines in birds - James J. Gilroy; Jennifer A. Gill; Stuart H. M. Butchart; Victoria R. Jones; Aldina M. A. Franco (Ecology Letters, 2016)
Declines in migratory species are a pressing concern worldwide, but the mechanisms underpinning these declines are not fully understood. We hypothesised that species with greater within‐population variability in migratory movements and destinations, here termed ‘migratory diversity’, might be more resilient to environmental change. To test this, we related map‐based metrics of migratory diversity to recent population trends for 340 European breeding birds. Species that occupy larger non‐breeding ranges relative to breeding, a characteristic we term ‘migratory dispersion’, were less likely to be declining than those with more restricted non‐breeding ranges. Species with partial migration strategies (i.e. overlapping breeding and non‐breeding ranges) were also less likely to be declining than full migrants or full residents, an effect that was independent of migration distance. Recent rates of advancement in Europe‐wide spring arrival date were greater for partial migrants than full migrants, suggesting that migratory diversity may also help facilitate species responses to climate change.

Effects of Paclitaxel and Eribulin in Mouse Sciatic Nerve: A Microtubule-Based Rationale for the Differential Induction of Chemotherapy-Induced Peripheral Neuropathy - Sarah J. Benbow; Brett M. Cook; Jack Reifert; Krystyna M. Wozniak; Barbara S. Slusher; Bruce A. Littlefield; Leslie Wilson; Mary Ann Jordan; Stuart C. Feinstein (Neurotoxicity Research, 2016)

An inability to distinguish edematous swelling from true hypertrophy still prevents a completely accurate interpretation of the time course of muscle hypertrophy - Felipe Damas; Stuart M. Phillips; Manoel E. Lixandrão; Felipe C. Vechin; Cleiton A. Libardi; Hamilton Roschel; Valmor Tricoli; Carlos Ugrinowitsch (European Journal of Applied Physiology, 2016)

Differential Effects of Pharmacologic and Genetic Modulation of NMDA Receptor Activity on HIV/gp120-Induced Neuronal Damage in an In Vivo Mouse Model - Nobuki Nakanishi; Yeon-Joo Kang; Shichun Tu; Scott R. McKercher; Eliezer Masliah; Stuart A. Lipton (Journal of Molecular Neuroscience, 2016)

Early resistance training-induced increases in muscle cross-sectional area are concomitant with edema-induced muscle swelling - Felipe Damas; Stuart M. Phillips; Manoel E. Lixandrão; Felipe C. Vechin; Cleiton A. Libardi; Hamilton Roschel; Valmor Tricoli; Carlos Ugrinowitsch (European Journal of Applied Physiology, 2016)

The role of parasite‐driven selection in shaping landscape genomic structure in red grouse ( Lagopus lagopus scotica ) - Marius A. Wenzel; Alex Douglas; Marianne C. James; Steve M. Redpath; Stuart B. Piertney (Molecular Ecology, 2016)
Landscape genomics promises to provide novel insights into how neutral and adaptive processes shape genome‐wide variation within and among populations. However, there has been little emphasis on examining whether individual‐based phenotype–genotype relationships derived from approaches such as genome‐wide association (GWAS) manifest themselves as a population‐level signature of selection in a landscape context. The two may prove irreconcilable as individual‐level patterns become diluted by high levels of gene flow and complex phenotypic or environmental heterogeneity. We illustrate this issue with a case study that examines the role of the highly prevalent gastrointestinal nematode Trichostrongylus tenuis in shaping genomic signatures of selection in red grouse ( Lagopus lagopus scotica ). Individual‐level GWAS involving 384 SNPs has previously identified five SNPs that explain variation in T. tenuis burden. Here, we examine whether these same SNPs display population‐level relationships between T. tenuis burden and genetic structure across a small‐scale landscape of 21 sites with heterogeneous parasite pressure. Moreover, we identify adaptive SNPs showing signatures of directional selection using outlier analysis and relate population‐ and individual‐level patterns of multilocus neutral and adaptive genetic structure to T. tenuis burden. The five candidate SNPs for parasite‐driven selection were neither associated with T. tenuis burden on a population level, nor under directional selection. Similarly, there was no evidence of parasite‐driven selection in SNPs identified as candidates for directional selection. We discuss these results in the context of red grouse ecology and highlight the broader consequences for the utility of landscape genomics approaches for identifying signatures of selection.

Relating belowground microbial composition to the taxonomic, phylogenetic, and functional trait distributions of trees in a tropical forest - Albert Barberán; Krista L. McGuire; Jeffrey A. Wolf; F. Andrew Jones; Stuart Joseph Wright; Benjamin L. Turner; Adam Essene; Stephen P. Hubbell; Brant C. Faircloth; Noah Fierer (Ecology Letters, 2015)
The complexities of the relationships between plant and soil microbial communities remain unresolved. We determined the associations between plant aboveground and belowground (root) distributions and the communities of soil fungi and bacteria found across a diverse tropical forest plot. Soil microbial community composition was correlated with the taxonomic and phylogenetic structure of the aboveground plant assemblages even after controlling for differences in soil characteristics, but these relationships were stronger for fungi than for bacteria. In contrast to expectations, the species composition of roots in our soil core samples was a poor predictor of microbial community composition perhaps due to the patchy, ephemeral, and highly overlapping nature of fine root distributions. Our ability to predict soil microbial composition was not improved by incorporating information on plant functional traits suggesting that the most commonly measured plant traits are not particularly useful for predicting the plot‐level variability in belowground microbial communities.

Cyclic Loading Effects on the Creep and Dilation of Salt Rock - Lance A. Roberts; Stuart A. Buchholz; Kirby D. Mellegard; Uwe Düsterloh (Rock Mechanics and Rock Engineering, 2015)

Haemodynamics of aerobic and resistance blood flow restriction exercise in young and older adults - Craig A. Staunton; Anthony K. May; Christopher R. Brandner; Stuart A. Warmington (European Journal of Applied Physiology, 2015)

Challenges for using quantitative PCR test batteries as a TIE-type approach to identify metal exposure in benthic invertebrates - Sharon E. Hook; Hannah L. Osborn; David A. Spadaro; Stuart L. Simpson (Environmental Science and Pollution Research, 2015)

Species traits and climate velocity explain geographic range shifts in an ocean‐warming hotspot - Jennifer M. Sunday; Gretta T. Pecl; Stewart Frusher; Alistair J. Hobday; Nicole Hill; Neil J. Holbrook; Graham J. Edgar; Rick Stuart‐Smith; Neville Barrett; Thomas Wernberg; Reg A. Watson; Dan A. Smale; et al. (Ecology Letters, 2015)
Species' ranges are shifting globally in response to climate warming, with substantial variability among taxa, even within regions. Relationships between range dynamics and intrinsic species traits may be particularly apparent in the ocean, where temperature more directly shapes species' distributions. Here, we test for a role of species traits and climate velocity in driving range extensions in the ocean‐warming hotspot of southeast Australia. Climate velocity explained some variation in range shifts, however, including species traits more than doubled the variation explained. Swimming ability, omnivory and latitudinal range size all had positive relationships with range extension rate, supporting hypotheses that increased dispersal capacity and ecological generalism promote extensions. We find independent support for the hypothesis that species with narrow latitudinal ranges are limited by factors other than climate. Our findings suggest that small‐ranging species are in double jeopardy, with limited ability to escape warming and greater intrinsic vulnerability to stochastic disturbances.

Erratum to: Pronounced genetic structure and low genetic diversity in European red-billed chough (Pyrrhocorax pyrrhocorax) populations - Marius A. Wenzel; Lucy M. I. Webster; Guillermo Blanco; Malcolm D. Burgess; Christian Kerbiriou; Gernot Segelbacher; Stuart B. Piertney; Jane M. Reid (Conservation Genetics, 2015)

Genome‐wide association and genome partitioning reveal novel genomic regions underlying variation in gastrointestinal nematode burden in a wild bird - Marius A. Wenzel; Marianne C. James; Alex Douglas; Stuart B. Piertney (Molecular Ecology, 2015)
Identifying the genetic architecture underlying complex phenotypes is a notoriously difficult problem that often impedes progress in understanding adaptive eco‐evolutionary processes in natural populations. Host–parasite interactions are fundamentally important drivers of evolutionary processes, but a lack of understanding of the genes involved in the host's response to chronic parasite insult makes it particularly difficult to understand the mechanisms of host life history trade‐offs and the adaptive dynamics involved. Here, we examine the genetic basis of gastrointestinal nematode ( Trichostrongylus tenuis ) burden in 695 red grouse ( Lagopus lagopus scotica ) individuals genotyped at 384 genome‐wide SNPs. We first use genome‐wide association to identify individual SNPs associated with nematode burden. We then partition genome‐wide heritability to identify chromosomes with greater heritability than expected from gene content, due to harbouring a multitude of additive SNPs with individually undetectable effects. We identified five SNPs on five chromosomes that accounted for differences of up to 556 worms per bird, but together explained at best 4.9% of the phenotypic variance. These SNPs were closely linked to genes representing a range of physiological processes including the immune system, protein degradation and energy metabolism. Genome partitioning indicated genome‐wide heritability of up to 29% and three chromosomes with excess heritability of up to 4.3% (total 8.9%). These results implicate SNPs and novel genomic regions underlying nematode burden in this system and suggest that this phenotype is somewhere between being based on few large‐effect genes (oligogenic) and based on a large number of genes with small individual but large combined effects (polygenic).

Phytoplankton traits predict ecosystem function in a global set of lakes - Jacob A. Zwart; Christopher T. Solomon; Stuart E. Jones (Ecology, 2015)
Predicting ecosystem function from environmental conditions is a central goal of ecosystem ecology. However, many traditional ecosystem models are tailored for specific regions or ecosystem types, requiring several regional models to predict the same function. Alternatively, trait‐based approaches have been effectively used to predict community structure in both terrestrial and aquatic environments and ecosystem function in a limited number of terrestrial examples. Here, we test the efficacy of a trait‐based model in predicting gross primary production (GPP) in lake ecosystems. We incorporated data from >1000 United States lakes along with laboratory‐generated phytoplankton trait data to build a trait‐based model of GPP and then validated the model with GPP observations from a separate set of globally distributed lakes. The trait‐based model performed as well as or outperformed two ecosystem models both spatially and temporally, demonstrating the efficacy of trait‐based models for predicting ecosystem function over a range of environmental conditions.

Development of the blood–brain barrier within the paraventricular nucleus of the hypothalamus: influence of fetal glucocorticoid excess - Krystle A. Frahm; Stuart A. Tobet (Brain Structure and Function, 2015)

In silico identification and characterisation of 17 polymorphic anonymous non-coding sequence markers (ANMs) for red grouse (Lagopus lagopus scotica) - Marius A. Wenzel; Stuart B. Piertney (Conservation Genetics Resources, 2015)

Resource availability affects individual niche variation and its consequences in group-living European badgers Meles meles - Andrew Robertson; Robbie A. McDonald; Richard J. Delahay; Simon D. Kelly; Stuart Bearhop (Oecologia, 2015)

Measuring coral size-frequency distribution using stereo video technology, a comparison with in situ measurements - Joseph A. Turner; Nicholas V. C. Polunin; Stuart N. Field; Shaun K. Wilson (Environmental Monitoring and Assessment, 2015)

Productivity and fishing pressure drive variability in fish parasite assemblages of the Line Islands, equatorial Pacific - Chelsea L. Wood; Julia K. Baum; Sheila M. W. Reddy; Rowan Trebilco; Stuart A. Sandin; Brian J. Zgliczynski; Amy A. Briggs; Fiorenza Micheli (Ecology, 2015)
Variability in primary productivity and fishing pressure can shape the abundance, species composition, and diversity of marine life. Though parasites comprise nearly half of marine species, their responses to these important forces remain little explored. We quantified parasite assemblages at two spatial scales, across a gradient in productivity and fishing pressure that spans six coral islands of the Line Islands archipelago and within the largest Line Island, Kiritimati, which experiences a west‐to‐east gradient in fishing pressure and upwelling‐driven productivity. In the across‐islands data set, we found that increasing productivity was correlated with increased parasite abundance overall, but that the effects of productivity differed among parasite groups. Trophically transmitted parasites increased in abundance with increasing productivity, but directly transmitted parasites did not exhibit significant changes. This probably arises because productivity has stronger effects on the abundance of the planktonic crustaceans and herbivorous snails that serve as the intermediate hosts of trophically transmitted parasites than on the higher‐trophic level fishes that are the sole hosts of directly transmitted parasites. We also found that specialist parasites increased in response to increasing productivity, while generalists did not, possibly because specialist parasites tend to be more strongly limited by host availability than are generalist parasites. After the effect of productivity was controlled for, fishing was correlated with decreases in the abundance of trophically transmitted parasites, while directly transmitted parasites appeared to track host density; we observed increases in the abundance of parasites using hosts that experienced fishing‐driven compensatory increases in abundance. The within‐island data set confirmed these patterns for the combined effects of productivity and fishing on parasite abundance, suggesting that our conclusions are robust across a span of spatial scales. Overall, these results indicate that there are strong and variable effects of anthropogenic and natural drivers on parasite abundance and taxonomic richness. These effects are likely to be mediated by parasite traits, particularly by parasite transmission strategies.

The role of exotic ladybeetles in the decline of native ladybeetle populations: evidence from long-term monitoring - Christine A. Bahlai; Manuel Colunga-Garcia; Stuart H. Gage; Douglas A. Landis (Biological Invasions, 2015)

Rival assessment and comparison of morphological and performance-based predictors of fighting ability in Lake Eyre dragon lizards, Ctenophorus maculosus - Claire A. McLean; Devi Stuart-Fox (Behavioral Ecology and Sociobiology, 2015)

Exploiting fungal cell wall components in vaccines - Stuart M. Levitz; Haibin Huang; Gary R. Ostroff; Charles A. Specht (Seminars in Immunopathology, 2015)

Benefits of gregarious feeding by aposematic caterpillars depend on group age structure - Stuart A. Campbell; Michael Stastny (Oecologia, 2015)

Carbon Footprint Analysis of Source Water for Hydraulic Fracturing: A Case Study of Mine Water Versus Freshwater - Taylor R. Macy; Natalie A. Kruse; Ben J. Stuart (Mine Water and the Environment, 2015)

Identification and characterisation of 17 polymorphic candidate genes for response to parasitic nematode (Trichostrongylus tenuis) infection in red grouse (Lagopus lagopus scotica) - Marius A. Wenzel; Lucy M. I. Webster; Steve Paterson; Stuart B. Piertney (Conservation Genetics Resources, 2015)

Does flood rhythm drive ecosystem responses in tropical riverscapes? - Timothy D. Jardine; Nicholas R. Bond; Michele A. Burford; Mark J. Kennard; Douglas P. Ward; Peter Bayliss; Peter M. Davies; Michael M. Douglas; Stephen K. Hamilton; John M. Melack; Robert J. Naiman; Neil E. Pettit; et al. (Ecology, 2015)
Biotic communities are shaped by adaptations from generations of exposure to selective pressures by recurrent and often infrequent events. In large rivers, floods can act as significant agents of change, causing considerable physical and biotic disturbance while often enhancing productivity and diversity. We show that the relative balance between these seemingly divergent outcomes can be explained by the rhythmicity, or predictability of the timing and magnitude, of flood events. By analyzing biological data for large rivers that span a gradient of rhythmicity in the Neotropics and tropical Australia, we find that systems with rhythmic annual floods have higher fish species richness, more stable avian populations, and elevated rates of riparian forest production compared with those with arrhythmic flood pulses. Intensification of the hydrological cycle driven by climate change, coupled with reductions in runoff due to water extractions for human use and altered discharge from impoundments, is expected to alter the hydrologic rhythmicity of floodplain rivers with significant consequences for both biodiversity and productivity.

Physical habitat and water quality correlates of crayfish distributions in a mined watershed - Stuart A. Welsh; Zachary J. Loughman (Hydrobiologia, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Understanding Human–Coyote Encounters in Urban Ecosystems Using Citizen Science Data: What Do Socioeconomics Tell Us? - Stuart Wine; Sara A. Gagné; Ross K. Meentemeyer (Environmental Management, 2015)

Intakes of fat and micronutrients between ages 13 and 18 years and the incidence of proliferative benign breast disease - Xuefen Su; Caroline E. Boeke; Laura C. Collins; Heather J. Baer; Walter C. Willett; Stuart J. Schnitt; James L. Connolly; Bernard Rosner; Graham A. Colditz; Rulla M. Tamimi (Cancer Causes & Control, 2015)

High-temperature structural phase transitions in neighborite: a high-resolution neutron powder diffraction investigation - Kevin S. Knight; G. David Price; John A. Stuart; Ian G. Wood (Physics and Chemistry of Minerals, 2015)

Linking the green and brown worlds: the prevalence and effect of multichannel feeding in food webs - Elizabeth M. Wolkovich; Stefano Allesina; Kathryn L. Cottingham; John C. Moore; Stuart A. Sandin; Claire de Mazancourt (Ecology, 2014)
Recent advances in food‐web ecology highlight that most real food webs (1) represent an interplay between producer‐ and detritus‐based webs and (2) are governed by consumers which are rampant omnivores; feeding on varied prey across trophic levels and resource channels. A possible avenue to unify these advances comes from models demonstrating that predators feeding on distinctly different channels may stabilize food webs. Empirical studies suggest many consumers engage in such behavior by feeding on prey items from both living‐autotroph (green) and detritus‐based (brown) webs, what we term “multichannel feeding,” yet we know little about how common such feeding is across systems and trophic levels, or its effect on system stability. Considering 23 empirical webs, we find that multichannel feeding is equally common across terrestrial, freshwater, and marine systems, with >50% of consumers classified as multichannel consumers. Multichannel feeding occurred most often at the first consumer level, indicating that most taxa at the herbivore/detritivore level are more aptly described as multichannel consumers, and that such feeding is not restricted to predators. We next developed a simple four‐compartment nutrient cycling model for consumers eating both autotrophs and detritus with separate parameter sets to represent aquatic vs. terrestrial ecosystems. Modeling results showed that, across terrestrial and aquatic ecosystems, multichannel feeding is stabilizing at low attack rates on autotrophs or when attack rates are asymmetric (moderate on autotrophs while low on detritus), but destabilizing at high attack rates on autotrophs, compared to herbivory‐ or detritivory‐only models. The set of conditions with stable webs with multichannel consumers is narrower, however, for aquatic systems, suggesting that multichannel feeding may generally be more stabilizing in terrestrial systems. Together, our results demonstrate that multichannel feeding is common across ecosystems and may be a stabilizing force in real webs that have consumers with low or asymmetric attack rates.

Endocrine regulation of predator-induced phenotypic plasticity - Stuart R. Dennis; Gerald A. LeBlanc; Andrew P. Beckerman (Oecologia, 2014)

Early-phase musculoskeletal adaptations to different levels of eccentric resistance after 8 weeks of lower body training - Kirk L. English; James A. Loehr; Stuart M. C. Lee; Scott M. Smith (European Journal of Applied Physiology, 2014)

An assessment of endocrine activity in Australian rivers using chemical and in vitro analyses - Philip D. Scott; Michael Bartkow; Stephen J. Blockwell; Heather M. Coleman; Stuart J. Khan; Richard Lim; James A. McDonald; Helen Nice; Dayanthi Nugegoda; Vincent Pettigrove; Louis A. Tremblay; Michael St. J. Warne; et al. (Environmental Science and Pollution Research, 2014)

Novel molecular approach demonstrates that turbid river plumes reduce predation mortality on larval fish - Lucia B. Carreon‐Martinez; Kyle W. Wellband; Timothy B. Johnson; Stuart A. Ludsin; Daniel D. Heath (Molecular Ecology, 2014)
Turbidity associated with river plumes is known to affect the search ability of visual predators and thus can drive ‘top‐down’ impacts on prey populations in complex ecosystems; however, traditional quantification of predator–prey relationships (i.e. stomach content analysis) often fails with larval fish due to rapid digestion rates. Herein, we use novel molecular genetic methods to quantify larval yellow perch ( YP ) in predator stomachs in western Lake Erie to test the hypothesis that turbidity drives variation in larval predation. We characterize predator stomach content DNA to first identify YP DNA (single nucleotide polymorphism) and then quantify larval YP predation (microsatellite allele counting) in two river plumes differing in turbidity. Our results showed elevated larval YP predation in the less turbid river plume, consistent with a top‐down impact of turbidity on larval survival. Our analyses highlight novel ecological hypothesis testing using the power of innovative molecular genetic approaches.

Individual foraging specialisation in a social mammal: the European badger (Meles meles) - Andrew Robertson; Robbie A. McDonald; Richard J. Delahay; Simon D. Kelly; Stuart Bearhop (Oecologia, 2014)

Cassava Ivorian bacilliform virus is a member of the genus Anulavirus - Simon W. Scott; Stuart A. MacFarlane; Wendy J. McGavin; Denis Fargette (Archives of Virology, 2014)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

The Biogeography of Globally Threatened Seabirds and Island Conservation Opportunities - DENA R. SPATZ; KELLY M. NEWTON; REINA HEINZ; BERNIE TERSHY; NICK D. HOLMES; STUART H. M. BUTCHART; DONALD A. CROLL (Conservation Biology, 2014)
Seabirds are the most threatened group of marine animals; 29% of species are at some risk of extinction. Significant threats to seabirds occur on islands where they breed, but in many cases, effective island conservation can mitigate these threats. To guide island‐based seabird conservation actions, we identified all islands with extant or extirpated populations of the 98 globally threatened seabird species, as recognized on the International Union for Conservation of Nature Red List, and quantified the presence of threatening invasive species, protected areas, and human populations. We matched these results with island attributes to highlight feasible island conservation opportunities. We identified 1362 threatened breeding seabird populations on 968 islands. On 803 (83%) of these islands, we identified threatening invasive species (20%), incomplete protected area coverage (23%), or both (40%). Most islands with threatened seabirds are amenable to island‐wide conservation action because they are small (57% were 2 ), uninhabited (74%), and occur in high‐ or middle‐income countries (96%). Collectively these attributes make islands with threatened seabirds a rare opportunity for effective conservation at scale. La Biogeografía de Aves Marinas Amenazadas Globalmente y las Oportunidades de Conservación en Islas

Small Molecule Specific Run Acceptance, Specific Assay Operation, and Chromatographic Run Quality Assessment: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Teams - Eric J. Woolf; Stuart McDougall; Douglas M. Fast; Maristela Andraus; Matthew Barfield; Michael Blackburn; Ben Gordon; David Hoffman; Noriko Inoue; Gabriel Marcelin-Jimenez; Amy Flynn; Richard LeLacheur; et al. (The AAPS Journal, 2014)

A reconstruction of extratropical Indo-Pacific sea-level pressure patterns during the Medieval Climate Anomaly - Ian D. Goodwin; Stuart Browning; Andrew M. Lorrey; Paul A. Mayewski; Steven J. Phipps; Nancy A. N. Bertler; Ross P. Edwards; Tim J. Cohen; Tas van Ommen; Mark Curran; Cameron Barr; J. Curt Stager (Climate Dynamics, 2014)

Fine‐scale population epigenetic structure in relation to gastrointestinal parasite load in red grouse ( Lagopus lagopus scotica ) - Marius A. Wenzel; Stuart B. Piertney (Molecular Ecology, 2014)
Epigenetic modification of cytosine methylation states can be elicited by environmental stresses and may be a key process affecting phenotypic plasticity and adaptation. Parasites are potent stressors with profound physiological and ecological effects on their host, but there is little understanding in how parasites may influence host methylation states. Here, we estimate epigenetic diversity and differentiation among 21 populations of red grouse ( Lagopus lagopus scotica ) in north‐east Scotland and test for association of gastrointestinal parasite load (caecal nematode Trichostrongylus tenuis ) with hepatic genome‐wide and locus‐specific methylation states. Following methylation‐sensitive AFLP (MSAP), 129 bands, representing 73 methylation‐susceptible and 56 nonmethylated epiloci, were scored across 234 individuals. The populations differed significantly in genome‐wide methylation levels and were also significantly epigenetically ( F SC = 0.0227; P F SC = 0.0058; P F ST outliers) using bayescan software and significant positive and negative association of 35 methylation states with parasite load from bespoke generalized estimating equations (GEE), simple logistic regression ( sam ) and Bayesian environmental analysis ( bayenv 2). Following Sanger sequencing, genome mapping and geneontology ( go ) annotation, some of these epiloci were linked to genes involved in regulation of cell cycle, signalling, metabolism, immune system and notably rRNA methylation, histone acetylation and small RNAs. These findings demonstrate an epigenetic signature of parasite load in populations of a wild bird and suggest intriguing physiological effects of parasite‐associated cytosine methylation.

Population genetics of Formica aquilonia wood ants in Scotland: the effects of long-term forest fragmentation and recent reforestation - Tytti Vanhala; Kevin Watts; Stuart A’Hara; Joan Cottrell (Conservation Genetics, 2014)

Congenic mice reveal genetic epistasis and overlapping disease loci for autoimmune diabetes and listeriosis - Nancy Wang; Colleen M. Elso; Leanne Mackin; Stuart I. Mannering; Richard A. Strugnell; Odilia L. Wijburg; Thomas C. Brodnicki (Immunogenetics, 2014)

Mechanisms underpinning climatic impacts on natural populations: altered species interactions are more important than direct effects - Nancy Ockendon; David J. Baker; Jamie A. Carr; Elizabeth C. White; Rosamunde E. A. Almond; Tatsuya Amano; Esther Bertram; Richard B. Bradbury; Cassie Bradley; Stuart H. M. Butchart; Nathalie Doswald; Wendy Foden; et al. (Global Change Biology, 2014)
Shifts in species' distribution and abundance in response to climate change have been well documented, but the underpinning processes are still poorly understood. We present the results of a systematic literature review and meta‐analysis investigating the frequency and importance of different mechanisms by which climate has impacted natural populations. Most studies were from temperate latitudes of North America and Europe; almost half investigated bird populations. We found significantly greater support for indirect, biotic mechanisms than direct, abiotic mechanisms as mediators of the impact of climate on populations. In addition, biotic effects tended to have greater support than abiotic factors in studies of species from higher trophic levels. For primary consumers, the impact of climate was equally mediated by biotic and abiotic mechanisms, whereas for higher level consumers the mechanisms were most frequently biotic, such as predation or food availability. Biotic mechanisms were more frequently supported in studies that reported a directional trend in climate than in studies with no such climatic change, although sample sizes for this comparison were small. We call for more mechanistic studies of climate change impacts on populations, particularly in tropical systems.

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

Fishing drives declines in fish parasite diversity and has variable effects on parasite abundance - Chelsea L. Wood; Stuart A. Sandin; Brian Zgliczynski; Ana Sofía Guerra; Fiorenza Micheli (Ecology, 2014)
Despite the ubiquity and ecological importance of parasites, relatively few studies have assessed their response to anthropogenic environmental change. Heuristic models have predicted both increases and decreases in parasite abundance in response to human disturbance, with empirical support for both. However, most studies focus on one or a few selected parasite species. Here, we assess the abundance of parasites of seven species of coral reef fishes collected from three fished and three unfished islands of the Line Islands archipelago in the central equatorial Pacific. Because we chose fish hosts that spanned different trophic levels, taxonomic groups, and body sizes, we were able to compare parasite responses across a broad cross section of the total parasite community in the presence and absence of fishing, a major human impact on marine ecosystems. We found that overall parasite species richness was substantially depressed on fished islands, but that the response of parasite abundance varied among parasite taxa: directly transmitted parasites were significantly more abundant on fished than on unfished islands, while the reverse was true for trophically transmitted parasites. This probably arises because trophically transmitted parasites require multiple host species, some of which are the top predators most sensitive to fishing impacts. The increase in directly transmitted parasites appeared to be due to fishing‐driven compensatory increases in the abundance of their hosts. Together, these results provide support for the predictions of both heuristic models, and indicate that the direction of fishing's impact on parasite abundance is mediated by parasite traits, notably parasite transmission strategies.

Mantle heat drives hydrothermal fluids responsible for carbonate-hosted base metal deposits: evidence from 3He/4He of ore fluids in the Irish Pb-Zn ore district - B. Davidheiser-Kroll; F. M. Stuart; A. J. Boyce (Mineralium Deposita, 2014)

Long-term copper partitioning of metal-spiked sediments used in outdoor mesocosms - Stephanie Gardham; Grant C. Hose; Stuart L. Simpson; Chad Jarolimek; Anthony A. Chariton (Environmental Science and Pollution Research, 2014)

Multilocation Corn Stover Harvest Effects on Crop Yields and Nutrient Removal - Douglas L. Karlen; Stuart J. Birrell; Jane M. F. Johnson; Shannon L. Osborne; Thomas E. Schumacher; Gary E. Varvel; Richard B. Ferguson; Jeff M. Novak; James R. Fredrick; John M. Baker; John A. Lamb; Paul R. Adler; et al. (BioEnergy Research, 2014)

Performance of an empirical bias‐correction of a high‐resolution climate dataset - James C. Bennett; Michael R. Grose; Stuart P. Corney; Christopher J. White; Gregory K. Holz; Jack J. Katzfey; David A. Post; Nathaniel L. Bindoff (International Journal of Climatology, 2014)
We describe the method and performance of a bias‐correction applied to high‐resolution (˜10 km) simulations from a stretched‐grid Regional Climate Model ( RCM ) over Tasmania, Australia. The bias‐correction is a quantile mapping of empirical cumulative frequency distributions. Corrections are applied at a daily time step to five variables: rainfall, potential evaporation (PE), solar radiation, maximum temperature and minimum temperature. Corrections are calculated independently for each season. We show that quantile mapping of empirical distributions can be highly effective in correcting biases in RCM outputs. Cross‐validation shows biases are effectively reduced across the range of cumulative frequency distributions, with few exceptions. The bias‐correction is not as effective at correcting biases for values at or near zero (e.g. in rainfall simulations), although even here the bias‐correction improves biases evident in the uncorrected simulations. In addition, the bias‐correction improves frequency characteristics of variables such as the number of rain days. We use a detrending technique to apply the bias‐correction to 140‐year time series of RCM variables. We show that the bias‐correction effectively preserves long‐term changes (e.g. to the mean and variance) to variables projected by the uncorrected RCM simulations. Correlations between key variables are also largely preserved, thus the bias‐corrected outputs reflect the dynamics of the underlying RCM . However, the bias‐corrected simulations still exhibit some of the deficiencies of the RCM simulations, e.g. the tendency to underestimate the magnitude and duration of large, multi‐day rain events, and the tendency to underestimate the duration of dry spells. The bias‐corrected simulations for six downscaled GCMs for the A2 and B1 emissions scenarios are available to researchers from http://www.tpac.org.au .

Adaptations of aortic and pulmonary artery flow parameters measured by phase-contrast magnetic resonance angiography during supine aerobic exercise - Guido E. Pieles; Gergely Szantho; Jonathan C. L. Rodrigues; Christopher B. Lawton; A. Graham Stuart; Chiara Bucciarelli-Ducci; Mark S. Turner; Craig A. Williams; Robert M. R. Tulloh; Mark C. K. Hamilton (European Journal of Applied Physiology, 2014)

The effects of 3,3′,4,4′-tetrabromobiphenyl on rats fed diets containing a constant level of copper and varying levels of molybdenum - Kadhim N. Salman; Mary A. Stuart; Jack Schmidt; T. Borges; Craig J. McClain; Farrel R. Robinson; Miao Li; Larry W. Robertson (Environmental Science and Pollution Research, 2014)

Digestive enzymes of two brachyuran and two anomuran land crabs from Christmas Island, Indian Ocean - Stuart M. Linton; Reinhard Saborowski; Alicia J. Shirley; Jake A. Penny (Journal of Comparative Physiology B, 2014)

Life history traits of Blaptostethus pallescens (Hemiptera: Anthocoridae), a candidate for use in augmentative biological control in Egypt - Islam S. Sobhy; Amany M. Abdul-Hamid; Awad A. Sarhan; Ahmed A. Shoukry; Nasser S. Mandour; Stuart R. Reitz (Applied Entomology and Zoology, 2014)

Potential Effect of S-Nitrosylated Protein Disulfide Isomerase on Mutant SOD1 Aggregation and Neuronal Cell Death in Amyotrophic Lateral Sclerosis - Gye Sun Jeon; Tomohiro Nakamura; Jeong-Seon Lee; Won-Jun Choi; Suk-Won Ahn; Kwang-Woo Lee; Jung-Joon Sung; Stuart A. Lipton (Molecular Neurobiology, 2014)

Introduction: E Pluribus Unum - Vidyanand Nanjundiah; Stuart A Newman (Journal of Biosciences, 2014)

Limb, tooth, beak: Three modes of development and evolutionary innovation of form - Marta Linde-Medina; Stuart A Newman (Journal of Biosciences, 2014)

Mesozoic exhumation history and palaeolandscape of the Iberian Massif in eastern Galicia from apatite fission-track and (U+Th)/He data - R. W. Grobe; J. Alvarez-Marrón; U. A. Glasmacher; F. M. Stuart (International Journal of Earth Sciences, 2014)

Resilience to Stress and Disturbance, and Resistance to Bromus tectorum L. Invasion in Cold Desert Shrublands of Western North America - Jeanne C. Chambers; Bethany A. Bradley; Cynthia S. Brown; Carla D’Antonio; Matthew J. Germino; James B. Grace; Stuart P. Hardegree; Richard F. Miller; David A. Pyke (Ecosystems, 2014)

Freshwater bacterial lifestyles inferred from comparative genomics - Joshua A. Livermore; Scott J. Emrich; John Tan; Stuart E. Jones (Environmental Microbiology, 2014)
Summary While micro‐organisms actively mediate and participate in freshwater ecosystem services, we know little about freshwater microbial genetic diversity. Genome sequences are available for many bacteria from the human microbiome and the ocean (over 800 and 200, respectively), but only two freshwater genomes are currently available: the streamlined genomes of Polynucleobacter necessarius ssp . asymbioticus and the Actinobacterium AcI ‐ B 1. Here, we sequenced and analysed draft genomes of eight phylogentically diverse freshwater bacteria exhibiting a range of lifestyle characteristics. Comparative genomics of these bacteria reveals putative freshwater bacterial lifestyles based on differences in predicted growth rate, capability to respond to environmental stimuli and diversity of useable carbon substrates. Our conceptual model based on these genomic characteristics provides a foundation on which further ecophysiological and genomic studies can be built. In addition, these genomes greatly expand the diversity of existing genomic context for future studies on the ecology and genetics of freshwater bacteria.

Tsunami inundation in Napier, New Zealand, due to local earthquake sources - Stuart A. Fraser; William L. Power; Xiaoming Wang; Laura M. Wallace; Christof Mueller; David M. Johnston (Natural Hazards, 2014)

A taxonomic comparison of local habitat niches of tropical trees - Claire A. Baldeck; Steven W. Kembel; Kyle E. Harms; Joseph B. Yavitt; Robert John; Benjamin L. Turner; George B. Chuyong; David Kenfack; Duncan W. Thomas; Sumedha Madawala; Nimal Gunatilleke; Savitri Gunatilleke; et al. (Oecologia, 2013)

Periprosthetic osteolysis after total hip replacement: molecular pathology and clinical management - Donald W. Howie; Susan D. Neale; David R. Haynes; Oksana T. Holubowycz; Margaret A. McGee; Lucian B. Solomon; Stuart A. Callary; Gerald J. Atkins; David M. Findlay (Inflammopharmacology, 2013)

Cycling time to failure is better maintained by cold than contrast or thermoneutral lower-body water immersion in normothermia - David Crampton; Bernard Donne; Stuart A. Warmington; Mikel Egaña (European Journal of Applied Physiology, 2013)

Characterisation of thirteen polymorphic microsatellite markers for cowslip (Primula veris L.) developed using a 454 sequencing approach - Charlotte Bickler; Stuart A’Hara; Joan Cottrell; Lucy Rogers; Jon Bridle (Conservation Genetics Resources, 2013)

Development and characterisation of ten polymorphic microsatellite markers for the pine-tree lappet moth Dendrolimus pini (Lepidoptera: Lasiocampidae) - Stuart A’Hara; Joan Cottrell (Conservation Genetics Resources, 2013)

Virus nomenclature below the species level: a standardized nomenclature for filovirus strains and variants rescued from cDNA - Jens H. Kuhn; Yīmíng Bào; Sina Bavari; Stephan Becker; Steven Bradfute; Kristina Brauburger; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; et al. (Archives of Virology, 2013)

Evaluation of the Oxoid Brilliance™ CRE Agar for the detection of carbapenemase-producing Enterobacteriaceae - J. Cohen Stuart; G. Voets; W. Rottier; S. Voskuil; J. Scharringa; K. Dijk; A. C. Fluit; M. Leverstein-Van Hall (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Relationship of heartwood traits with diameter growth, implications for genetic selection in Pinus radiata - Stuart G. Kennedy; Alvin D. Yanchuk; Paul A. Jefferson (Tree Genetics & Genomes, 2013)

The nitrate time bomb: a numerical way to investigate nitrate storage and lag time in the unsaturated zone - L. Wang; A. S. Butcher; M. E. Stuart; D. C. Gooddy; J. P. Bloomfield (Environmental Geochemistry and Health, 2013)

Evaluation of Gaussian approximations for data assimilation in reservoir models - Marco A. Iglesias; Kody J. H. Law; Andrew M. Stuart (Computational Geosciences, 2013)

Combined inequality in wealth and risk leads to disaster in the climate change game - Maxwell N. Burton-Chellew; Robert M. May; Stuart A. West (Climatic Change, 2013)

Contemporary and historical classification of crop types in Arizona - Kyle A. Hartfield; Stuart E. Marsh; Christa D. Kirk; Yves Carrière (International Journal of Remote Sensing, 2013)

Large birth size does not reduce negative latent effects of harsh environments across life stages in two coral species - Aaron C. Hartmann; Kristen L. Marhaver; Valérie F. Chamberland; Stuart A. Sandin; Mark J. A. Vermeij (Ecology, 2013)
When juveniles must tolerate harsh environments early in life, the disproportionate success of certain phenotypes across multiple early life stages will dramatically influence adult community composition and dynamics. In many species, large offspring have a higher tolerance for stressful environments than do smaller conspecifics (parental effects). However, we have a poor understanding of whether the benefits of increased parental investment carry over after juveniles escape harsh environments or progress to later life stages (latent effects). To investigate whether parental effects and latent effects interactively influence offspring success, we determined the degree to which latent effects of harsh abiotic conditions are mediated by offspring size in two stony coral species. Larvae of both species were sorted by size class and exposed to relatively high‐temperature or low‐salinity conditions. Survivorship was quantified for six days in these stressful environments, after which surviving larvae were placed in ambient conditions and evaluated for their ability to settle and metamorphose. We subsequently assessed long‐term post‐settlement survival of one species in its natural environment. Following existing theory, we expected that, within and between species, larger offspring would have a higher tolerance for harsh environmental conditions than smaller offspring. We found that large size did enhance offspring performance in each species. However, large offspring size within a species did not reduce the proportional, negative latent effects of harsh larval environments. Furthermore, the coral species that produces larger offspring was more, not less, prone to negative latent effects. We conclude that, within species, large offspring size does not increase resistance to latent effects. Comparing between species, we conclude that larger offspring size does not inherently confer greater robustness, and we instead propose that other life history characteristics such as larval duration better predict the tolerance of offspring to harsh and variable abiotic conditions. Additionally, when considering how stressful environments influence offspring performance, studies that only evaluate direct effects may miss crucial downstream (latent) effects on juveniles that have significant consequences for long‐term population dynamics.

Composition and Integrity of PAHs, Nitro-PAHs, Hopanes, and Steranes in Diesel Exhaust Particulate Matter - Lei Huang; Stanislav V. Bohac; Sergei M. Chernyak; Stuart A. Batterman (Water, Air, & Soil Pollution, 2013)

Milling plant and soil material in plastic tubes over-estimates carbon and under-estimates nitrogen concentrations - Stuart W. Smith; A. H. Jean Robertson; Andrew A. Meharg; Robin J. Pakeman; David Johnson; Sarah J. Woodin; René van der Wal (Plant and Soil, 2013)

Differences in the antibiotic susceptibility of human Escherichia coli with poultry-associated and non-poultry-associated extended-spectrum beta-lactamases - T. N. Platteel; M. A. Leverstein-Van Hall; J. W. Cohen Stuart; G. M. Voets; M. P. Munckhof; J. Scharringa; N. Sande; A. C. Fluit; M. J. M. Bonten (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Whisker growth in wild Eurasian badgers Meles meles: implications for stable isotope and bait marking studies - Andrew Robertson; Robbie A. McDonald; Richard J. Delahay; Simon D. Kelly; Stuart Bearhop (European Journal of Wildlife Research, 2013)

Virus nomenclature below the species level: a standardized nomenclature for laboratory animal-adapted strains and variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; et al. (Archives of Virology, 2013)

Permeability of Wellbore-Cement Fractures Following Degradation by Carbonated Brine - Stuart D. C. Walsh; Wyatt L. Du Frane; Harris E. Mason; Susan A. Carroll (Rock Mechanics and Rock Engineering, 2013)

Advantages of Geographically Weighted Regression for Modeling Benthic Substrate in Two Greater Yellowstone Ecosystem Streams - Kenneth R. Sheehan; Michael P. Strager; Stuart A. Welsh (Environmental Modeling & Assessment, 2013)

Individual variation in dispersal associated with phenotype influences fine-scale genetic structure in weasels - Allan D. McDevitt; Matthew K. Oliver; Stuart B. Piertney; Paulina A. Szafrańska; Marek Konarzewski; Karol Zub (Conservation Genetics, 2013)

Geographic evidence for source–sink dynamics in deep‐sea neogastropods of the eastern N orth A tlantic: an approach using nested analysis - Solange Brault; Carol T. Stuart; Martine C. Wagstaff; Michael A. Rex (Global Ecology and Biogeography, 2013)
Aim We conduct a nested analysis of bathymetric distributions in neogastropods to test the hypothesis that bathyal and abyssal populations represent a source–sink system. Abyssal assemblages are predicted to be significantly nested subsets of bathyal assemblages, and to be characterized by low density, which drives extinction, and a high incidence of species with larval dispersal for continued immigration to maintain diversity. Location Bathyal and abyssal regions of the eastern N orth A tlantic O cean. Methods We used published indices of beta diversity to distinguish the components of species dissimilarity among sites that are caused by turnover and nestedness. We used BINMATNEST and its most conservative null model to test specifically for nestedness along a depth gradient. Results Both turnover and nestedness affect beta diversity, but dissimilarity due to turnover predominates at depths of less than 3000 m, and dissimilarity due to nestedness at depths greater than 3000 m. Nestedness increases significantly down‐slope at depths greater than 1000 m. The rank order of nestedness is significantly predicted by macrofaunal density and by the proportion of neogastropod species with dispersing larvae. Main conclusions Bathymetric patterns of beta diversity in the deep‐sea benthos have been interpreted largely as a consequence of species turnover. Our results indicate that beta diversity in neogastropods is composed of two separate processes, turnover and nestedness, and that their relative importance changes with depth. Dissimilarity among sites due to nestedness, coupled with information on standing stock and life history, suggests that at least part of the abyssal neogastropod assemblage is maintained by source–sink dynamics.

Cue reactivity in non-daily smokers - Saul Shiffman; Michael S. Dunbar; Thomas R. Kirchner; Xiaoxue Li; Hilary A. Tindle; Stewart J. Anderson; Sarah M. Scholl; Stuart G. Ferguson (Psychopharmacology, 2013)

MDMA Increases Glutamate Release and Reduces Parvalbumin-Positive GABAergic Cells in the Dorsal Hippocampus of the Rat: Role of Cyclooxygenase - John H. Anneken; Jacobi I. Cunningham; Stuart A. Collins; Bryan K. Yamamoto; Gary A. Gudelsky (Journal of Neuroimmune Pharmacology, 2013)

Betaine supplementation enhances anabolic endocrine and Akt signaling in response to acute bouts of exercise - Jenna M. Apicella; Elaine C. Lee; Brooke L. Bailey; Catherine Saenz; Jeffrey M. Anderson; Stuart A. S. Craig; William J. Kraemer; Jeff S. Volek; Carl M. Maresh (European Journal of Applied Physiology, 2013)

Denning behaviour of the European badger (Meles meles) correlates with bovine tuberculosis infection status - Nicola Weber; Stuart Bearhop; Sasha R. X. Dall; Richard J. Delahay; Robbie A. McDonald; Stephen P. Carter (Behavioral Ecology and Sociobiology, 2013)

The origin of Ag–Au–S–Se minerals in adularia-sericite epithermal deposits: constraints from the Broken Hills deposit, Hauraki Goldfield, New Zealand - Helen A. Cocker; Jeffrey L. Mauk; Stuart D. C. Rabone (Mineralium Deposita, 2013)

Observations of Surface Energy Fluxes and Boundary-Layer Structure Over Heron Reef, Great Barrier Reef, Australia - Mellissa C. MacKellar; Hamish A. McGowan; Stuart R. Phinn; Joshua S. Soderholm (Boundary-Layer Meteorology, 2013)

A transcriptomic investigation of handicap models in sexual selection - Marius A. Wenzel; Lucy M. I. Webster; Steve Paterson; François Mougeot; Jesús Martínez-Padilla; Stuart B. Piertney (Behavioral Ecology and Sociobiology, 2013)

Plant chemistry underlies herbivore‐mediated inbreeding depression in nature - Stuart A. Campbell; Jennifer S. Thaler; André Kessler (Ecology Letters, 2013)
The cost of inbreeding (inbreeding depression, ID) is an important variable in the maintenance of reproductive variation. Ecological interactions such as herbivory could modulate this cost, provided that defence traits harbour deleterious mutations and herbivores are responsible for differences in fitness. In the field, we manipulated the presence of herbivores on experimentally inbred and outcrossed plants of Solanum carolinense (horsenettle) for three years. Damage was greater on inbred plants, and ID for growth and fitness was significantly greater under herbivory. Inbreeding reduced phenolic expression both qualitatively (phytochemical diversity) and quantitatively, indicating deleterious load at loci related to the biosynthesis of defence compounds. Our results indicate that inbreeding effects on plant–herbivore interactions are mediated by changes to functional plant metabolites, suggesting that variation in inbreeding could be a predictor of defence trait variation. The magnitude of herbivore‐mediated, ecological ID indicates that herbivores could maintain outcrossing mating systems in nature.

Big claims for big weights but with little evidence - Nicholas A. Burd; Daniel R. Moore; Cameron J. Mitchell; Stuart M. Phillips (European Journal of Applied Physiology, 2013)

Cardiac magnetic resonance imaging of rapid VCAM-1 up-regulation in myocardial ischemia–reperfusion injury - Stuart M. Grieve; Jacob Lønborg; Jawad Mazhar; Timothy C. Tan; Edwin Ho; Chia-Chi Liu; William Lay; Anthony J. Gill; Philip Kuchel; Ravinay Bhindi; Gemma A. Figtree (European Biophysics Journal, 2013)

Virus nomenclature below the species level: a standardized nomenclature for natural variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; Sven Enterlein; et al. (Archives of Virology, 2013)

Preface: Perspectives on progress in ornitholimnology - Francisco A. Comín; Stuart H. Hurlbert (Hydrobiologia, 2012)

The effect of BDNF val66met polymorphism on visuomotor adaptation - Raed A. Joundi; Virginia Lopez-Alonso; Angel Lago; John-Stuart Brittain; Miguel Fernandez-del-Olmo; Pilar Gomez-Garre; Pablo Mir; Ned Jenkinson; Binith Cheeran; Peter Brown (Experimental Brain Research, 2012)

Pronounced genetic structure and low genetic diversity in European red-billed chough (Pyrrhocorax pyrrhocorax) populations - Marius A. Wenzel; Lucy M. I. Webster; Guillermo Blanco; Malcolm D. Burgess; Christian Kerbiriou; Gernot Segelbacher; Stuart B. Piertney; Jane M. Reid (Conservation Genetics, 2012)

The origin of litter chemical complexity during decomposition - Kyle Wickings; A. Stuart Grandy; Sasha C. Reed; Cory C. Cleveland (Ecology Letters, 2012)
The chemical complexity of decomposing plant litter is a central feature shaping the terrestrial carbon ( C ) cycle, but explanations of the origin of this complexity remain contentious. Here, we ask: How does litter chemistry change during decomposition, and what roles do decomposers play in these changes? During a long‐term (730 days) litter decomposition experiment, we tracked concurrent changes in decomposer community structure and function and litter chemistry using high‐resolution molecular techniques. Contrary to the current paradigm, we found that the chemistry of different litter types diverged, rather than converged, during decomposition due to the activities of decomposers. Furthermore, the same litter type exposed to different decomposer communities exhibited striking differences in chemistry, even after > 90% mass loss. Our results show that during decomposition, decomposer community characteristics regulate changes in litter chemistry, which could influence the functionality of litter‐derived soil organic matter ( SOM ) and the turnover and stabilisation of soil C.

Mechanisms for Eliminating Monoterpenes of Sagebrush by Specialist and Generalist Rabbits - Lisa A. Shipley; Edward M. Davis; Laura A. Felicetti; Stuart McLean; Jennifer Sorensen Forbey (Journal of Chemical Ecology, 2012)

Experimental litterfall manipulation drives large and rapid changes in soil carbon cycling in a wet tropical forest - Jonathan W. Leff; William R. Wieder; Philip G. Taylor; Alan R. Townsend; Diana R. Nemergut; A. Stuart Grandy; Cory C. Cleveland (Global Change Biology, 2012)
Global changes such as variations in plant net primary production are likely to drive shifts in leaf litterfall inputs to forest soils, but the effects of such changes on soil carbon ( C ) cycling and storage remain largely unknown, especially in C ‐rich tropical forest ecosystems. We initiated a leaf litterfall manipulation experiment in a tropical rain forest in C osta R ica to test the sensitivity of surface soil C pools and fluxes to different litter inputs. After only 2 years of treatment, doubling litterfall inputs increased surface soil C concentrations by 31%, removing litter from the forest floor drove a 26% reduction over the same time period, and these changes in soil C concentrations were associated with variations in dissolved organic matter fluxes, fine root biomass, microbial biomass, soil moisture, and nutrient fluxes. However, the litter manipulations had only small effects on soil organic C ( SOC ) chemistry, suggesting that changes in C cycling, nutrient cycling, and microbial processes in response to litter manipulation reflect shifts in the quantity rather than quality of SOC . The manipulation also affected soil CO 2 fluxes; the relative decline in CO 2 production was greater in the litter removal plots (−22%) than the increase in the litter addition plots (+15%). Our analysis showed that variations in CO 2 fluxes were strongly correlated with microbial biomass pools, soil C and nitrogen ( N ) pools, soil inorganic P fluxes, dissolved organic C fluxes, and fine root biomass. Together, our data suggest that shifts in leaf litter inputs in response to localized human disturbances and global environmental change could have rapid and important consequences for belowground C storage and fluxes in tropical rain forests, and highlight differences between tropical and temperate ecosystems, where belowground C cycling responses to changes in litterfall are generally slower and more subtle.

Roots and fungi accelerate carbon and nitrogen cycling in forests exposed to elevated CO 2 - Richard P. Phillips; Ina C. Meier; Emily S. Bernhardt; A. Stuart Grandy; Kyle Wickings; Adrien C. Finzi (Ecology Letters, 2012)
A common finding in multiple CO 2 enrichment experiments in forests is the lack of soil carbon ( C ) accumulation owing to microbial priming of ‘old’ soil organic matter ( SOM ). However, soil C losses may also result from the accelerated turnover of ‘young’ microbial tissues that are rich in nitrogen ( N ) relative to bulk SOM . We measured root‐induced changes in soil C dynamics in a pine forest exposed to elevated CO 2 and N enrichment by combining stable isotope analyses, molecular characterisations of SOM and microbial assays. We find strong evidence that the accelerated turnover of root‐derived C under elevated CO 2 is sufficient in magnitude to offset increased belowground inputs. In addition, the C losses were associated with accelerated N cycling, suggesting that trees exposed to elevated CO 2 not only enhance N availability by stimulating microbial decomposition of SOM via priming but also increase the rate at which N cycles through microbial pools.

Genomic dissection and prioritizing of candidate genes of QTL for regulating spontaneous arthritis on chromosome 1 in mice deficient for interleukin-1 receptor antagonist - YANHONG CAO; JIFEI ZHANG; YAN JIAO; JIAN YAN; FENG JIAO; XIAOYUN LIU; ROBERT W. WILLIAMS; KAREN A. HASTY; JOHN M. STUART; WEIKUAN GU (Journal of Genetics, 2012)

Rodenticide exposure in wood mouse and house mouse populations on farms and potential secondary risk to predators - David G. Tosh; Robbie A. McDonald; Stuart Bearhop; Neville R. Llewellyn; W. Ian Montgomery; Richard F. Shore (Ecotoxicology, 2012)

Towards an integrated global framework to assess the impacts of land use and management change on soil carbon: current capability and future vision - Pete Smith; Christian A. Davies; Stephen Ogle; Giuliana Zanchi; Jessica Bellarby; Neil Bird; Robert M. Boddey; Niall P. McNamara; David Powlson; Annette Cowie; Meine van Noordwijk; Sarah C. Davis; et al. (Global Change Biology, 2012)
I ntergovernmental P anel on C limate C hange ( IPCC ) T ier 1 methodologies commonly underpin project‐scale carbon accounting for changes in land use and management and are used in frameworks for L ife C ycle A ssessment and carbon footprinting of food and energy crops. These methodologies were intended for use at large spatial scales. This can introduce error in predictions at finer spatial scales. There is an urgent need for development and implementation of higher tier methodologies that can be applied at fine spatial scales (e.g. farm/project/plantation) for food and bioenergy crop greenhouse gas (GHG) accounting to facilitate decision making in the land‐based sectors. Higher tier methods have been defined by IPCC and must be well evaluated and operate across a range of domains (e.g. climate region, soil type, crop type, topography), and must account for land use transitions and management changes being implemented. Furthermore, the data required to calibrate and drive the models used at higher tiers need to be available and applicable at fine spatial resolution, covering the meteorological, soil, cropping system and management domains, with quantified uncertainties. Testing the reliability of the models will require data either from sites with repeated measurements or from chronosequences. We review current global capability for estimating changes in soil carbon at fine spatial scales and present a vision for a framework capable of quantifying land use change and management impacts on soil carbon, which could be used for addressing issues such as bioenergy and biofuel sustainability, food security, forest protection, and direct/indirect impacts of land use change. The aim of this framework is to provide a globally accepted standard of carbon measurement and modelling appropriate for GHG accounting that could be applied at project to national scales (allowing outputs to be scaled up to a country level), to address the impacts of land use and land management change on soil carbon.

Pharmacokinetic Evaluation of Intranasally Administered Vinyl Polymer-Coated Lorazepam Microparticles in Rabbits - Yanjun Zhao; Marc B. Brown; Rajeshree H. Khengar; Matthew J. Traynor; Pedro Barata; Stuart A. Jones (The AAPS Journal, 2012)

A stochastic model of autocatalytic reaction networks - Alessandro Filisetti; Alex Graudenzi; Roberto Serra; Marco Villani; Rudolf M. Füchslin; Norman Packard; Stuart A. Kauffman; Irene Poli (Theory in Biosciences, 2012)

Response to “Comment on ‘Otolith Microchemistry Reveals Substantial Use of Freshwater by Southern Flounder in the Northern Gulf of Mexico’” by Pedro Morais - Michael R. Lowe; Stuart A. Ludsin; Brian J. Fryer; Russell A. Wright; Dennis R. DeVries; Troy M. Farmer (Estuaries and Coasts, 2012)

Altered Lung Motion is a Sensitive Indicator of Regional Lung Disease - Andreas Fouras; Beth J. Allison; Marcus J. Kitchen; Stephen Dubsky; Jayne Nguyen; Kerry Hourigan; Karen K. W. Siu; Rob A. Lewis; Megan J. Wallace; Stuart B. Hooper (Annals of Biomedical Engineering, 2012)

Spatial dynamics of benthic competition on coral reefs - Stuart A. Sandin; Dylan E. McNamara (Oecologia, 2012)

Exposure to Glyphosate- and/or Mn/Zn-Ethylene-bis-Dithiocarbamate-Containing Pesticides Leads to Degeneration of γ-Aminobutyric Acid and Dopamine Neurons in Caenorhabditis elegans - Rekek Negga; J. Andrew Stuart; Morgan L. Machen; Joel Salva; Amanda J. Lizek; S. Jayne Richardson; Amanda S. Osborne; Oriol Mirallas; Kenneth A. McVey; Vanessa A. Fitsanakis (Neurotoxicity Research, 2012)

An Economic Evaluation of a Small-Scale Timber Harvesting Operation in Western Maryland, USA - Stuart A. Moss; Daniel B. Hedderick (Small-scale Forestry, 2012)

Fish mediate high food web connectivity in the lower reaches of a tropical floodplain river - Timothy D. Jardine; Bradley J. Pusey; Stephen K. Hamilton; Neil E. Pettit; Peter M. Davies; Michael M. Douglas; Vivian Sinnamon; Ian A. Halliday; Stuart E. Bunn (Oecologia, 2012)

Variation in songbird migratory behavior offers clues about adaptability to environmental change - Anna M. Calvert; Stuart A. Mackenzie; Joanna Mills Flemming; Philip D. Taylor; Sandra J. Walde (Oecologia, 2012)

Using successional theory to measure marine ecosystem health - Stuart A. Sandin; Enric Sala (Evolutionary Ecology, 2012)

The Effects of Soil Bacterial Community Structure on Decomposition in a Tropical Rain Forest - Jonathan W. Leff; Diana R. Nemergut; A. Stuart Grandy; Sean P. O’Neill; Kyle Wickings; Alan R. Townsend; Cory C. Cleveland (Ecosystems, 2012)

Environmental and genetic influences on body mass and resting metabolic rates (RMR) in a natural population of weasel Mustela nivalis - KAROL ZUB; STUART PIERTNEY; PAULINA A. SZAFRAŃSKA; MAREK KONARZEWSKI (Molecular Ecology, 2012)
Body mass (BM) and resting metabolic rates (RMR) are two inexorably linked traits strongly related to mammalian life histories. Yet, there have been no studies attempting to estimate heritable variation and covariation of BM and RMR in natural populations. We used a marker‐based approach to construct a pedigree and then the ‘animal model’ to estimate narrow sense heritability ( h 2 ) of these traits in a free‐living population of weasels Mustela nivalis —a small carnivore characterised by a wide range of BM and extremely high RMR. The most important factors affecting BM of weasels were sex and habitat type, whereas RMR was significantly affected only by seasonal variation of this trait. All environmental factors had only small effect on estimates of additive genetic variance of both BM and RMR. The amount of additive genetic variance associated with BM and estimates of heritability were high and significant in males ( h 2 = 0.61), but low and not significant in females ( h 2 = 0.32), probably due to small sample size for the latter sex. The results from the two‐trait model revealed significant phenotypic (r P = 0.62) and genetic correlation (r A = 0.89) between BM and whole body RMR. The estimate of heritability of whole body RMR (0.54) and BM corrected RMR (0.45) were lower than estimates of heritability for BM. Both phenotypic and genetic correlations between BM corrected RMR and BM had negative signals (r P = −0.42 and r A = −0.58). Our results indicate that total energy expenditures of individuals can quickly evolve through concerted changes in BM and RMR.

Artificial gravity training reduces bed rest-induced cardiovascular deconditioning - Michael B. Stenger; Joyce M. Evans; Charles F. Knapp; Stuart M. C. Lee; Tiffany R. Phillips; Sondra A. Perez; Alan D. Moore; William H. Paloski; Steven H. Platts (European Journal of Applied Physiology, 2012)

Geophysical surveys of the sediments of Loch Ness, Scotland: implications for the deglaciation of the Moray Firth Ice Stream, British–Irish Ice Sheet - Andrew J. Turner; John Woodward; Stuart A. Dunning; Adrian J. Shine; Chris R. Stokes; Colm Ó Cofaigh (Journal of Quaternary Science, 2012)
We present results from three geophysical campaigns using high‐resolution sub‐bottom profiling to image sediments deposited in Loch Ness, Scotland. Sonar profiles show distinct packages of sediment, providing insight into the loch's deglacial history. A recessional moraine complex in the north of the loch indicates initial punctuated retreat. Subsequent retreat was rapid before stabilisation at Foyers Rise formed a large stillstand moraine. Here, the calving margin produced significant volumes of laminated sediments in a proglacial fjord‐like environment. Subsequent to this, ice retreated rapidly to the southern end of the loch, where it again deposited a sequence of proglacial laminated sediments. Sediment sequences were then disturbed by the deposition of a thick gravel layer and a large turbidite deposit as a result of a jökulhlaup from the Spean/Roy ice‐dammed lake. These sediments are overlain by a Holocene sheet drape. Data indicate: (i) a former tributary of the Moray Firth Ice Stream migrated back into Loch Ness as a major outlet glacier with a calving margin in a fjord‐like setting; (ii) there was significant sediment supply to the terminus of this outlet glacier in Loch Ness; and (iii) that jökulhlaups are important for sediment supply into proglacial fjord/lake environments and may compose >20% of proglacial sedimentary sequences. Copyright © 2011 John Wiley & Sons, Ltd.

Skeletal muscle ATP turnover and single fibre ATP and PCr content during intense exercise at different muscle temperatures in humans - Stuart R. Gray; Karin Soderlund; Moira Watson; Richard A. Ferguson (Pflügers Archiv - European Journal of Physiology, 2011)

Techniques for Studying Living Primates - Stuart A. Altmann (Journal of Mammalian Evolution, 2011)

Elevated species diversity in abyssal gastropods off Newfoundland: the potential role of food supply - Carol T. Stuart; Michael A. Rex; Derek P. Tittensor; Craig R. Smith (Marine Biodiversity, 2011)

Localised control of an introduced predator: creating problems for the future? - Thomas W. Bodey; Stuart Bearhop; Robbie A. McDonald (Biological Invasions, 2011)

Sexual segregation in distribution, diet and trophic level of seabirds: insights from stable isotope analysis - Richard A. Phillips; Rona A. R. McGill; Deborah A. Dawson; Stuart Bearhop (Marine Biology, 2011)

Spatial and temporal variabilities of δ13C and δ15N within lower trophic levels of a large lake: implications for estimating trophic relationships of consumers - Matthew M. Guzzo; G. Douglas Haffner; Stuart Sorge; Scott A. Rush; Aaron T. Fisk (Hydrobiologia, 2011)

Inducible expression of TGFβ, Snail and Zeb1 recapitulates EMT in vitro and in vivo in a NSCLC model - Gretchen M. Argast; Joseph S. Krueger; Stuart Thomson; Isabela Sujka-Kwok; Krista Carey; Stacia Silva; Matthew O’Connor; Peter Mercado; Iain J. Mulford; G. David Young; Regina Sennello; Robert Wild; et al. (Clinical & Experimental Metastasis, 2011)

An Assessment of Three Harpacticoid Copepod Species for Use in Ecotoxicological Testing - Daniel J. Ward; Victor Perez-Landa; David A. Spadaro; Stuart L. Simpson; Dianne F. Jolley (Archives of Environmental Contamination and Toxicology, 2011)

Seasonal occurrence and distribution of Bryde's whales in the Hauraki Gulf, New Zealand - Nicky Wiseman; Stuart Parsons; Karen A. Stockin; C. Scott Baker (Marine Mammal Science, 2011)
The Hauraki Gulf is a large, shallow embayment located north of Auckland City (36°51′S, 174°46′E), New Zealand. Bryde's whales ( Balaenoptera edeni) are the most frequently observed balaenopterid in these waters. To assess the use of the Hauraki Gulf for this species, we examined the occurrence and distribution in relation to environmental parameters. Data were collected from a platform of opportunity during 674 daily surveys between March 2003 and February 2006. A total of 760 observations of Bryde's whales were recorded throughout the study period during 371 surveys. The number of Bryde's whales sighted/day was highest in winter, coinciding with the coolest median sea‐surface temperature (14.6°C). Bryde's whales were recorded throughout the Hauraki Gulf in water depths ranging from 12.1–59.8 m (mean = 42.3, SD = 5.1). Cow–calf pairs were most frequently observed during the austral autumn in water depths of 29.9–53.9 m (mean = 40.8, SD = 5.2). Data from this study suggest Bryde's whales in the Hauraki Gulf exhibit a mix of both “inshore” and “offshore” characteristics from the Bryde's whales examined off the coast of South Africa.

Lifetime physical activity and the incidence of proliferative benign breast disease - Michelle M. Jung; Graham A. Colditz; Laura C. Collins; Stuart J. Schnitt; James L. Connolly; Rulla M. Tamimi (Cancer Causes & Control, 2011)

Integrated catchment management—interweaving social process and science knowledge - A Fenemor; C Phillips; W Allen; RG Young; G Harmsworth; B Bowden; L Basher; PA Gillespie; M Kilvington; R Davies‐Colley; J Dymond; A Cole; et al. (New Zealand Journal of Marine and Freshwater Research, 2011)
This paper provides an overview of the Motueka integrated catchment management (ICM) research programme. This research was based on the thesis that achieving ecosystem resilience at a catchment scale requires active measures to develop community resilience. We define a generic adaptive planning and action process, with associated knowledge management and stakeholder involvement processes, and illustrate those processes with observations from five research themes: (1) water allocation; (2) land use effects on water; (3) land and freshwater impacts on the coast; (4) integrative tools and processes for managing cumulative effects; and (5) building human capital and facilitating community action. Our research clearly illustrates the benefits for effective decision‐making of carrying out catchment scale science and management within collaborative processes which patiently develop trusting relationships. We conclude that coastal catchments should be managed as a holistic continuum from ridge tops to the sea and that some processes like floods or loss of community resilience have decadal consequences, which support the need for long‐term monitoring and investment.

Total mercury loadings in sediment from gold mining and conservation areas in Guyana - Joniqua Howard; Maya A. Trotz; Ken Thomas; Erlande Omisca; Hong Ting Chiu; Trina Halfhide; Fenda Akiwumi; Ryan Michael; Amy L. Stuart (Environmental Monitoring and Assessment, 2011)

Selection and preference of benthic habitat by small and large ammocoetes of the least brook lamprey (Lampetra aepyptera) - Dustin M. Smith; Stuart A. Welsh; Philip J. Turk (Environmental Biology of Fishes, 2011)

Fine-scale genetic structure of bottlenose dolphins, Tursiops truncatus, in Atlantic coastal waters of the Iberian Peninsula - Ruth Fernández; M. Begoña Santos; Graham J. Pierce; Ángela Llavona; Alfredo López; Mόnica A. Silva; Marisa Ferreira; Manuel Carrillo; Pablo Cermeño; Santiago Lens; Stuart B. Piertney (Hydrobiologia, 2011)

Nutrient provision increases signalling and protein synthesis in human skeletal muscle after repeated sprints - Vernon G. Coffey; Daniel R. Moore; Nicholas A. Burd; Tracy Rerecich; Trent Stellingwerff; Andrew P. Garnham; Stuart M. Phillips; John A. Hawley (European Journal of Applied Physiology, 2011)

Distinct Gene Expression Profiles Directed by the Isoforms of the Transcription Factor Neuron-Restrictive Silencer Factor in Human SK-N-AS Neuroblastoma Cells - Stuart G. Gillies; Kate Haddley; Sylvia A. Vasiliou; Gregory M. Jacobson; Bengt von Mentzer; Vivien J. Bubb; John P. Quinn (Journal of Molecular Neuroscience, 2011)

Otolith Microchemistry Reveals Substantial Use of Freshwater by Southern Flounder in the Northern Gulf of Mexico - Michael R. Lowe; Dennis R. DeVries; Russell A. Wright; Stuart A. Ludsin; Brian J. Fryer (Estuaries and Coasts, 2011)

A Method for Ensemble Wildland Fire Simulation - Mark A. Finney; Isaac C. Grenfell; Charles W. McHugh; Robert C. Seli; Diane Trethewey; Richard D. Stratton; Stuart Brittain (Environmental Modeling & Assessment, 2011)

A new dawn for industrial photosynthesis - Dan E. Robertson; Stuart A. Jacobson; Frederick Morgan; David Berry; George M. Church; Noubar B. Afeyan (Photosynthesis Research, 2011)

Earth stewardship: a strategy for social–ecological transformation to reverse planetary degradation - F. Stuart Chapin; Steward T. A. Pickett; Mary E. Power; Robert B. Jackson; David M. Carter; Clifford Duke (Journal of Environmental Studies and Sciences, 2011)

NIR Spectroscopy Applications in the Development of a Compacted Multiparticulate System for Modified Release - Stuart L. Cantor; Stephen W. Hoag; Christopher D. Ellison; Mansoor A. Khan; Robbe C. Lyon (AAPS PharmSciTech, 2011)

Best Management Practices and Long-Term Water Quality Trends in the Everglades Agricultural Area - Samira H. Daroub; Stuart Van Horn; Timothy A. Lang; Orlando A. Diaz (Critical Reviews in Environmental Science and Technology, 2011)

The diet of an invasive nonnative predator, the feral ferret Mustela furo, and implications for the conservation of ground-nesting birds - Thomas W. Bodey; Stuart Bearhop; Robbie A. McDonald (European Journal of Wildlife Research, 2011)

Short-term unilateral leg immobilization alters peripheral but not central arterial structure and function in healthy young humans - Mark Rakobowchuk; Jennifer Crozier; Elisa I. Glover; Nobuo Yasuda; Stuart M. Phillips; Mark A. Tarnopolsky; Maureen J. MacDonald (European Journal of Applied Physiology, 2011)

Qualitative Variation in Proanthocyanidin Composition of Populus Species and Hybrids: Genetics is the Key - Ashley N. Scioneaux; Michael A. Schmidt; Melissa A. Moore; Richard L. Lindroth; Stuart C. Wooley; Ann E. Hagerman (Journal of Chemical Ecology, 2011)

Solar energy harvesting in the epicuticle of the oriental hornet (Vespa orientalis) - Marian Plotkin; Idan Hod; Arie Zaban; Stuart A. Boden; Darren M. Bagnall; Dmitry Galushko; David J. Bergman (The Science of Nature, 2010)

Chronic cannabis users show altered neurophysiological functioning on Stroop task conflict resolution - Robert A. Battisti; Steven Roodenrys; Stuart J. Johnstone; Nicole Pesa; Daniel F. Hermens; Nadia Solowij (Psychopharmacology, 2010)

Concentrations, distributions and critical level exceedance assessment of SO2, NO2 and O3 in South Africa - Miroslav Josipovic; Harold J. Annegarn; Melanie A. Kneen; Jacobus J. Pienaar; Stuart J. Piketh (Environmental Monitoring and Assessment, 2010)

Development, consumption rates and reproductive biology of Orius albidipennis reared on various prey - Islam S. Sobhy; Awad A. Sarhan; Ahmed A. Shoukry; Gamal A. El-Kady; Nasser S. Mandour; Stuart R. Reitz (BioControl, 2010)

Nicotinic acetylcholine receptor genes on chromosome 15q25.1 are associated with nicotine and opioid dependence severity - Porat M. Erlich; Stuart N. Hoffman; Margaret Rukstalis; John J. Han; Xin Chu; W. H. Linda Kao; Glenn S. Gerhard; Walter F. Stewart; Joseph A. Boscarino (Human Genetics, 2010)

Redox regulation of mitochondrial fission, protein misfolding, synaptic damage, and neuronal cell death: potential implications for Alzheimer’s and Parkinson’s diseases - Tomohiro Nakamura; Stuart A. Lipton (Apoptosis, 2010)

Does food supplementation really enhance productivity of breeding birds? - Timothy J. E. Harrison; Jennifer A. Smith; Graham R. Martin; Dan E. Chamberlain; Stuart Bearhop; Gillian N. Robb; S. James Reynolds (Oecologia, 2010)

El Niño, grazers and fisheries interact to greatly elevate extinction risk for Galapagos marine species - GRAHAM J. EDGAR; STUART A. BANKS; MARGARITA BRANDT; RODRIGO H. BUSTAMANTE; ANGEL CHIRIBOGA; SYLVIA A. EARLE; LAUREN E. GARSKE; PETER W. GLYNN; JACK S. GROVE; SCOTT HENDERSON; CLEVE P. HICKMAN; KATHY A. MILLER; et al. (Global Change Biology, 2010)
Comparisons between historical and recent ecological datasets indicate that shallow reef habitats across the central Galapagos Archipelago underwent major transformation at the time of the severe 1982/1983 El Niño warming event. Heavily grazed reefs with crustose coralline algae (‘urchin barrens’) replaced former macroalgal and coral habitats, resulting in large local and regional declines in biodiversity. Following recent threat assessment workshops, a total of five mammals, six birds, five reptiles, six fishes, one echinoderm, seven corals, six brown algae and nine red algae reported from coastal environments in Galapagos are now recognized as globally threatened. The 2008 International Union for the Conservation of Nature (IUCN) Red List includes 43 of these species, while two additional species (Galapagos damsel Azurina eupalama and 24‐rayed sunstar Heliaster solaris ) not seen for > 25 years also fulfil IUCN threatened species criteria. Two endemic species (Galapagos stringweed Bifurcaria galapagensis and the damselfish A. eupalama ) are now regarded as probably extinct, while an additional six macroalgal species ( Dictyota galapagensis, Spatoglossum schmittii, Desmarestia tropica, Phycodrina elegans, Gracilaria skottsbergii and Galaxaura barbata ) and the seastar H. solaris are possibly extinct. The removal of large lobster and fish predators by artisanal fishing probably magnified impacts of the 1982/1983 El Niño through a cascade of indirect effects involving population expansion of grazing sea urchins. Marine protected areas with adequate enforcement are predicted to ameliorate but not eliminate ecosystem impacts caused by increasing thermal anomalies associated with El Niño and global climate change.

Exercise performance and $$ \dot{V}{\text{O}}_{ 2} $$ kinetics during upright and recumbent high-intensity cycling exercise - Mikel Egaña; Damien O’Riordan; Stuart A. Warmington (European Journal of Applied Physiology, 2010)

Isolation, characterisation and predicted genome locations of Light-bellied Brent goose (Branta bernicla hrota) microsatellite loci (Anatidae, AVES) - Xavier A. Harrison; Deborah A. Dawson; Gavin J. Horsburgh; Tom Tregenza; Stuart Bearhop (Conservation Genetics Resources, 2010)

Intake of fiber and nuts during adolescence and incidence of proliferative benign breast disease - Xuefen Su; Rulla M. Tamimi; Laura C. Collins; Heather J. Baer; Eunyoung Cho; Laura Sampson; Walter C. Willett; Stuart J. Schnitt; James L. Connolly; Bernard A. Rosner; Graham A. Colditz (Cancer Causes & Control, 2010)

Synthesizing mechanisms of density dependence in reef fishes: behavior, habitat configuration, and observational scale - J. Wilson White; Jameal F. Samhouri; Adrian C. Stier; Clare L. Wormald; Scott L. Hamilton; Stuart A. Sandin (Ecology, 2010)
Coral and rocky reef fish populations are widely used as model systems for the experimental exploration of density‐dependent vital rates, but patterns of density‐dependent mortality in these systems are not yet fully understood. In particular, the paradigm for strong, directly density‐dependent (DDD) postsettlement mortality stands in contrast to recent evidence for inversely density‐dependent (IDD) mortality. We review the processes responsible for DDD and IDD per capita mortality in reef fishes, noting that the pattern observed depends on predator and prey behavior, the spatial configuration of the reef habitat, and the spatial and temporal scales of observation. Specifically, predators tend to produce DDD prey mortality at their characteristic spatial scale of foraging, but prey mortality is IDD at smaller spatial scales due to attack‐abatement effects (e.g., risk dilution). As a result, DDD mortality may be more common than IDD mortality on patch reefs, which tend to constrain predator foraging to the same scale as prey aggregation, eliminating attack‐abatement effects. Additionally, adjacent groups of prey on continuous reefs may share a subset of refuges, increasing per capita refuge availability and relaxing DDD mortality relative to prey on patch reefs, where the patch edge could prevent such refuge sharing. These hypotheses lead to a synthetic framework to predict expected mortality patterns for a variety of scenarios. For nonsocial, nonaggregating species and species that aggregate in order to take advantage of spatially clumped refuges, IDD mortality is possible but likely superseded by DDD refuge competition, especially on patch reefs. By contrast, for species that aggregate socially, mortality should be IDD at the scale of individual aggregations but DDD at larger scales. The results of nearly all prior reef fish studies fit within this framework, although additional work is needed to test many of the predicted outcomes. This synthesis reconciles some apparent contradictions in the recent reef fish literature and suggests the importance of accounting for the scale‐sensitive details of predator and prey behavior in any study system.

Redox Reactions Induced by Nitrosative Stress Mediate Protein Misfolding and Mitochondrial Dysfunction in Neurodegenerative Diseases - Zezong Gu; Tomohiro Nakamura; Stuart A. Lipton (Molecular Neurobiology, 2010)

A model of direction selectivity in the starburst amacrine cell network - Germán A. Enciso; Michael Rempe; Andrey V. Dmitriev; Konstantin E. Gavrikov; David Terman; Stuart C. Mangel (Journal of Computational Neuroscience, 2010)

The potential influence of shallow gas and gas hydrates on sea floor erosion of Rock Garden, an uplifted ridge offshore of New Zealand - Gareth J. Crutchley; Sebastian Geiger; Ingo A. Pecher; Andrew R. Gorman; Hai Zhu; Stuart A. Henrys (Geo-Marine Letters, 2010)

Combining plant resistance and a natural enemy to control Amphorophora idaei - Carolyn Mitchell; Scott N. Johnson; Stuart C. Gordon; A. Nicholas E. Birch; Stephen F. Hubbard (BioControl, 2010)

Chronic use of cannabis and poor neural efficiency in verbal memory ability - Robert A. Battisti; Steven Roodenrys; Stuart J. Johnstone; Colleen Respondek; Daniel F. Hermens; Nadia Solowij (Psychopharmacology, 2010)

The effect of weight loss on lameness in obese dogs with osteoarthritis - William G. Marshall; Herman A. W. Hazewinkel; Dermot Mullen; Geert De Meyer; Katrien Baert; Stuart Carmichael (Veterinary Research Communications, 2010)

Response of benthic macroinvertebrate communities to highway construction in an Appalachian watershed - Lara B. Hedrick; Stuart A. Welsh; James T. Anderson; Lian-Shin Lin; Yushun Chen; Xinchao Wei (Hydrobiologia, 2010)

Effect of body tilt angle on fatigue and EMG activities in lower limbs during cycling - Mikel Egaña; Katie Ryan; Stuart A. Warmington; Simon Green (European Journal of Applied Physiology, 2010)

Upregulation of intracellular antioxidant enzymes in brain and heart during estivation in the African lungfish Protopterus dolloi - Melissa M. Page; Kurtis D. Salway; Yuen Kwong Ip; Shit F. Chew; Sarah A. Warren; James S. Ballantyne; Jeffrey A. Stuart (Journal of Comparative Physiology B, 2010)

The non-pest Australasian fungivore Cis bilamellatus Wood (Coleoptera: Ciidae) in northern Europe: spread dynamics, invasion success and ecological impact - Glenda M. Orledge; Paul A. Smith; Stuart E. Reynolds (Biological Invasions, 2010)

Soil drying and nitrogen availability modulate carbon and water exchange over a range of annual precipitation totals and grassland vegetation types - SAMUEL B. St. CLAIR; ERIKA A. SUDDERTH; MARC L. FISCHER; MARGARET S. TORN; STEPHANIE A. STUART; ROHIT SALVE; DENNIS L. EGGETT; DAVID D. ACKERLY (Global Change Biology, 2009)
Increased intensity in precipitation events and longer periods of water deficit are predicted as a general trend under future climate scenarios with potentially large effects on terrestrial ecosystem function. The primary objective of this study was to understand how variation in the intensity of precipitation inputs followed by intermittent soil drying events influence leaf and ecosystem carbon dioxide (CO 2 ) and water exchange in a California annual grassland mesocosm experiment. We further examined how nitrogen (N) availability, and differences in plant community composition (grass‐forb combinations) affected gas exchange responses to the precipitation treatments. Net ecosystem CO 2 exchange (NEE) and evapotranspiration (ET) increased significantly with greater precipitation and were positively correlated with soil moisture. A repeated 10‐day soil drying period, following 11 days of watering, strongly depressed NEE over a range of annual precipitation totals (297, 657 and 987 mm), and plant community types. Ecosystem dark respiration ( R e ) and leaf level photosynthesis ( A max ) showed greater sensitivity to periods of soil drying in the low precipitation plots (297 mm). N additions significantly increased NEE and R e , particularly as water availability was increased. Across the range of precipitation totals and plant community types, intermittent periods of soil moisture deficit and native soil N availability constrained leaf and ecosystem level CO 2 exchange, while the influence on water vapor exchange was less pronounced.

Cell state switching factors and dynamical patterning modules: complementary mediators of plasticity in development and evolution - Stuart A. Newman; Ramray Bhat; Nadejda V. Mezentseva (Journal of Biosciences, 2009)

Phenotypic and Developmental Plasticity - Vidyanand Nanjundiah; Stuart A. Newman (Journal of Biosciences, 2009)

Stable isotopes reveal individual variation in migration strategies and habitat preferences in a suite of seabirds during the nonbreeding period - Richard A. Phillips; Stuart Bearhop; Rona A. R. Mcgill; Deborah A. Dawson (Oecologia, 2009)

Snakes and ladders: the ups and downs of animal segmentation - Ramray Bhat; Stuart A. Newman (Journal of Biosciences, 2009)

Evaluation of the genetic variability of orchid fleck virus by single-strand conformational polymorphism analysis and nucleotide sequencing of a fragment from the nucleocapsid gene - Karen Sumire Kubo; R. M. Stuart; J. Freitas-Astúa; R. Antonioli-Luizon; E. C. Locali-Fabris; H. D. Coletta-Filho; M. A. Machado; E. W. Kitajima (Archives of Virology, 2009)

Bathymetric patterns of deep‐sea gastropod species diversity in 10 basins of the Atlantic Ocean and Norwegian Sea - Carol T. Stuart; Michael A. Rex (Marine Ecology, 2009)
Bathymetric patterns of macrofaunal species diversity are best documented in the western North Atlantic where diversity is a unimodal function of depth, peaking in the mid‐bathyal zone and being depressed in the upper slope and abyss. There are few inter‐basin studies of diversity‐depth trends that are controlled for taxonomy, sampling gear, and diversity measures. In this paper, we compare gastropod diversity gradients in the North American Basin of the Atlantic to estimates of diversity in 9 other regions: the Norwegian Sea, West European Basin, Guiana Basin, Gambia Basin, Equatorial Mid‐Atlantic, Brazil Basin, Angola Basin, Cape Basin and Argentine Basin. All samples were collected with epibenthic sleds, and diversity calculated by the Sanders‐Hurlbert normalized expected number of species. While sampling in other regions is generally less complete than in the western North Atlantic, results indicate that a unimodal pattern is not universal. Diversity can increase, decrease or show no relationship with depth. The level of diversity also varies among basins relative to the western North Atlantic, being depressed in the Norwegian Sea, at bathyal depths in the eastern North Atlantic, and below an oxygen minimum zone in the Cape Basin, and generally elevated at tropical latitudes and in abyssal regions where food supply is high. Associations between gastropod diversity and the ecology and geology of basins suggest that productivity, oxygen concentration, hydrographic disturbance and evolutionary‐historical processes may be implicated in shaping bathymetric diversity gradients, but specific causes are difficult to discern. Much more intensive sampling, analyses of other major taxa, and more detailed ecological data are necessary to understand deep‐sea biogeography at within‐ and between‐basin spatial scales.

Cell death: protein misfolding and neurodegenerative diseases - Tomohiro Nakamura; Stuart A. Lipton (Apoptosis, 2009)

Possible impacts of anthropogenic and natural aerosols on Australian climate: a review - Leon D. Rotstayn; Melita D. Keywood; Bruce W. Forgan; Albert J. Gabric; Ian E. Galbally; John L. Gras; Ashok K. Luhar; Grant H. McTainsh; Ross M. Mitchell; Stuart A. Young (International Journal of Climatology, 2009)
A review is presented of the aerosol–climate interaction with specific focus on the Australian region. The uncertainties associated with this interaction are much larger than those associated with greenhouse gases or other forcing agents, and are currently a major obstacle in climate‐change research. However, new research suggests that aerosol effects are of comparable importance to greenhouse gases as a driver of recent climate trends in the Southern Hemisphere, including Australia. A significant new result from climate modelling is that anthropogenic aerosol over Asia affects meridional temperature gradients and atmospheric circulation, and may have caused an increase in rainfall over north‐western Australia. Global ocean circulation provides another mechanism whereby aerosol changes in the Northern Hemisphere can affect climate in the Southern Hemisphere, suggesting an urgent need for further targeted studies using coupled ocean‐atmosphere global climate models. To better model climate variability and climate change in the Australian region, more research is needed into the sources of aerosol and their precursors, their atmospheric distributions and transformations, and how to incorporate these processes robustly in global climate models (GCMs). The following priorities are suggested for further research in Australia linking aerosol observations and modelling: natural aerosol over the Southern Ocean, tropical biomass‐burning aerosol in Indonesia and Australia, secondary organic aerosol (SOA) from volatile organic compounds (VOCs), wind‐blown dust and modulation of rainfall by anthropogenic aerosol. Copyright © 2008 Royal Meteorological Society

Cell state switching factors and dynamical patterning modules: complementary mediators of plasticity in development and evolution - Stuart A. Newman; Ramray Bhat; Nadejda V. Mezentseva (Journal of Biosciences, 2009)

The pharmacokinetic profile of recombinant human erythropoietin is unchanged in patients undergoing cardiac surgery - Stuart A. McCluskey; Wing K. Cheung; Rita Katznelson; Humara Poonawala; Ludwik Fedorko; George Djaiani; Bobby Mehta; Keyvan Karkouti (European Journal of Clinical Pharmacology, 2009)

Threatened fishes of the world: Crystallaria cincotta Welsh and Wood 2008 (Percidae) - Stuart A. Welsh; Robert M. Wood; Kenneth R. Sheehan (Environmental Biology of Fishes, 2009)

The position of repetitive DNA sequence in the southern cattle tick genome permits chromosome identification - Catherine A. Hill; Felix D. Guerrero; Janice P. Van Zee; Nicholas S. Geraci; Jason G. Walling; Jeffrey J. Stuart (Chromosome Research, 2009)

A Tsunami Detection and Warning-focused Sea Level Station Metadata Web Service - John J. Marra; Uday S. Kari; Stuart A. Weinstein (Pure and Applied Geophysics, 2008)

Manipulation of Corticosteroid Release from a Transiently Supersaturated Topical Metered Dose Aerosol Using A Residual Miscible Co-Solvent - Monica L. Reid; Marc B. Brown; Stuart A. Jones (Pharmaceutical Research, 2008)

Island biogeography of Caribbean coral reef fish - Stuart A. Sandin; Mark J. A. Vermeij; Allen H. Hurlbert (Global Ecology and Biogeography, 2008)
Aim The goal of our study was to test fundamental predictions of biogeographical theories in tropical reef fish assemblages, in particular relationships between fish species richness and island area, isolation and oceanographic variables (temperature and productivity) in the insular Caribbean. These analyses complement an analogous and more voluminous body of work from the tropical Indo‐Pacific. The Caribbean is more limited in area with smaller inter‐island distances than the Indo‐Pacific, providing a unique context to consider fundamental processes likely to affect richness patterns of reef fish. Location Caribbean Sea. Methods We compiled a set of data describing reef‐associated fish assemblages from 24 island nations across the Caribbean Sea, representing a wide range of isolation and varying in land area from 53 to 110,860 km 2 . Regression‐based analyses compared the univariate and combined effects of island‐specific physical predictors on fish species richness. Results We found that diversity of reef‐associated fishes increases strongly with increasing island area and with decreasing isolation. Richness also increases with increasing nearshore productivity. Analyses of various subsets of the entire data set reveal the robustness of the richness data and biogeographical patterns. Main conclusions Within the relatively small and densely packed Caribbean basin, fish species richness fits the classical species–area relationship. Richness also was related negatively to isolation, suggesting direct effects of dispersal limitation in community assembly. Because oceanic productivity was correlated with isolation, however, the related effects of system‐wide productivity on richness cannot be disentangled. These results highlight fundamental mechanisms that underlie spatial patterns of biodiversity among Caribbean coral reefs, and which are probably also are functioning in the more widespread and heterogeneous reefs of the Indo‐Pacific.

COMPARATIVE ECOLOGY OF NORTH ATLANTIC SHORES: DO DIFFERENCES IN PLAYERS MATTER FOR PROCESS? - Stuart R. Jenkins; Pippa Moore; Michael T. Burrows; David J. Garbary; Stephen J. Hawkins; Agnar Ingólfsson; Kenneth P. Sebens; Paul V. R. Snelgrove; David S. Wethey; Sarah A. Woodin (Ecology, 2008)
The contrasting histories of the western and eastern shores of the North Atlantic Ocean provide an excellent opportunity to consider the implications of past events for present ecological processes and the functioning of marine ecosystems. Similarities and differences in assemblage composition have been driven by large‐scale events, such as the trans‐Arctic interchange, which has shaped the species pool, and cycles of glaciation, which have determined phases of local or regional extinction and colonization. More recently, anthropogenically induced invasions and local extinctions have significantly altered biogeographic distributions. Here we consider for both hard and soft substrata how the presence or absence of key taxa influences the outcomes of trophic and other biological interactions, and evaluate the consequences for community structure and ecosystem functioning. On intertidal hard substratum shores, biodiversity of epilithic microphagous grazers differs across latitudinal and longitudinal scales. Diversity is high in southern Europe but declines to the north and across the Atlantic. Lower diversity and the absence of patellid limpets in Iceland and the northwest Atlantic compared to Europe result in differences in consumer pressure, and an apparent contrast in the importance of herbivory vs. competitive interactions and predation pressure as community structuring processes. Interestingly, despite differences in “process,” community patterns are remarkably similar between the east and west. On soft sediment shores, there are conspicuous geographic differences in importance of bioturbators and large digging predators. Hemichordates can be abundant and important infaunal bioturbators in the western Atlantic, but they generally play a much reduced role in the eastern Atlantic. In addition, the number and diversity of digging predators on western Atlantic shores is high; the horseshoe crab, swimming portunid crabs, large whelks, excavating waterfowl, and an abundance of skates and rays exert intense predation pressure and associated biogenic disturbance to sediments. In Europe, except for excavating waterfowl these taxa are rare or absent. Thus, the importance of large, biological agents of disturbance is lower on European shores as a consequence of both recent anthropogenic pressure and natural processes over larger time scales. Consideration of key structuring taxa over the Atlantic shows that human‐mediated transport has had considerable influence. Faunas on both sides of the Atlantic are becoming more similar to the point that some of the key differences in assemblage composition and hence community organization have blurred. Recent introductions as well as planned experimental manipulations provide the opportunity to understand the role of species identity in determining community structure and ecosystem functioning over large spatial scales; the North Atlantic may be an ideal test system to explore these areas.

From Genes to Ecosystems: The Genetic Basis of Condensed Tannins and Their Role in Nutrient Regulation in a Populus Model System - Jennifer A. Schweitzer; Michael D. Madritch; Joseph K. Bailey; Carri J. LeRoy; Dylan G. Fischer; Brian J. Rehill; Richard L. Lindroth; Ann E. Hagerman; Stuart C. Wooley; Stephen C. Hart; Thomas G. Whitham (Ecosystems, 2008)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Spatial distribution of mitochondrial and microsatellite DNA variation in Daubenton's bat within Scotland - THONGCHAI NGAMPRASERTWONG; IAIN J. MACKIE; PAUL A. RACEY; STUART B. PIERTNEY (Molecular Ecology, 2008)
Daubenton's bat ( Myotis daubentonii ) is a known reservoir for European bat lyssavirus type 2 (EBLV‐2). An appreciation of the potential for epidemiological spread and disease risk requires an understanding of the dispersal of the primary host, and any large‐scale geographical barriers that may impede gene flow. The spatial pattern of microsatellite and mitochondrial DNA variation was examined to infer patterns of dispersal of bats among 35 populations across Scotland. DNA sequence variation at the mitochondrial control region and ND1 genes revealed two distinct phylogeographical clades, with generally nonoverlapping geographical distributions except for a small number of populations where both matrilines were found in sympatry. Such discontinuity suggests that Scotland was recolonised twice following the retreat of the Pleistocene ice sheet with little subsequent matrilineal introgression. However, eight microsatellite loci showed low levels of genetic divergence among populations, even between populations from the two distinct mitochondrial DNA clades. An overall, macrogeographical genetic isolation‐by‐distance pattern was observed, with high levels of gene flow among local populations. Apparently contrasting patterns of mitochondrial and microsatellite divergence at different scales could be explained by sex‐specific differences in gene flow at large scales.

A cross‐system synthesis of consumer and nutrient resource control on producer biomass - Daniel S. Gruner; Jennifer E. Smith; Eric W. Seabloom; Stuart A. Sandin; Jacqueline T. Ngai; Helmut Hillebrand; W. Stanley Harpole; James J. Elser; Elsa E. Cleland; Matthew E. S. Bracken; Elizabeth T. Borer; Benjamin M. Bolker (Ecology Letters, 2008)
Nutrient availability and herbivory control the biomass of primary producer communities to varying degrees across ecosystems. Ecological theory, individual experiments in many different systems, and system‐specific quantitative reviews have suggested that (i) bottom–up control is pervasive but top–down control is more influential in aquatic habitats relative to terrestrial systems and (ii) bottom–up and top–down forces are interdependent, with statistical interactions that synergize or dampen relative influences on producer biomass. We used simple dynamic models to review ecological mechanisms that generate independent vs. interactive responses of community‐level biomass. We calibrated these mechanistic predictions with the metrics of factorial meta‐analysis and tested their prevalence across freshwater, marine and terrestrial ecosystems with a comprehensive meta‐analysis of 191 factorial manipulations of herbivores and nutrients. Our analysis showed that producer community biomass increased with fertilization across all systems, although increases were greatest in freshwater habitats. Herbivore removal generally increased producer biomass in both freshwater and marine systems, but effects were inconsistent on land. With the exception of marine temperate rocky reef systems that showed positive synergism of nutrient enrichment and herbivore removal, experimental studies showed limited support for statistical interactions between nutrient and herbivory treatments on producer biomass. Top–down control of herbivores, compensatory behaviour of multiple herbivore guilds, spatial and temporal heterogeneity of interactions, and herbivore‐mediated nutrient recycling may lower the probability of consistent interactive effects on producer biomass. Continuing studies should expand the temporal and spatial scales of experiments, particularly in understudied terrestrial systems; broaden factorial designs to manipulate independently multiple producer resources (e.g. nitrogen, phosphorus, light), multiple herbivore taxa or guilds (e.g. vertebrates and invertebrates) and multiple trophic levels; and – in addition to measuring producer biomass – assess the responses of species diversity, community composition and nutrient status.

The preparation and control of reversal movements as a single unit of action - Michael A. Khan; Luc Tremblay; Darian T. Cheng; Marlene Luis; Stuart J. Mourton (Experimental Brain Research, 2008)

A shift in the habitat use pattern of a lentic galaxiid fish: an acute behavioural response to an introduced predator - Rick D. Stuart-Smith; Robert W. G. White; Leon A. Barmuta (Environmental Biology of Fishes, 2008)

Temporal changes in kin structure through a population cycle in a territorial bird, the red grouse Lagopus lagopus scoticus - STUART B. PIERTNEY; XAVIER LAMBIN; ANDREW D. C. MACCOLL; KERRY LOCK; PHILIP J. BACON; JOHN F. DALLAS; FIONA LECKIE; FRANCOIS MOUGEOT; PAUL A. RACEY; STEVE REDPATH; ROBERT MOSS (Molecular Ecology, 2008)
Populations of red grouse ( Lagopus lagopus scoticus ) undergo regular multiannual cycles in abundance. The ‘kinship hypothesis’ posits that such cycles are caused by changes in kin structure among territorial males producing delayed density‐dependent changes in aggressiveness, which in turn influence recruitment and regulate density. The kinship hypothesis makes several specific predictions about the levels of kinship, aggressiveness and recruitment through a population cycle: (i) kin structure will build up during the increase phase of a cycle, but break down prior to peak density; (ii) kin structure influences aggressiveness, such that there will be a negative relationship between kinship and aggressiveness over the years; (iii) as aggressiveness regulates recruitment and density, there will be a negative relationship between aggressiveness in one year and both recruitment and density in the next; (iv) as kin structure influences recruitment via an affect on aggressiveness, there will be a positive relationship between kinship in one year and recruitment the next. Here we test these predictions through the course of an 8‐year cycle in a natural population of red grouse in northeast Scotland, using microsatellite DNA markers to resolve changing patterns of kin structure, and supra‐orbital comb height of grouse as an index of aggressiveness. Both kin structure and aggressiveness were dynamic through the course of the cycle, and changing patterns were entirely consistent with the expectations of the kinship hypothesis. Results are discussed in relation to potential drivers of population regulation and implications of dynamic kin structure for population genetics.

Finite Fault Modeling in a Tsunami Warning Center Context - Stuart A. Weinstein; Paul R. Lundgren (Pure and Applied Geophysics, 2008)

The Services-Oriented Architecture: Ecosystem Services as a Framework for Diagnosing Change in Social Ecological Systems - Philip A. Loring; F. Stuart Chapin; S. Craig Gerlach (Ecosystems, 2008)

Recovery of Aboveground Plant Biomass and Productivity After Fire in Mesic and Dry Black Spruce Forests of Interior Alaska - Michelle C. Mack; Kathleen K. Treseder; Kristen L. Manies; Jennifer W. Harden; Edward A. G. Schuur; Jason G. Vogel; James T. Randerson; F. Stuart Chapin (Ecosystems, 2008)

Early Life Stress on Brain Structure and Function Across the Lifespan: A Preliminary Study - Donna L. Seckfort; Robert Paul; Stuart M. Grieve; Brian Vandenberg; Richard A. Bryant; Leanne M. Williams; C. Richard Clark; Ronald A. Cohen; Steven Bruce; Evian Gordon (Brain Imaging and Behavior, 2008)

Asymmetric larval competition in the parasitoid wasp Nasonia vitripennis: a role in sex allocation? - Edward M. Sykes; Tabitha M. Innocent; Ido Pen; David M. Shuker; Stuart A. West (Behavioral Ecology and Sociobiology, 2008)

Order parameter coupling in leucite: a calorimetric study - Helen Newton; Stuart A. Hayward; Simon A. T. Redfern (Physics and Chemistry of Minerals, 2008)

Genes and proteins: Dogmas in decline - Stuart A. Newman; Ramray Bhat (Journal of Biosciences, 2007)

Trends in landslide occurrence in Nepal - David N. Petley; Gareth J. Hearn; Andrew Hart; Nicholas J. Rosser; Stuart A. Dunning; Katie Oven; Wishart A. Mitchell (Natural Hazards, 2007)

Asymmetric larval competition in the parasitoid wasp Nasonia vitripennis: a role in sex allocation? - Edward M. Sykes; Tabitha M. Innocent; Ido Pen; David M. Shuker; Stuart A. West (Behavioral Ecology and Sociobiology, 2007)

Bird densities are associated with household densities - JAMIE TRATALOS; RICHARD A. FULLER; KARL L. EVANS; RICHARD G. DAVIES; STUART E. NEWSON; JEREMY J. D. GREENWOOD; KEVIN J. GASTON (Global Change Biology, 2007)
Increasing housing density is an important component of global land transformation, with major impacts on patterns of biodiversity. However, while there have been many studies of the changes in biodiversity across rural–urban gradients, which are influenced in large part by housing densities, how biodiversity changes across the full range of regional variation in housing density remains poorly understood. Here, we explore these relationships for the richness and abundance of breeding birds across Britain. Total richness, and that of 27 urban indicator species, increased from low to moderate household densities and then declined at greater household densities. The richness of all species increased initially faster with household density than did that of the urban indicator species, but nonurban indicator species richness declined consistently after peaking at a very low housing density. Avian abundance showed a rather different pattern. Total abundance and that summed across all urban indicator species increased over a wide range of household densities, and declined only at the highest household densities. The abundance of individual urban indicator species generally exhibited a hump‐shaped relationship with housing density. While there was marked intraspecific variation in the form of such relationships, almost invariably avian abundance declined at housing densities below that at which the UK government requires new developments to be built. Our data highlight the difficulties of maintaining biodiversity while minimising land take for new development. High‐density housing developments are associated with declines in many of those species otherwise best able to exploit urban environments, and those components of native biodiversity with which human populations are often most familiar.

Groundwater Ostracods from the arid Pilbara region of northwestern Australia: distribution and water chemistry - Jessica M. Reeves; Patrick De Deckker; Stuart A. Halse (Hydrobiologia, 2007)

Gypsy moth response to landscape structure differs from neutral model predictions: implications for invasion monitoring - Geneviève M. Nesslage; Brian A. Maurer; Stuart H. Gage (Biological Invasions, 2007)

Global negative vegetation feedback to climate warming responses of leaf litter decomposition rates in cold biomes - Johannes H.C. Cornelissen; Peter M. Van Bodegom; Rien Aerts; Terry V. Callaghan; Richard S.P. Van Logtestijn; Juha Alatalo; F. Stuart Chapin; Renato Gerdol; Jon Gudmundsson; Dylan Gwynn‐Jones; Anne E. Hartley; David S. Hik; et al. (Ecology Letters, 2007)
Whether climate change will turn cold biomes from large long‐term carbon sinks into sources is hotly debated because of the great potential for ecosystem‐mediated feedbacks to global climate. Critical are the direction, magnitude and generality of climate responses of plant litter decomposition. Here, we present the first quantitative analysis of the major climate‐change‐related drivers of litter decomposition rates in cold northern biomes worldwide. Leaf litters collected from the predominant species in 33 global change manipulation experiments in circum‐arctic‐alpine ecosystems were incubated simultaneously in two contrasting arctic life zones. We demonstrate that longer‐term, large‐scale changes to leaf litter decomposition will be driven primarily by both direct warming effects and concomitant shifts in plant growth form composition, with a much smaller role for changes in litter quality within species. Specifically, the ongoing warming‐induced expansion of shrubs with recalcitrant leaf litter across cold biomes would constitute a negative feedback to global warming. Depending on the strength of other (previously reported) positive feedbacks of shrub expansion on soil carbon turnover, this may partly counteract direct warming enhancement of litter decomposition.

Are large‐scale distributional shifts of the blue‐winged macaw ( Primolius maracana ) related to climate change? - Maria Flávia Conti Nunes; Mauro Galetti; Stuart Marsden; Ricardo Scachetti Pereira; A. Townsend Peterson (Journal of Biogeography, 2007)
Aim To evaluate whether observed geographical shifts in the distribution of the blue‐winged macaw ( Primolius maracana ) are related to ongoing processes of global climate change. This species is vulnerable to extinction and has shown striking range retractions in recent decades, withdrawing broadly from southern portions of its historical distribution. Its range reduction has generally been attributed to the effects of habitat loss; however, as this species has also disappeared from large forested areas, consideration of other factors that may act in concert is merited. Location Historical distribution of the blue‐winged macaw in Brazil, eastern Paraguay and northern Argentina. Methods We used a correlative approach to test a hypothesis of causation of observed shifts by reduction of habitable areas mediated by climate change. We developed models of the ecological niche requirements of the blue‐winged macaw, based on point‐occurrence data and climate scenarios for pre‐1950 and post‐1950 periods, and tested model predictivity for anticipating geographical distributions within time periods. Then we projected each model to the other time period and compared distributions predicted under both climate scenarios to assess shifts of habitable areas across decades and to evaluate an explanation for observed range retractions. Results Differences between predicted distributions of the blue‐winged macaw over the twentieth century were, in general, minor and no change in suitability of landscapes was predicted across large areas of the species’ original range in different time periods. No tendency towards range retraction in the south was predicted, rather conditions in the southern part of the species’ range tended to show improvement for the species. Main conclusions Our test permitted elimination of climate change as a likely explanation for the observed shifts in the distribution of the blue‐winged macaw, and points rather to other causal explanations (e.g. changing regional land use, emerging diseases).

Chemical validation of molecular mimicry: interaction of cholera toxin with Campylobacter lipooligosaccharides - Seigo Usuki; Mohanasundari Pajaniappan; Stuart A. Thompson; Robert K. Yu (Glycoconjugate Journal, 2007)

Land-Use Intensity Effects on Soil Organic Carbon Accumulation Rates and Mechanisms - A. Stuart Grandy; G. Philip Robertson (Ecosystems, 2007)

Local habitat distribution determines the relative frequency and interbreeding potential for two Caribbean coral morphospecies - Mark J. A. Vermeij; Stuart A. Sandin; Jameal F. Samhouri (Evolutionary Ecology, 2007)

Sequencing EVC and EVC2 identifies mutations in two-thirds of Ellis–van Creveld syndrome patients - Stuart W. J. Tompson; Victor L. Ruiz-Perez; Helen J. Blair; Stephanie Barton; Victoria Navarro; Joanne L. Robson; Michael J. Wright; Judith A. Goodship (Human Genetics, 2006)

Hypertrophy with unilateral resistance exercise occurs without increases in endogenous anabolic hormone concentration - Sarah B. Wilkinson; Mark A. Tarnopolsky; Emily J. Grant; Caroline E. Correia; Stuart M. Phillips (European Journal of Applied Physiology, 2006)

Carboxylate release of wheat, canola and 11 grain legume species as affected by phosphorus status - Stuart J. Pearse; Erik J. Veneklaas; Greg R. Cawthray; Mike D. A. Bolland; Hans Lambers (Plant and Soil, 2006)

Thymic output, ageing and zinc - Wayne A Mitchell; Irene Meng; Stuart A Nicholson; Richard Aspinall (Biogerontology, 2006)

Experimental habitat fragmentation increases linkage disequilibrium but does not affect genetic diversity or population structure in the Amazonian liverwort Radula flaccida - CHARLES E. ZARTMAN; STUART F. MCDANIEL; A. JONATHAN SHAW (Molecular Ecology, 2006)
Habitat fragmentation increases the migration distances among remnant populations, and is predicted to play a significant role in altering both demographic and genetic processes. Nevertheless, few studies have evaluated the genetic consequences of habitat fragmentation in light of information about population dynamics in the same set of organisms. In a 10 000‐km 2 experimentally fragmented landscape of rainforest reserves in central Amazonia, we examine patterns of genetic variation (amplified fragment length polymorphisms, AFLPs) in the epiphyllous (e.g. leaf‐inhabiting) liverwort Radula flaccida Gott. Previous demographic work indicates that colonization rates in this species are significantly reduced in small forest reserves. We scored 113 polymorphic loci in 86 individuals representing five fragmented and five experimentally unmanipulated populations. Most of the variation (82%) in all populations was harboured at the smallest (400 m 2 ) sampling unit. The mean ( ± SD) within‐population genetic diversity (Nei's), of forest remnants (0.412 ± 0.2) was indistinguishable from continuous (0.413 ± 0.2) forests. Similarly, F ST was identical among small (1‐ and 10‐ha) and large (≥ 100‐ha) reserves (0.19 and 0.18, respectively), but linkage disequilibrium between pairs of loci was significantly elevated in fragmented populations relative to those in continuous forests. These results illustrate that inferences regarding the long‐term viability of fragmented populations based on neutral marker data alone must be viewed with caution, and underscore the importance of jointly evaluating information on both genetic structure and demography. Second, multilocus analyses may be more sensitive to the effects of fragmentation in the short term, although the effects of increasing linkage disequilibrium on population viability remain uncertain.

Initial cultivation of a temperate‐region soil immediately accelerates aggregate turnover and CO 2 and N 2 O fluxes - A. STUART GRANDY; G. PHILIP ROBERTSON (Global Change Biology, 2006)
The immediate effects of tillage on protected soil C and N pools and on trace gas emissions from soils at precultivation levels of native C remain largely unknown. We measured the response to cultivation of CO 2 and N 2 O emissions and associated environmental factors in a previously uncultivated U.S. Midwest Alfisol with C concentrations that were indistinguishable from those in adjacent late successional forests on the same soil type (3.2%). Within 2 days of initial cultivation in 2002, tillage significantly ( P =0.001, n =4) increased CO 2 fluxes from 91 to 196 mg CO 2 ‐C m −2 h −1 and within the first 30 days higher fluxes because of cultivation were responsible for losses of 85 g CO 2 ‐C m −2 . Additional daily C losses were sustained during a second and third year of cultivation of the same plots at rates of 1.9 and 1.0 g C m −2 day −1 , respectively. Associated with the CO 2 responses were increased soil temperature, substantially reduced soil aggregate size (mean weight diameter decreased 35% within 60 days), and a reduction in the proportion of intraaggregate, physically protected light fraction organic matter. Nitrous oxide fluxes in cultivated plots increased 7.7‐fold in 2002, 3.1‐fold in 2003, and 6.7‐fold in 2004 and were associated with increased soil NO 3 − concentrations, which approached 15 μg N g −1 . Decreased plant N uptake immediately after tillage, plus increased mineralization rates and fivefold greater nitrifier enzyme activity, likely contributed to increased NO 3 − concentrations. Our results demonstrate that initial cultivation of a soil at precultivation levels of native soil C immediately destabilizes physical and microbial processes related to C and N retention in soils and accelerates trace gas fluxes. Policies designed to promote long‐term C sequestration may thus need to protect soils from even occasional cultivation in order to preserve sequestered C.

Nocturnal foraging by great skuas Stercorarius skua: implications for conservation of storm-petrel populations - Stephen C. Votier; Jonathan E. Crane; Stuart Bearhop; Ana de León; Claire A. McSorley; Eduardo Mínguez; Ian P. Mitchell; Matthew Parsons; Richard A. Phillips; Robert W. Furness (Journal of Ornithology, 2006)

Facial Skin Surface Temperature Changes During a “Concealed Information” Test - Dean A. Pollina; Andrew B. Dollins; Stuart M. Senter; Troy E. Brown; Ioannis Pavlidis; James A. Levine; Andrew H. Ryan (Annals of Biomedical Engineering, 2006)

Indirect effects of algae on coral: algae‐mediated, microbe‐induced coral mortality - Jennifer E. Smith; Morrigan Shaw; Rob A. Edwards; David Obura; Olga Pantos; Enric Sala; Stuart A. Sandin; Steven Smriga; Mark Hatay; Forest L. Rohwer (Ecology Letters, 2006)
Declines in coral cover are generally associated with increases in the abundance of fleshy algae. In many cases, it remains unclear whether algae are responsible, directly or indirectly, for coral death or whether they simply settle on dead coral surfaces. Here, we show that algae can indirectly cause coral mortality by enhancing microbial activity via the release of dissolved compounds. When coral and algae were placed in chambers together but separated by a 0.02 μ m filter, corals suffered 100% mortality. With the addition of the broad‐spectrum antibiotic ampicillin, mortality was completely prevented. Physiological measurements showed complementary patterns of increasing coral stress with proximity to algae. Our results suggest that as human impacts increase and algae become more abundant on reefs a positive feedback loop may be created whereby compounds released by algae enhance microbial activity on live coral surfaces causing mortality of corals and further algal growth.

The GeoProfile metadata, exposure of instruments, and measurement bias in climatic record revisited - Rezaul Mahmood; Stuart A. Foster; David Logan (International Journal of Climatology, 2006)

Mechanisms of Neuroimmunity and Neurodegeneration Associated with HIV-1 Infection and AIDS - Marcus Kaul; Stuart A. Lipton (Journal of Neuroimmune Pharmacology, 2006)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

The human FK506-binding proteins: characterization of human FKBP19 - Stuart L. Rulten; Ross A. Kinloch; Hilda Tateossian; Colin Robinson; Lucy Gettins; John E. Kay (Mammalian Genome, 2006)

Drainage Size, Stream Intermittency, and Ecosystem Function in a Sonoran Desert Landscape - Ryan A. Sponseller; Stuart G. Fisher (Ecosystems, 2006)

A continental scale evaluation of the role of limpet grazing on rocky shores - Ross A. Coleman; Antony J. Underwood; Lisandro Benedetti-Cecchi; Per Åberg; Francisco Arenas; Julio Arrontes; João Castro; Richard G. Hartnoll; Stuart R. Jenkins; José Paula; Paolo Della Santina; Stephen J. Hawkins (Oecologia, 2006)

Coprological Surveys of Alouatta pigra at Two Sites in Belize - Katherine A. Eckert; Nina E. Hahn; Andrew Genz; Dawn M. Kitchen; Michael D. Stuart; Gary A. Averbeck; Bert E. Stromberg; Hal Markowitz (International Journal of Primatology, 2006)

Multi-Scale Controls on Water Quality Effects of Submerged Aquatic Vegetation in the Tidal Freshwater Hudson River - Stuart E. G. Findlay; William C. Nieder; Elizabeth A. Blair; David T. Fischer (Ecosystems, 2006)

Education in sustainable production in US universities - Gilbert L. Rochon; Loring F. Nies; Chad T. Jafvert; Julie A. Stuart; Rabi H. Mohtar; Joseph Quansah; Akilah Martin (Clean Technologies and Environmental Policy, 2006)

Acute meningoencephalitis caused by adenovirus serotype 26 - Erik R Dubberke; Benjamin Tu; Dennis J Rivet; Gregory A Storch; Anucha Apisarnthanarak; Robert E Schmidt; Stuart Weiss; Louis B Polish (Journal of NeuroVirology, 2006)

A numerical model of the partitioning of trace chemical solutes during drop freezing - A. L. Stuart; M. Z. Jacobson (Journal of Atmospheric Chemistry, 2006)

Incorporating Research Results into Wetland Management: Lessons from Recovery Catchments in Saline Landscapes - Stuart A. Halse; Tilo Massenbauer (Hydrobiologia, 2005)

The EPAS1 gene influences the aerobic–anaerobic contribution in elite endurance athletes - Jennifer Henderson; Jason M. Withford-Cave; David L. Duffy; Stuart J. Cole; Nicole A. Sawyer; Jason P. Gulbin; Allan Hahn; Ronald J. Trent; Bing Yu (Human Genetics, 2005)

Genetic Typing of Classical Swine Fever Viruses from Lao PDR by Analysis of the 5′ Non-Coding Region - Stuart D. Blacksell; Syseng Khounsy; David B. Boyle; Laurence J. Gleeson; Harvey A. Westbury; John S. Mackenzie (Virus Genes, 2005)

Species Review of Amphibian Extinction Risks in Madagascar: Conclusions from the Global Amphibian Assessment - FRANCO ANDREONE; JOHN E. CADLE; NEIL COX; FRANK GLAW; RONALD A. NUSSBAUM; CHRISTOPHER J. RAXWORTHY; SIMON N. STUART; DENIS VALLAN; MIGUEL VENCES (Conservation Biology, 2005)
We assessed the extinction risks of Malagasy amphibians by evaluating their distribution, occurrence in protected areas, population trends, habitat quality, and prevalence in commercial trade. We estimated and mapped the distribution of each of the 220 described Malagasy species and applied, for the first time, the IUCN Red List categories and criteria to all species described at the time of the assessment. Nine species were categorized as critically endangered, 21 as endangered, and 25 as vulnerable. The most threatened species occur on the High Plateau and/or have been subjected to overcollection for the pet trade, but restricted extent of occurrence and ongoing habitat destruction were identified as the most important factors influencing extinction threats. The two areas with the majority of threatened species were the northern Tsaratanana‐Marojejy‐Masoala highlands and the southeastern Anosy Mountains. The current system of protected areas includes 82% of the threatened amphibian species. Of the critically endangered species, 6 did not occur in any protected area. For conservation of these species we recommend the creation of a reserve for the species of the Mantella aurantiaca group, the inclusion of two Scaphiophryne species in the Convention on the International Trade in Endangered Species Appendix II, and the suspension of commercial collecting for Mantella cowani. Field surveys during the last 15 years reveal no pervasive extinction of Malagasy amphibians resulting from disease or other agents, as has been reported in some other areas of the world.

Methylphenidate effects in attention deficit/hyperactivity disorder: electrodermal and ERP measures during a continuous performance task - Carlie A. Lawrence; Robert J. Barry; Adam R. Clarke; Stuart J. Johnstone; Rory McCarthy; Mark Selikowitz; Samantha J. Broyd (Psychopharmacology, 2005)

Rainer Friedrich and Stefan Reis: Emissions of Air Pollutants. Measurements, Calculations and Uncertainties. Springer-Verlag, Berlin, Heidelberg, New York, 2004, pp. xviii + 335, ISBN 3-540-00840-3, EUR 99.95 - Stuart A. Penkett (Journal of Atmospheric Chemistry, 2005)

Combined D1/D2 receptor stimulation under conditions of dopamine depletion impairs spatial working memory performance in humans - Kathryn A. Ellis; Mitul A. Mehta; Keith A. Wesnes; Stuart Armstrong; Pradeep J. Nathan (Psychopharmacology, 2005)

Distribution and diversity of soil protozoa in the McMurdo Dry Valleys of Antarctica - Stuart S. Bamforth; Diana H. Wall; Ross A. Virginia (Polar Biology, 2005)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

Monitoring and Evaluation of Reef Protected Areas by Local Fishers in the Philippines: Tightening the Adaptive Management Cycle - Andre J. Uychiaoco; Hazel O. Arceo; Stuart J. Green; Margarita T. De La Cruz; Paulyn A. Gaite; Porfirio M. Aliño (Biodiversity and Conservation, 2005)

Pharmacokinetics/pharmacodynamics and the stages of drug development: Role of modeling and simulation - Jenny Y. Chien; Stuart Friedrich; Michael A. Heathman; Dinesh P. de Alwis; Vikram Sinha (The AAPS Journal, 2005)

Refinement and application of a conductiometric standpipe technique for measuring interstitial flow velocity in salmonid spawning gravels - Stuart M. Greig; Paul A. Carling; David A. Sear; Les J. Whitcombe (Hydrobiologia, 2005)

Occurrence of aquatic invertebrates of the wheatbelt region of Western Australia in relation to salinity - Adrian M. Pinder; Stuart A. Halse; Jane M. McRae; Russell J. Shiel (Hydrobiologia, 2005)

Selective sweeps and intercontinental migration in the cosmopolitan moss Ceratodon purpureus (Hedw.) Brid. - STUART F. McDANIEL; A. JONATHAN SHAW (Molecular Ecology, 2005)
The moss Ceratodon purpureus has long been used as a model system in plant development and physiology. However, the molecular population genetics of the species remains virtually unexplored. In this study, we used population genetic analyses of DNA sequence data from three unlinked loci ( atpB‐rbcL spacer, adk , and phy2 ) to examine biogeographical patterns in a global sample of this species. The three loci differed significantly in mutation frequency spectra and implied population structure. Pairs of haplotypes from single populations were frequently more divergent than haplotypes sampled from widely disjunct populations. In the atpB‐rbcL spacer and adk samples, Australasian haplotypes were more closely related to Northern Hemisphere haplotypes than to haplotypes found in the equatorial regions. In contrast, the phy2 sample showed that the north and south temperate regions were genetically divergent, with the equatorial regions intermediate. Maximum‐likelihood estimates (MLE) of the rates of migration between the two hemispheres were significantly different for the two nuclear genes. The frequency spectra of mutations indicated that differences in implied population structure among the three loci resulted from directional selection on the chloroplast genome and on the chromosomal segment containing adk . Collectively, these data suggest that long‐distance migration within the Northern Hemisphere and Australasian regions is common (relative to the mutation rate) and that migration between these two regions, potentially via equatorial populations, is more frequent than migration among equatorial populations.

Phylogeographic structure and postglacial evolutionary history of water voles ( Arvicola terrestris ) in the United Kingdom - STUART B. PIERTNEY; WENDY A. STEWART; XAVIER LAMBIN; SANDRA TELFER; JON AARS; JOHN F. DALLAS (Molecular Ecology, 2005)
The phylogeographic pattern of mitochondrial DNA variation in water voles ( Arvicola terrestris ) from 57 localities across the United Kingdom and representative samples from Spain, France, Switzerland and Finland was determined from sequence variation in the central portion of the control region. Twenty‐seven different haplotypes were resolved which formed two distinct phylogenetic clades. This major division separated haplotypes found in Scotland from those found in England and Wales. Nested clade analysis of haplotypes indicated that such a division was a consequence of allopatric fragmentation. The haplotypes found in Switzerland, France and Spain clustered with Scottish haplotypes, whereas the haplotype from Finland clustered with the English/Welsh haplotypes. These patterns indicate that contemporary Scottish populations are derived from an Iberian glacial refugium, whereas English and Welsh populations are derived from an eastern European refugium. As such, the postglacial recolonization of the United Kingdom must have involved two colonization events, either in different localities with no subsequent contact, or as two waves separated over time, with the second wave of colonizers displacing the first. An analysis of molecular variance ( amova ) identified significant population genetic divergence within both the major clades, indicative of restricted gene flow and regional population isolation. The implications of both phylogeographical and population genetic structure are discussed in context with the conservation of water voles in Britain.

Experimental and potential future therapeutic approaches for HIV-1 associated dementia targeting receptors for chemokines, glutamate and erythropoietin - Marcus Kaul; Stuart A. Lipton (Neurotoxicity Research, 2005)

Postfire Soil N Cycling in Northern Conifer Forests Affected by Severe, Stand-Replacing Wildfires - Erica A. H. Smithwick; Monica G. Turner; Michelle C. Mack; F. Stuart Chapin (Ecosystems, 2005)

The pre-Mendelian, pre-Darwinian world: Shifting relations between genetic and epigenetic mechanisms in early multicellular evolution - Stuart A. Newman (Journal of Biosciences, 2005)

Foreword - Vidyanand Nanjundiah; Stuart A. Newman; Scott F. Gilbert (Journal of Biosciences, 2005)

Four days of citalopram increase suppression of cortisol secretion by prednisolone in healthy volunteers - Carmine M. Pariante; Andrew S. Papadopoulos; Lucia Poon; Anthony J. Cleare; Stuart A. Checkley; Judie English; Robert W. Kerwin; Stafford Lightman (Psychopharmacology, 2004)

Modeling Sustainability of Arctic Communities: An Interdisciplinary Collaboration of Researchers and Local Knowledge Holders - Jack A. Kruse; Robert G. White; Howard E. Epstein; Billy Archie; Matt Berman; Stephen R. Braund; F. Stuart Chapin; Johnny Charlie; Colin J. Daniel; Joan Eamer; Nick Flanders; Brad Griffith; et al. (Ecosystems, 2004)

Three-dimensional Structure of an Old-growth Pseudotsuga-Tsuga Canopy and Its Implications for Radiation Balance, Microclimate, and Gas Exchange - Geoffrey G. Parker; Mark E. Harmon; Michael A. Lefsky; Jiquan Chen; Robert Van Pelt; Stuart B. Weis; Sean C. Thomas; William E. Winner; David C. Shaw; Jerry F. Frankling (Ecosystems, 2004)

Increasing turbidity significantly alters the diet of brown trout: a multi‐year longitudinal study - R. D. Stuart‐Smith; A. M. M. Richardson; R. W. G. White (Journal of Fish Biology, 2004)
The stomach contents of adult brown trout Salmo trutta from Lake Sorell, Tasmania, were analysed during 6 years of increasing turbidity to follow changes in the diet associated with dramatic changes in water clarity. Brown trout were sampled from 1996, when turbidity was 26 NTU, to 2001 when turbidity was 141 NTU. The mean relative volume of stomach contents decreased progressively to 2001, by which time it was only one sixth of that in 1996, and the mean diversity of prey in stomachs decreased from an average of more than six species per stomach in 1996 to one species in 2001. The species composition of stomach contents shifted from domination by the phreatoicid isopod Colubotelson sp., to the galaxiid fish Galaxias auratus and the amphipod Austrochiltonia australis , and then the cladoceran Daphnia carinata . To give an indication of diet changes over a typical yearly cycle in the current turbid state of the lake, a sample was taken from each season from December 2000 to September 2001. Two basic diets were found during the year; brown trout specialized on D. carinata in summer and autumn, and G. auratus in winter and spring. Mean diversity of prey was less than two species per stomach in all samples from 2000 to 2001, except for the sample from spring 2001 when it was 2·2 species per stomach, and the mean relative volume of stomach contents was more than three times greater in winter than any other season. The ways in which high turbidity may have influenced the changes in the brown trout diet observed since 1996 and the patterns evident during the seasons of 2000–2001 are discussed.

Using Solution-Phase Nanoparticles, Surface-Confined Nanoparticle Arrays and Single Nanoparticles as Biological Sensing Platforms - Amanda J. Haes; Douglas A. Stuart; Shuming Nie; Richard P. Van Duyne (Journal of Fluorescence, 2004)

Interactions among dissolved organic carbon, microbial processes, and community structure in the mesopelagic zone of the northwestern Sargasso Sea - Craig A. Carlson; Stephen J. Giovannoni; Dennis A. Hansell; Stuart J. Goldberg; Rachel Parsons; Kevin Vergin (Limnology and Oceanography, 2004)
At the Bermuda Atlantic Time‐Series Study (BATS) site, the field observations of dissolved organic carbon (DOC) dynamics indicate that seasonally produced “semilabile” DOC is resistant to rapid microbial degradation in the surface waters but available for microbial remineralization once it is delivered into the mesopelagic zone after convective overturn. In this study, we employed an experimental simulation of convective overturn events to determine whether the remineralization of semilabile DOC would occur in a controlled laboratory setting. Seawater culture experiments were conducted in which surface (≤10 m) and mesopelagic (250 m) 0.2‐mm filtrates were inoculated with unfiltered water from ≤10 and 250 m in an assortment of combinations to simulate various mixtures of nutrients, DOC quantity and quality, and microbial assemblages. Results indicate that (1) microbial inocula from the upper euphotic zone were incapable of remineralizing the seasonally accumulated semilabile DOC (µmol C L −1 resolution) on the timescales of the incubations; (2) the utilization of semilabile DOC was greatest when the inoculum source was from 250 m and the filtrate source was from the upper 10 m; and (3) the decrease in bacterioplankton diversity, estimated with the Shannon‐Wiener diversity index, was greater in treatments in which inoculum from 250 m was mixed with filtrate from 10 m than in treatments in which the surface inoculum was mixed with the surface filtrate. Our findings are that a portion of the surface semilabile DOC can be metabolized by microorganisms in a laboratory setting and that mesopelagic nutrients alone are insufficient to stimulate DOC drawdown >1.3 µmol L −1 . Transformations of microbial community structure were associated with the drawdown of surface DOC in simulated mixing events and suggest that microbial community structure is a factor in surface‐layer DOC dynamics.

Disconnects in Evaluating the Relative Effectiveness of Conservation Strategies - Kathryn A. Saterson; Norman L. Christensen; Robert B. Jackson; Randall A. Kramer; Stuart L. Pimm; Martin D. Smith; Jonathan B. Wiener (Conservation Biology, 2004)

Soil databases and the problem of establishing regional biogeochemical trends - Karen W. Holmes; Dar A. Roberts; Stuart Sweeney; Izaya Numata; Eraldo Matricardi; Trent W. Biggs; Getulio Batista; Oliver A. Chadwick (Global Change Biology, 2004)
Regional and global environmental modeling depend on soil data for input layers or parameterization. However, randomly located observations, such as provided by agricultural databases, are not always representative of trends identified in field studies conducted under carefully controlled conditions. Many researchers lament the paucity of soil profile data in Amazônia, and suggest that given more data, regional studies would more closely approximate field research results. We assess the ability of a well‐populated regional database collected in the southwestern Brazilian Amazon to reproduce expected biogeochemical trends associated with forest clearing and pasture establishment, and explore the ramifications of relying on independently collected soil data for regional modeling. The Soteron database includes analyses of approximately 3000 soil cores collected for zoning purposes in the state of Rondônia. Pasture ages were determined from a time series of Landsat TM images classified using spectral mixture analysis. Although regional averages showed some of the temporal trends expected based on field study results (e.g. increase in pH following forest clearing), the trends were not statistically significant. Stratification by precipitation and other variables showed pasture age to be important but difficult to separate from other potential controls on soil conditions, mainly because of the reduced number of observations in each stratum. Using multiple regression, which permitted the inclusion of all potential explanatory factors and interactions, pasture age was shown to be a statistically significant predictor of soil conditions. However, the expected temporal sequence of changes documented by field chronosequence studies could not be reproduced. Properties dominated by large‐scale environmental gradients – pH, sum of base cations, aluminum saturation, and exchangeable calcium – were moderately well modeled, while those more strongly linked to dynamic spatially heterogeneous processes such as biological cycling and land management, particularly organic carbon and nitrogen, could not be modeled. Management‐induced soil changes occur at too fine a scale to be captured by most maps, and the relative changes are small compared with spatial heterogeneity caused by controls on soil development over large regions. Therefore, regardless of whether chronosequence‐derived models of biogeochemical response to land‐cover change are correct, the results of these models will not lead to spatially explicit maps that can be validated by regional reconnaissance, nor will they facilitate realistic predictions of the regional biogeochemical consequences of land‐cover change. The change from local to regional scale entails a change in the relative importance of processes controlling soil property behavior.

Delineation of complex chromosomal rearrangements: evidence for increased complexity - Caroline Astbury; Laurie A. Christ; David J. Aughton; Suzanne B. Cassidy; Atsuko Fujimoto; Beth A. Pletcher; Irwin A. Schafer; Stuart Schwartz (Human Genetics, 2004)

Effects of synthetic local anaesthetics on the growth of the cyanobacterium Synechococcus leopoliensis - Takahiro Suzuki; Kazumichi Nakasato; Stuart Shapiro; Francesco Pomati; Brett A. Neilan (Journal of Applied Phycology, 2004)

Limit dextrinase from germinating barley has endotransglycosylase activity, which explains its activation by maltodextrins - Gordon J. McDougall; Heather A. Ross; J. Stuart Swanston; Howard V. Davies (Planta, 2004)

Signaling pathways to neuronal damage and apoptosis in human immunodeficiency virus type 1–associated dementia: Chemokine receptors, excitotoxicity, and beyond - Marcus Kaul; Stuart A Lipton (Journal of NeuroVirology, 2004)

Simplified seismic fatigue evaluation for rigid steel connections - Ayman A. Shama; John B. Mander; Stuart S. Chen (Earthquake Engineering and Engineering Vibration, 2003)

Remotely Sensed Data for Ecosystem Analyses: Combining Hierarchy Theory and Scene Models - Stuart R. PHINN; DOUGLAS A. STOW; JANET FRANKLIN; LEAL A. K. MERTES; JOEL MICHAELSEN (Environmental Management, 2003)

Spatial and temporal assessment of sources contributing to the annual austral spring mid‐tropospheric ozone maxima over the tropical South Atlantic - ROBERT J. SWAP; THOMAS A. SZUBA; MICHAEL GARSTANG; HAROLD J. ANNEGARN; LACKSON MARUFU; STUART J. PIKETH (Global Change Biology, 2003)
The primary source of the annual austral spring mid‐tropospheric ozone maxima over the tropical South Atlantic has generally been assumed to be biomass burning. However, ozone precursor emissions from biogenic, lightning, and anthropogenic sources in subequatorial Africa before and during the ozone peak are shown to be comparable, if not greater, in magnitude to regional biomass burning production. Moreover, an investigation of the spatial and temporal characteristics of these ozone precursor sources (i.e. vegetative and microbial activity, lightning‐induced generation, and anthropogenic emissions) suggests that these alternative sources can potentially make a substantial contribution to the seasonal ozone peak. This argument is supported by the practical limitations of atmospheric transport available to regionally produced ozone and ozone precursors.

Similar estimates of population genetic composition and sex ratio derived from carcasses and faeces of Eurasian otter Lutra lutra - John F. Dallas; Karen E. Coxon; Tim Sykes; Paul R. F. Chanin; Freda Marshall; David N. Carss; Philip J. Bacon; Stuart B. Piertney; Paul A. Racey (Molecular Ecology, 2003)
Collecting faeces is viewed as a potentially efficient way to sample elusive animals. Nonetheless, any biases in estimates of population composition associated with such sampling remain uncharacterized. The goal of this study was to compare estimates of genetic composition and sex ratio derived from Eurasian otter Lutra lutra spraints (faeces) with estimates derived from carcasses. Twenty per cent of 426 wild‐collected spraints from SW England yielded composite genotypes for 7–9 microsatellites and the SRY gene. The expected number of incorrect spraint genotypes was negligible, given the proportions of allele dropout and false allele detection estimated using paired blood and spraint samples of three captive otters. Fifty‐two different spraint genotypes were detected and compared with genotypes of 70 otter carcasses from the same area. Carcass and spraint genotypes did not differ significantly in mean number of alleles, mean unbiased heterozygosity or sex ratio, although statistical power to detect all but large differences in sex ratio was low. The genetic compositions of carcass and spraint genotypes were very similar according to confidence intervals of θ and two methods for assigning composite genotypes to groups. A distinct group of approximately 11 carcass and spraint genotypes was detected using the latter methods. The results suggest that spraints can yield unbiased estimates of population genetic composition and sex ratio.

Microbial growth and nitrogen retention in litter of Phragmites australis compared to Typha angustifolia - Stuart E. G. Findlay; Susan Dye; Kevin A. Kuehn (Wetlands, 2002)

Stephen Jay Gould - Stuart A. Newman (Journal of Biosciences, 2002)

Dispersion Moments of Fumigating Plumes – Lidar Estimates and Pdf Model Simulations - Ashok K. Luhar; Stuart A. Young (Boundary-Layer Meteorology, 2002)

Cases-97: Late-Morning Warming And Moistening Of The Convective Boundary Layer Over The Walnut River Watershed - Margaret A. LeMone; Robert L. Grossman; Robert T. Mcmillen; Kuo-Nan Liou; S.C. Ou; Stuart Mckeen; Wayne Angevine; Kyoko Ikeda; Fei Chen (Boundary-Layer Meteorology, 2002)

Metazooplankton dynamics in the Salton Sea, California, 1997–1999 - Mary A. Tiffany; Brandon K. Swan; James M. Watts; Stuart H. Hurlbert (Hydrobiologia, 2002)

Upstream passage of fish through a vertical‐slot fishway in an Australian subtropical river - I. G. STUART; A. P. BERGHUIS (Fisheries Management and Ecology, 2002)
The effectiveness of a vertical‐slot fishway on the Burnett River barrage for facilitating migration of fish was assessed. In 100 samples taken at the top and bottom of the fishway, over 52 000 fish representing 34 species were collected at a maximum rate of 4500 fish per day. In contrast, less than 2000 fish ascended the original pool‐and‐weir fishway in 128, 24 h samples at the top between 1984 and 1987. Juvenile size classes dominated the abundance of many species in the present study and fish between 24 and 930 mm in length ascended the vertical‐slot fishway. However, passage of small fish was restricted and for new fishways on tidal barriers a further reduction in head loss between pools is recommended. Importantly, the width of the vertical‐slots was too small for effective upstream passage of large Queensland lungfish, Neoceratodus forsteri (Krefft). The greatest diversity of fish species was found during low river flows. The findings suggest that vertical‐slot fishways with wide pools and low turbulence pass a diverse range of fish fauna present in subtropical coastal rivers.

Developmental mechanisms: putting genes in their place - Stuart A Newman (Journal of Biosciences, 2002)

Spatially restricted gene flow and reduced microsatellite polymorphism in the Eurasian otter Lutra lutra in Britain - John F. Dallas; Freda Marshall; Stuart B. Piertney; Philip J. Bacon; Paul A. Racey (Conservation Genetics, 2002)

Catchment-Scale Variation in the Nitrate Concentrations of Groundwater Seeps in the Catskill Mountains, New York, U.S.A. - A. Joshua West; Stuart E. G. Findlay; Douglas A. Burns; Kathleen C. Weathers; Gary M. Lovett (Water, Air, & Soil Pollution, 2001)

Chattonella marina (Raphidophyceae), a potentially toxic alga in the Salton Sea, California - Mary A. Tiffany; Steven B. Barlow; Victoria E. Matey; Stuart H. Hurlbert (Hydrobiologia, 2001)

Atmospheric motion systems that influence the redistribution and accumulation of insects on the beaches of the Great Lakes in North America - Scott A. Isard; David A. R. Kristovich; Stuart H. Gage; Carl J. Jones; Neil F. Laird (Aerobiologia, 2001)

Primary productivity of planet earth: biological determinants and physical constraints in terrestrial and aquatic habitats - Richard J. Geider; Evan H. Delucia; Paul G. Falkowski; Adrien C. Finzi; J. Philip Grime; John Grace; Todd M. Kana; Julie La Roche; Stephen P. Long; Bruce A. Osborne; Trevor Platt; I. Colin Prentice; et al. (Global Change Biology, 2001)

Evaluating the environmental performance of passenger vehicles - Stuart A. Batterman; William O. Mattick; Lawrence I. Ranka (The International Journal of Life Cycle Assessment, 2001)

Expression, purification and characterization of cytochrome P450 Biol: a novel P450 involved in biotin synthesis in Bacillus subtilis - Amanda J. Green; Stuart L. Rivers; Myles Cheesman; Graeme A. Reid; Luca G. Quaroni; Iain D. G. Macdonald; Stephen K. Chapman; Andrew W. Munro (JBIC Journal of Biological Inorganic Chemistry, 2001)

Agonistic behavior in naïve juvenile lobsters depleted of serotonin by 5,7-dihydroxytryptamine - Sarah B. Doernberg; Stuart I. Cromarty; Ralf Heinrich; Barbara S. Beltz; Edward A. Kravitz (Journal of Comparative Physiology A, 2001)

Fuzzy structure and spatial dynamics of a declining woodland caribou population - James A. Schaefer; Alasdair M. Veitch; Fred H. Harrington; W. Kent Brown; John B. Theberge; Stuart N. Luttich (Oecologia, 2001)

Land–atmosphere energy exchange in Arctic tundra and boreal forest: available data and feedbacks to climate - Werner Eugster; Wayne R Rouse; Roger A. Pielke Sr; Joseph P. Mcfadden; Dennis D Baldocchi; Timothy G. F Kittel; F. Stuart Chapin; Glen E. Liston; Pier Luigi Vidale; Eugene Vaganov; Scott Chambers (Global Change Biology, 2000)
Summary This paper summarizes and analyses available data on the surface energy balance of Arctic tundra and boreal forest. The complex interactions between ecosystems and their surface energy balance are also examined, including climatically induced shifts in ecosystem type that might amplify or reduce the effects of potential climatic change. High latitudes are characterized by large annual changes in solar input. Albedo decreases strongly from winter, when the surface is snow‐covered, to summer, especially in nonforested regions such as Arctic tundra and boreal wetlands. Evapotranspiration ( Q E ) of high‐latitude ecosystems is less than from a freely evaporating surface and decreases late in the season, when soil moisture declines, indicating stomatal control over Q E , particularly in evergreen forests. Evergreen conifer forests have a canopy conductance half that of deciduous forests and consequently lower Q E and higher sensible heat flux ( Q H ). There is a broad overlap in energy partitioning between Arctic and boreal ecosystems, although Arctic ecosystems and light taiga generally have higher ground heat flux because there is less leaf and stem area to shade the ground surface, and the thermal gradient from the surface to permafrost is steeper. Permafrost creates a strong heat sink in summer that reduces surface temperature and therefore heat flux to the atmosphere. Loss of permafrost would therefore amplify climatic warming. If warming caused an increase in productivity and leaf area, or fire caused a shift from evergreen to deciduous forest, this would increase Q E and reduce Q H . Potential future shifts in vegetation would have varying climate feedbacks, with largest effects caused by shifts from boreal conifer to shrubland or deciduous forest (or vice versa) and from Arctic coastal to wet tundra. An increase of logging activity in the boreal forests appears to reduce Q E by roughly 50% with little change in Q H , while the ground heat flux is strongly enhanced.

Modulation of corneal endothelial hydration control mechanisms by Rolipram - Christopher G. Wigham; Helen C. Turner; Jeremy Swan; Stuart A. Hodson (Pflügers Archiv - European Journal of Physiology, 2000)

Ultrasound for the Visualization and Quantification of Tumor Microcirculation - F. Stuart Foster; Peter N. Burns; David H. Simpson; Stephanie R. Wilson; Donald A. Christopher; David E. Goertz (Cancer and Metastasis Reviews, 2000)

Institutional Reform in Albania: Making Forest-Based Policies Work - Kozma Naka; A. L. Hammett; William B. Stuart (Journal of Forestry, 2000)
In response to such problems as illegal timber harvesting and overgrazing, policymakers in Albania are making efforts to increase the efficiency of the country's forest and pasture administration. Reforms include decentralization, development of infrastructure and human resources, and the introduction of a forestry extension service. The authors explore several options and posit that it is more appropriate to work with existing establishments and build partnerships among stakeholders than to create new organizations.

Holocene river development and environmental change in Upper Wharfedale, Yorkshire Dales, England - Andy J. Howard; Mark G. Macklin; Stuart Black; Karen A. Hudson-Edwards (Journal of Quaternary Science, 2000)

Hybridization, introgression, and linkage evolution - Loren H. Rieseberg; Stuart J.E. Baird; Keith A. Gardner (Plant Molecular Biology, 2000)

Predominance of ecophysiological controls on soil CO2 flux in a Minnesota grassland - Joseph M. Craine; David A. Wedin; F. Stuart Chapin (Plant and Soil, 1999)

Anaerobic transformation of 1,1,1-trichloroethane by municipal digester sludge - Chun Chen; Bhasker S. Ballapragada; Jaakko A. Puhakka; Stuart E. Strand; John F. Ferguson (Biodegradation, 1999)

Age constraints to the relationships between magmatism, metamorphism and tectonism in the Aracena metamorphic belt, southern Spain - A. Castro; C. Fernández; H. El-Hmidi; M. El-Biad; M. Díaz; J. de la Rosa; F. Stuart (International Journal of Earth Sciences, 1999)

Outbreak of Escherichia coli O157 Infection Associated with a Music Festival - T. Cheasty; J. Stuart; M. Crampin; G. Willshaw; T. Djuretic; R. Hancock; C. Elstob; A. Rouse (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Habitat partitioning in a community of darters in the Elk River, West Virginia - Stuart A. Welsh; Sue A. Perry (Environmental Biology of Fishes, 1998)

Vasopressin regulated trafficking of a green fluorescent protein-aquaporin 2 chimera in LLC-PK1 cells - Corinne E. Gustafson; Stuart Levine; Toshiya Katsura; Margaret McLaughlin; Maria Deize Aleixo; B. K. Tamarappoo; A. S. Verkman; D. Brown (Histochemistry and Cell Biology, 1998)

Metronidazole resistance and microaerophily in Campylobacter species - M. A. Smith; Margaret A. Jorgensen; George L. Mendz; Stuart L. Hazell (Archives of Microbiology, 1998)

Genotype/phenotype correlation in affected individuals of a family with a deletion of the entire coding sequence of the connexin 32 gene - P. J. Ainsworth; C. F. Bolton; B. C. Murphy; J. A. Stuart; A. F. Hahn (Human Genetics, 1998)

Breath, urine, and blood measurements as biological exposure indices of short-term inhalation exposure to methanol - Stuart A. Batterman; Alfred Franzblau; James B. D'Arcy; Nicholas E. Sargent; Kenneth B. Gross; Richard M. Schreck (International Archives of Occupational and Environmental Health, 1998)

Influence of genetic and environmental factors on egg and clutch sizes among populations of Paratya australiensis Kemp (Decapoda: Atyidae) in␣upland rainforest streams, south-east Queensland - Marty A. Hancock; Jane M. Hughes; Stuart E. Bunn (Oecologia, 1998)

O2 uptake during solid-state fermentation in a rotating drum bioreactor - Anna J. Marsh; David A. Mitchell; Deidre M. Stuart; Tony Howes (Biotechnology Letters, 1998)

Open system alkaline magmatism in northern Kenya: evidence from U-series disequilibria and radiogenic isotopes - Stuart Black; Ray Macdonald; Barbara A. Barreiro; Peter N. Dunkley; Martin Smith (Contributions to Mineralogy and Petrology, 1998)

MANDIBULAR DENTAL ONTOGENY OF RINGED SEALS ( PHOCA HISPIDA ) - Barbara E. Stewart; Stuart Innes; Robert E. A. Stewart (Marine Mammal Science, 1998)
A bstract X‐rays of mandibles from ringed seal fetuses ( n = 15), newborns ( n = 12), and young‐of‐the‐year ( n = 11), collected up to early June, were examined for the presence, location, and eruption patterns of deciduous and permanent teeth. The presence of a neonatal line and cementum in permanent canines was determined microscopically. Fetuses sampled in October‐November had only unerupted, deciduous tooth germs, but by late January there were robust, deciduous teeth at il‐2 pc2‐4 and small permanent teeth at 11‐2 Cl PCl‐5. In newborns collected in early April, 109 of 143 (76%) deciduous teeth were resorbed completely. The remaining 34 deciduous teeth were partially resorbed; six (18%) had erupted and likely would be shed. By late April young‐of‐the‐year had no deciduous teeth remaining. In newborns 54% of the permanent teeth (102/188) were erupted

Purine metabolism and the microaerophily of Helicobacter pylori - G. L. Mendz; Andrew J. Shepley; Stuart L. Hazell; Mark A. Smith (Archives of Microbiology, 1997)

Environmental Reporting by the Fortune 50 Firms - Paige Davis-Walling; Stuart A. Batterman (Environmental Management, 1997)

Measurement of PAN in the Polluted Boundary Layer and Free Troposphere Using a Luminol-NO2 Detector Combined with a Thermal Converter - Chloe Nikitas; Kevin C. Clemitshaw; David E. Oram; Stuart a. Penkett (Journal of Atmospheric Chemistry, 1997)

Isotopic compositions of lipid biomarker compounds in estuarine plants and surface sediments - Elizabeth A. Canuel; Katherine H. Freeman; Stuart G. Wakeham (Limnology and Oceanography, 1997)
We examined the isotopic compositions of fatty acids, sterols, and hydrocarbons isolated from three coastal macrophytes ( Zostera marina, Spartina alterniflora, and Juncus roemerianus ) in order to investigate the relative contribution of these vascular plants as sources of organic matter in coastal sediments such as Cape Lookout Bight, North Carolina. On average, lipid biomarker compounds extracted from the plants were depleted in 13 C by 3–5‰ relative to δ 13 C total organic carbon (TOC). However, individual compounds within each lipid class varied by up to 5.6‰. Trends in the isotopic compositions of lipids were consistent with δ 13 C TOC ; compounds obtained from Z. marina were the most enriched in 13 C and those from J. roemerianus were the most depleted. The range in isotopic abundances and molecular compositions of the sediments was greater than that obtained from the plants, indicating that additional, presently unidentified sources of organic matter contribute to the Cape Lookout Bight sediments. Similarity between the signatures for suspended particulate matter and the sediments indicates that much of the sedimentary organic matter is derived from algal and bacterial sources. Bacterial sources of organic matter are likely greater during summer/early fall, and incorporation of 13 C‐enriched bacterial biomass may contribute to observed seasonal shifts in δ 13 C TOC in the surficial sediments.

Effects of acute administration of d-amphetamine and haloperidol on procedural learning in man - Veena Kumari; Jeffrey A. Gray; Philip J. Corr; Owen F. Mulligan; Paul A. Cotter; Stuart A. Checkley (Psychopharmacology, 1997)

Effect of acute subcutaneous nicotine on prepulse inhibition of the acoustic startle reflex in healthy male non-smokers - V. Kumari; Paul A. Cotter; Stuart A. Checkley; Jeffrey A. Gray (Psychopharmacology, 1997)

Does prey dispersion affect frequency-dependent predation by wild birds? - Stuart C. Church; Michael Jowers; John A. Allen (Oecologia, 1997)

Identification of new Mamu-DRB alleles using DGGE and direct sequencing - L. A. Knapp; Luis F. Cadavid; Mary E. Eberle; Stuart J. Knechtle; Ronald E. Bontrop; David I. Watkins (Immunogenetics, 1997)

Comparison of sensors and techniques for crop yield mapping - Stuart J. Birrell; Kenneth A. Sudduth; Steven C. Borgelt (Computers and Electronics in Agriculture, 1996)

Integrin-binding peptide in solution inhibits or enhances endothelial cell migration, predictably from cell adhesion - Peng Wu; James B. Hoying; Stuart K. Williams; Barbara A. Kozikowski; Douglas A. Lauffenburger (Annals of Biomedical Engineering, 1994)

Evidence of chaotic dynamics underlying the human alpha-rhythm electroencephalogram - A. C. K. Soong; C. I. J. M. Stuart (Biological Cybernetics, 1989)

Assignment of histidase-regulating locus to chromosome 10 of the mouse - Stuart M. Arfin; William C. Hanford; Benjamin A. Taylor (Biochemical Genetics, 1979)

Two models for the evolution of polygyny - Stuart A. Altmann; Stephen S. Wagner; Sarah Lenington (Behavioral Ecology and Sociobiology, 1977)

Effects of suppressor mutations on nonallelic glucose 6-phosphate dehydrogenase mutants of Neurospora crassa - W. A. Scott; Stuart Brody (Biochemical Genetics, 1973)

Complement fixing antigens of herpes simplex virus - D. Balducci; D. A. J. Tyrrell; C. H. Stuart-Harris (Archives of Virology, 1956)

Notes - E. V. Hardenburg; J. T.; M. B. Chalker; F. M. Harrington; H. C. M; W. P. Kirkwood; A. G. Tolaas; W. Stuart (American Journal of Potato Research, 1930)

Seed certification in british columbia - S. S. Phillips; E. A. Stokdyk; W. Stuart; H. C. Moore (American Journal of Potato Research, 1926)

Physiological and storage problems number - H. S. Yohe; Wm. Stuart; C. O. Appleman; John Bushnell; Julian A. Dimock; J. T. Rosa; Earl S. Johnston; E. P. Miller; Freeman Weiss (American Journal of Potato Research, 1925)

Kiwanians sponsor potato club work - P. R. Young; E. V. Hardenburg; B. E. Brown; Paul M. Williams; Daniel Dean; A. G. Waller; H. R. Talmage; H. C. Moore; J. G. Milward; W. Stuart; H. B. Stevens; R. W. Goss; et al. (American Journal of Potato Research, 1925)

Potato notes - J. T. Rosa; C. Tice; A. E. Wilkinson; B. G. Southwick; E. A. Stokdyk; Ray D. Hews; E. L. Newdick; W. Stuart; H. C. Moore; H. O. Werner; J. F. Hockey; C. L. Bailey; et al. (American Journal of Potato Research, 1924)

Potato notes - C. W. Tice; J. T. Rosa; A. E. Wilkinson; E. A. Stokdyk; E. L. Newdick; Verdal T. Maxwell; C. F. Clark; W. Stuart; Charles A. Thompson; J. Gilbert Borton; Ellwood Douglass; Orley G. Bowen; et al. (American Journal of Potato Research, 1924)

Potato notes - C. Tice; W. C. Edmundson; W. Stuart; Seymour Bridge; Glen Carter; A. G. Allen; Daniel Dean; H. H. Zimmerly; J. O. Milward (American Journal of Potato Research, 1924)

Notes on recent literature - W. Stuart; W. M. Peacock; W. S. Baird; W. Saxby Blair; R. H. Helmer; W. H. Hicks; W. R. Leslie; B. F. Lutman; H. H. Mann; S. D. Nagpurkar; G. S. Kulkarni; R. S. Kasargode; et al. (American Journal of Potato Research, 1924)

Seed certification notes - M. F. Barrus; W. Stuart; A. W. Tompkins; A. H. Gilbert; J. G. Milward (American Journal of Potato Research, 1924)

Preliminary seed certification notes - E. R. Dykeman; C. H. Hadley; W. A. McCubbin; Harold L. Bailey; O Butler; M. F. Barrus; R. F. Payne; N. W. Glimes; H. O. Werner; W. Stuart; Donald Folsom; W. H. M. (American Journal of Potato Research, 1923)